Comparative Genomics of Escherichia coli Isolated from Skin and Soft Tissue and Other Extraintestinal Infections - Ranjan, Amit; Shaik, Sabiha; Nandanwar, Nishant; Hussain, Arif; Tiwari, Sumeet K.; Semmler, Torsten; Jadhav, Savita; Wieler, Lothar H.; Alam, Munirul; Rita R Colwell; Ahmed, Niyaz (mBio, 2017)
Escherichia coli, an intestinal Gram-negative bacterium, has been shown to be associated with a variety of diseases in addition to intestinal infections, such as urinary tract infections (UTIs), meningitis in neonates, septicemia, skin and soft tissue infections (SSTIs), and colisepticemia. Thus, for nonintestinal infections, it is categorized as extraintestinal pathogenic E. coli (ExPEC). It is also an opportunistic pathogen, causing cross infections, notably as an agent of zoonotic diseases. However, comparative genomic data providing functional and genetic coordinates for ExPEC strains associated with these different types of infections have not proven conclusive. In the study reported here, ExPEC E. coli isolated from SSTIs was characterized, including virulence and drug resistance profiles, and compared with isolates from patients suffering either pyelonephritis or septicemia. Results revealed that the majority of the isolates belonged to two pathogenic phylogroups, B2 and D. Approximately 67% of the isolates were multidrug resistant (MDR), with 85% producing extended-spectrum beta-lactamase (ESBL) and 6% producing metallo-beta-lactamase (MBL). The blaCTX-M-15 genotype was observed in at least 70% of the E. coli isolates in each category, conferring resistance to an extended range of beta-lactam antibiotics. Whole-genome sequencing and comparative genomics of the ExPEC isolates revealed that two of the four isolates from SSTIs, NA633 and NA643, belong to pandemic sequence type ST131, whereas functional characteristics of three of the ExPEC pathotypes revealed that they had equal capabilities to form biofilm and were resistant to human serum. Overall, the isolates from a variety of ExPEC infections demonstrated similar resistomes and virulomes and did not display any disease-specific functional or genetic coordinates. IMPORTANCE Infections caused by extraintestinal pathogenic E. coli (ExPEC) are of global concern as they result in significant costs to health care facilities management. The recent emergence of a multidrug-resistant pandemic clone, Escherichia coli ST131, is of primary concern as a global threat. In developing countries, such as India, skin and soft tissue infections (SSTIs) associated with E. coli are marginally addressed. In this study, we employed both genomic analysis and phenotypic assays to determine relationships, if any, among the ExPEC pathotypes. Similarity between antibiotic resistance and virulence profiles was observed, ST131 isolates from SSTIs were reported, and genomic similarities among strains isolated from different disease conditions were detected. This study provides functional molecular infection epidemiology insight into SSTI-associated E. coli compared with ExPEC pathotypes.

Comparison of inferred relatedness based on multilocus variable-number tandem-repeat analysis and whole genome sequencing of Vibrio cholerae O1 - Rashid, Mahamud-ur; Almeida, Mathieu; Azman, Andrew S.; Lindsay, Brianna R.; Sack, David A.; Rita R Colwell; Huq, Anwar; Morris, J. Glenn; Alam, Munirul; Stine, O. Colin (FEMS Microbiology Letters, 2016)
Vibrio cholerae causes cholera, a severe diarrheal disease. Understanding the local genetic diversity and transmission of V. cholerae will improve our ability to control cholera. Vibrio cholerae isolates clustered in genetically related groups (clonal complexes, CC) by multilocus variable tandem-repeat analysis (MLVA) were compared by whole genome sequencing (WGS). Isolates in CC1 had been isolated from two geographical locations. Isolates in a second genetically distinct group, CC2, were isolated only at one location. Using WGS, CC1 isolates from both locations revealed, on average, 43.8 nucleotide differences, while those strains comprising CC2 averaged 19.7 differences. Strains from both MLVA-CCs had an average difference of 106.6. Thus, isolates comprising CC1 were more closely related (P < 10−6) to each other than to isolates in CC2. Within a MLVA-CC, after removing all paralogs, alternative alleles were found in all possible combinations on separate chromosomes indicative of recombination within the core genome. Including recombination did not affect the distinctiveness of the MLVA-CCs when measured by WGS. We found that WGS generally reflected the same genetic relatedness of isolates as MLVA, indicating that isolates from the same MLVA-CC shared a more recent common ancestor than isolates from the same location that clustered in a distinct MLVA-CC.

Enrichment dynamics of Listeria monocytogenes and the associated microbiome from naturally contaminated ice cream linked to a listeriosis outbreak - Ottesen, Andrea; Ramachandran, Padmini; Reed, Elizabeth; White, James R.; Hasan, Nur; Subramanian, Poorani; Ryan, Gina; Jarvis, Karen; Grim, Christopher; Daquiqan, Ninalynn; Hanes, Darcy; Allard, Marc; et al. (BMC Microbiology, 2016)

Occurrence and Diversity of Clinically Important Vibrio Species in the Aquatic Environment of Georgia - Kokashvili, Tamar; Whitehouse, Chris A.; Tskhvediani, Ana; Grim, Christopher J.; Elbakidze, Tinatin; Mitaishvili, Nino; Janelidze, Nino; Jaiani, Ekaterine; Haley, Bradd J.; Lashkhi, Nino; Huq, Anwar; Rita R Colwell; et al. (Frontiers in Public Health, 2015)

Rapid Proliferation of Vibrio parahaemolyticus, Vibrio vulnificus, and Vibrio cholerae during Freshwater Flash Floods in French Mediterranean Coastal Lagoons - Esteves, Kevin; Hervio-Heath, Dominique; Mosser, Thomas; Rodier, Claire; Tournoud, Marie-George; Jumas-Bilak, Estelle; Rita R Colwell; Monfort, Patrick (Applied and Environmental Microbiology, 2015)
Vibrio parahaemolyticus, Vibrio vulnificus, and Vibrio cholerae of the non-O1/non-O139 serotype are present in coastal lagoons of southern France. In these Mediterranean regions, the rivers have long low-flow periods followed by short-duration or flash floods during and after heavy intense rainstorms, particularly at the end of the summer and in autumn. These floods bring large volumes of freshwater into the lagoons, reducing their salinity. Water temperatures recorded during sampling (15 to 24°C) were favorable for the presence and multiplication of vibrios. In autumn 2011, before heavy rainfalls and flash floods, salinities ranged from 31.4 to 36.1‰ and concentrations of V. parahaemolyticus, V. vulnificus, and V. cholerae varied from 0 to 1.5 × 103 most probable number (MPN)/liter, 0.7 to 2.1 × 103 MPN/liter, and 0 to 93 MPN/liter, respectively. Following heavy rainstorms that generated severe flash flooding and heavy discharge of freshwater, salinity decreased, reaching 2.2 to 16.4‰ within 15 days, depending on the site, with a concomitant increase in Vibrio concentration to ca. 104 MPN/liter. The highest concentrations were reached with salinities between 10 and 20‰ for V. parahaemolyticus, 10 and 15‰ for V. vulnificus, and 5 and 12‰ for V. cholerae. Thus, an abrupt decrease in salinity caused by heavy rainfall and major flooding favored growth of human-pathogenic Vibrio spp. and their proliferation in the Languedocian lagoons. Based on these results, it is recommended that temperature and salinity monitoring be done to predict the presence of these Vibrio spp. in shellfish-harvesting areas of the lagoons.

Molecular diversity and predictability of Vibrio parahaemolyticus along the Georgian coastal zone of the Black Sea - Haley, Bradd J.; Kokashvili, Tamar; Tskshvediani, Ana; Janelidze, Nino; Mitaishvili, Nino; Grim, Christopher J.; Constantin_de_Magny, Guillaume; Chen, Arlene J.; Taviani, Elisa; Eliashvili, Tamar; Tediashvili, Marina; Whitehouse, Chris A.; et al. (Frontiers in Microbiology, 2014)
Vibrio parahaemolyticus is a leading cause of seafood-related gastroenteritis and is also an autochthonous member of marine and estuarine environments worldwide. One-hundred seventy strains of V. parahaemolyticus were isolated from water and plankton samples collected along the Georgian coast of the Black Sea during 28 months of sample collection. All isolated strains were tested for presence of tlh, trh, and tdh. A subset of strains were serotyped and tested for additional factors and markers of pandemicity. Twenty-six serotypes, five of which are clinically relevant, were identified. Although all 170 isolates were negative for tdh, trh, and the Kanagawa Phenomenon, 7 possessed the GS-PCR sequence and 27 the 850 bp sequence of V. parahaemolyticus pandemic strains. The V. parahaemolyticus population in the Black Sea was estimated to be genomically heterogeneous by rep-PCR and the serodiversity observed did not correlate with rep-PCR genomic diversity. Statistical modeling was used to predict presence of V. parahaemolyticus as a function of water temperature, with strongest concordance observed for Green Cape site samples (Percent of total variance = 70, P < 0.001). Results demonstrate a diverse population of V. parahaemolyticus in the Black Sea, some of which carry pandemic markers, with increased water temperature correlated to an increase in abundance of V. parahaemolyticus.

Occurrence in Mexico, 1998–2008, of Vibrio cholerae CTX + El Tor carrying an additional truncated CTX prophage - Alam, Munirul; Rashed, Shah M; Mannan, Shahnewaj Bin; Islam, Tarequl; Lizarraga-Partida, Marcial L.; Delgado, Gabriela; Morales-Espinosa, Rosario; Mendez, Jose Luis; Navarro, Armando; Watanabe, Haruo; Ohnishi, Makoto; Hasan, Nur A.; et al. (Proceedings of the National Academy of Sciences, 2014)

Phylodynamic Analysis of Clinical and Environmental Vibrio cholerae Isolates from Haiti Reveals Diversification Driven by Positive Selection - Azarian, Taj; Ali, Afsar; Johnson, Judith A.; Mohr, David; Prosperi, Mattia; Veras, Nazle M.; Jubair, Mohammed; Strickland, Samantha L.; Rashid, Mohammad H.; Alam, Meer T.; Weppelmann, Thomas A.; Katz, Lee S.; et al. (mBio, 2014)
Phylodynamic analysis of genome-wide single-nucleotide polymorphism (SNP) data is a powerful tool to investigate underlying evolutionary processes of bacterial epidemics. The method was applied to investigate a collection of 65 clinical and environmental isolates of Vibrio cholerae from Haiti collected between 2010 and 2012. Characterization of isolates recovered from environmental samples identified a total of four toxigenic V. cholerae O1 isolates, four non-O1/O139 isolates, and a novel nontoxigenic V. cholerae O1 isolate with the classical tcpA gene. Phylogenies of strains were inferred from genome-wide SNPs using coalescent-based demographic models within a Bayesian framework. A close phylogenetic relationship between clinical and environmental toxigenic V. cholerae O1 strains was observed. As cholera spread throughout Haiti between October 2010 and August 2012, the population size initially increased and then fluctuated over time. Selection analysis along internal branches of the phylogeny showed a steady accumulation of synonymous substitutions and a progressive increase of nonsynonymous substitutions over time, suggesting diversification likely was driven by positive selection. Short-term accumulation of nonsynonymous substitutions driven by selection may have significant implications for virulence, transmission dynamics, and even vaccine efficacy.

Age-Related Differences in Performance with Touchscreens Compared to Traditional Mouse Input - Findlater,L.; Jon Froehlich; Fattal, K.; Wobbrock,J.O.; Dastyar, T. (CHI 2013 To Appear, 2013)
Despite the apparent popularity of touch screen for older adults, little is known about the psychomotor performance of these devices. We compare performance between older adults and younger adults in four desktop and touchscreen tasks: pointing, dragging, crossing and steering. On the touchscreen, we also examine pinch zoom. Our results show that while older adults were significantly slower than younger adults in general, the touchscreen reduced the performance gap relative to the desktop and mouse. Indeed, the touchscreen resulted in a significant movement time reduction of 35% over the mouse for older adults, compared to only 16% for younger adults. Error rates also decreased.

Distinct Rap1 Activity States Control the Extent of Epithelial Invagination via α-Catenin - Wang, Yu-Chiun; Zia Khan; Wieschaus, Eric F. (Developmental Cell, 2013)
Localized cell shape change initiates epithelial folding, while neighboring cell invagination determines the final depth of an epithelial fold. The mechanism that controls the extent of invagination remains unknown. During Drosophila gastrulation, a higher number of cells undergo invagination to form the deep posterior dorsal fold, whereas far fewer cells become incorporated into the initially very similar anterior dorsal fold. We find that a decrease in α-catenin activity causes the anterior fold to invaginate as extensively as the posterior fold. In contrast, constitutive activation of the small GTPase Rap1 restricts invagination of both dorsal folds in an α-catenin-dependent manner. Rap1 activity appears spatially modulated by Rapgap1, whose expression levels are high in the cells that flank the posterior fold but low in the anterior fold. We propose a model whereby distinct activity states of Rap1 modulate α-catenin-dependent coupling between junctions and actin to control the extent of epithelial invagination.

Drug response and genetic properties of Vibrio cholerae associated with endemic cholera in north-eastern Thailand, 2003-2011 - Chomvarin, C.; Johura, F.-T.; Mannan, S. B.; Jumroenjit, W.; Kanoktippornchai, B.; Tangkanakul, W.; Tantisuwichwong, N.; Huttayananont, S.; Watanabe, H.; Hasan, N. A.; Huq, A.; Cravioto, A.; et al. (Journal of Medical Microbiology, 2013)
Cholera, caused by Vibrio cholerae, results in significant morbidity and mortality worldwide, including Thailand. Representative V. cholerae strains associated with endemic cholera (n = 32), including strains (n = 3) from surface water sources, in Khon Kaen, Thailand (2003–2011), were subjected to microbiological, molecular and phylogenetic analyses. According to phenotypic and related genetic data, all tested V. cholerae strains belonged to serogroup O1, biotype El Tor (ET), Inaba (IN) or Ogawa (OG). All of the strains were sensitive to gentamicin and ciprofloxacin, while multidrug-resistant (MDR) strains showing resistance to erythromycin, tetracycline, trimethoprim/sulfamethoxazole and ampicillin were predominant in 2007. V. cholerae strains isolated before and after 2007 were non-MDR. All except six diarrhoeal strains possessed ctxA and ctxB genes and were toxigenic altered ET, confirmed by MAMA-PCR and DNA sequencing. Year-wise data revealed that V. cholerae INET strains isolated between 2003 and 2004, plus one strain isolated in 2007, lacked the RS1 sequence (rstC) and toxin-linked cryptic plasmid (TLC)-specific genetic marker, but possessed CTXCL prophage genes ctxB CL and rstR CL. A sharp genetic transition was noted, namely the majority of V. cholerae strains in 2007 and all in 2010 and 2011 were not repressor genotype rstR CL but instead were rstR ET, and all ctx + strains possessed RS1 and TLC-specific genetic markers. DNA sequencing data revealed that strains isolated since 2007 had a mutation in the tcpA gene at amino acid position 64 (N→S). Four clonal types, mostly of environmental origin, including subtypes, reflected genetic diversity, while distinct signatures were observed for clonally related, altered ET from Thailand, Vietnam and Bangladesh, confirmed by distinct subclustering patterns observed in the PFGE (NotI)-based dendrogram, suggesting that endemic cholera is caused by V. cholerae indigenous to Khon Kaen.

Environmental Factors Influencing Epidemic Cholera - Huq, Anwar; Hasan, Nur; Akanda, Ali; Whitcombe, Elizabeth; Rita R Colwell; Haley, Bradd; Alam, Munir; Jutla, Antarpreet; Sack, R. Bradley (The American Journal of Tropical Medicine and Hygiene, 2013)
Cholera outbreak following the earthquake of 2010 in Haiti has reaffirmed that the disease is a major public health threat. Vibrio cholerae is autochthonous to aquatic environment, hence, it cannot be eradicated but hydroclimatology-based prediction and prevention is an achievable goal. Using data from the 1800s, we describe uniqueness in seasonality and mechanism of occurrence of cholera in the epidemic regions of Asia and Latin America. Epidemic regions are located near regional rivers and are characterized by sporadic outbreaks, which are likely to be initiated during episodes of prevailing warm air temperature with low river flows, creating favorable environmental conditions for growth of cholera bacteria. Heavy rainfall, through inundation or breakdown of sanitary infrastructure, accelerates interaction between contaminated water and human activities, resulting in an epidemic. This causal mechanism is markedly different from endemic cholera where tidal intrusion of seawater carrying bacteria from estuary to inland regions, results in outbreaks.

"I Want to Imagine How That Place Looks": Designing Technologies to Support Connectivity Between Africans Living Abroad and Home - Wyche, Susan P.; Marshini Chetty (SIGCHI '13, 2013)
Uneven access to Information and Communication Technologies (ICTs) in parts of the African continent make it challenging for some Africans who migrate to the U.S. to communicate with family members in their countries of origin. However, Internet access is becoming more widespread throughout the continent and this development presents an opportunity to explore how future interactive systems can support exchanges between families with members living in developed and less developed countries. To investigate these design possibilities we interviewed 27 African-born students, currently living in Virginia, U.S., and asked them how they used ICTs to connect with family members in their home countries. Our findings informed the development of a low-fidelity prototype that eight students lived with for four to five months. Findings from this deployment study motivate a discussion regarding features to include in interfaces designed to support transnational family communication. Features include personally meaningful imagery, country specific content, and the ability to monitor the weather and changing currency rates in migrants' countries of origin.
Keywords: diaspora communities; family communication; hci4d/ictd; Interaction design; research through design; transnational

Modeling topic control to detect influence in conversations using nonparametric topic models - Nguyen, Viet-An; Jordan Boyd-Graber; Resnik, Philip; Cai, Deborah A; Midberry, Jennifer E; Wang, Yuanxin (Machine Learning, 2013)
Abstract Identifying influential speakers in multi-party conversations has been the focus of research in communication, sociology, and psychology for decades. It has been long acknowledged qualitatively that controlling the topic of a conversation is a sign of ...

Why “Fiat-Shamir for Proofs” Lacks a Proof - Bitansky, Nir; Dana Dachman-Soled; Garg, Sanjam; Jain, Abhishek; Kalai, Yael Tauman; López-Alt, Adriana; Wichs, Daniel (Theory of Cryptography, 2013)
The Fiat-Shamir heuristic [CRYPTO ’86] is used to convert any 3-message public-coin proof or argument system into a non-interactive argument, by hashing the prover’s first message to select the verifier’s challenge. It is known that this heuristic is sound when the hash function is modeled as a random oracle. On the other hand, the surprising result of Goldwasser and Kalai [FOCS ’03] shows that there exists a computationally sound argument on which the Fiat-Shamir heuristic is never sound, when instantiated with any actual efficient hash function. This leaves us with the following interesting possibility: perhaps we can securely instantiates the Fiat-Shamir heuristic for all 3-message public-coin statistically sound proofs, even if we must fail for some computationally sound arguments. Indeed, this has been conjectured to be the case by Barak, Lindell and Vadhan [FOCS ’03], but we do not have any provably secure instantiation under any “standard assumption”. In this work, we give a broad black-box separation result showing that the security of the Fiat-Shamir heuristic for statistically sound proofs cannot be proved under virtually any standard assumption via a black-box reduction. More precisely: –If we want to have a “universal” instantiation of the Fiat-Shamir heuristic that works for all 3-message public-coin proofs, then we cannot prove its security via a black-box reduction from any assumption that has the format of a “cryptographic game”. –For many concrete proof systems, if we want to have a “specific” instantiation of the Fiat-Shamir heuristic for that proof system, then we cannot prove its security via a black box reduction from any “falsifiable assumption” that has the format of a cryptographic game with an efficient challenger.
Keywords: Algorithm Analysis and Problem Complexity; Computation by Abstract Devices; Data Encryption; Systems and Data Security

AGORA: Assembly Guided by Optical Restriction Alignment - Lin, H.C.; Goldstein, S.; Mendelowitz, L.; Zhou, S.; Wetzel, J.; Schwartz, D.C.; Pop, Mihai (BMC bioinformatics, 2012)
Genome assembly is difficult due to repeated sequences within the genome, which create ambiguities and cause the final assembly to be broken up into many separate sequences (contigs). Long range linking information, such as mate-pairs or mapping data, is necessary to help assembly software resolve repeats, thereby leading to a more complete reconstruction of genomes. Prior work has used optical maps for validating assemblies and scaffolding contigs, after an initial assembly has been produced. However, optical maps have not previously been used within the genome assembly process. Here, we use optical map information within the popular de Bruijn graph assembly paradigm to eliminate paths in the de Bruijn graph which are not consistent with the optical map and help determine the correct reconstruction of the genome.We developed a new algorithm called AGORA: Assembly Guided by Optical Restriction Alignment. AGORA is the first algorithm to use optical map information directly within the de Bruijn graph framework to help produce an accurate assembly of a genome that is consistent with the optical map information provided. Our simulations on bacterial genomes show that AGORA is effective at producing assemblies closely matching the reference sequences. Additionally, we show that noise in the optical map can have a strong impact on the final assembly quality for some complex genomes, and we also measure how various characteristics of the starting de Bruijn graph may impact the quality of the final assembly. Lastly, we show that a proper choice of restriction enzyme for the optical map may substantially improve the quality of the final assembly. Our work shows that optical maps can be used effectively to assemble genomes within the de Bruijn graph assembly framework. Our experiments also provide insights into the characteristics of the mapping data that most affect the performance of our algorithm, indicating the potential benefit of more accurate optical mapping technologies, such as nano-coding.

Co-designing an e-health tutorial for older adults - Xie,Bo; Tom Yeh; Walsh,Greg; Watkins,Ivan; Huang,Man (Proceedings of the 2012 iConference, 2012)
Older adults' ability to access and use electronic health information is generally low, requiring innovative approaches for improvement. An integrated e-tutorial overlays instructions onto Websites. The literature suggests integrated e-tutorials are more effective than paper or video-based tutorials for younger people, but little is known about their effectiveness for older adults. This study explores the applicability of an integrated e-health tutorial for older adults. An integrated e-tutorial, the Online Tutorial Overlay Presenter (OnTOP), added an instructional overlay to the NIHSeniorHealth.gov Website. Overlay features were examined in seven participatory design sessions with seven older adults. Participatory design techniques were used to elicit participants' preferences for tutorial features. Three themes emerged: 1) using contextual cues; 2) tailoring to the learner's literacy level; and 3) enhancing interfaces with multimedia cues. These findings improved the design features of OnTOP. They also generated empirical evidence about the effects of multimedia learning among older adults.
Keywords: e-health literacy; health information seeking; integrated e-tutorial; participatory design

Collecting Semantic Similarity Ratings to Connect Concepts in Assistive Communication Tools - Nikolova,Sonya; Jordan Boyd-Graber; Fellbaum,Christiane (Modeling, Learning, and Processing of Text Technological Data StructuresModeling, Learning, and Processing of Text Technological Data Structures, 2012)
To compensate for the common inability of people with lexical production impairments to access and express intended concepts, we make use of models of human semantic memory that build on the notion of semantic similarity and relatedness. Such models, constructed on evidence gained from psycholinguistic experiments, form the basis of a large lexical database, WordNet . We augment WordNet with many additional links among words and concepts that are semantically related. Making this densely connected semantic network available to people with anomic aphasia through assistive technologies should enable them to navigate among related words and concepts and retrieve the words that they intend to express.

Constructing Inverted Files: To MapReduce or Not Revisited - Wei, Zheng; JaJa, Joseph F. (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2012)
Current high-throughput algorithms for constructing inverted files allfollow the MapReduce framework, which presents a high-level programming model that hides the complexities of parallel programming. In this paper, we take an alternative approach and develop a novel strategy that exploits the current and emerging architectures of multicore processors. Our algorithm is based on a high-throughput pipelined strategy that produces parallel parsed streams, which are immediately consumed at the same rate by parallel indexers. We have performed extensive tests of our algorithm on a cluster of 32 nodes, and were able to achieve a throughput close to the peak throughput of the I/O system: a throughput of 280 MB/s on a single node and a throughput that ranges between 5.15 GB/s (1 Gb/s Ethernet interconnect) and 6.12GB/s (10Gb/s InfiniBand interconnect) on a cluster with 32 nodes for processing the ClueWeb09 dataset. Such a performance represents a substantial gain over the best known MapReduce algorithms even when comparing the single node performance of our algorithm to MapReduce algorithms running on large clusters. Our results shed a light on the extent of the performance cost that may be incurred by using the simpler, higher-level MapReduce programming model for large scale applications.
Keywords: Technical Report

The design and evaluation of prototype eco-feedback displays for fixture-level water usage data - Jon Froehlich; Findlater,L.; Ostergren, M.; Ramanathan, S.; Peterson,J.; Wragg, I.; Larson,E.; Fu, F.; Bai, M.; Patel,S. (ACM, 2012)

Design and Synthesis for Multimedia Systems Using the Targeted Dataflow Interchange Format - Chung-Ching Shen; Wu, Shenpei; Sane, N.; Wu, Hsiang-Huang; Plishker,W.; Bhattacharyya, Shuvra S. (IEEE Transactions on Multimedia, 2012)
Development of multimedia systems that can be targeted to different platforms is challenging due to the need for rigorous integration between high-level abstract modeling, and low-level synthesis and optimization. In this paper, a new dataflow-based design tool called the targeted dataflow interchange format is introduced for retargetable design, analysis, and implementation of embedded software for multimedia systems. Our approach provides novel capabilities, based on principles of task-level dataflow analysis, for exploring and optimizing interactions across design components; object-oriented data structures for encapsulating contextual information for components; a novel model for representing parameterized schedules that are derived from repetitive graph structures; and automated code generation for programming interfaces and low-level customizations that are geared toward high-performance embedded-processing architectures. We demonstrate our design tool for cross-platform application design, parameterized schedule representation, and associated dataflow graph-code generation using a case study centered around an image registration application.
Keywords: associated dataflow graph-code generation; Computational modeling; contextual information encapsulation; cross-platform application design; data flow graphs; Data models; Data structures; Dataflow graphs; design components; design tools; Digital signal processing; electronic data interchange; embedded signal processing; Embedded software; high-level abstract modeling; high-performance embedded-processing architectures; Image coding; image registration application; image representation; low-level customizations; low-level optimization; low-level synthesis; Multimedia communication; multimedia systems; multimedia systems development; object-oriented data structures; object-oriented methods; parameterized schedule representation; programming interfaces; repetitive graph structures; retargetable design; Schedules; scheduling; software synthesis; Streaming media; targeted dataflow interchange format; task-level dataflow analysis

Determining Protein Dynamics from 15N Relaxation Data by Using DYNAMICS - Fushman, David (Protein NMR Techniques, 2012)
Motions are essential for protein function, and knowledge of protein dynamics is a key to our understanding the mechanisms underlying protein folding and stability, ligand recognition, allostery, and catalysis. In the last two decades, NMR relaxation measurements have become a powerful tool for characterizing backbone and side chain dynamics in complex biological macromolecules such as proteins and nucleic acids. Accurate analysis of the experimental data in terms of motional parameters is an essential prerequisite for developing physical models of motions to paint an adequate picture of protein dynamics. Here, I describe in detail how to use the software package DYNAMICS that was developed for accurate characterization of the overall tumbling and local dynamics in a protein from nuclear spin-relaxation rates measured by NMR. Step-by-step instructions are provided and illustrated through an analysis of 15 N relaxation data for protein G.
Keywords: Biomedical and Life Sciences

Dictionary-based Face Recognition Under Variable Lighting and Pose - Patel, Vishal M.; Wu,T.; Biswas,S.; Phillips,P.; Chellapa, Rama (IEEE Transactions on Information Forensics and Security, 2012)
We present a face recognition algorithm based on simultaneous sparse approximations under varying illumination and pose. A dictionary is learned for each class based on given training examples which minimizes the representation error with a sparseness constraint. A novel test image is projected onto the span of the atoms in each learned dictionary. The resulting residual vectors are then used for classification. To handle variations in lighting conditions and pose, an image relighting technique based on pose-robust albedo estimation is used to generate multiple frontal images of the same person with variable lighting. As a result, the proposed algorithm has the ability to recognize human faces with high accuracy even when only a single or a very few images per person are provided for training. The efficiency of the proposed method is demonstrated using publicly available databases and it is shown that this method is efficient and can perform significantly better than many competitive face recognition algorithms.
Keywords: Biometrics; dictionary learning; face recognition; illumination variation,; outlier rejection

Differential positioning of adherens junctions is associated with initiation of epithelial folding - Wang, Yu-Chiun; Zia Khan; Kaschube, Matthias; Wieschaus, Eric F. (Nature, 2012)
During tissue morphogenesis, simple epithelial sheets undergo folding to form complex structures. The prevailing model underlying epithelial folding involves cell shape changes driven by myosin-dependent apical constriction. Here we describe an alternative mechanism that requires differential positioning of adherens junctions controlled by modulation of epithelial apical–basal polarity. Using live embryo imaging, we show that before the initiation of dorsal transverse folds during Drosophila gastrulation, adherens junctions shift basally in the initiating cells, but maintain their original subapical positioning in the neighbouring cells. Junctional positioning in the dorsal epithelium depends on the polarity proteins Bazooka and Par-1. In particular, the basal shift that occurs in the initiating cells is associated with a progressive decrease in Par-1 levels. We show that uniform reduction of the activity of Bazooka or Par-1 results in uniform apical or lateral positioning of junctions and in each case dorsal fold initiation is abolished. In addition, an increase in the Bazooka/Par-1 ratio causes formation of ectopic dorsal folds. The basal shift of junctions not only alters the apical shape of the initiating cells, but also forces the lateral membrane of the adjacent cells to bend towards the initiating cells, thereby facilitating tissue deformation. Our data thus establish a direct link between modification of epithelial polarity and initiation of epithelial folding.
Keywords: cell biology; developmental biology

Efficient Password Authenticated Key Exchange via Oblivious Transfer - Canetti, Ran; Dana Dachman-Soled; Vaikuntanathan, Vinod; Wee, Hoeteck (Public Key Cryptography – PKC 2012, 2012)
We present a new framework for constructing efficient password authenticated key exchange (PAKE) protocols based on oblivious transfer (OT). Using this framework, we obtain: an efficient and simple UC-secure PAKE protocol that is secure against adaptive corruptions without erasures. efficient and simple PAKE protocols under the Computational Diffie-Hellman (CDH) assumption and the hardness of factoring. (Previous efficient constructions rely on hash proof systems, which appears to be inherently limited to decisional assumptions.) All of our constructions assume a common reference string (CRS) but do not rely on random oracles.
Keywords: adaptive security; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Data Encryption; Discrete Mathematics in Computer Science; Management of Computing and Information Systems; oblivious transfer; Password Authenticated Key Exchange; search assumptions; Systems and Data Security; UC security

The first international workshop on entity-oriented search (EOS) - Balog,Krisztian; de Vries,Arjen P.; Serdyukov,Pavel; Wen,Ji-Rong (SIGIR Forum, 2012)
The First International Workshop on Entity-Oriented Search (EOS) workshop was held on July 28, 2011 in Beijing, China, in conjunction with the 34th Annual International ACM SIGIR Conference (SIGIR 2011). The objective for the workshop was to bring together academic researchers and industry practitioners working on entity-oriented search to discuss tasks and challenges, and to uncover the next frontiers for academic research on the topic. The workshop program accommodated two invited talks, eleven refereed papers divided into three technical paper sessions, and a group discussion.

Genetic characteristics of drug-resistant Vibrio cholerae O1 causing endemic cholera in Dhaka, 2006-2011 - Rashed, S. M.; Mannan, S. B.; Johura, F.-T.; Islam, M. T.; Sadique, A.; Watanabe, H.; Sack, R. B.; Huq, A.; Rita R Colwell; Cravioto, A.; Alam, M. (Journal of Medical Microbiology, 2012)
Vibrio cholerae O1 biotype El Tor (ET), causing the seventh cholera pandemic, was recently replaced in Bangladesh by an altered ET possessing ctxB of the Classical (CL) biotype, which caused the first six cholera pandemics. In the present study, V. cholerae O1 strains associated with endemic cholera in Dhaka between 2006 and 2011 were analysed for major phenotypic and genetic characteristics. Of 54 representative V. cholerae isolates tested, all were phenotypically ET and showed uniform resistance to trimethoprim/sulfamethoxazole (SXT) and furazolidone (FR). Resistance to tetracycline (TE) and erythromycin (E) showed temporal fluctuation, varying from year to year, while all isolates were susceptible to gentamicin (CN) and ciprofloxacin (CIP). Year-wise data revealed erythromycin resistance to be 33.3 % in 2006 and 11 % in 2011, while tetracycline resistance accounted for 33, 78, 0, 100 and 27 % in 2006, 2007, 2008, 2009 and 2010, respectively; interestingly, all isolates tested were sensitive to TE in 2011, as observed in 2008. All V. cholerae isolates tested possessed genetic elements such as SXT, ctxAB, tcpA ET, rstR ET and rtxC; none had IntlI (Integron I). Double mismatch amplification mutation assay (DMAMA)-PCR followed by DNA sequencing and analysis of the ctxB gene revealed a point mutation at position 58 (C→A), which has resulted in an amino acid substitution from histidine (H) to asparagine (N) at position 20 (genotype 7) since 2008. Although the multi-resistant strains having tetracycline resistance showed minor genetic divergence, V. choleraestrains were clonal, as determined by a PFGE (NotI)-based dendrogram. This study shows 2008–2010 to be the time of transition from ctxB genotype 1 to genotype 7 in V. cholerae ET causing endemic cholera in Dhaka, Bangladesh.

Grammatical structures for word-level sentiment detection - Jordan Boyd-Graber; Sayeed,Asad B.; Rusk,Bryan; Weinberg, Amy (North American Association of Computational Linguistics, 2012)
Existing work in fine-grained sentiment anal- ysis focuses on sentences and phrases but ig- nores the contribution of individual words and their grammatical connections. This is because of a lack of both (1) annotated data at the word level and (2) algorithms that can leverage syn- tactic information in a principled way. We ad- dress the first need by annotating articles from the information technology business press via crowdsourcing to provide training and testing data. To address the second need, we propose a suffix-tree data structure to represent syntac- tic relationships between opinion targets and words in a sentence that are opinion-bearing. We show that a factor graph derived from this data structure acquires these relationships with a small number of word-level features. We demonstrate that our supervised model per- forms better than baselines that ignore syntac- tic features and constraints.

Gripper synthesis for indirect manipulation of cells using Holographic Optical Tweezers - Chowdhury,Sagar; Svec,Petr; Wang,Chenlu; Losert,Wolfgang; Gupta, Satyandra K. (2012)
Optical Tweezers (OT) are used for highly accurate manipulations of biological cells. However, the direct exposure of cells to focused laser beam may negatively influence their biological functions. In order to overcome this problem, we generate multiple optical traps to grab and move a 3D ensemble of inert particles such as silica microspheres to act as a reconfigurable gripper for a manipulated cell. The relative positions of the microspheres are important in order for the gripper to be robust against external environmental forces and the exposure of high intensity laser on the cell to be minimized. In this paper, we present results of different gripper configurations, experimentally tested using our OT setup, that provide robust gripping as well as minimize laser intensity experienced by the cell. We developed a computational approach that allowed us to perform preliminary modeling and synthesis of the gripper configurations. The gripper synthesis is cast as a multi-objective optimization problem.

InterPro in 2011: new developments in the family and domain prediction database. - Hunter, Sarah; Jones, Philip; Mitchell, Alex; Apweiler, Rolf; Attwood, Teresa K; Bateman, Alex; Bernard, Thomas; Binns, David; Bork, Peer; Burge, Sarah; de Castro, Edouard; Coggill, Penny; et al. (Nucleic Acids Res, 2012)
InterPro (http://www.ebi.ac.uk/interpro/) is a database that integrates diverse information about protein families, domains and functional sites, and makes it freely available to the public via Web-based interfaces and services. Central to the database are diagnostic models, known as signatures, against which protein sequences can be searched to determine their potential function. InterPro has utility in the large-scale analysis of whole genomes and meta-genomes, as well as in characterizing individual protein sequences. Herein we give an overview of new developments in the database and its associated software since 2009, including updates to database content, curation processes and Web and programmatic interfaces.
Keywords: Databases, Protein; Protein Structure, Tertiary; Proteins; Sequence Analysis, Protein; software; Terminology as Topic; User-Computer Interface

Vibrio Cholerae Classical Biotype Strains Reveal Distinct Signatures in Mexico - Alam,Munirul; Islam,M. Tarequl; Rashed,Shah Manzur; Johura,Fatema-Tuz; Bhuiyan,Nurul A.; Delgado,Gabriela; Morales,Rosario; Mendez,Jose Luis; Navarro,Armando; Watanabe,Haruo; Hasan,Nur-A.; Rita R Colwell; et al. (Journal of Clinical Microbiology, 2012)
Vibrio cholerae O1 Classical (CL) biotype caused the 5th and 6th, and probably the earlier cholera pandemics, before the El Tor (ET) biotype initiated the 7th pandemic in Asia in the 1970's by completely displacing the CL biotype. Although the CL biotype was thought to be extinct in Asia, and it had never been reported from Latin America, V. cholerae CL and ET biotypes, including hybrid ET were found associated with endemic cholera in Mexico between 1991 and 1997. In this study, CL biotype strains isolated from endemic cholera in Mexico, between 1983 and 1997 were characterized in terms of major phenotypic and genetic traits, and compared with CL biotype strains isolated in Bangladesh between 1962 and 1989. According to sero- and bio-typing data, all V. cholerae strains tested had the major phenotypic and genotypic characteristics specific for the CL biotype. Antibiograms revealed the majority of the Bangladeshi strains to be resistant to trimethoprim/sulfamethoxazole, furazolidone, ampicillin, and gentamycin, while the Mexican strains were sensitive to all of these drugs, as well as to ciprofloxacin, erythromycin, and tetracycline. Pulsed-field gel electrophoresis (PFGE) of NotI-digested genomic DNA revealed characteristic banding patterns for all the CL biotype strains, although the Mexican strains differed with the Bangladeshi strains in 1-2 DNA bands. The difference may be subtle, but consistent, as confirmed by the sub-clustering patterns in the PFGE-based dendrogram, and can serve as regional signature, suggesting pre-1991 existence and evolution of the CL biotype strains in the Americas, independent from that of Asia.

Making Recommendations in a Microblog to Improve the Impact of a Focal User - Wu,Shanchan; Gong, Leanna; Rand, William; Raschid, Louiqa (6th ACM Conference on Recommender Systems (RecSys), 2012)
We present a microblog recommendation system that can help monitor users, track conversations, and potentially improve diffusion impact. Given a Twitter network of active users and their followers, and historical activity of tweets, retweets and mentions, we build upon a prediction tool to predict the Top K users who will retweet or mention a focal user, in the future [10]. We develop personalized recommendations for each focal user. We identify characteristics of focal users such as the size of the follower network, or the level of sentiment averaged over all tweets; both have an impact on the quality of personalized recommendations. We use (high) betweenness centrality as a proxy of attractive users to target when making recommendations. Our recommendations successfully identify a greater fraction of users with higher betweenness centrality, in comparison to the overall distribution of betweenness centrality of the ground truth users for some focal user.

Mapping Parameterized Cyclo-static Dataflow Graphs onto Configurable Hardware - Kee, Hojin; Chung-Ching Shen; Bhattacharyya, Shuvra S.; Wong, Ian; Yong Rao; Kornerup, Jacob (Journal of Signal Processing Systems, 2012)
In recent years, parameterized dataflow has evolved as a useful framework for modeling synchronous and cyclo-static graphs in which arbitrary parameters can be changed dynamically. Parameterized dataflow has proven to have significant expressive power for managing dynamics of DSP applications in important ways. However, efficient hardware synthesis techniques for parameterized dataflow representations are lacking. This paper addresses this void; specifically, the paper investigates efficient field programmable gate array (FPGA)-based implementation of parameterized cyclo-static dataflow (PCSDF) graphs. We develop a scheduling technique for throughput-constrained minimization of dataflow buffering requirements when mapping PCSDF representations of DSP applications onto FPGAs. The proposed scheduling technique is integrated with an existing formal schedule model, called the generalized schedule tree, to reduce schedule cost. To demonstrate our new, hardware-oriented PCSDF scheduling technique, we have designed a real-time base station emulator prototype based on a subset of long-term evolution (LTE), which is a key cellular standard.
Keywords: 4G communication systems; Circuits and Systems; Computer Imaging, Vision, Pattern Recognition and Graphics; Dataflow modeling; Electrical Engineering; FPGA implementation; Image Processing and Computer Vision; Parameterized dataflow; pattern recognition; scheduling; Signal, Image and Speech Processing

Modeling Images using Transformed Indian Buffet Processes - Zhai,Ke; Hu,Yuening; Williamson,Sinead; Jordan Boyd-Graber (International Conference of Machine Learning, 2012)
Latent feature models are attractive for image modeling, since images generally contain mul- tiple objects. However, many latent feature models ignore that objects can appear at dif- ferent locations or require pre-segmentation of images. While the transformed Indian buffet process (tIBP) provides a method for modeling transformation-invariant features in unsegmented binary images, its current form is inappropriate for real images because of its computational cost and modeling assumptions. We combine the tIBP with likelihoods appropriate for real images and develop an efficient inference, using the cross- correlation between images and features, that is theoretically and empirically faster than existing inference techniques. Our method discovers rea- sonable components and achieve effective image reconstruction in natural images.

An Optimized High-Throughput Strategy for Constructing Inverted Files - Wei,Z.; JaJa, Joseph F. (Parallel and Distributed Systems, IEEE Transactions on, 2012)
Current high-throughput algorithms for constructing inverted files all follow the MapReduce framework, which presents a high-level programming model that hides the complexities of parallel programming. In this paper, we take an alternative approach and develop a novel strategy that exploits the current and emerging architectures of multicore processors. Our algorithm is based on a high-throughput pipelined strategy that produces parallel parsed streams, which are immediately consumed at the same rate by parallel indexers. We have performed extensive tests of our algorithm on a cluster of 32 nodes, and were able to achieve a throughput close to the peak throughput of the I/O system: a throughput of 280 MB/s on a single node and a throughput that ranges between 5.15 GB/s (1 Gb/s Ethernet interconnect) and 6.12GB/s (10Gb/s InfiniBand interconnect) on a cluster with 32 nodes for processing the ClueWeb09 dataset. Such a performance represents a substantial gain over the best known MapReduce algorithms even when comparing the single node performance of our algorithm to MapReduce algorithms running on large clusters. Our results shed a light on the extent of the performance cost that may be incurred by using the simpler, higher-level MapReduce programming model for large scale applications.

Querying event sequences by exact match or similarity search: Design and empirical evaluation - Wongsuphasawat,Krist; Plaisant, Catherine; Taieb-Maimon,Meirav; Shneiderman, Ben (Interacting with Computers, 2012)
Specifying event sequence queries is challenging even for skilled computer professionals familiar with SQL. Most graphical user interfaces for database search use an exact match approach, which is often effective, but near misses may also be of interest. We describe a new similarity search interface, in which users specify a query by simply placing events on a blank timeline and retrieve a similarity-ranked list of results. Behind this user interface is a new similarity measure for event sequences which the users can customize by four decision criteria, enabling them to adjust the impact of missing, extra, or swapped events or the impact of time shifts. We describe a use case with Electronic Health Records based on our ongoing collaboration with hospital physicians. A controlled experiment with 18 participants compared exact match and similarity search interfaces. We report on the advantages and disadvantages of each interface and suggest a hybrid interface combining the best of both.
Keywords: Event sequence; Similan; similarity measure; Similarity Search; temporal categorical data; Temporal query interface

Role of Shrimp Chitin in the Ecology of Toxigenic Vibrio cholerae and Cholera Transmission - Nahar,Shamsun; Sultana,Marzia; Naser,M. Niamul; Nair,Gopinath B.; Watanabe,Haruo; Ohnishi,Makoto; Yamamoto,Shouji; Endtz,Hubert; Cravioto,Alejandro; Sack,R. Bradley; Hasan,Nur A.; Sadique,Abdus; et al. (Frontiers in Microbiology, 2012)
Seasonal plankton blooms correlate with occurrence of cholera in Bangladesh, although the mechanism of how dormant Vibrio cholerae, enduring interepidemic period in biofilms and plankton, initiates seasonal cholera is not fully understood. In this study, laboratory microcosms prepared with estuarine Mathbaria water (MW) samples supported active growth of toxigenic V. cholerae O1 up to 7 weeks as opposed to 6 months when microcosms were supplemented with dehydrated shrimp chitin chips (CC) as the single source of nutrient. Bacterial counting and detection of wbe and ctxA genes were done employing culture, direct fluorescent antibody (DFA) assay, and multiplex-polymerase chain reaction methods. In MW microcosm, the aqueous phase became clear as the non-culturable cells settled, whereas the aqueous phase of the MW–CC microcosm became turbid from bacterial growth stimulated by chitin. Bacterial chitin degradation and biofilm formation proceeded from an initial steady state to a gradually declining bacterial culturable count. V. cholerae within the microenvironments of chitin and chitin-associated biofilms remained metabolically active even in a high acidic environment without losing either viability or virulence. It is concluded that the abundance of chitin that occurs during blooms plays an important role in the aquatic life cycle of V. cholerae and, ultimately, in the seasonal transmission of cholera.

A Temporal Pattern Search Algorithm for Personal History Event Visualization - Wang,T. D; Deshpande, Amol; Shneiderman, Ben (Knowledge and Data Engineering, IEEE Transactions on, 2012)
We present Temporal Pattern Search (TPS), a novel algorithm for searching for temporal patterns of events in historical personal histories. The traditional method of searching for such patterns uses an automaton-based approach over a single array of events, sorted by time stamps. Instead, TPS operates on a set of arrays, where each array contains all events of the same type, sorted by time stamps. TPS searches for a particular item in the pattern using a binary search over the appropriate arrays. Although binary search is considerably more expensive per item, it allows TPS to skip many unnecessary events in personal histories. We show that TPS's running time is bounded by O(m2n lg(n)), where m is the length of (number of events) a search pattern, and n is the number of events in a record (history). Although the asymptotic running time of TPS is inferior to that of a nondeterministic finite automaton (NFA) approach (O(mn)), TPS performs better than NFA under our experimental conditions. We also show TPS is very competitive with Shift-And, a bit-parallel approach, with real data. Since the experimental conditions we describe here subsume the conditions under which analysts would typically use TPS (i.e., within an interactive visualization program), we argue that TPS is an appropriate design choice for us.
Keywords: automaton-based approach; binary search; bit-parallel approach; data visualisation; electronic health records; event array; finite automata; interactive visualization program; Lifelines2 visualization tool; medical information systems; NFA approach; nondeterministic finite automaton; O(m2n lg(n)) problem; pattern matching; personal history event visualization; Shift-And approach; temporal pattern search algorithm; time stamp

Towards event sequence representation, reasoning and visualization for EHR data - Tao,Cui; Wongsuphasawat,Krist; Clark,Kimberly; Plaisant, Catherine; Shneiderman, Ben; Chute,Christopher G. (Proceedings of the 2nd ACM SIGHIT International Health Informatics Symposium, 2012)
Efficient analysis of event sequences and the ability to answer time-related, clinically important questions can accelerate clinical research in several areas such as causality assessments, decision support systems, and retrospective studies. The Clinical Narrative Temporal Reasoning Ontology (CNTRO)-based system is designed for semantically representing, annotating, and inferring temporal relations and constraints for clinical events in Electronic Health Records (EHR) represented in both structured and unstructured ways. The LifeFlow system is designed to support an interactive exploration of event sequences using visualization techniques. The combination of the two systems will provide a comprehensive environment for users to visualize inferred temporal relationships from EHR data. This paper discusses our preliminary efforts on connecting the two systems and the benefits we envision from such an environment.
Keywords: ehr; semantic web; temporal relation reasoning; time trend visualization

Whole genome analysis of Leptospira licerasiae provides insight into leptospiral evolution and pathogenicity. - Ricaldi, Jessica N; Fouts, Derrick E; Jeremy D Selengut; Harkins, Derek M; Patra, Kailash P; Moreno, Angelo; Lehmann, Jason S; Purushe, Janaki; Sanka, Ravi; Torres, Michael; Webster, Nicholas J; Vinetz, Joseph M; et al. (PLoS Negl Trop Dis, 2012)
The whole genome analysis of two strains of the first intermediately pathogenic leptospiral species to be sequenced (Leptospira licerasiae strains VAR010 and MMD0835) provides insight into their pathogenic potential and deepens our understanding of leptospiral evolution. Comparative analysis of eight leptospiral genomes shows the existence of a core leptospiral genome comprising 1547 genes and 452 conserved genes restricted to infectious species (including L. licerasiae) that are likely to be pathogenicity-related. Comparisons of the functional content of the genomes suggests that L. licerasiae retains several proteins related to nitrogen, amino acid and carbohydrate metabolism which might help to explain why these Leptospira grow well in artificial media compared with pathogenic species. L. licerasiae strains VAR010(T) and MMD0835 possess two prophage elements. While one element is circular and shares homology with LE1 of L. biflexa, the second is cryptic and homologous to a previously identified but unnamed region in L. interrogans serovars Copenhageni and Lai. We also report a unique O-antigen locus in L. licerasiae comprised of a 6-gene cluster that is unexpectedly short compared with L. interrogans in which analogous regions may include >90 such genes. Sequence homology searches suggest that these genes were acquired by lateral gene transfer (LGT). Furthermore, seven putative genomic islands ranging in size from 5 to 36 kb are present also suggestive of antecedent LGT. How Leptospira become naturally competent remains to be determined, but considering the phylogenetic origins of the genes comprising the O-antigen cluster and other putative laterally transferred genes, L. licerasiae must be able to exchange genetic material with non-invasive environmental bacteria. The data presented here demonstrate that L. licerasiae is genetically more closely related to pathogenic than to saprophytic Leptospira and provide insight into the genomic bases for its infectiousness and its unique antigenic characteristics.
Keywords: DNA, Bacterial; Evolution, Molecular; Gene Transfer, Horizontal; Genome, Bacterial; Genomic islands; HUMANS; Leptospira; Molecular Sequence Data; Multigene Family; Prophages; Sequence Analysis, DNA; Virulence factors

Ability-based design: Concept, principles and examples - Wobbrock,J.O.; Kane,S.K.; Gajos,K.Z.; Harada,S.; Jon Froehlich (ACM Transactions on Accessible Computing (TACCESS), 2011)

Analyzing Incident Management Event Sequences with Interactive Visualization - Guerra Gómez,J.; Wongsuphasawat,K.; Wang,T. D; Pack,M.; Plaisant, Catherine (Transportation Research Board 90th Annual Meeting Compendium of Papers, 2011)
While traditional safety and incident analysis has mostly focused on incident attributesdata, such as the location and time of the incident, there are other aspects in incident response that are temporal in nature and are more difficult to analyze. We describe a visual analytics tool for temporal data exploration, called LifeFlow, used for the analysis of incident response data. LifeFlow provides user-controlled overviews of event sequences (e.g. notification, arrival, clearance etc). It allows analysts to interactively explore temporal patterns, find anomalies in sequences and compare management practices. This type of analysis can potentially lead to process improvements and save human lives. We used NCHRP traffic incident data with more than 200,000 incidents are reported by 8 different agencies in a period of about 28 months. Our experience suggest that even non expert analysts can spot many anomalies in the data using the LifeFlow overviews, and are able to rapidly ask many questions and find differences between agencies.

Assessing the benefits of using mate-pairs to resolve repeats in de novo short-read prokaryotic assemblies - Wetzel,Joshua; Kingsford, Carl; Pop, Mihai (BMC Bioinformatics, 2011)
Next-generation sequencing technologies allow genomes to be sequenced more quickly and less expensively than ever before. However, as sequencing technology has improved, the difficulty of de novo genome assembly has increased, due in large part to the shorter reads generated by the new technologies. The use of mated sequences (referred to as mate-pairs) is a standard means of disambiguating assemblies to obtain a more complete picture of the genome without resorting to manual finishing. Here, we examine the effectiveness of mate-pair information in resolving repeated sequences in the DNA (a paramount issue to overcome). While it has been empirically accepted that mate-pairs improve assemblies, and a variety of assemblers use mate-pairs in the context of repeat resolution, the effectiveness of mate-pairs in this context has not been systematically evaluated in previous literature.

An assessment of systems and software engineering scholars and institutions (2003–2007 and 2004–2008) - Wong,W. Eric; Tse,T.H.; Glass,Robert L.; Basili, Victor R.; Chen,T.Y. (Journal of Systems and Software, 2011)
An ongoing, annual survey of publications in systems and software engineering identifies the top 15 scholars and institutions in the field over a 5-year period. Each ranking is based on the weighted scores of the number of papers published in TSE, TOSEM, JSS, SPE, EMSE, IST, and Software of the corresponding period. This report summarizes the results for 2003–2007 and 2004–2008. The top-ranked institution is Korea Advanced Institute of Science and Technology, Korea for 2003–2007, and Simula Research Laboratory, Norway for 2004–2008, while Magne Jørgensen is the top-ranked scholar for both periods.
Keywords: Research publications; Systems and software engineering; Top institutions; Top scholars

AVSS 2011 demo session: A large-scale benchmark dataset for event recognition in surveillance video - Oh,Sangmin; Hoogs,Anthony; Perera,Amitha; Cuntoor,Naresh; Chen,Chia-Chih; Lee,Jong Taek; Mukherjee,Saurajit; Aggarwal, JK; Lee,Hyungtae; Davis, Larry S.; Swears,Eran; Wang,Xiaoyang; et al. (Advanced Video and Signal-Based Surveillance (AVSS), 2011 8th IEEE International Conference on, 2011)
We introduce to the surveillance community the VIRAT Video Dataset[1], which is a new large-scale surveillance video dataset designed to assess the performance of event recognition algorithms in realistic scenes1.

Bacillus Anthracis Comparative Genome Analysis in Support of the Amerithrax Investigation - Rasko,David A; Worsham,Patricia L; Abshire,Terry G; Stanley,Scott T; Bannan,Jason D; Wilson,Mark R; Langham,Richard J; Decker,R. Scott; Jiang,Lingxia; Read,Timothy D.; Phillippy,Adam M; Salzberg,Steven L.; et al. (Proceedings of the National Academy of SciencesPNAS, 2011)
Before the anthrax letter attacks of 2001, the developing field of microbial forensics relied on microbial genotyping schemes based on a small portion of a genome sequence. Amerithrax, the investigation into the anthrax letter attacks, applied high-resolution whole-genome sequencing and comparative genomics to identify key genetic features of the letters’ Bacillus anthracis Ames strain. During systematic microbiological analysis of the spore material from the letters, we identified a number of morphological variants based on phenotypic characteristics and the ability to sporulate. The genomes of these morphological variants were sequenced and compared with that of the B. anthracis Ames ancestor, the progenitor of all B. anthracis Ames strains. Through comparative genomics, we identified four distinct loci with verifiable genetic mutations. Three of the four mutations could be directly linked to sporulation pathways in B. anthracis and more specifically to the regulation of the phosphorylation state of Spo0F, a key regulatory protein in the initiation of the sporulation cascade, thus linking phenotype to genotype. None of these variant genotypes were identified in single-colony environmental B. anthracis Ames isolates associated with the investigation. These genotypes were identified only in B. anthracis morphotypes isolated from the letters, indicating that the variants were not prevalent in the environment, not even the environments associated with the investigation. This study demonstrates the forensic value of systematic microbiological analysis combined with whole-genome sequencing and comparative genomics.

Believe Me—We Can Do This! Annotating Persuasive Acts in Blog Text - Anand,P.; King,J.; Jordan Boyd-Graber; Wagner,E.; Martell,C.; Oard, Douglas; Resnik, Philip (Workshops at the Twenty-Fifth AAAI Conference on Artificial Intelligence, 2011)

Can Deliberately Incomplete Gene Sample Augmentation Improve a Phylogeny Estimate for the Advanced Moths and Butterflies (Hexapoda: Lepidoptera)? - Cho,Soowon; Zwick,Andreas; Regier,Jerome C; Mitter,Charles; Cummings, Michael P.; Yao,Jianxiu; Du,Zaile; Zhao,Hong; Kawahara,Akito Y; Weller,Susan; Davis,Donald R; Baixeras,Joaquin; et al. (Systematic BiologySyst Biol, 2011)
This paper addresses the question of whether one can economically improve the robustness of a molecular phylogeny estimate by increasing gene sampling in only a subset of taxa, without having the analysis invalidated by artifacts arising from large blocks of missing data. Our case study stems from an ongoing effort to resolve poorly understood deeper relationships in the large clade Ditrysia ( > 150,000 species) of the insect order Lepidoptera (butterflies and moths). Seeking to remedy the overall weak support for deeper divergences in an initial study based on five nuclear genes (6.6 kb) in 123 exemplars, we nearly tripled the total gene sample (to 26 genes, 18.4 kb) but only in a third (41) of the taxa. The resulting partially augmented data matrix (45% intentionally missing data) consistently increased bootstrap support for groupings previously identified in the five-gene (nearly) complete matrix, while introducing no contradictory groupings of the kind that missing data have been predicted to produce. Our results add to growing evidence that data sets differing substantially in gene and taxon sampling can often be safely and profitably combined. The strongest overall support for nodes above the family level came from including all nucleotide changes, while partitioning sites into sets undergoing mostly nonsynonymous versus mostly synonymous change. In contrast, support for the deepest node for which any persuasive molecular evidence has yet emerged (78–85% bootstrap) was weak or nonexistent unless synonymous change was entirely excluded, a result plausibly attributed to compositional heterogeneity. This node (Gelechioidea + Apoditrysia), tentatively proposed by previous authors on the basis of four morphological synapomorphies, is the first major subset of ditrysian superfamilies to receive strong statistical support in any phylogenetic study. A “more-genes-only” data set (41 taxa×26 genes) also gave strong signal for a second deep grouping (Macrolepidoptera) that was obscured, but not strongly contradicted, in more taxon-rich analyses.
Keywords: Ditrysia; gene sampling; Hexapoda; Lepidoptera; missing data; molecular phylogenetics; nuclear genes; taxon sampling

A case for query by image and text content: searching computer help using screenshots and keywords - Tom Yeh; White,Brandyn; San Pedro,Jose; Katz,Boriz; Davis, Larry S. (Proceedings of the 20th international conference on World wide web, 2011)
The multimedia information retrieval community has dedicated extensive research effort to the problem of content-based image retrieval (CBIR). However, these systems find their main limitation in the difficulty of creating pictorial queries. As a result, few systems offer the option of querying by visual examples, and rely on automatic concept detection and tagging techniques to provide support for searching visual content using textual queries.This paper proposes and studies a practical multimodal web search scenario, where CBIR fits intuitively to improve the retrieval of rich information queries. Many online articles contain useful know-how knowledge about computer applications. These articles tend to be richly illustrated by screenshots. We present a system to search for such software know-how articles that leverages the visual correspondences between screenshots. Users can naturally create pictorial queries simply by taking a screenshot of the application to retrieve a list of articles containing a matching screenshot. We build a prototype comprising 150k articles that are classified into walkthrough, book, gallery, and general categories, and provide a comprehensive evaluation of this system, focusing on technical (accuracy of CBIR techniques) and usability (perceived system usefulness) aspects. We also consider the study of added value features of such a visual-supported search, including the ability to perform cross-lingual queries. We find that the system is able to retrieve matching screenshots for a wide variety of programs, across language boundaries, and provide subjectively more useful results than keyword-based web and image search engines.
Keywords: content-based image retrieval; multimodal search; online help

A case for query by image and text content: searching computer help using screenshots and keywords - Tom Yeh; White,Brandyn; San Pedro,Jose; Katz,Boriz; Davis, Larry S. (Proceedings of the 20th international conference on World wide web, 2011)
The multimedia information retrieval community has dedicated extensive research effort to the problem of content-based image retrieval (CBIR). However, these systems find their main limitation in the difficulty of creating pictorial queries. As a result, few systems offer the option of querying by visual examples, and rely on automatic concept detection and tagging techniques to provide support for searching visual content using textual queries. This paper proposes and studies a practical multimodal web search scenario, where CBIR fits intuitively to improve the retrieval of rich information queries. Many online articles contain useful know-how knowledge about computer applications. These articles tend to be richly illustrated by screenshots. We present a system to search for such software know-how articles that leverages the visual correspondences between screenshots. Users can naturally create pictorial queries simply by taking a screenshot of the application to retrieve a list of articles containing a matching screenshot. We build a prototype comprising 150k articles that are classified into walkthrough, book, gallery, and general categories, and provide a comprehensive evaluation of this system, focusing on technical (accuracy of CBIR techniques) and usability (perceived system usefulness) aspects. We also consider the study of added value features of such a visual-supported search, including the ability to perform cross-lingual queries. We find that the system is able to retrieve matching screenshots for a wide variety of programs, across language boundaries, and provide subjectively more useful results than keyword-based web and image search engines.
Keywords: content-based image retrieval; multimodal search; online help

Citation Handling for Improved Summarization of Scientific Documents - Whidby,Michael; Zajic, David; Dorr, Bonnie J (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2011)
In this paper we present the first steps toward improving summarizationof scientific documents through citation analysis and parsing. Prior work (Mohammad et al., 2009) argues that citation texts (sentences that cite other papers) play a crucial role in automatic summarization of a topical area, but did not take into account the noise introduced by the citations themselves. We demonstrate that it is possible to improve summarization output through careful handling of these citations. We base our experiments on the application of an improved trimming approach to summarization of citation texts extracted from Question-Answering and Dependency-Parsing documents. We demonstrate that confidence scores from the Stanford NLP Parser (Klein and Manning, 2003) are significantly improved, and that Trimmer (Zajic et al., 2007), a sentence-compression tool, is able to generate higher-quality candidates. Our summarization output is currently used as part of a larger system, Action Science Explorer (ASE) (Gove, 2011).
Keywords: Technical Report

Clonal transmission, dual peak, and off-season cholera in Bangladesh - Alam,M.; Islam,A.; Bhuiyan,N. A.; Rahim,N.; Hossain,A.; Khan,G. Y.; Ahmed,D.; Watanabe,H.; Izumiya,H.; Faruque,A. S. G.; Rita R Colwell (Infection Ecology & Epidemiology, 2011)
Vibrio cholerae is an estuarine bacterium associated with a single peak of cholera (March–May) in coastal villages of Bangladesh. For an unknown reason, however, cholera occurs in a unique dual peak (March–May and September–November) pattern in the city of Dhaka that is bordered by a heavily polluted freshwater river system and flood embankment. In August 2007, extreme flooding was accompanied by an unusually severe diarrhea outbreak in Dhaka that resulted in a record high illness. This study was aimed to understand the unusual outbreak and if it was related to the circulation of a new V. cholerae clone. Nineteen V. cholerae isolated during the peak of the 2007 outbreak were subjected to extensive phenotypic and molecular analyses, including multi-locus genetic screening by polymerase chain reaction (PCR), sequence-typing of the ctxB gene, and pulsed-field gel electrophoresis (PFGE). Factors associated with the unusual incidence of cholera were determined and analysis of the disease severity was done. Overall, microbiological and molecular data confirmed that the hypervirulent V. cholerae was O1 biotype El Tor (ET) that possessed cholera toxin (CT) of the classical biotype. The PFGE (NotI) and dendrogram clustering confirmed that the strains were clonal and related to the pre-2007 variant ET from Dhaka and Matlab and resembled one of two distinct clones of the variant ET confirmed to be present in the estuarine ecosystem of Bangladesh. Results of the analyses of both diarrheal case data for three consecutive years (2006–2008) and regional hydroclimatology over three decades (1980–2009) clearly indicate that the pattern of cholera occurring in Dhaka, and not seen at other endemic sites, was associated with flood waters transmitting the infectious clone circulating via the fecal-oral route during and between the dual seasonal cholera peaks in Dhaka. Circular river systems and flood embankment likely facilitate transmission of infectious V. cholerae throughout the year that leads to both sudden and off-season outbreaks in the densely populated urban ecosystem of Dhaka. Clonal recycling of hybrid El Tor with increasing virulence in a changing climate and in a region with a growing urban population represents a serious public health concern for Bangladesh.

A computational framework for authoring and searching product design specifications - Weissman,Alexander; Petrov,Martin; Gupta, Satyandra K. (Advanced Engineering Informatics, 2011)
The development of product design specifications (PDS) is an important part of the product development process. Incompleteness, ambiguity, or inconsistency in the PDS can lead to problems during the design process and may require unnecessary design iterations. This generally results in increased design time and cost. Currently, in many organizations, PDS are written using word processors. Since documents written by different authors can be inconsistent in style and word choice, it is difficult to automatically search for specific requirements. Moreover, this approach does not allow the possibility of automated design verification and validation against the design requirements and specifications.In this paper, we present a computational framework and a software tool based on this framework for writing, annotating, and searching computer-interpretable PDS. Our approach allows authors to write requirement statements in natural language to be consistent with the existing authoring practice. However, using mathematical expressions, keywords from predefined taxonomies, and other metadata the author of PDS can then annotate different parts of the requirement statements. This approach provides unambiguous meaning to the information contained in PDS, and helps to eliminate mistakes later in the process when designers must interpret requirements. Our approach also enables users to construct a new PDS document from the results of the search for requirements of similar devices and in similar contexts. This capability speeds up the process of creating PDS and helps authors write more detailed documents by utilizing previous, well written PDS documents. Our approach also enables checking for internal inconsistencies in the requirement statements.
Keywords: Engineering design; Product design specifications; Requirements engineering

A Constraint-Reduced Variant of Mehrotra's Predictor-Corrector Algorithm - Winternitz,Luke B.; Nicholls,Stacey O.; Tits,André; O'Leary, Dianne P. (Computational Optimization and Applications, 2011)

Constructing Inverted Files on a Cluster of Multicore Processors Near Peak I/O Throughput - Wei, Zheng; JaJa, Joseph F. (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2011)
We develop a new strategy for processing a collection of documents on a cluster of multicore processors to build the inverted files at almost the peak I/O throughput of the underlying system. Our algorithm is based on a number of novel techniques including: (i) a high-throughput pipelined strategy that produces parallel parsed streams that are consumed at the same rate by parallel indexers; (ii) a hybrid trie and B-tree dictionary data structure that enables efficient parallel construction of the global dictionary; and (iii) a partitioning strategy of the work of the indexers using random sampling, which achieve extremely good load balancing with minimal communication overhead. We have performed extensive tests of our algorithm on a cluster of 32 nodes, each consisting of two Intel Xeon X5560 Quad-core, and were able to achieve a throughput close to the peak throughput of the I/O system. In particular, we achieve a throughput of 280 MB/s on a single node and a throughput of 6.12GB/s on a cluster with 32 nodes for processing the ClueWeb09 dataset. Similar results were obtained for widely different datasets. The throughput of our algorithm is superior to the best known algorithms reported in the literature even when compared to those running on much larger clusters.
Keywords: Technical Report

Countering Botnets: Anomaly-Based Detection, Comprehensive Analysis, and Efficient Mitigation - Lee,Wenke; Dagon,David; Giffin,Jon; Feamster, Nick; Ollman,Gunter; Westby,Jody; Wesson,Rick; Vixie,Paul (GEORGIA TECH RESEARCH CORP ATLANTA, 2011)
We cover five general areas: (1) botnet detection, (2) botnet analysis, (3) botnet mitigation, (4) add-on tasks to the original contract, including the Conficker Working Group Lessons Learned, Layer-8 Exploration of Botnet Organization, and DREN research, and (5) commercialization in this paper. We have successfully developed new botnet detection and analysis capabilities in this project. These algorithms have been evaluated using real-world data, and have been put into actual, deployed systems. The most significant technical developments include a new dynamic reputation systems for DNS domains, a scalable anomaly detection system for botnet detection in very large network, and a transparent malware analysis system. In addition, on several occasions we have used our botnet data and analysis to help law enforcement agencies arrest botmasters. We also have had great success transitioning technologies to commercial products that are now used by government agencies, ISPs, and major corporations.
Keywords: *ELECTRONIC SECURITY; *INFORMATION SECURITY; *INTERNET; *INTRUSION DETECTION(COMPUTERS); algorithms; BGP ROUTE INJECTION; BGP(BORDER GATEWAY PROTOCOLS); BOTNET DETECTION; BOTNET TRACEBACK AND ATTRIBUTION; BOTNETS(MALWARE); CLIENT SERVER SYSTEMS; COMMUNICATIONS PROTOCOLS; COMPUTER PROGRAMMING AND SOFTWARE; COMPUTER SYSTEMS MANAGEMENT AND STANDARDS; CYBER ATTACKS; CYBER SECURITY; CYBERNETICS; CYBERTERRORISM; CYBERWARFARE; DATA PROCESSING SECURITY; DNS BASED MONITORING; DNS BASED REDIRECTION; DNS(DOMAIN NAME SYSTEMS); INFORMATION SCIENCE; INTERNET BROWSERS; ISP(INTERNET SERVICE PROVIDERS); MALWARE; MALWARE ANALYSIS; Online Systems; WUAFRLDHS1BOTN

Co‐designing contextual tutorials for older adults on searching health information on the internet - Xie,Bo; Tom Yeh; Walsh,Greg; Watkins,Ivan; Huang,Man (Proceedings of the American Society for Information Science and Technology, 2011)
Evidence in the literature suggests an integrated e-tutorial is more effective than a paper- or video-based tutorial among younger people. Yet, relatively little is known about the effectiveness of an integrated e-tutorial on the older population. This study explored the applicability of an integrated e-tutorial to an older population, focusing on the content area of e-health literacy. A specific integrated e- tutorial, the Online Tutorial Overlay Presenter (OnTOP), was used to add an overlay to the NIHSeniorHealth.gov Website. Features of the overlay were examined thoroughly in seven 2-hour-long participatory design sessions with ten older adults. Several participatory design techniques were used to elicit participants' preferences for design features of the OnTOP tutorial. These techniques included drawing on the board, voice recording and integration, and peer instruction. Three major themes emerged: 1) using contextual cues to facilitate learning; 2) tailoring to accommodate the learner's literacy level; and 3) enhancing existing interfaces with multimedia cues. These findings improved the design of OnTOP. They also contribute to the multimedia learning literature, generating empirical evidence about the effects of multimedia learning among the understudied older adult population.

Creating contextual help for GUIs using screenshots - Tom Yeh; Chang,Tsung-Hsiang; Xie,Bo; Walsh,Greg; Watkins,Ivan; Wongsuphasawat,Krist; Huang,Man; Davis, Larry S.; Bederson, Benjamin B. (Proceedings of the 24th annual ACM symposium on User interface software and technology, 2011)
Contextual help is effective for learning how to use GUIs by showing instructions and highlights on the actual interface rather than in a separate viewer. However, end-users and third-party tech support typically cannot create contextual help to assist other users because it requires programming skill and source code access. We present a creation tool for contextual help that allows users to apply common computer skills-taking screenshots and writing simple scripts. We perform pixel analysis on screenshots to make this tool applicable to a wide range of applications and platforms without source code access. We evaluated the tool's usability with three groups of participants: developers, in-structors, and tech support. We further validated the applicability of our tool with 60 real tasks supported by the tech support of a university campus.
Keywords: contextual help; help; pixel analysis

Cross-Language Entity Linking in Maryland during a Hurricane - McNamee,Paul; Mayfield,James; Oard, Douglas; David Doermann; Xu,Tan; Wu,Ke (TAC, 2011)
Our team from the JHUHLTCOE and the University of Maryland submitted runs for all three variants of the TACKBP entity linking task. For the monolingual tasks, we essentially mirrored our HLTCOETAC-KBP 2010 submission, making only modest changes to accommodate differences in 2011, namely the requirement to cluster NIL responses, and the change in evaluation measure. However, our work on the cross-lingual task was significantly more involved, requiring development of robust, multiphased transliteration software, use of techniques in cross-language information retrieval, and reliance on a Chinese-to- English statistical machine translation system. In this paper we describe our work for the 2011 evaluation and the results we obtained.

Dataflow-Based Implementation of Layered Sensing Applications - Bhattacharyya, Shuvra S.; Chung-Ching Shen; Plishker,William; Sane, Nimish; Wu, Hsiang-Huang; Gu, Ruirui (2011)
This report describes a new dataflow-based technology and associated design tools for high-productivity design, analysis, and optimization of layered sensing software for signal processing systems. Our approach provides novel capabilities, based on the principles of task-level dataflow analysis, for exploring and optimizing interactions across application behavior; operational context; high performance embedded processing platforms, and implementation constraints. Particularly, we introduce and deliver novel software tools, called the targeted dataflow interchange format (TDIF) and Dataflow Interchange Format Markup Language (DIFML), for design and implementation of layered sensing and signal processing systems. The TDIF-CUDA (Compute Unified Device Architecture) environment is a graphics processing unit targeted software synthesis tool that provides a unique integration of dynamic dataflow modeling; retargetable actor construction; software synthesis; and instrumentation-based schedule evaluation and tuning. The DIFML package is a software package for the DIFML format, which is an Extensible Markup Language (XML)-based format for exchanging information between DIF and other tools.
Keywords: *COMPUTER AIDED DESIGN; *DATA FUSION; *DATAFLOW; *LAYERS; *SOFTWARE TOOLS; COMPUTER PROGRAMMING AND SOFTWARE; DETECTION; High performance computing; LAYERED SENSING; OPTIMIZATION; Signal processing; synthesis; T2KA

A design tool for efficient mapping of multimedia applications onto heterogeneous platforms - Chung-Ching Shen; Wu, Hsiang-Huang; Sane, N.; Plishker,W.; Bhattacharyya, Shuvra S. (2011 IEEE International Conference on Multimedia and Expo (ICME), 2011)
Development of multimedia systems on heterogeneous platforms is a challenging task with existing design tools due to a lack of rigorous integration between high level abstract modeling, and low level synthesis and analysis. In this paper, we present a new dataflow-based design tool, called the targeted dataflow interchange format (TDIF), for design, analysis, and implementation of embedded software for multimedia systems. Our approach provides novel capabilities, based on the principles of task-level dataflow analysis, for exploring and optimizing interactions across application behavior; operational context; heterogeneous platforms, including high performance embedded processing architectures; and implementation constraints.
Keywords: Dataflow graphs; design tools; embedded signal processing; software synthesis

Direct targeting of Sec23a by miR-200s influences cancer cell secretome and promotes metastatic colonization - Korpal, Manav; Ell, Brian J.; Buffa, Francesca M.; Ibrahim, Toni; Blanco, Mario A.; Celià-Terrassa, Toni; Mercatali, Laura; Zia Khan; Goodarzi, Hani; Hua, Yuling; Wei, Yong; Hu, Guohong; et al. (Nature Medicine, 2011)
Although the role of miR-200s in regulating E-cadherin expression and epithelial-to-mesenchymal transition is well established, their influence on metastatic colonization remains controversial. Here we have used clinical and experimental models of breast cancer metastasis to discover a pro-metastatic role of miR-200s that goes beyond their regulation of E-cadherin and epithelial phenotype. Overexpression of miR-200s is associated with increased risk of metastasis in breast cancer and promotes metastatic colonization in mouse models, phenotypes that cannot be recapitulated by E-cadherin expression alone. Genomic and proteomic analyses revealed global shifts in gene expression upon miR-200 overexpression toward that of highly metastatic cells. miR-200s promote metastatic colonization partly through direct targeting of Sec23a, which mediates secretion of metastasis-suppressive proteins, including Igfbp4 and Tinagl1, as validated by functional and clinical correlation studies. Overall, these findings suggest a pleiotropic role of miR-200s in promoting metastatic colonization by influencing E-cadherin–dependent epithelial traits and Sec23a-mediated tumor cell secretome.View full text

A Dive into Online Community Properties - Wagstrom, Patrick; Martino, Jacquelyn; von Kaenel, Juerg; Marshini Chetty; Thomas, John; Jones, Lauretta (CSCW '11, 2011)
As digital communities grow in size their feature sets also grow with them. Different users have different experiences with the same tools and communities. Enterprises and other organizations seeking to leverage these communities need a straightforward way to analyze and compare a variety of salient attributes of these communities. We describe a taxonomy and tool for crowd-sourcing user based evaluations of enterprise relevant attributes of digital communities and present the results of a small scale study on its usefulness and stability across multiple raters.
Keywords: enterprise; Online communities; Taxonomy; Visualization

The DSPCAD Lightweight Dataflow Environment: Introduction to LIDE Version 0.1 - Chung-Ching Shen; Wang, Lai-Huei; Cho, Inkeun; Kim, Scott; Won, Stephen; Plishker,William; Bhattacharyya, Shuvra S. (Technical Reports from UMIACS, 2011)
LIDE (the DSPCAD Lightweight Dataflow Environment) is a flexible,lightweight design environment that allows designers to experiment with dataflow-based approaches for design and implementation of digital signal processing (DSP) systems. LIDE contains libraries of dataflow graph elements (primitive actors, hierarchical actors, and edges) and utilities that assist designers in modeling, simulating, and implementing DSP systems using formal dataflow techniques. The libraries of dataflow graph elements (mainly actors) contained in LIDE provide useful building blocks that can be used to construct signal processing applications, and that can be used as examples that designers can adapt to create their own, customized LIDE actors. Furthermore, by using LIDE along with the DSPCAD Integrative Command Line Environment (DICE), designers can efficiently create and execute unit tests for user-designed actors. This report provides an introduction to LIDE. The report includes details on the process for setting up the LIDE environment, and covers methods for using pre-designed libraries of graph elements, as well as creating user-designed libraries and associated utilities using the C language. The report also gives an introduction to the C language plug-in for dicelang. This plug-in, called dicelang-C, provides features for efficient C-based project development and maintenance that are useful to apply when working with LIDE.
Keywords: Technical Report

EAAI-10: The First Symposium on Educational Advances in Artificial Intelligence - desJardins, Marie; Sahami,Mehran; Wagstaff,Kiri (AI Magazine, 2011)
Keywords: education, AI, symposium

Exploring compression effects for improved source camera identification using strongly compressed video - Chuang,Wei-Hong; Su,Hui; M. Wu (Image Processing (ICIP), 2011 18th IEEE International Conference on, 2011)
This paper presents a study of the video compression effect on source camera identification based on the Photo-Response Non-Uniformity (PRNU). Specifically, the reliability of different types of frames in a compressed video is first investigated, which shows quantitatively that I-frames are more reliable than P-frames for PRNU estimation. Motivated by this observation, a new mechanism for estimating the reference PRNU and two mechanisms for estimating the test-video PRNU are proposed to achieve higher accuracy with fewer frames used. Experiments are performed to validate the effectiveness of the proposed mechanisms.
Keywords: camera; cameras; video; coding; compression; computer; compression; video; estimation; photoresponse; forensics; data; identification; video; non-uniformity; reliability; source; PRNU

Extracting Insights from Electronic Health Records: Case Studies, a Visual Analytics Process Model, and Design Recommendations - Wang,Taowei; Wongsuphasawat,Krist; Plaisant, Catherine; Shneiderman, Ben (Journal of Medical Systems, 2011)
Current electronic health record (EHR) systems facilitate the storage, retrieval, persistence, and sharing of patient data. However, the way physicians interact with EHRs has not changed much. More specifically, support for temporal analysis of a large number of EHRs has been lacking. A number of information visualization techniques have been proposed to alleviate this problem. Unfortunately, due to their limited application to a single case study, the results are often difficult to generalize across medical scenarios. We present the usage data of Lifelines2 (Wang et al. 2008 ), our information visualization system, and user comments, both collected over eight different medical case studies. We generalize our experience into a visual analytics process model for multiple EHRs. Based on our analysis, we make seven design recommendations to information visualization tools to explore EHR systems.

A Fast Algorithm for Constructing Inverted Files on Heterogeneous Platforms - Wei, Zheng; JaJa, Joseph F. (Parallel Distributed Processing Symposium (IPDPS), 2011 IEEE International, 2011)
Given a collection of documents residing on a disk, we develop a new strategy for processing these documents and building the inverted files extremely fast. Our approach is tailored for a heterogeneous platform consisting of a multicore CPU and a highly multithreaded GPU. Our algorithm is based on a number of novel techniques including: (i) a high-throughput pipelined strategy that produces parallel parsed streams that are consumed at the same rate by parallel indexers, (ii) a hybrid trie and B-tree dictionary data structure in which the trie is represented by a table for fast look-up and each B-tree node contains string caches, (iii) allocation of parsed streams with frequent terms to CPU threads and the rest to GPU threads so as to match the throughput of parsed streams, and (iv) optimized CUDA indexer implementation that ensures coalesced memory accesses and effective use of shared memory. We have performed extensive tests of our algorithm on a single node (two Intel Xeon X5560 Quad-core) with two NVIDIA Tesla C1060 attached to it, and were able to achieve a throughput of more than 262 MB/s on the ClueWeb09 dataset. Similar results were obtained for widely different datasets. The throughput of our algorithm is superior to the best known algorithms reported in the literature even when compared to those run on large clusters.
Keywords: architecture; graphics; B-tree; C1060; central; construction; multicore; CPU; multithreaded; data; device; dictionary; equipment; coprocessors; data; files; GPU; computer; graphic; indexer; Intel; pipelined; platform; high-throughput; PROCESSING; Quad-core; NVIDIA; strategy; hybrid; structure; CUDA; structure; inverted; structures; multiprocessing; systems; Tesla; trie; unified; unit; computer; unit; heterogeneous; X5560; Xeon

Future link prediction in the blogosphere for recommendation - Wu,S.; Raschid, Louiqa; Rand, William (Proceedings of the International Conference on Weblogs and Social Media (ICWSM), 2011)
The phenomenal growth in both scale and importance of so-cial media such as blogs, micro-blogs and user-generated content, has created a need for tools that monitor information diffusion and make recommendations within these platforms. An essential element of social media, particularly blogs, is the hyperlink graph that connects various pieces of content. There are two types of links within the blogosphere; one from blog post to blog post, and another from blog post to blog channel (an event stream of blog posts). These links can be viewed as a proxy for the flow of information between blog channels and to reflect influence. Given this assumption about links, the ability to predict future links can facilitate the monitoring of information diffusion, making recommen- dations, and word-of-mouth (WOM) marketing. We propose different methods for link predictions and we evaluate these methods on an extensive blog dataset.

Gene Coexpression Network Topology of Cardiac Development, Hypertrophy, and FailureClinical Perspective - Dewey,Frederick E; Perez,Marco V; Wheeler,Matthew T; Watt,Clifton; Spin,Joshua; Langfelder,Peter; Horvath,Steve; Hannenhalli, Sridhar; Cappola,Thomas P.; Ashley,Euan A (Circulation: Cardiovascular GeneticsCirc Cardiovasc Genet, 2011)
Background— Network analysis techniques allow a more accurate reflection of underlying systems biology to be realized than traditional unidimensional molecular biology approaches. Using gene coexpression network analysis, we define the gene expression network topology of cardiac hypertrophy and failure and the extent of recapitulation of fetal gene expression programs in failing and hypertrophied adult myocardium.Methods and Results— We assembled all myocardial transcript data in the Gene Expression Omnibus (n=1617). Because hierarchical analysis revealed species had primacy over disease clustering, we focused this analysis on the most complete (murine) dataset (n=478). Using gene coexpression network analysis, we derived functional modules, regulatory mediators, and higher-order topological relationships between genes and identified 50 gene coexpression modules in developing myocardium that were not present in normal adult tissue. We found that known gene expression markers of myocardial adaptation were members of upregulated modules but not hub genes. We identified ZIC2 as a novel transcription factor associated with coexpression modules common to developing and failing myocardium. Of 50 fetal gene coexpression modules, 3 (6%) were reproduced in hypertrophied myocardium and 7 (14%) were reproduced in failing myocardium. One fetal module was common to both failing and hypertrophied myocardium. Conclusions— Network modeling allows systems analysis of cardiovascular development and disease. Although we did not find evidence for a global coordinated program of fetal gene expression in adult myocardial adaptation, our analysis revealed specific gene expression modules active during both development and disease and specific candidates for their regulation.
Keywords: fetal; Gene expression; heart failure; hypertrophy; myocardium

GPU algorithms for diamond-based multiresolution terrain processing - Yalçın,M. A.; Weiss,K.; De Floriani, Leila (Eurographics Symposium on Parallel Graphics and Visualization, 2011)
We present parallel algorithms for processing, extracting and rendering adaptively sampled regular terraindatasets represented as a multiresolution model defined by a super-square-based diamond hierarchy. This model represents a terrain as a nested triangle mesh generated through a series of longest edge bisections and encoded in an implicit hierarchical structure, which clusters triangles into diamonds and diamonds into super-squares. We decompose the problem into three parallel algorithms for performing: generation of the diamond hierarchy from a regularly distributed terrain dataset, selective refinement on the diamond hierarchy and generation of the corre- sponding crack-free triangle mesh for processing and rendering. We avoid the data transfer bottleneck common to previous approaches by processing all data entirely on the GPU. We demonstrate that this parallel approach can be successfully applied to interactive terrain visualization with a high tessellation quality on commodity GPUs.

Graph Analytics-Lessons Learned and Challenges Ahead - Wong,Pak Chung; Chen,Chaomei; Gorg,Carsten; Shneiderman, Ben; Stasko,John; Thomas,Jim (IEEE Computer Graphics and Applications, 2011)
Graph analytics is one of the most influential and important R&D topics in the visual analytics community. Researchers with diverse backgrounds from information visualization, human-computer interaction, computer graphics, graph drawing, and data mining have pursued graph analytics from scientific, technical, and social approaches. These studies have addressed both distinct and common challenges. Past successes and mistakes can provide valuable lessons for revising the research agenda. In this article, six researchers from four academic and research institutes identify graph analytics' fundamental challenges and present both insightful lessons learned from their experience and good practices in graph analytics research. The goal is to critically assess those lessons and shed light on how they can stimulate research and draw attention to grand challenges for graph analytics. The article also establishes principles that could lead to measurable standards and criteria for research.
Keywords: citation analysis; citespace; Computer Graphics; document analysis; graphics and multimedia; greengrid; jigsaw system; modeling; power grid analysis; semantic substrates; simulation; social networks; text analysis; Visualization

IA*: An adjacency-based representation for non-manifold simplicial shapes in arbitrary dimensions - Canino,David; De Floriani, Leila; Weiss,Kenneth (Computers & Graphics, 2011)
We propose a compact, dimension-independent data structure for manifold, non-manifold and non-regular simplicial complexes, that we call the Generalized Indexed Data Structure with Adjacencies (IA⁎ data structure). It encodes only top simplices, i.e. the ones that are not on the boundary of any other simplex, plus a suitable subset of the adjacency relations. We describe the IA⁎ data structure in arbitrary dimensions, and compare the storage requirements of its 2D and 3D instances with both dimension-specific and dimension-independent representations. We show that the IA⁎ data structure is more cost effective than other dimension-independent representations and is even slightly more compact than the existing dimension-specific ones. We present efficient algorithms for navigating a simplicial complex described as an IA⁎ data structure. This shows that the IA⁎ data structure allows retrieving all topological relations of a given simplex by considering only its local neighborhood and thus it is a more efficient alternative to incidence-based representations when information does not need to be encoded for boundary simplices.
Keywords: Non-manifold data structures; simplicial complexes; Topological data structures

Illumination robust dictionary-based face recognition - Patel, Vishal M.; Tao Wu; Biswas,S.; Phillips,P.J.; Chellapa, Rama (2011 18th IEEE International Conference on Image Processing (ICIP), 2011)
In this paper, we present a face recognition method based on simultaneous sparse approximations under varying illumination. Our method consists of two main stages. In the first stage, a dictionary is learned for each face class based on given training examples which minimizes the representation error with a sparseness constraint. In the second stage, a test image is projected onto the span of the atoms in each learned dictionary. The resulting residual vectors are then used for classification. Furthermore, to handle changes in lighting conditions, we use a relighting approach based on a non-stationary stochastic filter to generate multiple images of the same person with different lighting. As a result, our algorithm has the ability to recognize human faces with good accuracy even when only a single or a very few images are provided for training. The effectiveness of the proposed method is demonstrated on publicly available databases and it is shown that this method is efficient and can perform significantly better than many competitive face recognition algorithms.
Keywords: albedo; approximation theory; classification; competitive face recognition algorithms; Databases; Dictionaries; Face; face recognition; face recognition method; filtering theory; human face recognition; illumination robust dictionary-based face recognition; illumination variation; image representation; learned dictionary; learning (artificial intelligence); lighting; lighting conditions; multiple images; nonstationary stochastic filter; publicly available databases; relighting; relighting approach; representation error; residual vectors; Robustness; simultaneous sparse approximations; simultaneous sparse signal representation; sparseness constraint; Training; varying illumination; vectors

Improved Identification and Visualization of Emergency Department Patient Visits - Hettinger,AZ; Rackoff,A.; Wongsuphasawat,K.; Cheng,H.; Fairbanks,RJ; Plaisant, Catherine; Smith,M. S (Annals of Emergency Medicine, 2011)

Increased gene sampling provides stronger support for higher-level groups within gracillariid leaf mining moths and relatives (Lepidoptera: Gracillariidae) - Kawahara,A. Y; Ohshima,I; Kawakita,A; Regier,J. C; Mitter,C; Cummings, Michael P.; Davis,DR; Wagner,DL; De Prinis,J; Lopez-Vaamonde,C (BMC Evol Biol, 2011)

Interaction of Vibrio cholerae non-O1/non-O139 with Copepods, Cladocerans and Competing Bacteria in the Large Alkaline Lake Neusiedler See, Austria - Kirschner,A. K. T.; Schauer,S.; Steinberger,B.; Wilhartitz,I.; Grim,C. J.; Huq,A.; Rita R Colwell; Herzig,A.; Sommer,R. (Microbial ecology, 2011)
Vibrio cholerae is a human pathogen and natural inhabitant of aquatic environments. Serogroups O1/O139 have been associated with epidemic cholera, while non-O1/non-O139 serogroups usually cause human disease other than classical cholera. V. cholerae non-O1/non-O139 from the Neusiedler See, a large Central European lake, have caused ear and wound infections, including one case of fatal septicaemia. Recent investigations demonstrated rapid planktonic growth of V. cholerae non-O1/non-O139 and correlation with zooplankton biomass. The aim of this study was to elucidate the interaction of autochthonous V. cholerae with two dominant crustacean zooplankton species in the lake and investigate the influence of the natural bacterial community on this interaction. An existing data set was evaluated for statistical relationships between zooplankton species and V. cholerae and co-culture experiments were performed in the laboratory. A new fluorescence in situ hybridisation protocol was applied for quantification of V. cholerae non-O1/non-O139 cells, which significantly reduced analysis time. The experiments clearly demonstrated a significant relationship of autochthonous V. cholerae non-O1/non-O139 with cladocerans by promoting growth of V. cholerae non-O1/non-O139 in the water and on the surfaces of the cladocerans. In contrast, copepods had a negative effect on the growth of V. cholerae non-O1/non-O139 via competing bacteria from their surfaces. Thus, beside other known factors, biofilm formation by V. cholerae on crustacean zooplankton appears to be zooplankton taxon specific and may be controlled by the natural bacterial community.

A large-scale benchmark dataset for event recognition in surveillance video - Oh,Sangmin; Hoogs, A.; Perera,A.; Cuntoor, N.; Chen,Chia-Chih; Lee,Jong Taek; Mukherjee,S.; Aggarwal, JK; Lee,Hyungtae; Davis, Larry S.; Swears,E.; Wang,Xioyang; et al. (Computer Vision and Pattern Recognition (CVPR), 2011 IEEE Conference on, 2011)
We introduce a new large-scale video dataset designed to assess the performance of diverse visual event recognition algorithms with a focus on continuous visual event recognition (CVER) in outdoor areas with wide coverage. Previous datasets for action recognition are unrealistic for real-world surveillance because they consist of short clips showing one action by one individual [15, 8]. Datasets have been developed for movies [11] and sports [12], but, these actions and scene conditions do not apply effectively to surveillance videos. Our dataset consists of many outdoor scenes with actions occurring naturally by non-actors in continuously captured videos of the real world. The dataset includes large numbers of instances for 23 event types distributed throughout 29 hours of video. This data is accompanied by detailed annotations which include both moving object tracks and event examples, which will provide solid basis for large-scale evaluation. Additionally, we propose different types of evaluation modes for visual recognition tasks and evaluation metrics along with our preliminary experimental results. We believe that this dataset will stimulate diverse aspects of computer vision research and help us to advance the CVER tasks in the years ahead.
Keywords: algorithm; evaluation; CVER; databases; databases; video; dataset; moving; event; metrics; large-scale; object; recognition; recognition; diverse; recognition; video; scenes; surveillance; surveillance; visual; tasks; computer; tracks; outdoor; video; video; computer; vision; continuous; vision; image; visual

LifeFlow: visualizing an overview of event sequences - Wongsuphasawat,Krist; Guerra Gómez,John Alexis; Plaisant, Catherine; Wang,Taowei David; Taieb-Maimon,Meirav; Shneiderman, Ben (Proceedings of the 2011 annual conference on Human factors in computing systems, 2011)
Event sequence analysis is an important task in many domains: medical researchers may study the patterns of transfers within the hospital for quality control; transportation experts may study accident response logs to identify best practices. In many cases they deal with thousands of records. While previous research has focused on searching and browsing, overview tasks are often overlooked. We introduce a novel interactive visual overview of event sequences called LifeFlow. LifeFlow is scalable, can summarize all possible sequences, and represents the temporal spacing of the events within sequences. Two case studies with healthcare and transportation domain experts are presented to illustrate the usefulness of LifeFlow. A user study with ten participants confirmed that after 15 minutes of training novice users were able to rapidly answer questions about the prevalence and temporal characteristics of sequences, find anomalies, and gain significant insight from the data.
Keywords: Information Visualization; overview visualization; temporal categorical data; timestamped event sequences

LifeFlow: visualizing an overview of event sequences (video preview) - Wongsuphasawat,Krist; Guerra Gómez,John Alexis; Plaisant, Catherine; Wang,Taowei; Taieb-Maimon,Meirav; Shneiderman, Ben (Proceedings of the 2011 annual conference extended abstracts on Human factors in computing systems, 2011)
Event sequence analysis is an important task in many domains: medical researchers may study the patterns of transfers within the hospital for quality control; transportation experts may study accident response logs to identify best practices. In many cases they deal with thousands of records. While previous research has focused on searching and browsing, overview tasks are often overlooked. We introduce a novel interactive visual overview of event sequences called LifeFlow. LifeFlow is scalable, can summarize all possible sequences, and represents the temporal spacing of the events within sequences. In this video, we show an example of patient transfer data and briefly demonstrate how to analyze them with LifeFlow. Please see [11] or visit http:www.cs.umd.eduhcillifeflow for more detail.
Keywords: emergency room; healthcare; Information Visualization; overview visualization; temporal categorical data; timestamped event sequences

A Model-Based Schedule Representation for Heterogeneous Mapping of Dataflow Graphs - Wu, Hsiang-Huang; Chung-Ching Shen; Sane, N.; Plishker,W.; Bhattacharyya, Shuvra S. (2011 IEEE International Symposium on Parallel and Distributed Processing Workshops and Phd Forum (IPDPSW), 2011)
Dataflow-based application specifications are widely used in model-based design methodologies for signal processing systems. In this paper, we develop a new model called the dataflow schedule graph (DSG) for representing a broad class of dataflow graph schedules. The DSG provides a graphical representation of schedules based on dataflow semantics. In conventional approaches, applications are represented using dataflow graphs, whereas schedules for the graphs are represented using specialized notations, such as various kinds of sequences or looping constructs. In contrast, the DSG approach employs dataflow graphs for representing both application models and schedules that are derived from them. Our DSG approach provides a precise, formal framework for unambiguously representing, analyzing, manipulating, and interchanging schedules. We develop detailed formulations of the DSG representation, and present examples and experimental results that demonstrate the utility of DSGs in the context of heterogeneous signal processing system design.
Keywords: Computational modeling; data flow graphs; dataflow schedule graph; dataflow semantics; dataflow-based application specifications; Dynamic scheduling; heterogeneous mapping; heterogeneous signal processing system design; model-based design methodologies; model-based schedule representation; Processor scheduling; Program processors; Schedules; semantics; Signal processing; synchronization

Modeling and Analysis of Correlated Binary Fingerprints for Content Identification - Varna,A.L.; M. Wu (Information Forensics and Security, IEEE Transactions on, 2011)
Multimedia identification via content fingerprints is used in many applications, such as content filtering on user-generated content websites, and automatic multimedia identification and tagging. A compact #x201C;fingerprint #x201D; is computed for each multimedia signal that captures robust and unique properties of the perceptual content, which is later used for identifying the multimedia. Several different multimedia fingerprinting schemes have been proposed in the literature and have been evaluated through experiments. To complement these experimental evaluations and provide guidelines for choosing system parameters and designing better schemes, this paper develops models for content fingerprinting and provides an analysis of the identification performance under these models. As a first step, bounds on the identification accuracy and the required fingerprint length for the simplest case when the fingerprint bits are modeled as i.i.d. are summarized. Markov Random Fields are then used to address more realistic settings of fingerprints with correlated components. The optimal likelihood ratio detector is derived and a statistical physics inspired approach for computing the probability of detection and probability of false alarm is described. The analysis shows that the commonly used Hamming distance detection criterion is susceptible to correlations among fingerprint bits, whereas the optimal log-likelihood ratio decision rule yields 5-20% improvement in the accuracy over a range of correlations. Simulation results demonstrate the validity of the theoretical predictions.
Keywords: alarm; approach; user; binary; computing; content; criterion; Markov; decision; DETECTION; detector; statistical; distance; fields; content; filtering; content; filtering; multimedia; fingerprinting; fingerprints; detection; generated; Hamming; identification; correlated; identification; optimal; inspired; likelihood; Physics; probability; false; probability; log; processes; Web; random; ratio; rule; multimedia; schemes; multimedia; sites; information; Websites; Markov

Modeling and optimization of dynamic signal processing in resource-aware sensor networks - Bhattacharyya, Shuvra S.; Plishker,W.; Sane, N.; Chung-Ching Shen; Wu, Hsiang-Huang (2011 8th IEEE International Conference on Advanced Video and Signal-Based Surveillance (AVSS), 2011)
Sensor node processing in resource-aware sensor networks is often critically dependent on dynamic signal processing functionality - i.e., signal processing functionality in which computational structure must be dynamically assessed and adapted based on time-varying environmental conditions, operating constraints or application requirements. In dynamic signal processing systems, it is important to provide flexibility for run-time adaptation of application behavior and execution characteristics, but in the domain of resource-aware sensor networks, such flexibility cannot come with significant costs in terms of power consumption overhead or reduced predictability. In this paper, we review a variety of complementary models of computation that are being developed as part of the dataflow interchange format (DIF) project to facilitate efficient and reliable implementation of dynamic signal processing systems. We demonstrate these methods in the context of resource-aware sensor networks.
Keywords: Adaptation models; Aerodynamics; Computational modeling; data flow graphs; dataflow interchange format; Dynamic scheduling; dynamic signal processing; power consumption overhead; Program processors; resource-aware sensor networks; run-time adaptation; Schedules; sensor node processing; Signal processing; Wireless sensor networks

Modeling Multiresolution 3D Scalar Fields through Regular Simplex Bisection - Weiss,K.; De Floriani, Leila; Hagen,H. (Scientific Visualization: Interactions, Features, Metaphors, 2011)
We review modeling techniques for multiresolution three-dimensional scalar fields based on a dis-cretization of the field domain into nested tetrahedral meshes generated through regular simplex bisection. Such meshes are described through hierarchical data structures and their representa- tion is characterized by the modeling primitive used. The primary conceptual distinction among the different approaches proposed in the literature is whether they treat tetrahedra or clusters of tetrahedra, called diamonds, as the modeling primitive. We first focus on representations for the modeling primitive and for nested meshes. Next, we survey the applications of these meshes to modeling multiresolution 3D scalar fields, with an emphasis on interactive visualization. We also consider the relationship of such meshes to octrees. Finally, we discuss directions for further research

Modeling temporal correlations in content fingerprints - Varna,A.L.; M. Wu (Acoustics, Speech and Signal Processing (ICASSP), 2011 IEEE International Conference on, 2011)
Previous analysis of content fingerprints has mainly focused on the case of independent and identically distributed finger prints. Practical fingerprints, however, exhibit correlations between components computed from successive frames. In this paper, a Markov chain based model is used to capture the temporal correlations, and the suitability of this model is evaluated through experiments on a video database. The results indicate that the Markov chain model is a good fit only in a certain regime. A hybrid model is then developed to account for this behavior and a corresponding adaptive detector is derived. The adaptive detector achieves better identification accuracy at a small computational expense.
Keywords: chain; correlations; video; database; Markov; databases; databases; video; detection; fingerprint; detector; certain; fingerprints; hybrid; identification; temporal; Markov; model; adaptive; model; temporal; processes; adaptive; regime; content; signal

Oblivious RAM with O((logN)^3) Worst-Case Cost - Elaine Shi; Chan, T.; Stefanov, Emil; Li, Mingfei (Advances in Cryptology – ASIACRYPT 2011, 2011)
Oblivious RAM is a useful primitive that allows a client to hide its data access patterns from an untrusted server in storage outsourcing applications. Until recently, most prior works on Oblivious RAM aim to optimize its amortized cost, while suffering from linear or even higher worst-case cost. Such poor worst-case behavior renders these schemes impractical in realistic settings, since a data access request can occasionally be blocked waiting for an unreasonably large number of operations to complete. This paper proposes novel Oblivious RAM constructions that achieves poly-logarithmic worst-case cost, while consuming constant client-side storage. To achieve the desired worst-case asymptotic performance, we propose a novel technique in which we organize the O-RAM storage into a binary tree over data buckets, while moving data blocks obliviously along tree edges.
Keywords: Computer science

Predicting author blog channels with high value future posts for monitoring - Wu,S.; Elsayed,T.; Rand, William; Raschid, Louiqa (Proceedings of the Twenty-Fifth Conference on Artificial Intelligence (AAAI), 2011)
The phenomenal growth of social media, both in scale andimportance, has created a unique opportunity to track infor- mation diffusion and the spread of influence, but can also make efficient tracking difficult. Given data streams rep- resenting blog posts on multiple blog channels and a focal query post on some topic of interest, our objective is to pre- dict which of those channels are most likely to contain a fu- ture post that is relevant, or similar, to the focal query post. We denote this task as the future author prediction problem (FAPP). This problem has applications in information diffu- sion for brand monitoring and blog channel personalization and recommendation. We develop prediction methods in- spired by (naıve) information retrieval approaches that use historical posts in the blog channel for prediction. We also train a ranking support vector machine (SVM) to solve the problem. We evaluate our methods on an extensive social media dataset; despite the difficulty of the task, all methods perform reasonably well. Results show that ranking SVM prediction can exploit blog channel and diffusion characteris- tics to improve prediction accuracy. Moreover, it is surpris- ingly good for prediction in emerging topics and identifying inconsistent authors.

The PR-star octree: a spatio-topological data structure for tetrahedral meshes - Weiss,Kenneth; De Floriani, Leila; Fellegara,Riccardo; Velloso,Marcelo (Proceedings of the 19th ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems, 2011)
We propose the PR-star octree as a combined spatial data structure for performing efficient topological queries on tetrahedral meshes. The PR-star octree augments the Point Region octree (PR Octree) with a list of tetrahedra incident to its indexed vertices, i.e. those in the star of its vertices. Thus, each leaf node encodes the minimal amount of information necessary to locally reconstruct the topological connectivity of its indexed elements. This provides the flexibility to efficiently construct the optimal data structure to solve the task at hand using a fraction of the memory required for a corresponding data structure on the global tetrahedral mesh. Due to the spatial locality of successive queries in typical GIS applications, the construction costs of these runtime data structures are amortized over multiple accesses while processing each node. We demonstrate the advantages of the PR-star octree representation in several typical GIS applications, including detection of the domain boundaries, computation of local curvature estimates and mesh simplification.

Recommendations in social media for brand monitoring - Wu,Shanchan; Rand, William; Raschid, Louiqa (Proceedings of the fifth ACM conference on Recommender systems, 2011)
We present a recommendation system for social media that draws upon monitoring and prediction methods. We use historical posts on some focal topic or historical links to a focal blog channel to recommend a set of authors to follow. Such a system would be useful for brand managers interested in monitoring conversations about their products. Our recommendations are based on a prediction system that trains a ranking Support Vector Machine (RSVM) using multiple features including the content of a post, similarity between posts, links between posts and/or blog channels, and links to external websites. We solve two problems, Future Author Prediction (FAP) and Future Link Prediction (FLP), and apply the prediction outcome to make recommendations. Using an extensive experimental evaluation on a blog dataset, we demonstrate the quality and value of our recommendations.
Keywords: blog; brand monitoring; recommendation; social media

Research Directions in Data Wrangling: Visualizations and Transformations for Usable and Credible Data - Kandel,Sean; Heer,Jeffrey; Plaisant, Catherine; Kennedy,Jessie; Van Ham,Frank; Riche,Nathalie Henry; Weaver,Chris; Lee,Bongshin; Brodbeck,Dominique; Buono,Paolo (Information VisualizationInformation Visualization, 2011)
In spite of advances in technologies for working with data, analysts still spend an inordinate amount of time diagnosing data quality issues and manipulating data into a usable form. This process of ‘data wrangling’ often constitutes the most tedious and time-consuming aspect of analysis. Though data cleaning and integration arelongstanding issues in the database community, relatively little research has explored how interactive visualization can advance the state of the art. In this article, we review the challenges and opportunities associated with addressing data quality issues. We argue that analysts might more effectively wrangle data through new interactive systems that integrate data verification, transformation, and visualization. We identify a number of outstanding research questions, including how appropriate visual encodings can facilitate apprehension of missing data, discrepant values, and uncertainty; how interactive visualizations might facilitate data transform specification; and how recorded provenance and social interaction might enable wider reuse, verification, and modification of data transformations.
Keywords: data cleaning; data quality; data transformation; Uncertainty; Visualization

Seam carving estimation using forensic hash - Lu,Wenjun; M. Wu (Proceedings of the thirteenth ACM multimedia workshop on Multimedia and security, 2011)
Seam carving is an adaptive multimedia retargeting technique to resize multimedia data for different display sizes. This technique has found promising applications in media consumption on mobile devices such as tablets and smartphones. However, seam carving can also be used to maliciously alter image content and when combined with other tampering operations, makes tampering detection very difficult by traditional multimedia forensic techniques. In this paper, we study the problem of seam carving estimation and tampering localization using very compact side information called forensic hash. The forensic hash technique bridges two related areas, namely robust image hashing and blind multimedia forensics, to answer a broader scope of forensic questions in a more efficient and accurate manner. We show that our recently proposed forensic hash construction can be extended to accurately estimate seam carving and detect local tampering.
Keywords: forensic hash; seam carving; sift; visual words

Secure video processing: Problems and challenges - Lu,Wenjun; Varna,A.; M. Wu (Acoustics, Speech and Signal Processing (ICASSP), 2011 IEEE International Conference on, 2011)
Secure signal processing is an emerging technology to enable signal processing tasks in a secure and privacy-preserving fashion. It has attracted a great amount of research attention due to the increasing demand to enable rich functionalities for private data stored online. Desirable functionalities may include search, analysis, clustering, etc. In this paper, we discuss the research issues and challenges in secure video processing with focus on the application of secure online video management. Video is different from text due to its large data volume and rich content diversity. To be practical, secure video processing requires efficient solutions that may involve a trade-off between security and complexity. We look at three representative video processing tasks and review existing techniques that can be applied. Many of the tasks do not have efficient solutions yet, and we discuss the challenges and research questions that need to be addressed.
Keywords: data; video; fashion; secure; management; secure; of; online; privacy-preserving; processing; processing; security; signal; video

"Seeing" ENF: natural time stamp for digital video via optical sensing and signal processing - Garg,Ravi; Varna,Avinash L.; M. Wu (Proceedings of the 19th ACM international conference on Multimedia, 2011)
Electric Network Frequency (ENF) fluctuates slightly over time from its nominal value of 50 Hz/60 Hz. The fluctuations in the ENF remain consistent across the entire power grid even when measured at physically distant locations. The near-invisible flickering of fluorescent lights connected to the power mains reflect these fluctuations present in the ENF. In this paper, mechanisms using optical sensors and video cameras to record and validate the presence of the ENF fluctuations in fluorescent lighting are presented. Signal processing techniques are applied to demonstrate a high correlation between the fluctuations in the ENF signal captured from fluorescent lighting and the ENF signal captured directly from power mains supply. The proposed technique is then used to demonstrate the presence of the ENF signal in video recordings taken in various geographical areas. Experimental results show that the ENF signal can be used as a natural timestamp for optical sensor recordings and video surveillance recordings from indoor environments under fluorescent lighting. Application of the ENF signal analysis to tampering detection of surveillance video recordings is also demonstrated.
Keywords: electric network frequency; information forensics; timestamp; video authentication

Simplex and Diamond Hierarchies: Models and Applications - Weiss,K.; De Floriani, Leila (Computer Graphics Forum, 2011)
Hierarchical spatial decompositions are a basic modelling tool in a variety of application domains. Several papers on this subject deal with hierarchical simplicial decompositions generated through regular simplex bisection. Such decompositions, originally developed for finite elements, are extensively used as the basis for multi-resolution models of scalar fields, such as terrains, and static or time-varying volume data. They have also been used as an alternative to quadtrees and octrees as spatial access structures. The primary distinction among all such approaches is whether they treat the simplex or clusters of simplices, called diamonds, as the modelling primitive. This leads to two classes of data structures and to different query approaches. We present the hierarchical models in a dimension-independent manner, and organize the description of the various applications, primarily interactive terrain rendering and isosurface extraction, according to the dimension of the domain.
Keywords: hierarchy of diamonds; hierarchy of simplices; I.3.5 [Computer Graphics]: Computational Geometry and Object Modelling— Hierarchy and geometric transformations; I.3.6 [Computer Graphics]: Methodology and Techniques—Graphics data structures and data types; interactive terrain visualization; mesh‐based multiresolution models; multiresolution isosurfaces; nested refinement schemes; Regular simplex bisection; scalar field visualization; spatial access structures

Spam or ham?: characterizing and detecting fraudulent "not spam" reports in web mail systems - Ramachandran,Anirudh; Dasgupta,Anirban; Feamster, Nick; Weinberger,Kilian (Proceedings of the 8th Annual Collaboration, Electronic messaging, Anti-Abuse and Spam Conference, 2011)
Web mail providers rely on users to "vote" to quickly and col-laboratively identify spam messages. Unfortunately, spammers have begun to use bots to control large collections of compromised Web mail accounts not just to send spam, but also to vote "not spam" on incoming spam emails in an attempt to thwart collaborative filtering. We call this practice a vote gaming attack. This attack confuses spam filters, since it causes spam messages to be mislabeled as legitimate; thus, spammer IP addresses can continue sending spam for longer. In this paper, we introduce the vote gaming attack and study the extent of these attacks in practice, using four months of email voting data from a large Web mail provider. We develop a model for vote gaming attacks, explain why existing detection mechanisms cannot detect them, and develop a new, scalable clustering-based detection method that identifies compromised accounts that engage in vote-gaming attacks. Our method detected 1.1 million potentially compromised accounts with only a 0.17% false positive rate, which is nearly 10 times more effective than existing clustering methods used to detect bots that send spam from compromised Web mail accounts.

Special Issue on Video Analysis on Resource-Limited Systems - Chellapa, Rama; Cavallaro, A.; Wu,Y.; Shan, C.; Fu, Y.; Pulli, K. (IEEE Transactions on Circuits and Systems for Video Technology, 2011)
The 17 papers in this special issue focus on resource-limited systems.
Keywords: computational complexity; Image Enhancement; Special issues and sections; Video compression

Structure and recognition of polyubiquitin chains of different lengths and linkage - Fushman, David; Wilkinson,Keith D. (F1000 Biology ReportsF1000 Biol Rep, 2011)
The polyubiquitin signal is post-translationally attached to a large number of proteins, often directing formation of macromolecular complexes resulting in the translocation, assembly or degradation of the attached protein. Recent structural and functional studies reveal general mechanisms by which different architectures and length of the signal are distinguished.

Tracking and Identification via Object Reflectance Using a Hyperspectral Video Camera - Nguyen,Hien Van; Banerjee,Amit; Burlina,Philippe; Broadwater,Joshua; Chellapa, Rama (Machine Vision Beyond Visible SpectrumMachine Vision Beyond Visible Spectrum, 2011)
Recent advances in electronics and sensor design have enabled the development of a hyperspectral video camera that can capture hyperspectral datacubes at near video rates. The sensor offers the potential for novel and robust methods for surveillance by combining methods from computer vision and hyperspectral image analysis. Here, we focus on the problem of tracking objects through challenging conditions, such as rapid illumination and pose changes, occlusions, and in the presence of confusers. A new framework that incorporates radiative transfer theory to estimate object reflectance and particle filters to simultaneously track and identify an object based on its reflectance spectra is proposed. By exploiting high-resolution spectral features in the visible and near-infrared regimes, the framework is able to track objects that appear featureless to the human eye. For example, we demonstrate that near-IR spectra of human skin can also be used to distinguish different people in a video sequence. These capabilities are illustrated using experiments conducted on real hyperspectral video data.

Tutorial-Graph Analytics — Lessons Learned and Challenges Ahead - Wong,P.C.; Chen,C.; Görg,C.; Shneiderman, Ben; Stasko,J.; Thomas,J. (IEEE Computer Graphics and Applications, 2011)

AI Theory and Practice: A Discussion on Hard Challenges and Opportunities Ahead - Horvitz,Eric; Getoor, Lise; Guestrin,Carlos; Hendler,James; Konstan,Joseph; Subramanian,Devika; Wellman,Michael; Kautz,Henry (AI Magazine, 2010)
AI Theory and Practice: A Discussion on Hard Challenges and Opportunities Ahead

Alignment and clustering of phylogenetic markers - implications for microbial diversity studies - White,James R; Navlakha,Saket; Nagarajan,Niranjan; Ghodsi,Mohammad-Reza; Kingsford, Carl; Pop, Mihai (BMC Bioinformatics, 2010)
Molecular studies of microbial diversity have provided many insights into the bacterial communities inhabiting the human body and the environment. A common first step in such studies is a survey of conserved marker genes (primarily 16S rRNA) to characterize the taxonomic composition and diversity of these communities. To date, however, there exists significant variability in analysis methods employed in these studies.

Assessor error in stratified evaluation - Webber,W.; Oard, Douglas; Scholer,F.; Hedin,B. (Proceedings of the 19th ACM international conference on Information and knowledge management, 2010)

Broadcasting on networks of workstations - Khuller, Samir; Kim,Y. A; Wan,Y. C.J (Algorithmica, 2010)
Broadcasting and multicasting are fundamental operations. In this work we develop algorithms for performing broadcast and multicast in clusters of workstations. In this model, sending a message to a machine in the same cluster takes 1 time unit, and sending a message to a machine in a different cluster takes C(≥1) time units. The clusters may have arbitrary sizes. Lowekamp and Beguelin proposed heuristics for this model, but their algorithms may produce broadcast times that are arbitrarily worse than optimal. We develop the first constant factor approximation algorithms for this model. Algorithm LCF (Largest Cluster First) for the basic model is simple, efficient and has a worst case approximation guarantee of 2. We then extend these models to more complex models where we remove the assumption that an unbounded amount of communication may happen using the global network. The algorithms for these models build on the LCF method developed for the basic problem. Finally, we develop broadcasting algorithms for the postal model where the sending node does not block for C time units when the message is in transit.

Buffer management for multi-application image processing on multi-core platforms: Analysis and case study - Ko,Dong-Ik; Won, N.; Bhattacharyya, Shuvra S. (2010 IEEE International Conference on Acoustics Speech and Signal Processing (ICASSP), 2010)
Due to the limited amounts of on-chip memory, large volumes of data, and performance and power consumption overhead associated with interprocessor communication, efficient management of buffer memory is critical to multi-core image processing. To address this problem, this paper develops new modeling and analysis techniques based on dataflow representations, and demonstrates these techniques on a multi-core implementation case study involving multiple, concurrently-executing image processing applications. Our techniques are based on careful representation and exploitation of frame- or block-based operations, which involve repeated invocations of the same computations across regularly- arranged subsets of data. Using these new approaches to manage block-based image data, this paper demonstrates methods to analyze synchronization overhead and FIFO buffer sizes when mapping image processing applications onto heterogeneous, multi core architectures.
Keywords: block-based image data; buffer memory management; buffer storage; concurrently-executing image processing application; data flow computing; data flow representation; data subset; Dataflow; Digital signal processing; Energy consumption; Energy management; Engineering management; FIFO buffer sizes; Hardware; Image analysis; IMAGE PROCESSING; image processing application; image representation; interprocessor communication; memory architecture; Memory management; multiapplication image processing; multicore image processing; multiprocessing; on-chip memory; power consumption; power consumption overhead; Runtime; scheduling; set theory; shared memory; storage management chips; synchronization overhead

Building an IT Taxonomy with Co-occurrence Analysis, Hierarchical Clustering, and Multidimensional Scaling - Tsui,C.; Wang,P.; Fleischmann,K.R.; Sayeed,A. B.; Weinberg, Amy (2010)
Different information technologies (ITs) are related in complex ways. How can the relationships among a large number of ITs be described and analyzed in a representative, dynamic, and scalable way? In this study, we employed co-occurrence analysis to explore the relationships among 50 information technologies discussed in six magazines over ten years (1998-2007). Using hierarchical clustering and multidimensional scaling, we have found that the similarities of the technologies can be depicted in hierarchies and two-dimensional plots, and that similar technologies can be classified into meaningful categories. The results imply reasonable validity of our approach for understanding technology relationships and building an IT taxonomy. The methodology that we offer not only helps IT practitioners and researchers make sense of numerous technologies in the iField but also bridges two related but thus far largely separate research streams in iSchools - information management and IT management.

cdec: A decoder, alignment, and learning framework for finite-state and context-free translation models - Dyer,C.; Weese,J.; Setiawan,H.; Lopez,A.; Ture,F.; Eidelman,V.; Ganitkevitch,J.; Blunsom,P.; Resnik, Philip (Proceedings of the ACL 2010 System Demonstrations, 2010)

Clear Panels: a technique to design mobile application interactivity - Brown,Q.; Bonsignore,E.; Hatley,L.; Druin, Allison; Walsh,G.; Foss,E.; Brewer,R.; Hammer,J.; Golub,E. (Proceedings of the 8th ACM Conference on Designing Interactive Systems, 2010)

Compressive Video Acquisition, Fusion and Processing - Baraniuk,Richard G.; Chellapa, Rama; Wakin,Michael (2010)
Modern developments in sensor technology, signal processing, and wireless communications have enabled the conception and deployment of large-scale networked sensing systems spanning numerous collection platforms and varied modalities. These systems have the potential to make intelligent decisions by integrating information from massive amounts of sensor data. Before such benefits can be achieved, significant advances must be made in methods for communicating, fusing, and processing this evergrowing volume of diverse data. In this one-year research project, we aimed to expose the fundamental issues and pave the way for further careful study of compressive approaches to video acquisition, fusion, and processing. In doing so, we developed a theoretical definition of video temporal bandwidth and applied the theory to compressive sampling and reconstruction. We created a new framework for compressive video sensing based on linear dynamical systems, lowering the compressive measurement rate. Finally, we applied our own joint manifold model to a variety of relevant image processing problems, demonstrating the model's effectiveness and ability to overcome noise and occlusion obstacles. We also showed how joint manifold models can discover an object's trajectory, an important step towards video fusion.
Keywords: *DATA FUSION; *DETECTORS; *SIGNAL PROCESSING; *VIDEO SIGNALS; ACQUISITION; COLLECTION; COMMUNICATION AND RADIO SYSTEMS; COMPRESSIVE PROPERTIES; COMPRESSIVE SAMPLING; compressive sensing; COMPRESSIVE VIDEO; decision making; DEPLOYMENT; DETECTION; DYNAMICS; IMAGE PROCESSING; Linear systems; Linearity; MANIFOLDS(ENGINES); measurement; MISCELLANEOUS DETECTION AND DETECTORS; MODELS; sampling; THEORY; TRAJECTORIES

Confidence-based feature acquisition to minimize training and test costs - desJardins, Marie; MacGlashan,James; Wagstaff,Kiri L (Proceedings of the SIAM Conference on Data Mining, 2010)
We present Confidence-based Feature Acquisition (CFA), a novel supervised learning method for acquiring missing feature values when there is missing data at both training and test time. Previous work has considered the cases of missing data at training time (e.g., Active Feature Acquisition, AFA 8), or at test time (e.g., Cost-Sensitive Naive Bayes, CSNB 2), but not both. At training time, CFA constructs a cascaded ensemble of classifiers, starting with the zero-cost features and adding a single feature for each successive model. For each model, CFA selects a subset of training instances for which the added feature should be acquired. At test time, the set of models is applied sequentially (as a cascade), stopping when a user-supplied confidence threshold is met. We compare CFA to AFA, CSNB, and several other baselines, and find that CFAs accuracy is at least as high as the other methods, while incurring significantly lower feature acquisition costs.

Crowdsourcing the evaluation of a domain-adapted named entity recognition system - Sayeed,Asad B.; Meyer,Timothy J.; Nguyen,Hieu C.; Buzek,Olivia; Weinberg, Amy (Association for Computational Linguistics, 2010)
Named entity recognition systems sometimes have difficulty when applied to data from domains that do not closely match the training data. We first use a simple rule-based technique for domain adaptation. Data for robust validation of the technique is then generated, and we use crowdsourcing techniques to show that this strategy produces reliable results even on data not seen by the rule designers. We show that it is possible to extract large improvements on the target data rapidly at low cost using these techniques.

Data hiding in compiled program binaries for supplementing computer functionality - M. Wu; Swaminathan,Ashwin; Mao,Yinian (2010)
Bit reductions in program instructions are achieved by determining the set of bit patterns in bit locations of the instructions. If only a subset of bit patterns is present in the instructions, they may be represented by an index value having a smaller number of bits. The index value may be substituted into the instruction and later used in decoding by referencing a corresponding bit pattern in a lookup table. The bit-reduction in the instruction makes way for supplemental data bits which may then be embedded.

Deliberate Interactions: Characterizing Technology Use in Nairobi, Kenya - Wyche, Susan P.; Smyth, Thomas N.; Marshini Chetty; Aoki, Paul M.; Grinter, Rebecca E. (SIGCHI '10, 2010)
We present results from a qualitative study examining how professionals living and working in Nairobi, Kenya regularly use ICT in their everyday lives. There are two contributions of this work for the HCI community. First, we provide empirical evidence demonstrating constraints our participants encountered when using technology in an infrastructure-poor setting. These constraints are limited bandwidth, high costs, differing perceptions of responsiveness, and threats to physical and virtual security. Second, we use our findings to critically evaluate the "access, anytime and anywhere" construct shaping the design of future technologies. We present an alternative vision called deliberate interactions--a planned and purposeful interaction style that involves offline preparation and discuss ways ICT can support this online usage behavior.
Keywords: everyday technology; hci4d; Kenya; urban computing

Design and Fabrication of a Multi-Material Compliant Flapping Wing Drive Mechanism for Miniature Air Vehicles - Bejgerowski,Wojciech; Gerdes,John W.; Gupta, Satyandra K.; Bruck,Hugh A.; Wilkerson,Stephen (ASME, 2010)
Successful realization of a flapping wing micro air vehicle (MAV) requires development of a light weight drive mechanism converting the rotary motion of the motor into flapping motion of the wings. Low weight of the drive mechanism is required to maximize the payload and battery capacity. In order to make flapping wing MAVs attractive in search, rescue, and recovery missions, they should be disposable from the cost point of view. Injection molded compliant drive mechanisms are an attractive design option to satisfy the weight, efficiency and cost requirements. In the past, we have successfully used multi-piece molding to create mechanisms utilizing distributed compliance for smaller MAVs. However, as the size of the MAV increases, mechanisms with distributed compliance exhibit excessive deformation. Therefore localizing rather than distributing the compliance in the mechanism becomes a more attractive option. Local compliance can be realized through multimaterial designs. A multi-material injection molded mechanism additionally offers reduction in the number of parts. This paper describes an approach for determining the drive mechanism shape and size that meets both the functional design and multi-material molding requirements. The design generated by the approach described in this paper was utilized to realize a flapping wing MAV with significant enhancements in the payload capabilities.

Design and implementation of real-time signal processing applications on heterogeneous multiprocessor arrays - Wu, Hsiang-Huang; Chung-Ching Shen; Bhattacharyya, Shuvra S.; Compton, K.; Schulte, M.; Wolf, M.; Zhang, Tong (2010 Conference Record of the Forty Fourth Asilomar Conference on Signals, Systems and Computers (ASILOMAR), 2010)
Processing structures based on arrays of computational elements form an important class of architectures, which includes field programmable gate arrays (FPGAs), systolic arrays, and various forms of multicore processors. A wide variety of design methods and tools have been targeted to regular processing arrays involving homogeneous processing elements. In this paper, we introduce the concept of field programmable X arrays (FPXAs) as an abstract model for design and implementation of heterogeneous multiprocessor arrays for signal processing systems. FPXAs are abstract structures that can be targeted for implementation on application-specific integrated circuits, FPGAs, or other kinds of reconfigurable processors. FPXAs can also be mapped onto multicore processors for flexible emulation. We discuss the use of dataflow models as an integrated application representation and intermediate representation for efficient specification and mapping of signal processing systems on FPXAs. We demonstrate our proposed models and techniques with a case study involving the embedding of an application-specific FPXA system on an off-the-shelf FPGA device.
Keywords: application specific integrated circuits; application-specific integrated circuits; computational elements; Computer architecture; decoding; Field programmable gate arrays; field programmable X arrays; FPGA; FPXA; Integrated circuit modeling; Logic Design; microprocessor chips; multicore processors; multiprocessor arrays; real-time signal processing; reconfigurable architectures; reconfigurable processors; Routing; Signal processing; Signal processing systems; systolic arrays; Viterbi algorithm

Evolutionary framework for Lepidoptera model systems - Roe,A.; Weller,S.; Baixeras,J.; Brown,J. W; Cummings, Michael P.; Davis,DR; Horak,M; Kawahara,A. Y; Mitter,C; Parr,C.S.; Regier,J. C; Rubinoff,D; et al. (Genetics and Molecular Biology of LepidopteraGenetics and Molecular Biology of Lepidoptera, 2010)
“Model systems” are specific organisms upon which detailed studies have been conducted examining a fundamental biological question. If the studies are robust, their results can be extrapolated among an array of organisms that possess features in common with the subject organism. The true power of model systems lies in the ability to extrapolate these details across larger groups of organisms. In order to generalize these results, comparative studies are essential and require that model systems be placed into their evolutionary or phylogenetic context. This chapter examines model systems in the insect order Lepidoptera from the perspective of several different superfamilies. Historically, many species of Lepidoptera have been essential in the development of invaluable model systems in the fields of development biology, genetics, molecular biology, physiology, co-evolution, population dynamics, and ecology.

Evolving viral marketing strategies - Stonedahl,Forrest; Rand, William; Wilensky,Uri (Proceedings of the 12th annual conference on Genetic and evolutionary computation, 2010)
One method of viral marketing involves seeding certain consumers within a population to encourage faster adoption of the product throughout the entire population. However, determining how many and which consumers within a particular social network should be seeded to maximize adoption is challenging. We define a strategy space for consumer seeding by weighting a combination of network characteristics such as average path length, clustering coefficient, and degree. We measure strategy effectiveness by simulating adoption on a Bass-like agent-based model, with five different social network structures: four classic theoretical models (random, lattice, small-world, and preferential attachment) and one empirical (extracted from Twitter friendship data). To discover good seeding strategies, we have developed a new tool, called BehaviorSearch, which uses genetic algorithms to search through the parameter-space of agent-based models. This evolutionary search also provides insight into the interaction between strategies and network structure. Our results show that one simple strategy (ranking by node degree) is near-optimal for the four theoretical networks, but that a more nuanced strategy performs significantly better on the empirical Twitter-based network. We also find a correlation between the optimal seeding budget for a network, and the inequality of the degree distribution.
Keywords: Agent-based modeling; business; diffusion; Genetic algorithms; simulation; social networks; viral marketing

Exploring the Linkage Dependence of Polyubiquitin Conformations Using Molecular Modeling - Fushman, David; Walker,Olivier (Journal of Molecular Biology, 2010)
Posttranslational modification of proteins by covalent attachment of a small protein ubiquitin (Ub) or a polymeric chain of Ub molecules (called polyubiquitin) is involved in controlling a vast variety of processes in eukaryotic cells. The question of how different polyubiquitin signals are recognized is central to understanding the specificity of various types of polyubiquitination. In polyubiquitin, monomers are linked to each other via an isopeptide bond between the C-terminal glycine of one Ub and a lysine of the other. The functional outcome of polyubiquitination depends on the particular lysine involved in chain formation and appears to rely on linkage-dependent conformation of polyubiquitin. Thus, K48-linked chains, a universal signal for proteasomal degradation, under physiological conditions adopt a closed conformation where functionally important residues L8, I44, and V70 are sequestered at the interface between two adjacent Ub monomers. By contrast, K63-linked chains, which act as a nonproteolytic regulatory signal, adopt an extended conformation that lacks hydrophobic interubiquitin contact. Little is known about the functional roles of the so-called “noncanonical” chains (linked via K6, K11, K27, K29, or K33, or linked head-to-tail), and no structural information on these chains is available, except for information on the crystal structure of the head-to-tail-linked diubiquitin (Ub2). In this study, we use molecular modeling to examine whether any of the noncanonical chains can adopt a closed conformation similar to that in K48-linked polyubiquitin. Our results show that the eight possible Ub2 chains can be divided into two groups: chains linked via K6, K11, K27, or K48 are predicted to form a closed conformation, whereas chains linked via K29, K33, or K63, or linked head-to-tail are unable to form such a contact due to steric occlusion. These predictions are validated by the known structures of K48-, K63-, and head-to-tail-linked chains. Our study also predicts structural models for Ub2 chains linked via K6, K11, or K27. The implications of these findings for linkage-selective recognition of noncanonical polyubiquitin signals by various receptors are discussed.
Keywords: head-to-tail; isopeptide linkage; modeling; noncanonical linkage; polyubiquitin

Exploring the Relationships among ICTs: A Scalable Computational Approach Using KL Divergence and Hierarchical Clustering - Tsui,Chia-jung; Wang,Ping; Fleischmann,Kenneth R.; Oard, Douglas; Sayeed,Asad B. (Hawaii International Conference on System Sciences, 2010)
Different information and communication technologies (ICTs) are related in complex ways and, accordingly, their diffusion trajectories are related, too. How can the relationships among multiple ICTs be described and analyzed in a scalable way? In this study, we offer a scalable methodology, based on computational analysis of discourse, to examine the relationships among ICTs. Specifically, we employed Kullback-Leibler (KL) divergence to compare the semantic similarity of forty-seven ICTs discussed in the trade magazine InformationWeek over a decade. Using hierarchical clustering, we have found that the similarity of the technologies can be mapped in a hierarchy and similar technologies demonstrated similar discourses. The results establish the validity of our approach and demonstrate its scalability and richness. This analytical approach not only enables diffusion researchers to undertake multi-innovation, multi-source, and multi-period studies, but also helps practitioners effectively adopt and efficiently use new ICTs in their organizations.

Expresses-an-opinion-about: using corpus statistics in an information extraction approach to opinion mining - Sayeed,Asad B.; Nguyen,Hieu C.; Meyer,Timothy J.; Weinberg, Amy (Association for Computational Linguistics, 2010)
We present a technique for identifying the sources and targets of opinions without actually identifying the opinions themselves. We are able to use an information extraction approach that treats opinion mining as relation mining; we identify instances of a binary "expresses-an-opinion-about" relation. We find that we can classify source-target pairs as belonging to the relation at a performance level significantly higher than two relevant baselines. This technique is particularly suited to emerging approaches in corpus-based social science which focus on aggregating interactions between sources to determine their effects on socio-economically significant targets. Our application is the analysis of information technology (IT) innovations. This is an example of a more general problem where opinion is expressed using either sub- or supersets of expressive words found in newswire. We present an annotation scheme and an SVM-based technique that uses the local context as well as the corpus-wide frequency of a source-target pair as data to determine membership in "expresses-an-opinion-about". While the presence of conventional subjectivity keywords appears significant in the success of this technique, we are able to find the most domain-relevant keywords without sacrificing recall.

Finding Biologically Accurate Clusterings in Hierarchical Tree Decompositions Using the Variation of Information - Navlakha,Saket; White,James; Nagarajan,Niranjan; Pop, Mihai; Kingsford, Carl (Journal of Computational Biology, 2010)
Hierarchical clustering is a popular method for grouping together similar elements based on a distance measure between them. In many cases, annotations for some elements are known beforehand, which can aid the clustering process. We present a novel approach for decomposing a hierarchical clustering into the clusters that optimally match a set of known annotations, as measured by the variation of information metric. Our approach is general and does not require the user to enter the number of clusters desired. We apply it to two biological domains: finding protein complexes within protein interaction networks and identifying species within metagenomic DNA samples. For these two applications, we test the quality of our clusters by using them to predict complex and species membership, respectively. We find that our approach generally outperforms the commonly used heuristic methods.

Forensic hash for multimedia information - Lu,W.; Varna,A.L.; Wu,M. (SPIE Media Forensics and Security, 2010)
Digital multimedia such as images and videos are prevalent on today’s internet and cause significantsocial impact, which can be evidenced by the proliferation of social networking sites with user generated contents. Due to the ease of generating and modifying images and videos, it is critical to establish trustworthiness for online multimedia information. In this paper, we propose a new framework to perform multimedia forensics by using compact side information to reconstruct the processing history of a multimedia document. We refer to this framework as FASHION, standing for Forensic hASH for informatION assurance. As a first step in the modular design for FASHION, we propose new algorithms based on Radon transform and scale space theory to effectively estimate the parameters of geometric transforms and detect local tampering that an image may have undergone. The FASHION framework is designed to answer a much broader range of questions regarding the processing history of multimedia data than simple binary decision from robust image hashing, and also offers more efficient and accurate forensic analysis than multimedia forensic techniques that do not use any side information.

FPGA-based design and implementation of the 3GPP-LTE physical layer using parameterized synchronous dataflow techniques - Kee, Hojin; Bhattacharyya, Shuvra S.; Wong, I.; Yong Rao (2010 IEEE International Conference on Acoustics Speech and Signal Processing (ICASSP), 2010)
Synchronous dataflow (SDF) is an ubiquitous dataflow model of computation that has been studied extensively for efficient simulation and software synthesis of DSP applications. In recent years, parameterized SDF (PSDF) has evolved as a useful framework for modeling SDF graphs in which arbitrary parameters can be changed dynamically. However, the potential to enable efficient hardware synthesis has been treated relatively sparsely in the literature for SDF and even more so for the newer, more general PSDF model. This paper investigates efficient FPGA-based design and implementation of the physical layer for 3GPP-Long Term Evolution (LTE), a next generation cellular standard. To capture the SDF behavior of the functional core of LTE along with higher level dynamics in the standard, we use a novel PSDF-based FPGA architecture framework. We implement our PSDF-based, LTE design framework using National Instrument's LabVIEW FPGA, a recently-introduced commercial platform for reconfigurable hardware implementation. We show that our framework can effectively model the dynamics of the LTE protocol, while also providing a synthesis framework for efficient FPGA implementation.
Keywords: 3G mobile communication; 3GPP-long term evolution; 3GPP-LTE physical layer; 4G communication systems; Computational modeling; data flow analysis; data flow graphs; Dataflow modeling; Digital signal processing; DSP applications; Field programmable gate arrays; FPGA architecture framework; FPGA implementation; FPGA-based design; Hardware; hardware synthesis; Instruments; LabVIEW FPGA; Logic Design; LTE; next generation cellular standard; parameterized synchronous data flow technique; Pervasive computing; Physical layer; Physics computing; Production; PSDF graph; reconfigurable hardware implementation; Runtime; software synthesis; Ubiquitous Computing; ubiquitous data flow model

A framework for theoretical analysis of content fingerprinting - Varna,A.L.; Chuang,W.H.; Wu,M. (Proc. of SPIE Media Forensics and Security, 2010)
The popularity of video sharing platforms such as Youtube has prompted the need for the development of efficienttechniques for multimedia identification. Content fingerprinting is a promising solution for this problem, whereby a short “fingerprint” that captures robust and unique characteristics of a signal is computed from each multimedia document. This fingerprint is then compared with a database to identify the multimedia. Several fingerprinting techniques have been proposed in the literature and have been evaluated using experiments. To complement these experimental evaluations and gain a deeper understanding, this paper proposes a framework for theoretical modeling and analysis of content fingerprinting schemes. Analysis of some key modules for fingerprint encoding and matching are also presented under this framework.

Gradient descent approach for secure localization in resource constrained wireless sensor networks - Garg,R.; Varna,A.L.; M. Wu (Acoustics Speech and Signal Processing (ICASSP), 2010 IEEE International Conference on, 2010)
Many sensor network related applications require precise knowledge of the location of constituent nodes. In these applications, it is desirable for the wireless nodes to be able to autonomously determine their locations before they start sensing and transmitting data. Most localization algorithms rely on anchor nodes whose locations are known to determine the positions of the remaining nodes. In an adversarial scenario, some of these anchor nodes could be compromised and used to transmit misleading information aimed at preventing the accurate localization of the remaining sensors. In this paper, a computationally efficient algorithm to determine the location of sensors that can resist such attacks is described. The proposed algorithm combines gradient descent with a selective pruning of inconsistent measurements to achieve good localization accuracy. Simulation results show that the proposed algorithm has performance comparable to existing schemes while requiring less computational resources.
Keywords: algorithms; resource; approach; localization; computational; constrained; descent; localization; gradient; methods; wireless; networks; networks; secure; resources; gradient; sensor; wireless

Hopx and Hdac2 Interact to Modulate Gata4 Acetylation and Embryonic Cardiac Myocyte Proliferation - Trivedi,Chinmay M.; Zhu,Wenting; Wang,Qiaohong; Jia,Cheng; Kee,Hae Jin; Li,Li; Hannenhalli, Sridhar; Epstein,Jonathan A. (Developmental Cell, 2010)
SummaryRegulation of chromatin structure via histone modification has recently received intense attention. Here, we demonstrate that the chromatin-modifying enzyme histone deacetylase 2 (Hdac2) functions with a small homeodomain factor, Hopx, to mediate deacetylation of Gata4, which is expressed by cardiac progenitor cells and plays critical roles in the regulation of cardiogenesis. In the absence of Hopx and Hdac2 in mouse embryos, Gata4 hyperacetylation is associated with a marked increase in cardiac myocyte proliferation, upregulation of Gata4 target genes, and perinatal lethality. Hdac2 physically interacts with Gata4, and this interaction is stabilized by Hopx. The ability of Gata4 to transactivate cell cycle genes is impaired by Hopx/Hdac2-mediated deacetylation, and this effect is abrogated by loss of Hdac2-Gata4 interaction. These results suggest that Gata4 is a nonhistone target of Hdac2-mediated deacetylation and that Hdac2, Hopx, and Gata4 coordinately regulate cardiac myocyte proliferation during embryonic development.

Identification of Pathogenic Vibrio Species by Multilocus PCR-Electrospray Ionization Mass Spectrometry and Its Application to Aquatic Environments of the Former Soviet Republic of Georgia - Whitehouse,Chris A.; Baldwin,Carson; Sampath,Rangarajan; Blyn,Lawrence B.; Melton,Rachael; Li,Feng; Hall,Thomas A.; Harpin,Vanessa; Matthews,Heather; Tediashvili,Marina; Jaiani,Ekaterina; Kokashvili,Tamar; et al. (Applied and Environmental MicrobiologyAppl. Environ. Microbiol., 2010)
The Ibis T5000 is a novel diagnostic platform that couples PCR and mass spectrometry. In this study, we developed an assay that can identify all known pathogenic Vibrio species and field-tested it using natural water samples from both freshwater lakes and the Georgian coastal zone of the Black Sea. Of the 278 total water samples screened, 9 different Vibrio species were detected, 114 (41%) samples were positive for V. cholerae, and 5 (0.8%) samples were positive for the cholera toxin A gene (ctxA). All ctxA-positive samples were from two freshwater lakes, and no ctxA-positive samples from any of the Black Sea sites were detected.

Intensity normalization improves color calling in SOLiD sequencing - Wu,Hao; Irizarry,Rafael A; Corrada Bravo, Hector (Nat MethNat Meth, 2010)

Interactive information visualization for exploring and querying electronic health records: A systematic review - Rind,A.; Wang,T. D; Aigner,W.; Miksh,S.; Wongsuphasawat,K.; Plaisant, Catherine; Shneiderman, Ben (Human-Computer Interaction Lab, University of Maryland, 2010)
To overcome the complexity and scale of making medical decisions based on electronic health records (EHRs) a variety of visual methods have been proposed. This paper surveys twelve state-of-the-art information visualization systems described in the scientific literature and compares them based on a set of carefully selected criteria. It aims to systematically examine the systems’ strengths and weaknesses to inform future information visualization designs.We select twelve state-of-the-art information visualization systems from information visualization, medical information systems and human-computer interaction conferences and journals. We compare the systems using the following criteria: (1) data types covered, (2) multivariate analysis support, (3) number of patients records used (one or many), and (4) user intents addressed. The review describes the twelve systems in detail and evaluates the systems using the aforementioned criteria. We discuss how the systems differ in their features and highlight how these differences are related to their design and affect the user intent model. Examples of findings include: (1) most systems handle numerical or categorical data but not both, (2) most systems are specifically designed for looking at a single patient or multiple patients but not both, (3) most systems utilize horizontal time lines to represent time, (4) only systems that handle multiple patient records have good support for Filter, and (5) some specific user intents (e.g. the Encode and Connect intents) are rarely addressed. Based on our review results, we believe that effective information visualization can facilitate analysis of patient records, and we encourage the information visualization community to study the application of their systems and conduct more in depth evaluations. We identify potential future research topics in interactive support for data abstraction and medical tasks that involve looking at a single or multiple records. Finally, we propose to create a repository for data and tasks so benchmarks can be established for both academic and commercial patient record visualization systems.

Isodiamond Hierarchies: An Efficient Multiresolution Representation for Isosurfaces and Interval Volumes - Weiss,K.; De Floriani, Leila (Visualization and Computer Graphics, IEEE Transactions on, 2010)
Efficient multiresolution representations for isosurfaces and interval volumes are becoming increasingly important as the gap between volume data sizes and processing speed continues to widen. Our multiresolution scalar field model is a hierarchy of tetrahedral clusters generated by longest edge bisection that we call a hierarchy of diamonds. We propose two multiresolution models for representing isosurfaces, or interval volumes, extracted from a hierarchy of diamonds which exploit its regular structure. These models are defined by subsets of diamonds in the hierarchy that we call isodiamonds, which are enhanced with geometric and topological information for encoding the relation between the isosurface, or interval volume, and the diamond itself. The first multiresolution model, called a relevant isodiamond hierarchy, encodes the isodiamonds intersected by the isosurface, or interval volume, as well as their nonintersected ancestors, while the second model, called a minimal isodiamond hierarchy, encodes only the intersected isodiamonds. Since both models operate directly on the extracted isosurface or interval volume, they require significantly less memory and support faster selective refinement queries than the original multiresolution scalar field, but do not support dynamic isovalue modifications. Moreover, since a minimal isodiamond hierarchy only encodes intersected isodiamonds, its extracted meshes require significantly less memory than those extracted from a relevant isodiamond hierarchy. We demonstrate the compactness of isodiamond hierarchies by comparing them to an indexed representation of the mesh at full resolution.
Keywords: Computer-Assisted; Imaging; data processing speed; edge bisection; encoding; interval volumes; isodiamond hierarchies; isosurfaces; mesh representation; minimal isodiamond hierarchy; multiresolution representation; multiresolution scalar field model; relevant isodiamond hierarchy; volume data; Theoretical; User-Computer Interface; Three-Dimensional; Models

Learning to efficiently rank - Wang,Lidan; Jimmy Lin; Metzler,Donald (Proceedings of the 33rd international ACM SIGIR conference on Research and development in information retrieval, 2010)
It has been shown that learning to rank approaches are capable of learning highly effective ranking functions. However, these approaches have mostly ignored the important issue of efficiency. Given that both efficiency and effectiveness are important for real search engines, models that are optimized for effectiveness may not meet the strict efficiency requirements necessary to deploy in a production environment. In this work, we present a unified framework for jointly optimizing effectiveness and efficiency. We propose new metrics that capture the tradeoff between these two competing forces and devise a strategy for automatically learning models that directly optimize the tradeoff metrics. Experiments indicate that models learned in this way provide a good balance between retrieval effectiveness and efficiency. With specific loss functions, learned models converge to familiar existing ones, which demonstrates the generality of our framework. Finally, we show that our approach naturally leads to a reduction in the variance of query execution times, which is important for query load balancing and user satisfaction.
Keywords: effectiveness and efficiency tradeoff; Learning to rank; Linear Models

A Lightweight Dataflow Approach for Design and Implementation of SDR Systems - Chung-Ching Shen; Plishker,William; Wu, Hsiang-Huang; Bhattacharyya, Shuvra S. (Wireless Innovation Conference and Product Exposition, Washington DC, USA, 2010)
Model-based design methods based on dataflow modelsof computation are attractive for design and implementation of wireless communication systems because of their intuitive correspondence to communication system block diagrams, and the formal structure that is exposed through formal dataflow representations (e.g., see [2]). In this paper, we introduce a novel lightweight dataflow (LWDF) programming model for model-based design and implementation of wireless communication and software-defined radio systems. The approach is suitable for improving the productivity of the design process; the agility with which designs can be retargeted across different platforms; and the quality of derived implementations. By “lightweight”, we meant that the programming model is designed to be minimally intrusive on existing design processes, and require minimal dependence on specialized tools or libraries. This allows designers to integrate and experiment with dataflow modeling approaches relatively quickly and flexibly into existing design methodologies and processes.

The Metacognitive Loop: An Architecture for Building Robust Intelligent Systems - Shahri,Hamid Haidarian; Dinalankara,Wikum; Fults,Scott; Wilson,Shomir; Perlis, Don; Schmill,Matt; Oates,Tim; Josyula,Darsana; Anderson,Michael (2010 AAAI Fall Symposium Series, 2010)
The Metacognitive Loop: An Architecture for Building Robust Intelligent Systems
Keywords: commonsense; ontologies; robust intelligent systems

Method for concealing data in curves of an image - M. Wu; Gou,Hongmei (2010)
A method of concealing data in images imperceptibly alters curves therein, such as through adding a value representing the data to be hidden to each of a number of B-spline control points representing the original curve. The altered control points characterize the imperceptibly altered curve, which replaces the original curve in the image. The altered control points may be later extracted from the image and compared with the original control points to determine the hidden value. Prudent selection of the values altering the control points as well as an iterative alignment-minimization algorithm in the detection process provides protection against numerous techniques for preventing the hidden values from being recovered.

Method for fingerprinting multimedia content - He,Shan; M. Wu (2010)
To identify participants in collusion directed to altering a digital fingerprint embedded in multimedia content, an ECC based fingerprinting technique establishes a code symbol for each of a plurality of segments of digital data forming the multimedia content. The code symbols are concatenated to form a fingerprint signal, which is subdivided into a plurality of subsegments for each segment in the digital data. The subsegments are permuted and embedded into the digital data. When a suspicious copy of the multimedia content is discovered, the permuted fingerprint signal is extracted from the content and inversely permuted to form a test fingerprint. The identity of one of the colluders is determined by correlation with characteristics of the codeword originally assigned to the user. The determination of identity may be enhanced by the addition of group data embedded as an additional fingerprint in the digital data. Joint consideration of coding and embedding provide benefits over...

Multimedia forensic hash based on visual words - Lu,W.; Wu,M. (IEEE Computer Society International Conference on Image Processing, 2010)
In recent years, digital images and videos have become in-creasingly popular over the internet and bring great social im- pact to a wide audience. In the meanwhile, technology ad- vancement allows people to easily alter the content of dig- ital multimedia and brings serious concern on the trustwor- thiness of online multimedia information. Forensic hash is a short signature attached to an image before transmission and acts as side information for analyzing the processing history and trustworthiness of the received image. In this paper, we propose a new construction of forensic hash based on visual words representation. We encode SIFT features into a com- pact visual words representation for robust estimation of geo- metric transformations and propose a hybrid construction us- ing both SIFT and block-based features to detect and localize image tampering. The proposed hash construction achieves more robust and accurate forensic analysis than prior work.

Multiresolution analysis of 3D images based on discrete distortion - Weiss,K.; De Floriani, Leila; Mesmoudi,M. M. (International Conference on Pattern Recognition (ICPR), 2010)
We consider a model of a 3D image obtained bydiscretizing it into a multiresolution tetrahedral mesh known as a hierarchy of diamonds. This model enables us to extract crack-free approximations of the 3D image at any uniform or variable resolution, thus reducing the size of the data set without reducing the accuracy. A 3D intensity image is a scalar field (the intensity field) defined at the vertices of a 3D regular grid and thus the graph of the image is a hypersurface in R4. We measure the discrete distortion, a generalization of the notion of curvature, of the transformation which maps the tetrahedralized 3D grid onto its graph in R4. We evaluate the use of a hierarchy of diamonds to analyze properties of a 3D image, such as its discrete distortion, directly on lower resolution approximations. Our results indicate that distortion-guided extractions focus the resolution of approximated images on the salient features of the intensity image.

Nested refinement domains for tetrahedral and diamond hierarchies - Weiss,K.; De Floriani, Leila (IEEE Visualization, 2010)
Three nested refinement domains for hierarchies of tetrahedra and diamonds. The descendant domain (left) is the limit shape of thedomain covered by all descendants of a given diamond (colored). Due to the fractal nature of these shapes, we introduce the more conservative convex descendant domain (middle) and bounding box descendant domain (right) to simplify the computation while still tightly covering the descendant domain. In each case, the refinement domain of one of the diamond’s parents, grandparents and great-grandparents is shown.

Online Empirical Evaluation of Tracking Algorithms - Wu,Hao; Sankaranarayanan,A. C; Chellapa, Rama (IEEE Transactions on Pattern Analysis and Machine Intelligence, 2010)
Evaluation of tracking algorithms in the absence of ground truth is a challenging problem. There exist a variety of approaches for this problem, ranging from formal model validation techniques to heuristics that look for mismatches between track properties and the observed data. However, few of these methods scale up to the task of visual tracking, where the models are usually nonlinear and complex and typically lie in a high-dimensional space. Further, scenarios that cause track failures and/or poor tracking performance are also quite diverse for the visual tracking problem. In this paper, we propose an online performance evaluation strategy for tracking systems based on particle filters using a time-reversed Markov chain. The key intuition of our proposed methodology relies on the time-reversible nature of physical motion exhibited by most objects, which in turn should be possessed by a good tracker. In the presence of tracking failures due to occlusion, low SNR, or modeling errors, this reversible nature of the tracker is violated. We use this property for detection of track failures. To evaluate the performance of the tracker at time instant t, we use the posterior of the tracking algorithm to initialize a time-reversed Markov chain. We compute the posterior density of track parameters at the starting time t = 0 by filtering back in time to the initial time instant. The distance between the posterior density of the time-reversed chain (at t = 0) and the prior density used to initialize the tracking algorithm forms the decision statistic for evaluation. It is observed that when the data are generated by the underlying models, the decision statistic takes a low value. We provide a thorough experimental analysis of the evaluation methodology. Specifically, we demonstrate the effectiveness of our approach for tackling common challenges such as occlusion, pose, and illumination changes and provide the Receiver Operating Characteristic (ROC) curves. Finally, we also s how the applicability of the core ideas of the paper to other tracking algorithms such as the Kanade-Lucas-Tomasi (KLT) feature tracker and the mean-shift tracker.
Keywords: Back; Biomedical imaging; Computer vision; Filtering; formal model validation techniques; formal verification; ground truth; Kanade Lucas Tomasi feature tracker; Karhunen-Loeve transforms; lighting; Markov processes; mean shift tracker; model validation.; online empirical evaluation; particle filtering (numerical methods); Particle filters; Particle tracking; performance evaluation; receiver operating characteristic curves; Robustness; SNR; Statistics; Surveillance; time reversed Markov chain; tracking; tracking algorithms; visual tracking

Optimization of linked list prefix computations on multithreaded GPUs using CUDA - Wei, Zheng; JaJa, Joseph F. (Parallel Distributed Processing (IPDPS), 2010 IEEE International Symposium on, 2010)
We present a number of optimization techniques to compute prefix sums on linked lists and implement them on multithreaded GPUs using CUDA. Prefix computations on linked structures involve in general highly irregular fine grain memory accesses that are typical of many computations on linked lists, trees, and graphs. While the current generation of GPUs provides substantial computational power and extremely high bandwidth memory accesses, they may appear at first to be primarily geared toward streamed, highly data parallel computations. In this paper, we introduce an optimized multithreaded GPU algorithm for prefix computations through a randomization process that reduces the problem to a large number of fine-grain computations. We map these fine-grain computations onto multithreaded GPUs in such a way that the processing cost per element is shown to be close to the best possible. Our experimental results show scalability for list sizes ranging from 1M nodes to 256M nodes, and significantly improve on the recently published parallel implementations of list ranking, including implementations on the Cell Processor, the MTA-8, and the NVIDIA GeForce 200 series. They also compare favorably to the performance of the best known CUDA algorithm for the scan operation on the Tesla C1060.
Keywords: 200; accesses; fine; accesses; linked; Bandwidth; C1060; cell; computations; extremely; computations; multithreaded; CUDA; MTA; NVIDIA; GeForce; GPUs; optimization; prefix; grain; high; list; memory; Parallel; prefix; process; coprocessors; multi-threading; processor; data; series; Tesla; sums; randomization

Performance impact of ordinal ranking on content fingerprinting - Chuang,W.H.; Varna,A.L.; Wu,M. (IEEE Int. Conf. on Image Processing, 2010)
Content fingerprinting provides a compact representation ofmultimedia objects for copy identification. This paper ana- lyzes the impact of the ordinal-ranking based feature encod- ing on the performance of content fingerprinting. Expressions are derived for the identification performance of a fingerprint- ing system with and without ordinal ranking. The analysis in- dicates that when the number of features is moderately large, ordinal ranking can improve the robustness of the fingerprint- ing system to large distortions of the features and significantly increase the probability of detection. These results enhance understandings of ordinal ranking and provide design guide- lines for choosing different system parameters to achieve a desired identification accuracy.

Perturbing the Ubiquitin Pathway Reveals How Mitosis Is Hijacked to Denucleate and Regulate Cell Proliferation and Differentiation In Vivo - Caceres,Andrea; Shang,Fu; Wawrousek,Eric; Liu,Qing; Avidan,Orna; Cvekl,Ales; Yang,Ying; Haririnia,Aydin; Storaska,Andrew; Fushman, David; Kuszak,Jer; Dudek,Edward; et al. (PLoS ONEPLoS ONE, 2010)
BackgroundThe eye lens presents a unique opportunity to explore roles for specific molecules in cell proliferation, differentiation and development because cells remain in place throughout life and, like red blood cells and keratinocytes, they go through the most extreme differentiation, including removal of nuclei and cessation of protein synthesis. Ubiquitination controls many critical cellular processes, most of which require specific lysines on ubiquitin (Ub). Of the 7 lysines (K) least is known about effects of modification of K6. Methodology and Principal Findings We replaced K6 with tryptophan (W) because K6 is the most readily modified K and W is the most structurally similar residue to biotin. The backbone of K6W-Ub is indistinguishable from that of Wt-Ub. K6W-Ub is effectively conjugated and deconjugated but the conjugates are not degraded via the ubiquitin proteasome pathways (UPP). Expression of K6W-ubiquitin in the lens and lens cells results in accumulation of intracellular aggregates and also slows cell proliferation and the differentiation program, including expression of lens specific proteins, differentiation of epithelial cells into fibers, achieving proper fiber cell morphology, and removal of nuclei. The latter is critical for transparency, but the mechanism by which cell nuclei are removed has remained an age old enigma. This was also solved by expressing K6W-Ub. p27kip, a UPP substrate accumulates in lenses which express K6W-Ub. This precludes phosphorylation of nuclear lamin by the mitotic kinase, a prerequisite for disassembly of the nuclear membrane. Thus the nucleus remains intact and DNAseIIβ neither gains entry to the nucleus nor degrades the DNA. These results could not be obtained using chemical proteasome inhibitors that cannot be directed to specific tissues. Conclusions and Significance K6W-Ub provides a novel, genetic means to study functions of the UPP because it can be targeted to specific cells and tissues. A fully functional UPP is required to execute most stages of lens differentiation, specifically removal of cell nuclei. In the absence of a functional UPP, small aggregate prone, cataractous lenses are formed.

Picturing signal processing [From the Editor] - Wu,M. (Signal Processing Magazine, IEEE, 2010)

Ranking under temporal constraints - Wang,Lidan; Metzler,Donald; Jimmy Lin (Proceedings of the 19th ACM international conference on Information and knowledge management, 2010)
This paper introduces the notion of temporally constrained ranked retrieval, which, given a query and a time constraint, produces the best possible ranked list within the specified time limit. Naturally, more time should translate into better results, but the ranking algorithm should always produce some results. This property is desirable from a number of perspectives: to cope with diverse users and information needs, as well as to better manage system load and variance in query execution times. We propose two temporally constrained ranking algorithms based on a class of probabilistic prediction models that can naturally incorporate efficiency constraints: one that makes independent feature selection decisions, and the other that makes joint feature selection decisions. Experiments on three different test collections show that both ranking algorithms are able to satisfy imposed time constraints, although the joint model outperforms the independent model in being able to deliver more effective results, especially under tight time constraints, due to its ability to capture feature dependencies.
Keywords: efficiency; Learning to rank; Linear Models

Rapid prototyping for digital signal processing systems using Parameterized Synchronous Dataflow graphs - Wu, Hsiang-Huang; Kee, Hojin; Sane, N.; Plishker,W.; Bhattacharyya, Shuvra S. (2010 21st IEEE International Symposium on Rapid System Prototyping (RSP), 2010)
Parameterized Synchronous Dataflow (PSDF) has been used previously for abstract scheduling and as a model for architecting embedded software and FPGA implementations. PSDF has been shown to be attractive for these purposes due to its support for flexible dynamic reconfiguration, and efficient quasi-static scheduling. To apply PSDF techniques more deeply into the design flow, support for comprehensive functional simulation and efficient hardware mapping is important. By building on the DIF (Dataflow Interchange Format), which is a design language and associated software package for developing and experimenting with dataflow-based design techniques for signal processing systems, we have developed a tool for functional simulation of PSDF specifications. This simulation tool allows designers to model applications in PSDF and simulate their functionality, including use of the dynamic parameter reconfiguration capabilities offered by PSDF. Based on this simulation tool, we also present a systematic design methodology for applying PSDF to the design and implementation of digital signal processing systems, with emphasis on FPGA-based systems for signal processing. We demonstrate capabilities for rapid and accurate prototyping offered by our proposed design methodology, along with its novel support for PSDF-based FPGA system implementation.
Keywords: abstract scheduling; Computational modeling; Computer architecture; data flow graphs; dataflow based design; dataflow interchange format; design flow; design language; Digital signal processing; digital signal processing systems; dynamic parameter reconfiguration; Dynamic scheduling; efficient hardware mapping; efficient quasistatic scheduling; Embedded software; embedded systems; Field programmable gate arrays; flexible dynamic reconfiguration; FPGA based systems; FPGA implementations; functional simulation; Hardware; parameterized synchronous dataflow graphs; rapid prototyping; Schedules; scheduling; semantics; simulation tool; software package; systematic design methodology

REPORTS AI Theory and Practice: A Discussion on Hard Challenges and Opportunities Ahead - Horvitz,E.; Getoor, Lise; Guestrin,C.; Hendler,J.; Kautz,H.; Konstan,J.; Subramanian,D.; Wellman,M. (AI Magazine, 2010)

A Review of Bird-Inspired Flapping Wing Miniature Air Vehicle Designs - Gerdes,John W.; Gupta, Satyandra K.; Wilkerson,Stephen A. (ASME, 2010)
Physical and aerodynamic characteristics of the bird in flight may offer benefits over typical propeller or rotor driven miniature air vehicle (MAV) locomotion designs in certain types of scenarios. A number of research groups and companies have developed flapping wing vehicles that attempt to harness these benefits. The purpose of this paper is to report different types of flapping wing designs and compare their salient characteristics. For each category, advantages and disadvantages will be discussed. The discussion presented will be limited to miniature-sized flapping wing air vehicles, defined as 10–100 grams total weight. The discussion will be focused primarily on ornithopters which have performed at least one successful test flight. Additionally, this paper is intended to provide a representation of the field of current technology, rather than providing a comprehensive listing of all possible designs. This paper will familiarize a newcomer to the field with existing designs and their distinguishing features. By studying existing designs, future designers will be able to adopt features from other successful designs. This paper also summarizes the design challenges associated with the further advancement of the field and deploying flapping wing vehicles in practice.

Security analysis for privacy preserving search of multimedia - Lu,W.; Varna,A.L.; Wu,M. (Image Processing (ICIP), 2010)
With the increasing popularity of digital multimedia such asimages and videos and the advent of the cloud computing paradigm, a fast growing amount of private and sensitive mul- timedia data are being stored and managed over the network cloud. To provide enhanced security and privacy protection beyond traditional access control techniques, privacy preserv- ing multimedia retrieval techniques have been proposed re- cently to allow content-based multimedia retrieval directly over encrypted databases and achieve accurate retrieval com- parable to conventional retrieval schemes. In this paper, we introduce a security definition for the privacy preserving re- trieval scenario and show that the recently proposed schemes are secure under the proposed security definition.

Semantic Video Content Analysis - Albanese,Massimiliano; Turaga,Pavan; Chellapa, Rama; Pugliese,Andrea; Subrahmanian,V. (Video Search and MiningVideo Search and Mining, 2010)
In recent years, there has been significant interest in the area of automatically recognizing activities occurring in a camera’s field of view and detecting abnormalities. The practical applications of such a system could include airport tarmac monitoring, or monitoring of activities in secure installations, to name a few. The difficulty of the problem is compounded by several factors: detection of primitive actions in spite of changes in illumination, occlusions and noise; complexmultiagent interaction;mapping of higher-level activities to lower-level primitive actions; variations in which the same semantic activity can be performed. In this chapter, we develop a theory of semantic activity analysis that addresses each of these issues in an integrated manner. Specifically, we discuss ontological representations of knowledge of a domain, integration of domain knowledge and statistical models for achieving semantic mappings, definition of logical languages to describe activities, and design of frameworks which integrate all the above aspects in a coherent way, thus laying the foundations of effective Semantic Video Content Analysis systems.

Semi non-intrusive training for cell-phone camera model linkage - Chuang,Wei-Hong; M. Wu (Information Forensics and Security (WIFS), 2010 IEEE International Workshop on, 2010)
This paper presents a study of cell-phone camera model linkage that matches digital images against potential makes / models of cell-phone camera sources using camera color interpolation features. The matching performance is examined and the dependency on the content of training image collection is evaluated via variance analysis. Training content dependency can be dealt with under the framework of component forensics, where cell-phone camera model linkage is seen as a combination of semi non-intrusive training and completely non-intrusive testing. Such a viewpoint suggests explicitly the goodness criterion of testing accuracy for training data selection. It also motivates other possible alternative training procedures based on different criteria, such as the training complexity, for which preliminary but promising experiment designs and results have been obtained.
Keywords: accuracy; training; analysis; cameras; cellular; analysis; image; camera; Color; colour; complexity; training; content; dependency; variance; feature; cell; forensics; digital; forensics; image; image; Interpolation; linkage; component; matching; interpolation; matching; semi; model; nonintrusive; phone; radio; computer; training; testing

Special Section on Distributed Camera Networks: Sensing, Processing, Communication, and Implementation - Chellapa, Rama; Heinzelman, W.; Konrad, J.; Schonfeld, D.; Wolf, M. (Image Processing, IEEE Transactions on, 2010)
The eight papers in this special section span across theoretical and practical considerations of various aspects of distributed camera networks, including adaptive sensing, distributed processing, efficient communications, and versatile implementations.

Statistical Analysis on Manifolds and Its Applications to Video Analysis - Turaga,Pavan; Veeraraghavan,Ashok; Srivastava,Anuj; Chellapa, Rama (Video Search and MiningVideo Search and Mining, 2010)
The analysis and interpretation of video data is an important component of modern vision applications such as biometrics, surveillance, motionsynthesis and web-based user interfaces. A common requirement among these very different applications is the ability to learn statistical models of appearance and motion from a collection of videos, and then use them for recognizing actions or persons in a new video. These applications in video analysis require statistical inference methods to be devised on non-Euclidean spaces or more formally on manifolds. This chapter outlines a broad survey of applications in video analysis that involve manifolds. We develop the required mathematical tools needed to perform statistical inference on manifolds and show their effectiveness in real video-understanding applications.

System and Method for Confidentiality-Preserving Rank-Ordered Search - Swaminathan,Ashwin; Mao,Yinian; Su,Guan-Ming; Gou,Hongmei; Varna,Avinash L.; He,Shan; M. Wu; Oard, Douglas (2010)
A confidentiality preserving system and method for performing a rank-ordered search and retrieval of contents of a data collection. The system includes at least one computer system including a search and retrieval algorithm using term frequency and/or similar features for rank-ordering selective contents of the data collection, and enabling secure retrieval of the selective contents based on the rank-order. The search and retrieval algorithm includes a baseline algorithm, a partially server oriented algorithm, and/or a fully server oriented algorithm. The partially and/or fully server oriented algorithms use homomorphic and/or order preserving encryption for enabling search capability from a user other than an owner of the contents of the data collection. The confidentiality preserving method includes using term frequency for rank-ordering selective contents of the data collection, and retrieving the selective contents based on the rank-order.

A Systematic Methodology for Accurate Design-Stage Estimation of Energy Consumption for Injection Molded Parts - Weissman,A.; Ananthanarayanan,A.; Gupta,S.K.; Sriram,R.D. (2010)
Today's ubiquitous use of plastics in product designand manufacturing presents significant environmental and human health challenges. Injection molding, one of the most commonly used processes for making plastic products, consumes a significant amount of energy. A methodology for accurately estimating the energy consumed to injection-mold a part would enable environmentally conscious decision making during the product design. Unfortunately, only limited information is available at the design stage. Therefore, accurately estimating energy consumption before the part has gone into production can be challenging. In this paper, we describe a methodology for energy estimation that works with the limited amount of data available during the design stage, namely the CAD model of the part, the material name, and the production requirements. This methodology uses this data to estimate the parameters of the runner system and an appropriately sized molding machine. It then uses these estimates to compute the machine setup time and the cycle time required for the injection molding operation. This is done by appropriately abstracting information available from the mold flow simulation tools and analytical models that are traditionally used during the manufacturing stage. These times are then multiplied by the power consumed by the appropriately sized machine during each stage of the molding cycle to compute the estimated energy consumption per part.

Toque: designing a cooking-based programming language for and with children - Tarkan,S.; Sazawal,V.; Druin, Allison; Golub,E.; Bonsignore,E. M; Walsh,G.; Atrash,Z. (Proceedings of the 28th international conference on Human factors in computing systems, 2010)

Values of Stakeholders in the Net Neutrality Debate: Applying Content Analysis to Telecommunications Policy - Cheng,An-Shou; Fleischmann,Kenneth R.; Wang,Ping; Ishita,Emi; Oard, Douglas (Hawaii International Conference on System Sciences, 2010)
Net neutrality is an important telecommunications policy debate. This debate is closely tied to technological innovation, economic development, and information access. Values help shape stakeholders' positions on this debate. This paper examines the role of values in shaping the Net neutrality debate through a content analysis of public hearings on Net neutrality. The paper presents a quantitative analysis that reveals the top values implicated in the Net neutrality debate and statistically significant differences among individuals on opposite sides of the Net neutrality debate. A qualitative analysis reveals insights into the connection between specific values and positions on the Net neutrality debate. The paper concludes that values, technology, and policy are interconnected, and that it is useful to understand the values of the various stakeholders within policy debates.

VAST 2010 Challenge: Arms dealings and pandemics - Grinstein,G.; Konecni,S.; Scholtz,J.; Whiting,M.; Plaisant, Catherine (Visual Analytics Science and Technology (VAST), 2010 IEEE Symposium on, 2010)
The 5th VAST Challenge consisted of three mini-challenges that involved both intelligence analysis and bioinformatics. Teams could solve one, two or all three mini-challenges and assess the overall situation to enter the Grand Challenge. Mini-challenge one involved text reports about people and events giving information about arms dealers, situations in various countries and linkages between different countries. Mini-challenge two involved hospital admission and death records from various countries providing information about the spread of a world wide pandemic. Mini-challenge three involved genetic data to be used to identify the origin of the pandemic and the most dangerous viral mutations. The Grand Challenge was to determine how these various mini-challenges were connected. As always the goal was to analyze the data and provide novel interactive visualizations useful in the analytic process. We received 58 submissions in total and gave 15 awards.
Keywords: 2010; administrative; admission; intelligence; analysis; interactive; analysis; medical; challenge; arms; challenge; hospital; data; data; grand; dealings; bioinformatics; dangerous; mutations; death; processing; weapons; records; genetic; reports; bioinformatics; data; VAST; viral; visualizations; minichallenge; pandemics; text

Visual information seeking in multiple electronic health records: design recommendations and a process model - Wang,Taowei David; Wongsuphasawat,Krist; Plaisant, Catherine; Shneiderman, Ben (Proceedings of the 1st ACM International Health Informatics Symposium, 2010)
Current electronic health record (EHR) systems facilitate the storage, retrieval, persistence, and sharing of patient data. However, the way physicians interact with EHRs has not changed much. More specifically, support for temporal analysis of a large number of EHRs has been lacking. A number of information visualization techniques have been proposed to alleviate this problem. Unfortunately, due to their limited application to a single case study, the results are often difficult to generalize across medical scenarios. We present the usage data of Lifelines2,[22] our information visualization system, and user comments, both collected over eight different medical case studies. We generalize our experience into an information-seeking process model for multiple EHRs. Based on our analysis, we make recommendations to future information visualization designers for EHRs on design requirements and future research directions.
Keywords: design requriements; electronic health records; human-computer interaction (hci); Information Visualization

VizWiz: nearly real-time answers to visual questions - Bigham,Jeffrey P.; Jayant,Chandrika; Ji,Hanjie; Little,Greg; Miller,Andrew; Miller,Robert C.; Miller,Robin; Tatarowicz,Aubrey; White,Brandyn; White,Samual; Tom Yeh (Proceedings of the 23nd annual ACM symposium on User interface software and technology, 2010)
The lack of access to visual information like text labels, icons, and colors can cause frustration and decrease independence for blind people. Current access technology uses automatic approaches to address some problems in this space, but the technology is error-prone, limited in scope, and quite expensive. In this paper, we introduce VizWiz, a talking application for mobile phones that offers a new alternative to answering visual questions in nearly real-time - asking multiple people on the web. To support answering questions quickly, we introduce a general approach for intelligently recruiting human workers in advance called quikTurkit so that workers are available when new questions arrive. A field deployment with 11 blind participants illustrates that blind people can effectively use VizWiz to cheaply answer questions in their everyday lives, highlighting issues that automatic approaches will need to address to be useful. Finally, we illustrate the potential of using VizWiz as part of the participatory design of advanced tools by using it to build and evaluate VizWiz::LocateIt, an interactive mobile tool that helps blind people solve general visual search problems.
Keywords: blind users; non-visual interfaces; real-time human computation

VizWiz::LocateIt - enabling blind people to locate objects in their environment - Bigham,Jeffrey P.; Jayant,Chandrika; Miller,Andrew; White,Brandyn; Tom Yeh (Computer Vision and Pattern Recognition Workshops (CVPRW), 2010 IEEE Computer Society Conference on, 2010)
Blind people face a number of challenges when interacting with their environments because so much information is encoded visually. Text is pervasively used to label objects, colors carry special significance, and items can easily become lost in surroundings that cannot be quickly scanned. Many tools seek to help blind people solve these problems by enabling them to query for additional information, such as color or text shown on the object. In this paper we argue that many useful problems may be better solved by directly modeling them as search problems, and present a solution called VizWiz::LocateIt that directly supports this type of interaction. VizWiz::LocateIt enables blind people to take a picture and ask for assistance in finding a specific object. The request is first forwarded to remote workers who outline the object, enabling efficient and accurate automatic computer vision to guide users interactively from their existing cellphones. A two-stage algorithm is presented that uses this information to guide users to the appropriate object interactively from their phone.

Web-scale computer vision using MapReduce for multimedia data mining - White,Brandyn; Tom Yeh; Jimmy Lin; Davis, Larry S. (Proceedings of the Tenth International Workshop on Multimedia Data Mining, 2010)
This work explores computer vision applications of the MapReduce framework that are relevant to the data mining community. An overview of MapReduce and common design patterns are provided for those with limited MapReduce background. We discuss both the high level theory and the low level implementation for several computer vision algorithms: classifier training, sliding windows, clustering, bag-of-features, background subtraction, and image registration. Experimental results for the k-means clustering and single Gaussian background subtraction algorithms are performed on a 410 node Hadoop cluster.
Keywords: background subtraction; bag-of-features; Cloud computing; clustering; Computer vision; image registration; MapReduce

Algorithms for distributional and adversarial pipelined filter ordering problems - Condon,Anne; Deshpande, Amol; Hellerstein,Lisa; Wu,Ning (ACM Trans. Algorithms, 2009)
Pipelined filter ordering is a central problem in database query optimization. The problem is to determine the optimal order in which to apply a given set of commutative filters (predicates) to a set of elements (the tuples of a relation), so as to find, as efficiently as possible, the tuples that satisfy all of the filters. Optimization of pipelined filter ordering has recently received renewed attention in the context of environments such as the Web, continuous high-speed data streams, and sensor networks. Pipelined filter ordering problems are also studied in areas such as fault detection and machine learning under names such as learning with attribute costs, minimum-sum set cover, and satisficing search. We present algorithms for two natural extensions of the classical pipelined filter ordering problem: (1) a distributional-type problem where the filters run in parallel and the goal is to maximize throughput, and (2) an adversarial-type problem where the goal is to minimize the expected value of multiplicative regret. We present two related algorithms for solving (1), both running in time O(n2), which improve on the O(n3 log n) algorithm of Kodialam. We use techniques from our algorithms for (1) to obtain an algorithm for (2).
Keywords: flow algorithms; Pipelined filter ordering; Query optimization; selection ordering

ApproxRank: Estimating Rank for a Subgraph - Yao Wu; Raschid, Louiqa (IEEE 25th International Conference on Data Engineering, 2009. ICDE '09, 2009)
Customized semantic query answering, personalized search, focused crawlers and localized search engines frequently focus on ranking the pages contained within a subgraph of the global Web graph. The challenge for these applications is to compute PageRank-style scores efficiently on the subgraph, i.e., the ranking must reflect the global link structure of the Web graph but it must do so without paying the high overhead associated with a global computation. We propose a framework of an exact solution and an approximate solution for computing ranking on a subgraph. The IdealRank algorithm is an exact solution with the assumption that the scores of external pages are known. We prove that the IdealRank scores for pages in the subgraph converge. Since the PageRank-style scores of external pages may not typically be available, we propose the ApproxRank algorithm to estimate scores for the subgraph. Both IdealRank and ApproxRank represent the set of external pages with an external node L1 and extend the subgraph with links to L1. They also modify the PageRank-style transition matrix with respect to L1. We analyze the L1 distance between IdealRank scores and ApproxRank scores of the subgraph and show that it is within a constant factor of the L1 distance of the external pages (e.g., the true PageRank scores and uniform scores assumed by ApproxRank). We compare ApproxRank and a stochastic complementation approach (SC), a current best solution for this problem, on different types of subgraphs. ApproxRank has similar or superior performance to SC and typically improves on the runtime performance of SC by an order of magnitude or better. We demonstrate that ApproxRank provides a good approximation to PageRank for a variety of subgraphs.
Keywords: Application software; ApproxRank; Computer applications; Crawlers; customized semantic query answering; Data engineering; Educational institutions; Explosions; focused crawlers; global Web graph; graph theory; IdealRank algorithm; Internet; localized search engines; PageRank-style; personalized search; Query processing; Runtime; Search engines; Stochastic processes; Web pages

An architectural level design methodology for smart camera applications - Saha,S.; Kianzad,V.; Schlessman,J.; Aggarwal,G.; Bhattacharyya, Shuvra S.; Chellapa, Rama; Wolf,W. (International Journal of Embedded Systems, 2009)
Today's embedded computing applications are characterised by increased functionality, and hence increased design complexity and processing requirements. The resulting design spaces are vast and designers are typically able to evaluate only small subsets of solutions due to lack of efficient design tools. In this paper, we propose an architectural level design methodology that provides a means for a comprehensive design space exploration for smart camera applications and enable designers to select higher quality solutions and provides substantial savings on the overall cost of the system. We present efficient, accurate and intuitive models for performance estimation and validate them with experiments.

An assessment of systems and software engineering scholars and institutions (2002–2006) - Wong,W. Eric; Tse,T.H.; Glass,Robert L.; Basili, Victor R.; Chen,T.Y. (Journal of Systems and Software, 2009)
This paper summarizes a survey of publications in the field of systems and software engineering from 2002 to 2006. The survey is an ongoing, annual event that identifies the top 15 scholars and institutions over a 5-year period. The rankings are calculated based on the number of papers published in TSE, TOSEM, JSS, SPE, EMSE, IST, and Software. The top-ranked institution is Korea Advanced Institute of Science and Technology, Korea, and the top-ranked scholar is Magne Jørgensen of Simula Research Laboratory, Norway.
Keywords: Research publications; Systems and software engineering; Top institutions; Top scholars

Automatic classification of human values: Applying computational thinking to information ethics - Fleischmann,K.R.; Oard, Douglas; Cheng,A.S.; Wang,P.; Ishita,E. (Proceedings of the American Society for Information Science and Technology, 2009)

Brief announcement: performance potential of an easy-to-program PRAM-on-chip prototype versus state-of-the-art processor - Caragea,G.C.; Saybasili,A. B; Wen,X.; Vishkin, Uzi (Proceedings of the twenty-first annual symposium on Parallelism in algorithms and architectures, 2009)

Component forensics - Swaminathan,A.; M. Wu; Liu,K. J.R (Signal Processing Magazine, IEEE, 2009)
Visual sensor technologies have experienced tremendous growth in recent decades, and digital devices are becoming ubiquitous. Digital images taken by various imaging devices have been used in a growing number of applications, from military and reconnaissance to medical diagnosis and consumer photography. Consequently, a series of new forensic issues arise amidst such rapid advancement and widespread adoption of imaging technologies. For example, one can readily ask what kinds of hardware and software components as well as their parameters have been employed inside these devices? Given a digital image, which imaging sensor or which brand of sensor was used to acquire the image? How was the image acquired? Was it captured using a digital camera, cell phone camera, image scanner, or was it created artificially using an imageediting software? Has the image undergone any manipulation after capture? Is it authentic, or has it been tampered in any way? Does it contain any hidden information or steganographic data? Many of these forensic questions are related to tracing the origin of the digital image to its creation process. Evidence obtained from such analysis would provide useful forensic information to law enforcement, security, and intelligence agencies. Knowledge of image acquisition techniques can also help answer further forensic questions regarding the nature of additional processing that the image might have undergone after capture.
Keywords: ACQUISITION; component; data; forensics; digital; image; of; processing; image; sensor; sensors; security; technique; visual; technology; image

Composability and on-line deniability of authentication - Dodis,Y.; Katz, Jonathan; Smith,A.; Walfish,S. (Theory of Cryptography, 2009)
Protocols for deniable authentication achieve seemingly paradoxical guarantees: upon completion of the protocol the receiver is convinced that the sender authenticated the message, but neither party can convince anyone else that the other party took part in the protocol. We introduce and study on-line deniability, where deniability should hold even when one of the parties colludes with a third party during execution of the protocol. This turns out to generalize several realistic scenarios that are outside the scope of previous models.We show that a protocol achieves our definition of on-line deniability if and only if it realizes the message authentication functionality in the generalized universal composability framework; any protocol satisfying our definition thus automatically inherits strong composability guarantees. Unfortunately, we show that our definition is impossible to realize in the PKI model if adaptive corruptions are allowed (even if secure erasure is assumed). On the other hand, we show feasibility with respect to static corruptions (giving the first separation in terms of feasibility between the static and adaptive setting), and show how to realize a relaxation termed deniability with incriminating abort under adaptive corruptions.

Context-based message expansion for disentanglement of interleaved text conversations - Wang,L.; Oard, Douglas (Proceedings of Human Language Technologies: The 2009 Annual Conference of the North American Chapter of the Association for Computational Linguistics, 2009)

Design guidelines for agent based model visualization - Kornhauser,D.; Wilensky,U.; Rand, William (Journal of Artificial Societies and Social Simulation, 2009)
In the field of agent-based modeling (ABM), visualizations play an important role in identifying, communicating and understanding important behavior of the modeled phenomenon. However, many modelers tend to create ineffective visualizations of Agent Based Models (ABM) due to lack of experience with visual design. This paper provides ABM visualization design guidelines in order to improve visual design with ABM toolkits. These guidelines will assist the modeler in creating clear and understandable ABM visualizations. We begin by introducing a non-hierarchical categorization of ABM visualizations. This categorization serves as a starting point in the creation of an ABM visualization. We go on to present well-known design techniques in the context of ABM visualization. These techniques are based on Gestalt psychology, semiology of graphics, and scientific visualization. They improve the visualization design by facilitating specific tasks, and providing a common language to critique visualizations through the use of visual variables. Subsequently, we discuss the application of these design techniques to simplify, emphasize and explain an ABM visualization. Finally, we illustrate these guidelines using a simple redesign of a NetLogo ABM visualization. These guidelines can be used to inform the development of design tools that assist users in the creation of ABM visualizations.

Design of data warehouse in teaching state based on OLAP and data mining - Zhou,L.; Wu,M.; Li,S. (Proceedings of SPIE, 2009)
The data warehouse and the data mining technology is one of information technology research hot topics. Atpresent the data warehouse and the data mining technology in aspects and so on commercial, financial industry as well as enterprise's production, market marketing obtained the widespread application, but is relatively less in educational fields' application. Over the years, the teaching and management have been accumulating large amounts of data in colleges and universities, while the data can not be effectively used, in the light of social needs of the university development and the current status of data management, the establishment of data warehouse in university state, the better use of existing data, and on the basis dealing with a higher level of disposal --data mining are particularly important. In this paper, starting from the decision-making needs design data warehouse structure of university teaching state, and then through the design structure and data extraction, loading, conversion create a data warehouse model, finally make use of association rule mining algorithm for data mining, to get effective results applied in practice. Based on the data analysis and mining, get a lot of valuable information, which can be used to guide teaching management, thereby improving the quality of teaching and promoting teaching devotion in universities and enhancing teaching infrastructure. At the same time it can provide detailed, multi-dimensional information for universities assessment and higher education research.

Detection of toxigenic Vibrio cholerae O1 in freshwater lakes of the former Soviet Republic of Georgia - Grim,Christopher J.; Jaiani,Ekaterina; Whitehouse,Chris A.; Janelidze,Nino; Kokashvili,Tamuna; Tediashvili,Marina; Rita R Colwell; Huq,Anwar (Environmental Microbiology Reports, 2009)
Three freshwater lakes, Lisi Lake, Kumisi Lake and Tbilisi Sea, near Tbilisi, Georgia, were studied from January 2006 to December 2007 to determine the presence of Vibrio cholerae employing both bacteriological culture method and direct detection methods, namely PCR and direct fluorescent antibody (DFA). For PCR, DNA extracted from water samples was tested for presence of V. cholerae and genes coding for selected virulence factors. Vibrio cholerae non-O1/non-O139 was routinely isolated by culture from all three lakes; whereas V. cholerae O1 and O139 were not. Water samples collected during the summer months from Lisi Lake and Kumisi Lake were positive for both V. cholerae and V. cholerae ctxA, tcpA, zot, ompU and toxR by PCR. Water samples collected during the same period from both Lisi and Kumisi Lake were also positive for V. cholerae serogroup O1 by DFA. All of the samples were negative for V. cholerae serotype O139. The results of this study provide evidence for an environmental presence of toxigenic V. cholerae O1, which may represent a potential source of illness as these lakes serve as recreational water in Tbilisi, Georgia.

Diamond Hierarchies of Arbitrary Dimension - Weiss,Kenneth; De Floriani, Leila (Computer Graphics Forum, 2009)
Nested simplicial meshes generated by the simplicial bisection decomposition proposed by Maubach [Mau95] have been widely used in 2D and 3D as multi-resolution models of terrains and three-dimensional scalar fields, They are an alternative to octree representation since they allow generating crack-free representations of the underlying field. On the other hand, this method generates conforming meshes only when all simplices sharing the bisection edge are subdivided concurrently. Thus, efficient representations have been proposed in 2D and 3D based on a clustering of the simplices sharing a common longest edge in what is called a diamond. These representations exploit the regularity of the vertex distribution and the diamond structure to yield an implicit encoding of the hierarchical and geometric relationships among the triangles and tetrahedra, respectively. Here, we analyze properties of d-dimensional diamonds to better understand the hierarchical and geometric relationships among the simplices generated by Maubach's bisection scheme and derive closed-form equations for the number of vertices, simplices, parents and children of each type of diamond. We exploit these properties to yield an implicit pointerless representation for d-dimensional diamonds and reduce the number of required neighbor-finding accesses from O(d!) to O(d).
Keywords: I.3.5 [Computer Graphics]: Computational Geometry and Object Modeling—Hierarchy and geometric transformations; I.3.6 [Computer Graphics]: Methodology and Techniques—Graphics data structures and data types

Digital forensics [From the Guest Editors] - Delp,E.; Memon, N.; Wu,M. (Signal Processing Magazine, IEEE, 2009)
This special issue provides a comprehensive overview of recent developments and open problems in digital forensics that are amenable to signal processing techniques.

Distinguishing knowledge vs social capital in social media with roles and context - Barash,V.; Smith,M.; Getoor, Lise; Welser,H. T (Proceedings of the ICWSM, 2009)
Social media communities (e.g. Wikipedia, Flickr, Live Q&A) give rise to distinct types of content, foremost among which are relational content (discussion, chat) and factual content (answering questions, problem-solving). Both users and researchers are increasingly interested in developing strategies that can rapidly distinguish these types of content. While many text-based and structural strategies are possible, we extend two bodies of research that show how social context, and the social roles of answerers can predict content type. We test our framework on a dataset of manually labeled contributions to Microsoft's Live Q&A and find that it reliably extracts factual and relational messages from the data.

Diversity and Seasonality of Bioluminescent Vibrio Cholerae Populations in Chesapeake Bay - Zo,Young-Gun; Chokesajjawatee,Nipa; Grim,Christopher; Arakawa,Eiji; Watanabe,Haruo; Rita R Colwell (Applied and Environmental MicrobiologyAppl. Environ. Microbiol., 2009)
Association of luminescence with phenotypic and genotypic traits and with environmental parameters was determined for 278 strains of Vibrio cholerae isolated from the Chesapeake Bay during 1998 to 2000. Three clusters of luminescent strains (A, B, and C) and two nonluminescent clusters (X and Y) were identified among 180 clonal types. V. cholerae O1 strains isolated during pandemics and endemic cholera in the Ganges Delta were related to cluster Y. Heat-stable enterotoxin (encoded by stn) and the membrane protein associated with bile resistance (encoded by ompU) were found to be linked to luminescence in strains of cluster A. Succession from nonluminescent to luminescent populations of V. cholerae occurred during spring to midsummer. Occurrence of cluster A strains in water with neutral pH was contrasted with that of cluster Y strains in water with a pH of >8. Cluster A was found to be associated with a specific calanoid population cooccurring with cyclopoids. Cluster B was related to cluster Y, with its maximal prevalence at pH 8. Occurrence of cluster B strains was more frequent with warmer water temperatures and negatively correlated with maturity of the copepod community. It is concluded that each cluster of luminescent V. cholerae strains occupies a distinct ecological niche. Since the dynamics of these niche-specific subpopulations are associated with zooplankton community composition, the ecology of luminescent V. cholerae is concluded to be related to its interaction with copepods and related crustacean species.

Enabling search over encrypted multimedia databases - Lu,W.; Swaminathan,A.; Varna,A.L.; Wu,M. (SPIE/IS&T Media Forensics and Security, 2009)
Performing information retrieval tasks while preserving data confidentiality is a desirable capability when adatabase is stored on a server maintained by a third-party service provider. This paper addresses the problem of enabling content-based retrieval over encrypted multimedia databases. Search indexes, along with multimedia documents, are first encrypted by the content owner and then stored onto the server. Through jointly apply- ing cryptographic techniques, such as order preserving encryption and randomized hash functions, with image processing and information retrieval techniques, secure indexing schemes are designed to provide both privacy protection and rank-ordered search capability. Retrieval results on an encrypted color image database and se- curity analysis of the secure indexing schemes under different attack models show that data confidentiality can be preserved while retaining very good retrieval performance. This work has promising applications in secure multimedia management.

Energy loss in MEMS resonators and the impact on inertial and RF devices - Weinberg,M.; Candler,R.; Chandorkar,S.; Varsanik,J.; Kenny,T.; Duwel,A. (2009)
In this paper, we review the current understanding of energy loss mechanisms in micromachined (MEMS and NEMS) devices. We describe the importance of high quality factor (Q) to the performance of MEMS gyros and MEMS resonators used in radio-frequency applications.
Keywords: energy loss; gyroscopes; inertial devices; MEMS gyros; MEMS resonators; micromachined devices; micromechanical resonators; NEMS devices; Q-factor; quality factor; radiofrequency applications; RF devices

Evidence for Bidentate Substrate Binding as the Basis for the K48 Linkage Specificity of Otubain 1 - Wang,Tao; Yin,Luming; Cooper,Eric M.; Lai,Ming-Yih; Dickey,Seth; Pickart,Cecile M.; Fushman, David; Wilkinson,Keith D.; Cohen,Robert E.; Wolberger,Cynthia (Journal of Molecular Biology, 2009)
Otubain 1 belongs to the ovarian tumor (OTU) domain class of cysteine protease deubiquitinating enzymes. We show here that human otubain 1 (hOtu1) is highly linkage-specific, cleaving Lys48 (K48)-linked polyubiquitin but not K63-, K29-, K6-, or K11-linked polyubiquitin, or linear α-linked polyubiquitin. Cleavage is not limited to either end of a polyubiquitin chain, and both free and substrate-linked polyubiquitin are disassembled. Intriguingly, cleavage of K48-diubiquitin by hOtu1 can be inhibited by diubiquitins of various linkage types, as well as by monoubiquitin. NMR studies and activity assays suggest that both the proximal and distal units of K48-diubiquitin bind to hOtu1. Reaction of Cys23 with ubiquitin-vinylsulfone identified a ubiquitin binding site that is distinct from the active site, which includes Cys91. Occupancy of the active site is needed to enable tight binding to the second site. We propose that distinct binding sites for the ubiquitins on either side of the scissile bond allow hOtu1 to discriminate among different isopeptide linkages in polyubiquitin substrates. Bidentate binding may be a general strategy used to achieve linkage-specific deubiquitination.
Keywords: deubiquitination; isopeptide; linkage specificity; otubain; polyubiquitin

Finding Biologically Accurate Clusterings in Hierarchical Decompositions Using the Variation of Information - Navlakha,S.; White,J. R.; Nagarajan,N.; Pop, Mihai; Kingsford, Carl (Lecture Notes in Computer Science: Research in Computational Molecular Biology, 2009)

Finding Biologically Accurate Clusterings in Hierarchical Tree Decompositions Using the Variation of Information - Navlakha,Saket; White,James; Nagarajan,Niranjan; Pop, Mihai; Kingsford, Carl (Research in Computational Molecular Biology, 2009)
Hierarchical clustering is a popular method for grouping together similar elements based on a distance measure between them. In many cases, annotations for some elements are known beforehand, which can aid the clustering process. We present a novel approach for decomposing a hierarchical clustering into the clusters that optimally match a set of known annotations, as measured by the variation of information metric. Our approach is general and does not require the user to enter the number of clusters desired. We apply it to two biological domains: finding protein complexes within protein interaction networks and identifying species within metagenomic DNA samples. For these two applications, we test the quality of our clusters by using them to predict complex and species membership, respectively. We find that our approach generally outperforms the commonly used heuristic methods.

Finding comparable temporal categorical records: A similarity measure with an interactive visualization - Wongsuphasawat,K.; Shneiderman, Ben (IEEE Symposium on Visual Analytics Science and Technology, 2009. VAST 2009, 2009)
An increasing number of temporal categorical databases are being collected: Electronic Health Records in healthcare organizations, traffic incident logs in transportation systems, or student records in universities. Finding similar records within these large databases requires effective similarity measures that capture the searcher's intent. Many similarity measures exist for numerical time series, but temporal categorical records are different. We propose a temporal categorical similarity measure, the M&M (Match & Mismatch) measure, which is based on the concept of aligning records by sentinel events, then matching events between the target and the compared records. The M&M measure combines the time differences between pairs of events and the number of mismatches. To accom-modate customization of parameters in the M&M measure and results interpretation, we implemented Similan, an interactive search and visualization tool for temporal categorical records. A usability study with 8 participants demonstrated that Similan was easy to learn and enabled them to find similar records, but users had difficulty understanding the M&M measure. The usability study feedback, led to an improved version with a continuous timeline, which was tested in a pilot study with 5 participants.
Keywords: data visualisation; Educational institutions; Feedback; Information retrieval; interactive search tool; interactive systems; interactive visualization tool; large databases; M&M Measure; Match & Mismatch measure; Medical services; numerical time series; parameters customization; Particle measurements; Similan; similarity measure; Similarity Search; temporal categorical databases; Temporal Categorical Records; temporal databases; Testing; Time measurement; time series; transportation; usability; very large databases; visual databases; Visualization

Fingerprinting Compressed Multimedia Signals - Varna,A.L.; He,Shan; Swaminathan,A.; M. Wu (Information Forensics and Security, IEEE Transactions on, 2009)
Digital fingerprinting is a technique to deter unauthorized redistribution of multimedia content by embedding a unique identifying signal in each legally distributed copy. The embedded fingerprint can later be extracted and used to trace the originator of an unauthorized copy. A group of users may collude and attempt to create a version of the content that cannot be traced back to any of them. As multimedia data is commonly stored in compressed form, this paper addresses the problem of fingerprinting compressed signals. Analysis is carried out to show that due to the quantized nature of the host signal and the embedded fingerprint, directly extending traditional fingerprinting techniques for uncompressed signals to the compressed case leads to low collusion resistance. To overcome this problem and improve the collusion resistance, a new technique for fingerprinting compressed signals called Anti-Collusion Dither (ACD) is proposed, whereby a random dither signal is added to the compressed host before embedding so as to make the effective host signal appear more continuous. The proposed technique is shown to reduce the accuracy with which attackers can estimate the host signal, and from an information theoretic perspective, the proposed ACD technique increases the maximum number of users that can be supported by the fingerprinting system under a given attack. Both analytical and experimental studies confirm that the proposed technique increases the probability of identifying a guilty user and can approximately quadruple the collusion resistance compared to conventional Gaussian fingerprinting.
Keywords: coding; coding; copy; collusion; digital; communication; video; compression; digital; compression; video; dither; collusion; domain; fingerprinting; anti-collusion; fingerprinting; multimedia; Gaussian; management; multimedia; protection; data; resistance; compressed; rights

Formal Representation of Product Design Specifications for Validating Product Design - Weissman,Alexander; Gupta, Satyandra K.; Fiorentini,Xenia; Sudarsan,Rachuri; Sriram,Ram (ASME, 2009)
As collaborative efforts in electro-mechanical design have scaled to large, distributed groups working for years on a single product, an increasingly large gulf has developed between the original stated goals of the project and the final design solution. It has thus become necessary to validate the final design solution against a set of requirements to ensure that these goals have, in fact, been met. This process has become tedious for complex products with hundreds of design aspects and requirements. By formalizing the representation of requirements and the design solution, tools can be developed to a large extent automatically perform this validation. In this paper, we propose a formal approach for relating product requirements to the design solution. First, we present a formal model for representing product requirements. Then, we introduce the Core Product Model (CPM) and the Open Assembly Model (OAM) for representing the design solution. Finally, we link these models formally and provide an example with an actual consumer device.

From New Zealand to Mongolia: Co-designing and deploying a digital library for the world's children - Druin, Allison; Bederson, Benjamin B.; Rose,A.; Weeks,A. (Special issue of Children, Youth and Environments: Children in Technological Environments: Interaction, Development, and Design, 2009)

Gene Profiling of Human Adipose Tissue During Evoked Inflammation In Vivo - Shah,Rachana; Lu,Yun; Hinkle,Christine C; McGillicuddy,Fiona C; Kim,Roy; Hannenhalli, Sridhar; Cappola,Thomas P.; Heffron,Sean; Wang,XingMei; Mehta,Nehal N; Putt,Mary; Reilly,Muredach P (DiabetesDiabetes, 2009)
OBJECTIVE Adipose inflammation plays a central role in obesity-related metabolic and cardiovascular complications. However, few human adipose-secreted proteins are known to mediate these processes. We hypothesized that microarray mRNA profiling of human adipose during evoked inflammation could identify novel adipocytokines.RESEARCH DESIGN AND METHODS Healthy human volunteers (n = 14) were treated with intravenous endotoxin (3 ng/kg lipopolysaccharide [LPS]) and underwent subcutaneous adipose biopsies before and after LPS. On Affymetrix U133Plus 2.0 arrays, adipose mRNAs modulated >1.5-fold (with P < 0.00001) were selected. SignalP 3.0 and SecretomeP 2.0 identified genes predicted to encode secreted proteins. Of these, 86 candidates were chosen for validation in adipose from an independent human endotoxemia protocol (N = 7, with 0.6 ng/kg LPS) and for exploration of cellular origin in primary human adipocytes and macrophages in vitro. RESULTS Microarray identified 776 adipose genes modulated by LPS; 298 were predicted to be secreted. Of detectable prioritized genes, 82 of 85 (96% [95% CI 90–99]) were upregulated (fold changes >1.0) during the lower-dose (LPS 0.6 ng/kg) validation study and 51 of 85 (59% [49–70]) were induced greater than 1.5-fold. Treatment of primary adipocytes with LPS and macrophage polarization to M1 proinflammatory phenotype increased expression by 1.5-fold for 58 and 73% of detectable genes, respectively. CONCLUSIONS We demonstrate that evoked inflammation of human adipose in vivo modulated expression of multiple genes likely secreted by adipocytes and monocytes. These included established adipocytokines and chemokines implicated in recruitment and activation of lymphocytes, adhesion molecules, antioxidants, and several novel genes with unknown function. Such candidates may represent biomarkers and therapeutic targets for obesity-related complications.

Genome assortment, not serogroup, defines Vibrio cholerae pandemic strains - Brettin,Thomas S[Los Alamos National Laboratory; Bruce,David C[Los Alamos National Laboratory; Challacombe,Jean F[Los Alamos National Laboratory; Detter,John C[Los Alamos National Laboratory; Han,Cliff S[Los Alamos National Laboratory; Munik,A. C[Los Alamos National Laboratory; Chertkov,Olga[Los Alamos National Laboratory; Meincke,Linda[Los Alamos National Laboratory; Saunders,Elizabeth[Los Alamos National Laboratory; Choi,Seon Y[SEOUL NATL UNIV; Haley,Bradd J[U MARYLAND; Taviani,Elisa[U MARYLAND; et al. (Nature, 2009)
Vibrio cholerae, the causative agent of cholera, is a bacterium autochthonous to the aquatic environment, and a serious public health threat. V. cholerae serogroup O1 is responsible for the previous two cholera pandemics, in which classical and El Tor biotypes were dominant in the 6th and the current 7th pandemics, respectively. Cholera researchers continually face newly emerging and re-emerging pathogenic clones carrying combinations of new serogroups as well as of phenotypic and genotypic properties. These genotype and phenotype changes have hampered control of the disease. Here we compare the complete genome sequences of 23 strains of V. cholerae isolated from a variety of sources and geographical locations over the past 98 years in an effort to elucidate the evolutionary mechanisms governing genetic diversity and genesis of new pathogenic clones. The genome-based phylogeny revealed 12 distinct V. cholerae phyletic lineages, of which one, designated the V. cholerae core genome (CG), comprises both O1 classical and EI Tor biotypes. All 7th pandemic clones share nearly identical gene content, i.e., the same genome backbone. The transition from 6th to 7th pandemic strains is defined here as a 'shift' between pathogenic clones belonging to the same O1 serogroup, but from significantly different phyletic lineages within the CG clade. In contrast, transition among clones during the present 7th pandemic period can be characterized as a 'drift' between clones, differentiated mainly by varying composition of laterally transferred genomic islands, resulting in emergence of variants, exemplified by V.cholerae serogroup O139 and V.cholerae O1 El Tor hybrid clones that produce cholera toxin of classical biotype. Based on the comprehensive comparative genomics presented in this study it is concluded that V. cholerae undergoes extensive genetic recombination via lateral gene transfer, and, therefore, genome assortment, not serogroup, should be used to define pathogenic V. cholerae clones.
Keywords: 59; CHOLERA; GENES; GENETICS; GENOTYPE; ISLANDS; ORIGIN; PHENOTYPE; PUBLIC HEALTH; RECOMBINATION; STRAINS; TOXINS

High-Fidelity Data Embedding for Image Annotation - He,Shan; Kirovski,D.; M. Wu (Image Processing, IEEE Transactions on, 2009)
High fidelity is a demanding requirement for data hiding, especially for images with artistic or medical value. This correspondence proposes a high-fidelity image watermarking for annotation with robustness to moderate distortion. To achieve the high fidelity of the embedded image, we introduce a visual perception model that aims at quantifying the local tolerance to noise for arbitrary imagery. Based on this model, we embed two kinds of watermarks: a pilot watermark that indicates the existence of the watermark and an information watermark that conveys a payload of several dozen bits. The objective is to embed 32 bits of metadata into a single image in such a way that it is robust to JPEG compression and cropping. We demonstrate the effectiveness of the visual model and the application of the proposed annotation technology using a database of challenging photographic and medical images that contain a large amount of smooth regions.
Keywords: Automated; Product Labeling; Reproducibility of Results; Sensitivity and Specificity; Signal Processing; Computer-Assisted; Computer-Assisted; Information Storage and Retrieval; Pattern Recognition; JPEG compression; JPEG cropping; arbitrary imagery; data hiding; high-fidelity data embedding; image annotation; image watermarking; medical images; photographic images; data compression; image coding; watermarking; Algorithms; Computer Graphics; Documentation; Image En

Improved Non-committing Encryption with Applications to Adaptively Secure Protocols - Choi, Seung Geol; Dana Dachman-Soled; Malkin, Tal; Wee, Hoeteck (Advances in Cryptology – ASIACRYPT 2009, 2009)
We present a new construction of non-committing encryption schemes. Unlike the previous constructions of Canetti et al. (STOC ’96) and of Damgård and Nielsen (Crypto ’00), our construction achieves all of the following properties: Optimal round complexity. Our encryption scheme is a 2-round protocol, matching the round complexity of Canetti et al. and improving upon that in Damgård and Nielsen. Weaker assumptions. Our construction is based on trapdoor simulatable cryptosystems, a new primitive that we introduce as a relaxation of those used in previous works. We also show how to realize this primitive based on hardness of factoring. Improved efficiency. The amortized complexity of encrypting a single bit is O(1) public key operations on a constant-sized plaintext in the underlying cryptosystem. As a result, we obtain the first non-committing public-key encryption schemes under hardness of factoring and worst-case lattice assumptions; previously, such schemes were only known under the CDH and RSA assumptions. Combined with existing work on secure multi-party computation, we obtain protocols for multi-party computation secure against a malicious adversary that may adaptively corrupt an arbitrary number of parties under weaker assumptions than were previously known. Specifically, we obtain the first adaptively secure multi-party protocols based on hardness of factoring in both the stand-alone setting and the UC setting with a common reference string.
Keywords: adaptive corruption; Algorithm Analysis and Problem Complexity; Applications of Mathematics; Data Encryption; Data Structures, Cryptology and Information Theory; Discrete Mathematics in Computer Science; non-committing encryption; public-key encryption; secure multi-party computation; Systems and Data Security

Interacting with eHealth: towards grand challenges for HCI - André,P.; White,R.; Tan,D.; Berners-Lee,T.; Consolvo,S.; Jacobs,R.; Kohane,I.; Le Dantec,C.A.; Mamykina,L.; Marsden,G. (Proceedings of the 27th international conference extended abstracts on Human factors in computing systems, 2009)
While health records are increasingly stored electronically, we, as citizens, have little access to this data about ourselves. We are not used to thinking of these official records either as ours or as useful to us. We increasingly turn to the Web, however, to query any ache, pain or health goal we may have before consulting with health care professionals. Likewise, for proactive health care such as nutrition or fitness, or to find fellow-sufferers for post diagnosis support, we turn to online resources. There is a potential disconnect between points at which professional and lay eHealth data and resources intersect for preventative or proactive health care. Such gaps in information sharing may have direct impact on practices we decide to take up, the care we seek, or the support professionals offer. In this panel, we consider several places within proactive, preventative health care in particular HCI has a role towards enhancing health knowledge discovery and health support interaction. Our goal is to demonstrate how now is the time for eHealth to come to the forefront of the HCI research agenda.

Interactive direct volume rendering on desktop multicore processors - Wang,Qin; JaJa, Joseph F. (Concurrency and Computation: Practice and Experience, 2009)
We present a new multithreaded implementation for the computationally demanding direct volume rendering (DVR) of volumetric data sets on desktop multicore processors using ray casting. The new implementation achieves interactive rendering of very large volumes, even on high resolution screens. Our implementation is based on a new algorithm that combines an object-order traversal of the volumetric data followed by a focused ray casting. Using a very compact data structure, our method starts with a quick association of data subcubes with fine-grain screen tiles appearing along the viewing direction in front-to-back order. The next stage uses very limited ray casting on the generated sets of subcubes while skipping empty or transparent space and applying early ray termination in an effective way. Our multithreaded implementation makes use of new dynamic techniques to ensure effective memory management and load balancing. Our software enables a user to interactively explore large data sets through DVR while arbitrarily specifying a 2D transfer function. We test our system on a wide variety of well-known volumetric data sets on a two-processor Clovertown platform, each consisting of a Quad-Core 1.86 GHz Intel Xeon Processor. Our experimental tests demonstrate DVR at interactive rates for the largest data sets that can fit in the main memory on our platform. These tests also indicate a high degree of scalability, excellent load balancing, and efficient memory management across the data sets used. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: direct volume rendering; multicore processors; multithreaded algorithms; Parallel algorithms; volume visualization

Interlingual annotation of multilingual text corpora and FrameNet - Farwell,David; Dorr, Bonnie J; Habash,Nizar; Helmreich,Stephen; Hovy,Eduard; Green,Rebecca; Levin,Lori; Miller,Keith; Mitamura,Teruko; Rambow,Owen; Reeder,Flo; Siddharthan,Advaith (Multilingual FrameNets in Computational LexicographyMultilingual FrameNets in Computational Lexicography, 2009)

Intrinsic Sensor Noise Features for Forensic Analysis on Scanners and Scanned Images - Gou,Hongmei; Swaminathan,A.; M. Wu (Information Forensics and Security, IEEE Transactions on, 2009)
A large portion of digital images available today are acquired using digital cameras or scanners. While cameras provide digital reproduction of natural scenes, scanners are often used to capture hard-copy art in a more controlled environment. In this paper, new techniques for nonintrusive scanner forensics that utilize intrinsic sensor noise features are proposed to verify the source and integrity of digital scanned images. Scanning noise is analyzed from several aspects using only scanned image samples, including through image denoising, wavelet analysis, and neighborhood prediction, and then obtain statistical features from each characterization. Based on the proposed statistical features of scanning noise, a robust scanner identifier is constructed to determine the model/brand of the scanner used to capture a scanned image. Utilizing these noise features, we extend the scope of acquisition forensics to differentiating scanned images from camera-taken photographs and computer-generated graphics. The proposed noise features also enable tampering forensics to detect postprocessing operations on scanned images. Experimental results are presented to demonstrate the effectiveness of employing the proposed noise features for performing various forensic analysis on scanners and scanned images.
Keywords: analysis; image; camera-taken; cameras; digital; denoising; intrinsic; denoising; wavelet; features; natural; forensics; scanned; graphics; digital; identifier; wavelet; images; digital; images; scanner; NOISE; photographs; computer-generated; prediction; nonintrusive; reproduction; forensic; scanner; scenes; neighborhood; sensor; transforms

The Maryland Modular Method: An Approach to Doctoral Education in Information Studies - Druin, Allison; Jaeger,P. T; Golbeck,J.; Fleischmann,K.R.; Jimmy Lin; Qu,Y.; Wang,P.; Xie,B. (Journal of education for library and information science, 2009)

Matching person names through name transformation - Gong,Jun; Wang,Lidan; Oard, Douglas (Proceedings of the 18th ACM conference on Information and knowledge management, 2009)
Matching person names plays an important role in many applications, including bibliographic databases and indexing systems. Name variations and spelling errors make exact string matching problematic; therefore, it is useful to develop methodologies that can handle variant forms for the same named entity. In this paper, a novel person name matching model is presented. Common name variations in the English speaking world are formalized, and the concept of name transformation paths is introduced; name similarity is measured after the best transformation path has been selected. Supervised techniques are used to learn a similarity function and a decision rule. Experiments with three datasets show the method to be effective.
Keywords: name matching; string distance metrics; string similarity

Modeling actions of PubMed users with n-gram language models - Jimmy Lin; Wilbur,W. J (Information retrieval, 2009)
Transaction logs from online search engines are valuable for two reasons: First, they provide insight into human information-seeking behavior. Second, log data can be used to train user models, which can then be applied to improve retrieval systems. This article presents a study of logs from PubMed®, the public gateway to the MEDLINE® database of bibliographic records from the medical and biomedical primary literature. Unlike most previous studies on general Web search, our work examines user activities with a highly-specialized search engine. We encode user actions as string sequences and model these sequences using n-gram language models. The models are evaluated in terms of perplexity and in a sequence prediction task. They help us better understand how PubMed users search for information and provide an enabler for improving users’ search experience.

Modeling and analysis of content identification - Varna,A.L.; M. Wu (Multimedia and Expo, 2009. ICME 2009. IEEE International Conference on, 2009)
Content fingerprinting provides a compact content-based representation of a multimedia document. An important application of fingerprinting is the identification of modified copies of the original media content. These modifications may be incidental changes that occur during the usage of multimedia, or intentional modifications made by an adversary to avoid detection. Currently, the effectiveness of content identification techniques is often assessed through benchmark databases. To complement these experimental performance evaluations, this paper develops a theoretical framework for analyzing content identification techniques. Beneficial aspects from decision theory and game theory are exploited to gain insights toward optimal system design and parameter selection.
Keywords: benchmark; databases; content; design; decision; document; optimal; identification; identification; game; representation; decision; system; systems; techniques; content-based; theory; fingerprint; theory; fingerprinting; theory; multimedia

Modeling and analysis of ordinal ranking in content fingerprinting - Chuang,Wei-Hong; Varna,A.L.; M. Wu (Information Forensics and Security, 2009. WIFS 2009. First IEEE International Workshop on, 2009)
Content fingerprinting provides a compact representation of multimedia objects for copy detection. This paper analyzes the robustness of the ordinal ranking module frequently used in content fingerprinting by examining the changes in ranks as local variations are introduced in feature values. Closed-form expressions to measure such sensitivity are derived when feature values are jointly Gaussian-distributed. The results show that sensitivity depends on the strength of local variation, the total number of blocks, and the correlations among block-based feature values. Experiments with both synthesized data and image data validate the analysis and provide interesting insights, inspiring an approach to reduce the sensitivity.
Keywords: detection; detection; multimedia; fingerprinting; copy; Gaussian-distributed; content; identification; multimedia; objects; ordinal; processes; fingerprint; ranking; Gaussian; systems; object

Modeling content fingerprints using markov random fields - Varna,A.L.; M. Wu (Information Forensics and Security, 2009. WIFS 2009. First IEEE International Workshop on, 2009)
Content fingerprints are widely employed for identifying multimedia in various applications. A Â¿fingerprintÂ¿ of a video or audio is a short signature that captures unique characteristics of the signal and can be used to perform robust identification. Several fingerprinting techniques have been proposed in the literature and are often evaluated using benchmark databases. To complement these experimental evaluations, this paper develops a theoretical model for content fingerprints and evaluates the identification accuracy. Fingerprints and the noise are modeled as Markov random fields and the optimal decision rule for matching is derived. An algorithm to compute the probability of correct detection and the false alarm rate by estimating the density of states is described. Numerical results are provided for a model of a block based binary fingerprinting scheme and the influence of the fingerprint correlation and the noise on the detection accuracy is studied.
Keywords: based; binary; correlation; multimedia; noise; optimal; data; decision; field; block; fingerprint; fingerprint; fingerprinting; content; Markov; of; processes; multimedia; random; rule; Markov; systems; probability; security

Opinion graphs for polarity and discourse classification - Somasundaran,Swapna; Namata,Galileo; Getoor, Lise; Wiebe,Janyce (Proceedings of the 2009 Workshop on Graph-based Methods for Natural Language Processing, 2009)
This work shows how to construct discourse-level opinion graphs to perform a joint interpretation of opinions and discourse relations. Specifically, our opinion graphs enable us to factor in discourse information for polarity classification, and polarity information for discourse-link classification. This inter-dependent framework can be used to augment and improve the performance of local polarity and discourse-link classifiers.

An oscillatory hebbian network model of short-term memory - Winder,R. K; Reggia, James A.; Weems,S. A; Bunting,M. F (Neural computation, 2009)

Predicate Privacy in Encryption Systems - Shen, Emily; Elaine Shi; Waters,Brent (Theory of Cryptography, 2009)
Predicate encryption is a new encryption paradigm which gives a master secret key owner fine-grained control over access to encrypted data. The master secret key owner can generate secret key tokens corresponding to predicates. An encryption of data x can be evaluated using a secret token corresponding to a predicate f ; the user learns whether the data satisfies the predicate, i.e., whether f ( x ) = 1. Prior work on public-key predicate encryption has focused on the notion of data or plaintext privacy, the property that ciphertexts reveal no information about the encrypted data to an attacker other than what is inherently revealed by the tokens the attacker possesses. In this paper, we consider a new notion called predicate privacy , the property that tokens reveal no information about the encoded query predicate. Predicate privacy is inherently impossible to achieve in the public-key setting and has therefore received little attention in prior work. In this work, we consider predicate encryption in the symmetric-key setting and present a symmetric-key predicate encryption scheme which supports inner product queries. We prove that our scheme achieves both plaintext privacy and predicate privacy.
Keywords: Computer science

Querying timestamped event sequences by exact search or similarity-based search: design and empirical evaluation - Wongsuphasawat,K.; Plaisant, Catherine; Shneiderman, Ben (Human-Computer Interaction Lab, University of Maryland, 2009)

Reading tea leaves: How humans interpret topic models - Chang,J.; Jordan Boyd-Graber; Gerrish,S.; Wang,C.; Blei,D.M. (Proceedings of the 23rd Annual Conference on Neural Information Processing Systems, 2009)
Probabilistic topic models are a popular tool for the unsupervised analysis of text, providing both a predictive model of future text and a latent topic representation of the corpus. Practitioners typically assume that the latent space is semantically meaningful. It is used to check models, summarize the corpus, and guide explo- ration of its contents. However, whether the latent space is interpretable is in need of quantitative evaluation. In this paper, we present new quantitative methods for measuring semantic meaning in inferred topics. We back these measures with large-scale user studies, showing that they capture aspects of the model that are undetected by previous measures of model quality based on held-out likelihood. Surprisingly, topic models which perform better on held-out likelihood may infer less semantically meaningful topics.

Recognition of quantized still face images - Tao Wu; Chellapa, Rama (Biometrics: Theory, Applications, and Systems, 2009. BTAS '09. IEEE 3rd International Conference on, 2009)
In applications such as document understanding, only binary face images may be available as inputs to a face recognition (FR) algorithm. In this paper, we investigate the effects of the number of grey levels on PCA, multiple exemplar discriminant analysis (MEDA) and the elastic bunch graph matching (EBGM) FR algorithms. The inputs to these FR algorithms are quantized images (binary images or images with small number of grey levels) modified by distance and Box-Cox transforms. The performances of PCA and MEDA algorithms are at 87.66% for images in FRGC version 1 experiment 1 after they are thresholded and transformed while the EBGM algorithm achieves only 37.5%. In many document understanding applications, it is also required to verify a degraded low-quality image against a high-quality image, both of which are from the same source. For this problem, the performances of PCA and MEDA are stable when the images were degraded by noise, downsampling or different thresholding parameters.
Keywords: (signal); algorithm; grey; algorithms; face; analysis; quantisation; analysis; quantized; Box-Cox; bunch; component; discriminant; exemplar; Face; FR; graph; images; distance; images; face; levels; multiple; MATCHING; recognition; recognition; principal; transforms; document; transforms; PCA; binary; understanding; elastic

Resistin gene variation is associated with systemic inflammation but not plasma adipokine levels, metabolic syndrome or coronary atherosclerosis in nondiabetic Caucasians - Qasim,Atif N; Metkus,Thomas S; Tadesse,Mahlet; Lehrke,Michael; Restine,Stephanie; Wolfe,Megan L; Hannenhalli, Sridhar; Cappola,Thomas; Rader,Daniel J; Reilly,Muredach P (Clinical Endocrinology, 2009)
Objective  Resistin causes insulin resistance and diabetes in mice whereas in humans it is linked to inflammation and atherosclerosis. Few human genetic studies of resistin in inflammation and atherosclerosis have been performed. We hypothesized that the –420C>G putative gain-of-function resistin variant would be associated with inflammatory markers and atherosclerosis but not with metabolic syndrome or adipokines in humans.Design and methods  We examined the association of three resistin polymorphisms, –852A>G, –420C>G and +157C>T, and related haplotypes with plasma resistin, cytokines, C-reactive protein (CRP), adipokines, plasma lipoproteins, metabolic syndrome and coronary artery calcification (CAC) in nondiabetic Caucasians (n = 851). Results  Resistin levels were higher, dose-dependently, with the –420G allele (CC 5·9 ± 2·7 ng/ml, GC 6·5 ± 4·0 ng/ml and GG 7·2 ± 4·8 ng/ml, trend P = 0·04) after age and gender adjustment [fold higher for GC + GG vs. CC; 1·07 (1·00–1·15), P < 0·05)]. The –852A>G single nucleotide polymorphism (SNP) was associated with higher soluble tumour necrosis factor-receptor 2 (sol-TNFR2) levels in fully adjusted models [1·06 (95% CI 1·01–1·11), P = 0·01)]. The estimated resistin haplotype (GGT) was associated with sol-TNFR2 (P = 0·04) and the AGT haplotype was related to CRP (P = 0·04) in the fully adjusted models. Resistin SNPs and haplotypes were not associated with body mass index (BMI), fasting glucose, insulin resistance, metabolic syndrome, adipokines or CAC scores. Conclusions  Despite modest associations with plasma resistin and inflammatory biomarkers, resistin 5′ variants were not associated with metabolic parameters or coronary calcification. This suggests that resistin is an inflammatory cytokine in humans but has little influence on adiposity, metabolic syndrome or atherosclerosis.

Running memory span: A comparison of behavioral capacity limits with those of an attractor neural network - Weems,Scott A.; Winder,Ransom K.; Bunting,Michael; Reggia, James A. (Cognitive Systems Research, 2009)
We studied a computational model of short term memory capacity that performs a simulated running memory span task using Hebbian learning and rapid decay of connection strengths to keep recent items active for later recall. This model demonstrates recall performance similar to humans performing the same task, with a capacity limit of approximately three items and a prominent recency effect. The model also shows that this capacity depends on decay to release the model from accumulating interference. Model findings are compared with data from two behavioral experiments that used varying task demands to tax memory capacity limits. Following additional theoretical predictions from the computational model, behavioral data support that when task demands require attention to be spread too thin to keep items available for later recall, capacity limits suffer. These findings are important both for understanding the mechanisms underlying short term memory capacity, and also to memory researchers interested in the role of attention in capacity limitations.
Keywords: Attractor neural network; Computational model; Running span; Short term memory; Working memory capacity

Secure image retrieval through feature protection - Lu,Wenjun; Varna,A.L.; Swaminathan,A.; M. Wu (Acoustics, Speech and Signal Processing, 2009. ICASSP 2009. IEEE International Conference on, 2009)
This paper addresses the problem of image retrieval from an encrypted database, where data confidentiality is preserved both in the storage and retrieval process. The paper focuses on image feature protection techniques which enable similarity comparison among protected features. By utilizing both signal processing and cryptographic techniques, three schemes are investigated and compared, including bit-plane randomization, random projection, and randomized unary encoding. Experimental results show that secure image retrieval can achieve comparable retrieval performance to conventional image retrieval techniques without revealing information about image content. This work enriches the area of secure information retrieval and can find applications in secure online services for images and videos.
Keywords: bit-plane; confidentiality; data; database; image; databases; encoding; signal; extraction; image; feature; processes; visual; processing; content-based; projection; randomized; protection; image; randomization; cryptographic; retrieval; cryptography; feature; retrieval; random; storage; encrypted; technique; data; unary

Serogroup, Virulence, and Genetic Traits of Vibrio Parahaemolyticus in the Estuarine Ecosystem of Bangladesh - Alam,Munirul; Chowdhury,Wasimul B.; Bhuiyan,N. A.; Islam,Atiqul; Hasan,Nur A.; Nair,G. Balakrish; Watanabe,H.; Siddique,A. K.; Huq,Anwar; Sack,R. Bradley; Akhter,M. Z.; Grim,Christopher J.; et al. (Applied and Environmental MicrobiologyAppl. Environ. Microbiol., 2009)
Forty-two strains of Vibrio parahaemolyticus were isolated from Bay of Bengal estuaries and, with two clinical strains, analyzed for virulence, phenotypic, and molecular traits. Serological analysis indicated O8, O3, O1, and K21 to be the major O and K serogroups, respectively, and O8:K21, O1:KUT, and O3:KUT to be predominant. The K antigen(s) was untypeable, and pandemic serogroup O3:K6 was not detected. The presence of genes toxR and tlh were confirmed by PCR in all but two strains, which also lacked toxR. A total of 18 (41%) strains possessed the virulence gene encoding thermostable direct hemolysin (TDH), and one had the TDH-related hemolysin (trh) gene, but not tdh. Ten (23%) strains exhibited Kanagawa phenomenon that surrogates virulence, of which six, including the two clinical strains, possessed tdh. Of the 18 tdh-positive strains, 17 (94%), including the two clinical strains, had the seromarker O8:K21, one was O9:KUT, and the single trh-positive strain was O1:KUT. None had the group-specific or ORF8 pandemic marker gene. DNA fingerprinting employing pulsed-field gel electrophoresis (PFGE) of SfiI-digested DNA and cluster analysis showed divergence among the strains. Dendrograms constructed using PFGE (SfiI) images from a soft database, including those of pandemic and nonpandemic strains of diverse geographic origin, however, showed that local strains formed a cluster, i.e., “clonal cluster,” as did pandemic strains of diverse origin. The demonstrated prevalence of tdh-positive and diarrheagenic serogroup O8:K21 strains in coastal villages of Bangladesh indicates a significant human health risk for inhabitants.

Signing a linear subspace: Signature schemes for network coding - Boneh,D.; Freeman,D.; Katz, Jonathan; Waters,B. (Public Key Cryptography–PKC 2009, 2009)
Network coding offers increased throughput and improved robustness to random faults in completely decentralized networks. In contrast to traditional routing schemes, however, network coding requires intermediate nodes to modify data packets en route; for this reason, standard signature schemes are inapplicable and it is a challenge to provide resilience to tampering by malicious nodes.We propose two signature schemes that can be used in conjunction with network coding to prevent malicious modification of data. Our schemes can be viewed as signing linear subspaces in the sense that a signature σ on a subspace V authenticates exactly those vectors in V. Our first scheme is (suitably) homomorphic and has constant public-key size and per-packet overhead. Our second scheme does not rely on random oracles and is based on weaker assumptions. We also prove a lower bound on the length of signatures for linear subspaces showing that our schemes are essentially optimal in this regard.

Simple, Black-Box Constructions of Adaptively Secure Protocols - Choi, Seung Geol; Dana Dachman-Soled; Malkin, Tal; Wee, Hoeteck (Theory of Cryptography, 2009)
We present a compiler for transforming an oblivious transfer (OT) protocol secure against an adaptive semi-honest adversary into one that is secure against an adaptive malicious adversary. Our compiler achieves security in the universal composability framework, assuming access to an ideal commitment functionality, and improves over previous work achieving the same security guarantee in two ways: it uses black-box access to the underlying protocol and achieves a constant multiplicative overhead in the round complexity. As a corollary, we obtain the first constructions of adaptively secure protocols in the stand-alone model using black-box access to a low-level primitive.
Keywords: Algorithm Analysis and Problem Complexity; computers and society; Data Encryption; Discrete Mathematics in Computer Science; Management of Computing and Information Systems; Systems and Data Security

Statistical Methods for Detecting Differentially Abundant Features in Clinical Metagenomic Samples - White,James Robert; Nagarajan,Niranjan; Pop, Mihai (PLoS Comput Biology, 2009)
The emerging field of metagenomics aims to understand the structure and function of microbial communities solely through DNA analysis. Current metagenomics studies comparing communities resemble large-scale clinical trials with multiple subjects from two general populations (e.g. sick and healthy). To improve analyses of this type of experimental data, we developed a statistical methodology for detecting differentially abundant features between microbial communities, that is, features that are enriched or depleted in one population versus another. We show our methods are applicable to various metagenomic data ranging from taxonomic information to functional annotations. We also provide an assessment of taxonomic differences in gut microbiota between lean and obese humans, as well as differences between the functional capacities of mature and infant gut microbiomes, and those of microbial and viral metagenomes. Our methods are the first to statistically address differential abundance in comparative metagenomics studies with multiple subjects, and we hope will give researchers a more complete picture of how exactly two environments differ.

Structure of the S5a:K48-Linked Diubiquitin Complex and Its Interactions with Rpn13 - Zhang,Naixia; Wang,Qinghua; Ehlinger,Aaron; Randles,Leah; Lary,Jeffrey W.; Kang,Yang; Haririnia,Aydin; Storaska,Andrew J.; Cole,James L.; Fushman, David; Walters,Kylie J. (Molecular Cell, 2009)
SummaryDegradation by the proteasome typically requires substrate ubiquitination. Two ubiquitin receptors exist in the proteasome, S5a/Rpn10 and Rpn13. Whereas Rpn13 has only one ubiquitin-binding surface, S5a binds ubiquitin with two independent ubiquitin-interacting motifs (UIMs). Here, we use nuclear magnetic resonance (NMR) and analytical ultracentrifugation to define at atomic level resolution how S5a binds K48-linked diubiquitin, in which K48 of one ubiquitin subunit (the “proximal” one) is covalently bonded to G76 of the other (the “distal” subunit). We demonstrate that S5a's UIMs bind the two subunits simultaneously with a preference for UIM2 binding to the proximal subunit while UIM1 binds to the distal one. In addition, NMR experiments reveal that Rpn13 and S5a bind K48-linked diubiquitin simultaneously with subunit specificity, and a model structure of S5a and Rpn13 bound to K48-linked polyubiquitin is provided. Altogether, our data demonstrate that S5a is highly adaptive and cooperative toward binding ubiquitin chains.
Keywords: Proteins

Supercubes: A High-Level Primitive for Diamond Hierarchies - Weiss,K.; De Floriani, Leila (Visualization and Computer Graphics, IEEE Transactions on, 2009)
Volumetric datasets are often modeled using a multiresolution approach based on a nested decomposition of the domain into a polyhedral mesh. Nested tetrahedral meshes generated through the longest edge bisection rule are commonly used to decompose regular volumetric datasets since they produce highly adaptive crack-free representations. Efficient representations for such models have been achieved by clustering the set of tetrahedra sharing a common longest edge into a structure called a diamond. The alignment and orientation of the longest edge can be used to implicitly determine the geometry of a diamond and its relations to the other diamonds within the hierarchy. We introduce the supercube as a high-level primitive within such meshes that encompasses all unique types of diamonds. A supercube is a coherent set of edges corresponding to three consecutive levels of subdivision. Diamonds are uniquely characterized by the longest edge of the tetrahedra forming them and are clustered in supercubes through the association of the longest edge of a diamond with a unique edge in a supercube. Supercubes are thus a compact and highly efficient means of associating information with a subset of the vertices, edges and tetrahedra of the meshes generated through longest edge bisection. We demonstrate the effectiveness of the supercube representation when encoding multiresolution diamond hierarchies built on a subset of the points of a regular grid. We also show how supercubes can be used to efficiently extract meshes from diamond hierarchies and to reduce the storage requirements of such variable-resolution meshes.
Keywords: (computer; adaptive; approach; nested; bisection; crack-free; datasets; computational; decomposition; nested; diamond; generation; rendering; geometry; mesh; graphics); hierarchies; edge; mesh; supercubes; tetrahedra; meshes; polyhedral; representations; multiresolution; rule; highly; sharing; volumetric; tetrahedral

Supervised and unsupervised methods in employing discourse relations for improving opinion polarity classification - Somasundaran,Swapna; Namata,Galileo; Wiebe,Janyce; Getoor, Lise (Proceedings of the 2009 Conference on Empirical Methods in Natural Language Processing: Volume 1 - Volume 1, 2009)
This work investigates design choices in modeling a discourse scheme for improving opinion polarity classification. For this, two diverse global inference paradigms are used: a supervised collective classification framework and an unsupervised optimization framework. Both approaches perform substantially better than baseline approaches, establishing the efficacy of the methods and the underlying discourse scheme. We also present quantitative and qualitative analyses showing how the improvements are achieved.

SYSTEM AND METHOD FOR THREAD HANDLING IN MULTITHREADED PARALLEL COMPUTING OF NESTED THREADS - Wen,Xingzhi; Vishkin, Uzi (2009)
An Explicit Multi-Threading (XMT) system and method is provided for processing multiple spawned threads associated with SPAWN-type commands of an XMT program. The method includes executing a plurality of child threads by a plurality of TCUs including a first TCU executing a child thread which is allocated to it; completing execution of the child thread by the first TCU; announcing that the first TCU is available to execute another child thread; executing by a second TCU a parent child thread that includes a nested spawn-type command for spawning additional child threads of the plurality of child threads, wherein the parent child thread is related in a parent-child relationship to the child threads that are spawned in conjunction with the nested spawn-type command; assigning a thread ID (TID) to each child thread, wherein the TID is unique with respect to the other TIDs; and allocating a new child thread to the first TCU.

Tampering identification using Empirical Frequency Response - Chuang,Wei-Hong; Swaminathan,A.; M. Wu (Acoustics, Speech and Signal Processing, 2009. ICASSP 2009. IEEE International Conference on, 2009)
With the widespread popularity of digital images and the presence of easy-to-use image editing software, content integrity can no longer be taken for granted, and there is a strong need for techniques that not only detect the presence of tampering but also identify its type. This paper focusses on tampering-type identification and introduces a new approach based on the empirical frequency response (EFR) to address this problem. We show that several types of tampering operations, both linear shift invariant (LSI) and non-LSI, can be characterized consistently and distinctly by their EFRs. We then extend the approach to estimate the EFR for scenarios where only the final image is available. Theoretical reasoning supported by experimental results verify the effectiveness of this method for identifying the type of a tampering operation.
Keywords: aproach; JPEG; coding; multimedia; compression; frequency; compression; LSI; computing; security; data; editing; EFR; forensics; tampering-type; Frequency; identification; data; image; invariant; multimedia; of; response; image; response; linear; shift; software; empirical; system; digital

Temporal Summaries: Supporting Temporal Categorical Searching, Aggregation and Comparison - Wang,T. D; Plaisant, Catherine; Shneiderman, Ben; Spring, Neil; Roseman,D.; Marchand,G.; Mukherjee,V.; Smith,M. (Visualization and Computer Graphics, IEEE Transactions on, 2009)
When analyzing thousands of event histories, analysts often want to see the events as an aggregate to detect insights and generate new hypotheses about the data. An analysis tool must emphasize both the prevalence and the temporal ordering of these events. Additionally, the analysis tool must also support flexible comparisons to allow analysts to gather visual evidence. In a previous work, we introduced align, rank, and filter (ARF) to accentuate temporal ordering. In this paper, we present temporal summaries, an interactive visualization technique that highlights the prevalence of event occurrences. Temporal summaries dynamically aggregate events in multiple granularities (year, month, week, day, hour, etc.) for the purpose of spotting trends over time and comparing several groups of records. They provide affordances for analysts to perform temporal range filters. We demonstrate the applicability of this approach in two extensive case studies with analysts who applied temporal summaries to search, filter, and look for patterns in electronic health records and academic records.
Keywords: Automated; Thrombocytopenia; Time Factors; Computerized; Pattern Recognition; Factual; Heparin; Humans; Medical Records Systems; interactive visualization technique; temporal categorical searching; temporal ordering; temporal summaries; data visualisation; human computer interaction; Computational Biology; Computer Graphics; Databases

Temporal Summaries: Supporting Temporal Categorical Searching, Aggregation and Comparison - Wang,T. D; Plaisant, Catherine; Shneiderman, Ben; Spring, Neil; Roseman,D.; Marchand,G.; Mukherjee,V.; Smith,M. (IEEE Transactions on Visualization and Computer Graphics, 2009)
When analyzing thousands of event histories, analysts often want to see the events as an aggregate to detect insights and generate new hypotheses about the data. An analysis tool must emphasize both the prevalence and the temporal ordering of these events. Additionally, the analysis tool must also support flexible comparisons to allow analysts to gather visual evidence. In a previous work, we introduced align, rank, and filter (ARF) to accentuate temporal ordering. In this paper, we present temporal summaries, an interactive visualization technique that highlights the prevalence of event occurrences. Temporal summaries dynamically aggregate events in multiple granularities (year, month, week, day, hour, etc.) for the purpose of spotting trends over time and comparing several groups of records. They provide affordances for analysts to perform temporal range filters. We demonstrate the applicability of this approach in two extensive case studies with analysts who applied temporal summaries to search, filter, and look for patterns in electronic health records and academic records.
Keywords: Aggregates; Collaborative work; Computational Biology; Computer Graphics; Data analysis; data visualisation; Data visualization; Databases, Factual; Displays; Event detection; Filters; Heparin; History; Human computer interaction; Human-computer interaction; HUMANS; Information Visualization; Interaction design; interactive visualization technique; Medical Records Systems, Computerized; Pattern Recognition, Automated; Performance analysis; Springs; temporal categorical data visualization; temporal categorical searching; temporal ordering; temporal summaries; Thrombocytopenia; Time factors

Three genomes from the phylum Acidobacteria provide insight into the lifestyles of these microorganisms in soils. - Ward, Naomi L; Challacombe, Jean F; Janssen, Peter H; Henrissat, Bernard; Coutinho, Pedro M; Wu, Martin; Xie, Gary; Haft, Daniel H; Sait, Michelle; Badger, Jonathan; Barabote, Ravi D; Bradley, Brent; et al. (Appl Environ Microbiol, 2009)
The complete genomes of three strains from the phylum Acidobacteria were compared. Phylogenetic analysis placed them as a unique phylum. They share genomic traits with members of the Proteobacteria, the Cyanobacteria, and the Fungi. The three strains appear to be versatile heterotrophs. Genomic and culture traits indicate the use of carbon sources that span simple sugars to more complex substrates such as hemicellulose, cellulose, and chitin. The genomes encode low-specificity major facilitator superfamily transporters and high-affinity ABC transporters for sugars, suggesting that they are best suited to low-nutrient conditions. They appear capable of nitrate and nitrite reduction but not N(2) fixation or denitrification. The genomes contained numerous genes that encode siderophore receptors, but no evidence of siderophore production was found, suggesting that they may obtain iron via interaction with other microorganisms. The presence of cellulose synthesis genes and a large class of novel high-molecular-weight excreted proteins suggests potential traits for desiccation resistance, biofilm formation, and/or contribution to soil structure. Polyketide synthase and macrolide glycosylation genes suggest the production of novel antimicrobial compounds. Genes that encode a variety of novel proteins were also identified. The abundance of acidobacteria in soils worldwide and the breadth of potential carbon use by the sequenced strains suggest significant and previously unrecognized contributions to the terrestrial carbon cycle. Combining our genomic evidence with available culture traits, we postulate that cells of these isolates are long-lived, divide slowly, exhibit slow metabolic rates under low-nutrient conditions, and are well equipped to tolerate fluctuations in soil hydration.
Keywords: Anti-Bacterial Agents; bacteria; Biological Transport; Carbohydrate Metabolism; Cyanobacteria; DNA, Bacterial; Fungi; Genome, Bacterial; Macrolides; Molecular Sequence Data; Nitrogen; Phylogeny; Proteobacteria; Sequence Analysis, DNA; sequence homology; Soil Microbiology

Toward reconstructing the evolution of advanced moths and butterflies (Lepidoptera: Ditrysia): an initial molecular study - Regier,J. C; Zwick,A.; Cummings, Michael P.; Kawahara,A. Y; Cho,S.; Weller,S.; Roe,A.; Baixeras,J.; Brown,J. W; Parr,C.; Davis,DR; Epstein,M; et al. (BMC Evol Biol, 2009)
BACKGROUND: In the mega-diverse insect order Lepidoptera (butterflies and moths; 165,000 described species), deeper relationships are little understood within the clade Ditrysia, to which 98% of the species belong. To begin addressing this problem, we tested the ability of five protein-coding nuclear genes (6.7 kb total), and character subsets therein, to resolve relationships among 123 species representing 27 (of 33) superfamilies and 55 (of 100) families of Ditrysia under maximum likelihood analysis. RESULTS: Our trees show broad concordance with previous morphological hypotheses of ditrysian phylogeny, although most relationships among superfamilies are weakly supported. There are also notable surprises, such as a consistently closer relationship of Pyraloidea than of butterflies to most Macrolepidoptera. Monophyly is significantly rejected by one or more character sets for the putative clades Macrolepidoptera as currently defined (P < 0.05) and Macrolepidoptera excluding Noctuoidea and Bombycoidea sensu lato (P < or = 0.005), and nearly so for the superfamily Drepanoidea as currently defined (P < 0.08). Superfamilies are typically recovered or nearly so, but usually without strong support. Relationships within superfamilies and families, however, are often robustly resolved. We provide some of the first strong molecular evidence on deeper splits within Pyraloidea, Tortricoidea, Geometroidea, Noctuoidea and others.Separate analyses of mostly synonymous versus non-synonymous character sets revealed notable differences (though not strong conflict), including a marked influence of compositional heterogeneity on apparent signal in the third codon position (nt3). As available model partitioning methods cannot correct for this variation, we assessed overall phylogeny resolution through separate examination of trees from each character set. Exploration of "tree space" with GARLI, using grid computing, showed that hundreds of searches are typically needed to find the best-feasible phylogeny estimate for these data. CONCLUSION: Our results (a) corroborate the broad outlines of the current working phylogenetic hypothesis for Ditrysia, (b) demonstrate that some prominent features of that hypothesis, including the position of the butterflies, need revision, and (c) resolve the majority of family and subfamily relationships within superfamilies as thus far sampled. Much further gene and taxon sampling will be needed, however, to strongly resolve individual deeper nodes.

Understanding IT Innovations Through Computational Analysis of Discourse - Tsui,Chia-jung; Wang,Ping; Fleischmann,Kenneth; Oard, Douglas; Sayeed,Asad (ICIS 2009 Proceedings, 2009)

Using formal specifications to support testing - Hierons,Robert M.; Krause,Paul; Lüttgen,Gerald; Simons,Anthony J. H.; Vilkomir,Sergiy; Woodward,Martin R.; Zedan,Hussein; Bogdanov,Kirill; Bowen,Jonathan P.; Cleaveland, Rance; Derrick,John; Dick,Jeremy; et al. (ACM Computing Surveys, 2009)

VAST 2009 challenge: An insider threat - Grinstein,G.; Scholtz,J.; Whiting,M.; Plaisant, Catherine (Visual Analytics Science and Technology, 2009. VAST 2009. IEEE Symposium on, 2009)
The 4th VAST Challenge centered on a cyber analytics scenario and offered three mini-challenges with datasets of badge and network traffic data, a social network including geospatial information, and security video. Teams could also enter the Grand challenge which combined all three datasets. In this paper, we summarize the dataset, the overall scenario and the questions asked in the challenges. We describe the judging process and new infrastructure developed to manage the submissions and compute accuracy measures in the social network mini challenge. We received 49 entries from 30 teams, and gave 23 different awards to a total of 16 teams.
Keywords: 2009; analytics; data; analytics; geospatial; challenge; cyber; data; security; information; information; human; interaction; network; interfaces; network; visual; traffic; user; VAST; video; social; visualisation; graphical

Advancing social science research by applying computational linguistics - Cheng,A.S.; Fleischmann,K.R.; Wang,P.; Oard, Douglas (Proceedings of the American Society for Information Science and Technology, 2008)

Aligning temporal data by sentinel events: discovering patterns in electronic health records - Wang,Taowei David; Plaisant, Catherine; Quinn,Alexander J.; Stanchak,Roman; Murphy,Shawn; Shneiderman, Ben (Proceedings of the twenty-sixth annual SIGCHI conference on Human factors in computing systems, 2008)
Electronic Health Records (EHRs) and other temporal databases contain hidden patterns that reveal important cause-and-effect phenomena. Finding these patterns is a challenge when using traditional query languages and tabular displays. We present an interactive visual tool that complements query formulation by providing operations to align, rank and filter the results, and to visualize estimates of the intervals of validity of the data. Display of patient histories aligned on sentinel events (such as a first heart attack) enables users to spot precursor, co-occurring, and aftereffect events. A controlled study demonstrates the benefits of providing alignment (with a 61% speed improvement for complex tasks). A qualitative study and interviews with medical professionals demonstrates that the interface can be learned quickly and seems to address their needs.
Keywords: electronic health record; Evaluation; Information Visualization; search; temporal data; Uncertainty

An assessment of systems and software engineering scholars and institutions (2001–2005) - Wong,W. Eric; Tse,T.H.; Glass,Robert L.; Basili, Victor R.; Chen,T.Y. (Journal of Systems and Software, 2008)
This paper presents the findings of a five-year study of the top scholars and institutions in the systems and software engineering field, as measured by the quantity of papers published in the journals of the field in 2001–2005. The top scholar is Magne Jørgensen of Simula Research Laboratory, Norway, and the top institution is Korea Advanced Institute of Science and Technology, Korea.This paper is part of an ongoing study, conducted annually, that identifies the top 15 scholars and institutions in the most recent five-year period.
Keywords: Research publications; Systems and software engineering; Top institutions; Top scholars

Biofilms in water, its role and impact in human disease transmission - Huq,Anwar; Whitehouse,Chris A.; Grim,Christopher J.; Alam,Munirul; Rita R Colwell (Current Opinion in Biotechnology, 2008)
Understanding the mechanism of biofilm formation is the first step in determining its function and, thereby, its impact and role in the environment. Extensive studies accomplished during the past few years have elucidated the genetics and biochemistry of biofilm formation. Cell-to-cell communication, that is, quorum sensing, is a key factor in the initiation of biofilm. Occurrence of viable but nonculturable bacteria, including Vibrio cholerae in biofilms has been reported and most likely such cells were overlooked previously because appropriate methods of detection were not employed. For this reason discovery and investigation of this important bacterial ecological niche in the environment were impeded.

Black-Box Construction of a Non-malleable Encryption Scheme from Any Semantically Secure One - Choi, Seung Geol; Dana Dachman-Soled; Malkin, Tal; Wee, Hoeteck (Theory of Cryptography, 2008)
We show how to transform any semantically secure encryption scheme into a non-malleable one, with a black-box construction that achieves a quasi-linear blow-up in the size of the ciphertext. This improves upon the previous non-black-box construction of Pass, Shelat and Vaikuntanathan (Crypto ’06). Our construction also extends readily to guarantee non-malleability under a bounded-CCA2 attack, thereby simultaneously improving on both results in the work of Cramer et al. (Asiacrypt ’07). Our construction departs from the oft-used paradigm of re-encrypting the same message with different keys and then proving consistency of encryptions; instead, we encrypt an encoding of the message with certain locally testable and self-correcting properties. We exploit the fact that low-degree polynomials are simultaneously good error-correcting codes and a secret-sharing scheme.
Keywords: Algorithm Analysis and Problem Complexity; black-box constructions; computers and society; Data Encryption; Discrete Mathematics in Computer Science; Management of Computing and Information Systems; non-malleability; public-key encryption; semantic security; Systems and Data Security

Combining Domain-Independent Planning and HTN Planning: The Duet Planner - Gerevini,Alfonso; Kuter,Ugur; Nau, Dana S.; Saetti,Alessandro; Waisbrot,Nathaniel (IOS Press, 2008)
Despite the recent advances in planning for classical domains, the question of how to use domain knowledge in planning is yet to be completely and clearly answered. Some of the existing planners use domain-independent search heuristics, and some others depend on intensively-engineered domain-specific knowledge to guide the planning process. In this paper, we describe an approach to combine ideas from both of the above schools of thought. We present Duet, our planning system that incorporates the ability of using hierarchical domain knowledge in the form of Hierarchical Task Networks (HTNs) as in SHOP2 [14] and using domain-independent local search techniques as in LPG [8]. In our experiments, Duet was able to solve much larger problems than LPG could solve, with only minimal domain knowledge encoded in HTNs (much less domain knowledge than SHOP2 needed to solve those problems by itself).

Community response grid (CRG) for a university campus: Design requirements and implications - Wu,P.F.; Qu,Y.; Preece,J.; Fleischmann,K.; Golbeck,J.; Jaeger,P.; Shneiderman, Ben (Proceedings of the 5th International ISCRAM Conference, 2008)
This paper describes the initial stages of the participatory design of a community-oriented emergency responsesystem for a university campus. After reviewing related work and the current University emergency response system, this paper describes our participatory design process, discusses initial findings from a design requirement survey and from our interactions with different stakeholders, and proposes a Web interface design for a community response grid system. The prototyping of the system demonstrates the possibility of fostering a social-network-based community participation in emergency response, and also identifies concerns raised by potential users and by the professional responder community.

Computational Cultural Dynamics - Nau, Dana S.; Wilkenfeld,J. (Intelligent Systems, IEEE, 2008)
Computational cultural dynamics blends the behavioral and social sciences - fields such as political science, psychology, journalism, anthropology, and sociology - with technological fields such as computer science, computational linguistics, game theory, statistical modeling, and operations research.
Keywords: anthropology; behavioral science; behavioural sciences computing; computational cultural dynamics; computational linguistics; Computer science; game theory; journalism; operations research; political science; Psychology; social sciences; social sciences computing; sociology; statistical modeling

Covariability of Vibrio Cholerae Microdiversity and Environmental Parameters - Zo,Young-Gun; Chokesajjawatee,Nipa; Arakawa,Eiji; Watanabe,Haruo; Huq,Anwar; Rita R Colwell (Applied and Environmental MicrobiologyAppl. Environ. Microbiol., 2008)
Fine-scale diversity of natural bacterial assemblages has been attributed to neutral radiation because correspondence between bacterial phylogenetic signals in the natural environment and environmental parameters had not been detected. Evidence that such correspondence occurs is provided for Vibrio cholerae, establishing a critical role for environmental parameters in bacterial diversity.

CrossNet: a framework for crossover with network-based chromosomal representations - Stonedahl,Forrest; Rand, William; Wilensky,Uri (Proceedings of the 10th annual conference on Genetic and evolutionary computation, 2008)
We propose a new class of crossover operators for genetic algorithms (CrossNet) which use a network-based (or graph-based) chromosomal representation. We designed CrossNet with the intent of providing a framework for creating crossover operators that take advantage of domain-specific knowledge for solving problems. Specifically, GA users supply a network which defines the epistatic relationships between genes in the genotype. CrossNet-based crossover uses this information with the goal of improving linkage. We performed two experiments that compared CrossNet-based crossover with one-point and uniform crossover. The first experiment involved the density classification problem for cellular automata (CA), and the second experiment involved fitting two randomly generated hyperplane-defined functions (hdf's). Both of these exploratory experiments support the hypothesis that CrossNet-based crossover can be useful, although performance improvements were modest. We discuss the results and remain hopeful about the successful application of CrossNet to other domains. We conjecture that future work with the CrossNet framework will provide a useful new perspective for investigating linkage and chromosomal representations.
Keywords: crossover; Genetic algorithms; graphs; linkage; NETWORKS; recombination

CrossTalk: The Journal of Defense Software Engineering. Volume 21, Number 10, October 2008 - Basili, Victor R.; Dangle,K.; Esker,L.; Marotta,F.; Rus,I.; Brosgol,B. M; Jamin,S.; Arthur,J. D; Ravichandar,R.; Wisnosky,D. E (DTIC Document, 2008)

A decision theoretic framework for analyzing binary hash-based content identification systems - Varna,Avinash L.; Swaminathan,Ashwin; M. Wu (Proceedings of the 8th ACM workshop on Digital rights management, 2008)
Content identification has many applications, ranging from preventing illegal sharing of copyrighted content on video sharing websites, to automatic identification and tagging of content. Several content identification techniques based on watermarking or robust hashes have been proposed in the literature, but they have mostly been evaluated through experiments. This paper analyzes binary hash-based content identification schemes under a decision theoretic framework and presents a lower bound on the length of the hash required to correctly identify multimedia content that may have undergone modifications. A practical scheme for content identification is evaluated under the proposed framework. The results obtained through experiments agree very well with the performance suggested by the theoretical analysis.
Keywords: content fingerprinting; content identification; decision theory

Delegating Capabilities in Predicate Encryption Systems - Elaine Shi; Waters,Brent (Automata, Languages and Programming, 2008)
In predicate encryption systems, given a capability, one can evaluate one or more predicates on the plaintext encrypted, while all other information about the plaintext remains hidden. We consider the role of delegation in such predicate encryption systems. Suppose Alice has a capability, and she wishes to delegate to Bob a more restrictive capability allowing the decryption of a subset of the information Alice can learn about the plaintext encrypted. We formally define delegation in predicate encryption systems, propose a new security definition for delegation, and give an efficient construction supporting conjunctive queries. The security of our construction can be reduced to the general 3-party Bilinear Diffie-Hellman assumption, and the Bilinear Decisional Diffie-Hellman assumption in composite order bilinear groups.
Keywords: Computer science

Digital image forensics via intrinsic fingerprints - Swaminathan,A.; M. Wu; Liu,K. J.R (Information Forensics and Security, IEEE Transactions on, 2008)
Digital imaging has experienced tremendous growth in recent decades, and digital camera images have been used in a growing number of applications. With such increasing popularity and the availability of low-cost image editing software, the integrity of digital image content can no longer be taken for granted. This paper introduces a new methodology for the forensic analysis of digital camera images. The proposed method is based on the observation that many processing operations, both inside and outside acquisition devices, leave distinct intrinsic traces on digital images, and these intrinsic fingerprints can be identified and employed to verify the integrity of digital data. The intrinsic fingerprints of the various in-camera processing operations can be estimated through a detailed imaging model and its component analysis. Further processing applied to the camera captured image is modelled as a manipulation filter, for which a blind deconvolution technique is applied to obtain a linear time-invariant approximation and to estimate the intrinsic fingerprints associated with these postcamera operations. The absence of camera-imposed fingerprints from a test image indicates that the test image is not a camera output and is possibly generated by other image production processes. Any change or inconsistencies among the estimated camera-imposed fingerprints, or the presence of new types of fingerprints suggest that the image has undergone some kind of processing after the initial capture, such as tampering or steganographic embedding. Through analysis and extensive experimental studies, this paper demonstrates the effectiveness of the proposed framework for nonintrusive digital image forensics.
Keywords: ACQUISITION; analysis; intrinsic; approximation; cameras; digital; camera; deconvolution; digital; devices; blind; fingerprints; time; forensics; forensic; identification; image; image; images; digital; invariant; photography; fingerprint; sensors

The draft genome of the transgenic tropical fruit tree papaya (Carica papaya Linnaeus) - Ming,R.; Hou,S.; Feng,Y.; Yu,Q.; Dionne-Laporte,A.; Saw,J.H.; Senin,P.; Wang,W.; Ly,B.V.; Lewis,K.L.T.; others (Nature, 2008)
Papaya, a fruit crop cultivated in tropical and subtropical regions, is known for its nutritional benefits and medicinal applications. Here we report a 3 draft genome sequence of 'SunUp' papaya, the first commercial virus-resistant transgenic fruit tree to be sequenced. The papaya genome is three times the size of the Arabidopsis genome, but contains fewer genes, including significantly fewer disease-resistance gene analogues. Comparison of the five sequenced genomes suggests a minimal angiosperm gene set of 13,311. A lack of recent genome duplication, atypical of other angiosperm genomes sequenced so far, may account for the smaller papaya gene number in most functional groups. Nonetheless, striking amplifications in gene number within particular functional groups suggest roles in the evolution of tree-like habit, deposition and remobilization of starch reserves, attraction of seed dispersal agents, and adaptation to tropical daylengths. Transgenesis at three locations is closely associated with chloroplast insertions into the nuclear genome, and with topoisomerase I recognition sites. Papaya offers numerous advantages as a system for fruit-tree functional genomics, and this draft genome sequence provides the foundation for revealing the basis of Carica's distinguishing morpho-physiological, medicinal and nutritional properties.

Dynamic Rebinding for Marshalling and Update, Via Redex-Time and Destruct-Time Reduction - Sewell,Peter; Stoyle,Gareth; Hicks, Michael W.; Bierman,Gavin; Wansbrough,Keith (Journal of Functional Programming, 2008)
Most programming languages adopt static binding, but for distributed programming an exclusive reliance on static binding is too restrictive: dynamic binding is required in various guises, for example, when a marshalled value is received from the network, containing identifiers that must be rebound to local resources. Typically, it is provided only by ad hoc mechanisms that lack clean semantics. In this paper, we adopt a foundational approach, developing core dynamic rebinding mechanisms as extensions to the simply typed call-by-value λ calculus. To do so, we must first explore refinements of the call-by-value reduction strategy that delay instantiation, to ensure computations make use of the most recent versions of rebound definitions. We introduce redex-time and destruct-time strategies. The latter forms the basis for a λmarsh calculus that supports dynamic rebinding of marshalled values, while remaining as far as possible statically typed. We sketch an extension of λmarsh with concurrency and communication, giving examples showing how wrappers for encapsulating untrusted code can be expressed. Finally, we show that a high-level semantics for dynamic updating can also be based on the destruct-time strategy, defining a λupdate calculus with simple primitives to provide type-safe updating of running code. We show how the ideas of this simple calculus extend to more real-world, module-level dynamic updating in the style of Erlang. We thereby establish primitives and a common semantic foundation for a variety of real-world dynamic rebinding requirements.

Dynamic Resource Allocation for Robust Distributed Multi-Point Video Conferencing - Chen,Meng; Su,Guan-Ming; M. Wu (Multimedia, IEEE Transactions on, 2008)
This paper proposes a distributed multi-point video conferencing system over packet erasure channels, where the aggregation of multiple video streams and resource allocation are performed in a distributed manner. Video stream combiners, which are located in different geographical areas and serve as portals for conferees, aggregate incoming streams supplied by local users with other streams aggregated from nearby video stream combiners. A packet-division multiple-access (PDMA)-based error protection scheme is proposed to be performed at each video stream combiner to minimize the maximal expected video distortion among aggregated streams. The proposed error protection scheme for multi-stream aggregation also supports user preference. In order to deliver video streams to end users with different preferred quality, a consensus algorithm is proposed to adaptively perform resource allocation based on user preference. Simulation results show that the proposed multi-stream aggregation and error protection scheme has significant gains over traditional multi-stream error protection schemes for a multi-point video conferencing system.
Keywords: allocation; error; channels; packet-division; communication; conferencing; conferencing; multi-access; distributed; dynamic; erasure; error; multiple-access-based; multipoint; Protection; resource; scheme; multi-point; scheme; robust; schemes; packet; streams; multistream; system; multiple; systems; teleconferencing; video; video

Estimating Tree-Structured Covariance Matrices via Mixed-Integer Programming with an Application to Phylogenetic Analysis of Gene Expression - Corrada Bravo, Hector; Eng,K. H; Keles,S.; Wahba,G.; Wright,S. (Department of Statistics, University of Wisconsin, 2008)
We present a novel method for estimating tree-structured covariance matrices directly fromobserved continuous data. A representation of these classes of matrices as linear combinations of rank-one matrices indicating object partitions is used to formulate estimation as instances of well-studied numerical optimization problems. In particular, we present estimation based on projection where the covariance estimate is the nearest tree-structured covariance matrix to an observed sample covariance matrix. The problem is posed as a linear or quadratic mixed-integer program (MIP) where a setting of the integer variables in the MIP specifies a set of tree topologies of the structured covariance matrix. We solve these problems to optimality using efficient and robust existing MIP solvers. We also show that the least squares distance method of Fitch and Margoliash (1967) can be formulated as a quadratic MIP and thus solved exactly using existing, robust branch-and-bound MIP solvers. Our motivation for this method is the discovery of phylogenetic structure directly from gene expression data. Recent studies have adapted traditional phylogenetic comparative anal- ysis methods to expression data. Typically, these methods first estimate a phylogenetic tree from genomic sequence data and subsequently analyze expression data. A covariance matrix constructed from the sequence-derived tree is used to correct for the lack of independence in phy- logenetically related taxa. However, recent results have shown that the hierarchical structure of sequence-derived tree estimates are highly sensitive to the genomic region chosen to build them. To circumvent this difficulty, we propose a stable method for deriving tree-structured covariance matrices directly from gene expression as an exploratory step that can guide investigators in their modelling choices for these types of comparative analysis. We present a case study in phylogenetic analysis of expression in yeast gene families. Our method is able to corroborate the presence of phylogenetic structure in the response of expression in a subset of the gene families under particular experimental conditions. Additionally, when used in conjunction with transcription factor occupancy data, our methods show that alternative modelling choices should be considered when creating sequence-derived trees for this comparative analysis.

Evaluating Visual Analytics at the 2007 VAST Symposium Contest - Plaisant, Catherine; Grinstein,G.; Scholtz,J.; Whiting,M.; O'Connell,T.; Laskowski,S.; Chien,L.; Tat,A.; Wright,W.; Gorg,C.; Zhicheng Liu; Parekh,N.; et al. (Computer Graphics and Applications, IEEE, 2008)
In this article, we report on the contest's data set and tasks, the judging criteria, the winning tools, and the overall lessons learned in the competition. We believe that by organizing these contests, we're creating useful resources for researchers and are beginning to understand how to better evaluate VA tools. Competitions encourage the community to work on difficult problems, improve their tools, and develop baselines for others to build or improve upon. We continue to evolve a collection of data sets, scenarios, and evaluation methodologies that reflect the richness of the many VA tasks and applications.
Keywords: 2007; analytics; analytics; data; and; Contest; Visual; Science; Symposium; Technology; data; VAST; visualisation; visualization; visual

Extended abstract: A hardware-assisted data hiding based approach in building high performance secure execution systems - Taylor,M.; Yin,Chi-En; M. Wu; Gang Qu (Hardware-Oriented Security and Trust, 2008. HOST 2008. IEEE International Workshop on, 2008)
Recently, a novel data hiding technique was proposed to embed information into compiled binary codes in order to enhance system performance. Using this technique as a vehicle, we propose a framework to build high-performance secure execution systems by embedding data for security and trust purposes. We illustrate this approach in a mobile computing environment by an instruction-block level data hiding technique, which can be used to defend against malicious attacks (such as Trojan injection). This improves the trustworthiness of mobile codes. It also protects the code providerpsilas intellectual property because the code can be executed only on the designated device. When combined with the existing approach in [4], the proposed data hiding framework can provide trust and high-performance simultaneously. Finally, we conduct a proof-of-the-concept FPGA prototyping to validate the data hiding technique and evaluate the hardware cost in terms of gate count, power consumption, and gate delay.
Keywords: arrays; invasive; attacks; mobile; codes; data; codes; mobile; computing; computing; power; consumption; proof-of-the-concept; count; gate; data; delay; hardware-assisted; embedding; gate; embedding; instruction-block; encapsulation; distributed; execution; FPGA; gate; hiding; information; injection; binary; level; malicious; programmable; programming; field; prototyping; secure; software; mobile; systems; binary; Trojan

Exurbia from the bottom-up: Confronting empirical challenges to characterizing a complex system - Brown,Daniel G.; Robinson,Derek T.; An,Li; Nassauer,Joan I.; Zellner,Moira; Rand, William; Riolo,Rick; Page,Scott E.; Low,Bobbi; Wang,Zhifang (Geoforum, 2008)
We describe empirical results from a multi-disciplinary project that support modeling complex processes of land-use and land-cover change in exurban parts of Southeastern Michigan. Based on two different conceptual models, one describing the evolution of urban form as a consequence of residential preferences and the other describing land-cover changes in an exurban township as a consequence of residential preferences, local policies, and a diversity of development types, we describe a variety of empirical data collected to support the mechanisms that we encoded in computational agent-based models. We used multiple methods, including social surveys, remote sensing, and statistical analysis of spatial data, to collect data that could be used to validate the structure of our models, calibrate their specific parameters, and evaluate their output. The data were used to investigate this system in the context of several themes from complexity science, including have (a) macro-level patterns; (b) autonomous decision making entities (i.e., agents); (c) heterogeneity among those entities; (d) social and spatial interactions that operate across multiple scales and (e) nonlinear feedback mechanisms. The results point to the importance of collecting data on agents and their interactions when producing agent-based models, the general validity of our conceptual models, and some changes that we needed to make to these models following data analysis. The calibrated models have been and are being used to evaluate landscape dynamics and the effects of various policy interventions on urban land-cover patterns.
Keywords: Ecological effects; Land-cover change; Land-use change; spatial modeling; Urban sprawl

A Feature Generation Algorithm with Applications to Biological Sequence Classification - Dogan,R. I; Getoor, Lise; Wilbur,W. J (Computational Methods, 2008)

Figaro: A Novel Statistical Method for Vector Sequence Removal - White,James Robert; Roberts,Michael; Yorke,James A.; Pop, Mihai (Bioinformatics, 2008)
Motivation: Sequences produced by automated Sanger sequencing machines frequently contain fragments of the cloning vector on their ends. Software tools currently available for identifying and removing the vector sequence require knowledge of the vector sequence, specific splice sites and any adapter sequences used in the experiment—information often omitted from public databases. Furthermore, the clipping coordinates themselves are missing or incorrectly reported. As an example, within the ∼1.24 billion shotgun sequences deposited in the NCBI Trace Archive, as many as ∼735 million (∼60%) lack vector clipping information. Correct clipping information is essential to scientists attempting to validate, improve and even finish the increasingly large number of genomes released at a ‘draft’ quality level.Results: We present here Figaro, a novel software tool for identifying and removing the vector from raw sequence data without prior knowledge of the vector sequence. The vector sequence is automatically inferred by analyzing the frequency of occurrence of short oligo-nucleotides using Poisson statistics. We show that Figaro achieves 99.98% sensitivity when tested on ∼1.5 million shotgun reads from Drosophila pseudoobscura. We further explore the impact of accurate vector trimming on the quality of whole-genome assemblies by re-assembling two bacterial genomes from shotgun sequences deposited in the Trace Archive. Designed as a module in large computational pipelines, Figaro is fast, lightweight and flexible. Availability: Figaro is released under an open-source license through the AMOS package (http://amos.sourceforge.net/Figaro). Contact: mpop@umiacs.umd.edu

Fpga-based prototype of a pram-on-chip processor - Wen,Xingzhi; Vishkin, Uzi (Proceedings of the 5th conference on Computing frontiers, 2008)
PRAM (Parallel Random Access Model) has been widely regarded a desirable parallel machine model for many years, but it is also believed to be "impossible in reality." As the new billion-transistor processor era begins, the eXplicit Multi-Threading (XMT) PRAM-On-Chip project is attempting to design an on-chip parallel processor that efficiently supports PRAM algorithms. This paper presents the first prototype of the XMT architecture that incorporates 64 simple in-order processors operating at 75MHz. The microarchitecture of the prototype is described and the performance is studied with respect to some micro-benchmarks. Using cycle accurate emulation, the projected performance of an 800MHz XMT ASIC processor is compared with AMD Opteron 2.6GHz, which uses similar area as would a 64-processor ASIC version of the XMT prototype. The results suggest that an only 800MHz XMT ASIC system outperforms AMD Opteron 2.6GHz, with speedups ranging between 1.57 and 8.56.
Keywords: ease-of-programming; explicit multi-threading; on-chip parallel processor; Parallel algorithms; PRAM; XMT

GoGoBot: group collaboration, multi-agent modeling, and robots - Rand, William; Blikstein,Paulo; Wilensky,Uri (Proceedings of the 7th international joint conference on Autonomous agents and multiagent systems: demo papers, 2008)
Multi-agent simulation is a powerful technique used to encode real-world simple rules in virtual agents and then simulate their interactions [1]. Participatory simulations are similar to multi-agent simulation except individuals play the role of virtual agents, sometimes in combination with these virtual agents [2]. Finally, the bifocal modeling framework has enabled the examination of agents embodied in physical entities using sensors and actuators [3]. All three of these technologies are concerned with the creation, manipulation, and development of agents in one form or another. Thus combining these three disparate systems in to one unified platform would be useful. Multi-agent simulation platforms, participatory simulations, and bifocal modeling have all been demonstrated separately in the past. However many extant systems are difficult if not impossible to integrate.
Keywords: multi-agent simulation; participatory simulation; ROBOTICS

Image acquisition forensics: Forensic analysis to identify imaging source - McKay,C.; Swaminathan,A.; Gou,Hongmei; M. Wu (Acoustics, Speech and Signal Processing, 2008. ICASSP 2008. IEEE International Conference on, 2008)
With widespread availability of digital images and easy-to-use image editing softwares, the origin and integrity of digital images has become a serious concern. This paper introduces the problem of image acquisition forensics and proposes a fusion of a set of signal processing features to identify the source of digital images. Our results show that the devices' color interpolation coefficients and noise statistics can jointly serve as good forensic features to help accurately trace the origin of the input image to its production process and to differentiate between images produced by cameras, cell phone cameras, scanners, and computer graphics. Further, the proposed features can also be extended to determining the brand and model of the device. Thus, the techniques introduced in this work provide a unified framework for image acquisition forensics.
Keywords: ACQUISITION; acquisition; image; analysis; analysis; image; analysis; interpolation; statistical; cameras; color; cell; coefficients; computer; colour; editing; forensics; image; graphics; digital; identification; noise; images; forensic; Interpolation; phone; processing; data; softwares; imaging; source; statistics; scanners; signal

Interactive High-Resolution Isosurface Ray Casting on Multicore Processors - Wang,Qin; JaJa, Joseph F. (Visualization and Computer Graphics, IEEE Transactions on, 2008)
We present a new method for the interactive rendering of isosurfaces using ray casting on multicore processors. This method consists of a combination of an object-order traversal that coarsely identifies possible candidate three-dimensional (3D) data blocks for each small set of contiguous pixels and an isosurface ray casting strategy tailored for the resulting limited-size lists of candidate 3D data blocks. Our implementation scheme results in a compact indexing structure and makes careful use of multithreading and memory management environments commonly present in multicore processors. Although static screen partitioning is widely used in the literature, our scheme starts with an image partitioning for the initial stage and then performs dynamic allocation of groups of ray casting tasks among the different threads to ensure almost equal loads among the different cores while maintaining spatial locality. We also pay a particular attention to the overhead incurred by moving the data across the different levels of the memory hierarchy. We test our system on a two-processor Clovertown platform, each consisting of a Quad-Core 1.86-GHz Intel Xeon Processor and present detailed experimental results for a number of widely different benchmarks. We show that our system is efficient and scalable and achieves high cache performance and excellent load balancing, resulting in an overall performance that is superior to any of the previous algorithms. In fact, we achieve interactive isosurface rendering on a screen with 1.0242 resolution for all the data sets tested up to the maximum size that can fit in the main memory of our platform.
Keywords: compact indexing structure; interactive high-resolution isosurface ray casting; interactive isosurface rendering; memory management; multicore processor; multithreading; object-order traversal; static screen partitioning; multi-threading; multiprocessing systems; r; Computer-Assisted; Imaging; Computer-Assisted; User-Computer Interface; Three-Dimensional; Information Storage and Retrieval; Reproducibility of Results; Sensitivity and Specificity; Signal Processing

The Lattice Project: a Grid research and production environment combining multiple Grid computing models - Bazinet,A. L; Cummings, Michael P. (Distributed & Grid Computing — Science Made Transparent for Everyone. Principles, Applications and Supporting CommunitiesDistributed & Grid Computing — Science Made Transparent for Everyone. Principles, Applications and Supporting Communities, 2008)

The Maryland Large-Scale Integrated Neurocognitive Architecture - Reggia, James A.; Tagamets,M.; Contreras-Vidal,J.; Jacobs, David W.; Weems,S.; Naqvi,W.; Yang,C. (University of Maryland College Park, 2008)
Recent progress in neural computation, high performance computing, neuroscience and cognitive science suggests that an effort to produce a general-purpose, adaptive machine intelligence is likely to yield a qualitatively more powerful system than those currently existing. Here we outline our progress in developing a framework for creating such a large-scale machine intelligence, or neurocognitive architecture that is based on the modularity, dynamics and plasticity of the human brain. We successfully implemented three intermediate-scale parts of such a system, and these are described. Based on this experience, we concluded that for the short term, optimal results would be obtained by using a hybrid design including neural, symbolic AI, and artificial life methods. We propose a three-tiered architecture that integrates these different methods, and describe a prototype mini-Roboscout that we implemented and evaluated based on this architecture. We also examined, via computational experiments, the effectiveness of genetic programming as a design tool for recurrent neural networks, and the speed-up obtained for adaptive neural networks when they are executed on a graphical processing unit. We conclude that the implementation of a large-scale neurocognitive architecture is feasible, and outline a roadmap for proceeding.
Keywords: *COMPUTATIONS; *HYBRID SYSTEMS; *NEURAL NETS; *NEUROCOGNITIVE ARCHITECTURE; ADAPTIVE SYSTEMS; Artificial intelligence; BRAIN; Cognition; COMPUTER PROGRAMMING; COMPUTER PROGRAMMING AND SOFTWARE; HYBRID AI; Machine intelligence; MECHANICAL ORGANS; MODULAR CONSTRUCTION; NERVOUS SYSTEM; PE61101E; PLASTIC PROPERTIES; PROCESSING EQUIPMENT; RECURRENT NEURAL NETWORK

Matchmaking and implementation issues for a P2P desktop grid - Marsh,M.; Kim,Jik-Soo; Nam,Beomseok; Jaehwan Lee; Ratanasanya,S.; Bhattacharjee, Bobby; Keleher,P.; Richardson,D.; Wellnitz,D. (Parallel and Distributed Processing, 2008. IPDPS 2008. IEEE International Symposium on, 2008)
We present some recent and ongoing work in our decentralized desktop computing grid project. Specifically, we discuss matching jobs with compute nodes in a peer-to-peer grid of heterogeneous platforms, and the implementation of our algorithms in a concrete system.
Keywords: computing; computing; computing; peer-to-peer; desktop; grid; decentralized; grid; grid; grid; peer-to-peer; P2P

Maternal depletion of CTCF reveals multiple functions during oocyte and preimplantation embryo development - Wan,Le-Ben; Pan,Hua; Hannenhalli, Sridhar; Cheng,Yong; Ma,Jun; Fedoriw,Andrew; Lobanenkov,Victor; Latham,Keith E.; Schultz,Richard M.; Bartolomei,Marisa S. (Development, 2008)
CTCF is a multifunctional nuclear factor involved in epigenetic regulation. Despite recent advances that include the systematic discovery of CTCF-binding sites throughout the mammalian genome, the in vivo roles of CTCF in adult tissues and during embryonic development are largely unknown. Using transgenic RNAi, we depleted maternal stores of CTCF from growing mouse oocytes, and identified hundreds of misregulated genes. Moreover, our analysis suggests that CTCF predominantly activates or derepresses transcription in oocytes. CTCF depletion causes meiotic defects in the egg, and mitotic defects in the embryo that are accompanied by defects in zygotic gene expression, and culminate in apoptosis. Maternal pronuclear transfer and CTCF mRNA microinjection experiments indicate that CTCF is a mammalian maternal effect gene, and that persistent transcriptional defects rather than persistent chromosomal defects perturb early embryonic development. This is the first study detailing a global and essential role for CTCF in mouse oocytes and preimplantation embryos.

Modeling and visualization approaches for time-varying volumetric data - Weiss,K.; De Floriani, Leila (Advances in Visual Computing, 2008)
Time-varying volumetric data arise in a variety of application domains, and thus several techniques for dealing with such data have been proposed in the literature. A time-varying dataset is typically modeled either as a collection of discrete snapshots of volumetric data, or as a four-dimensional dataset. This choice influences the operations that can be efficiently performed on such data. Here, we classify the various approaches to modeling time-varying scalar fields, and briefly describe them. Since most models of time-varying data have been abstracted from well-known approaches to volumetric data, we review models of volumetric data as well as schemes to accelerate isosurface extraction and discuss how these approaches have been applied to time-varying datasets. Finally, we discuss multi-resolution approaches which allow interactive processing and visualization of large time varying datasets.

A molecular footprint of limb loss: sequence variation of the autopodial identity gene Hoxa-13 - Kohlsdorf,T; Cummings, Michael P.; Lynch,VJ; Stopper,GF; Takahashi,K; Wagner,GP (J Mol Evol, 2008)
The homeobox gene Hoxa-13 codes for a transcription factor involved in multiple functions, including body axis and hand/foot development in tetrapods. In this study we investigate whether the loss of one function (e.g., limb loss in snakes) left a molecular footprint in exon 1 of Hoxa-13 that could be associated with the release of functional constraints caused by limb loss. Fragments of the Hoxa-13 exon 1 were sequenced from 13 species and analyzed, with additional published sequences of the same region, using relative rates and likelihood-ratio tests. Five amino acid sites in exon 1 of Hoxa-13 were detected as evolving under positive selection in the stem lineage of snakes. To further investigate whether there is an association between limb loss and sequence variation in Hoxa-13, we used the random forest method on an alignment that included shark, basal fish lineages, and "eu-tetrapods" such as mammals, turtle, alligator, and birds. The random forest method approaches the problem as one of classification, where we seek to predict the presence or absence of autopodium based on amino acid variation in Hoxa-13 sequences. Different alignments tested were associated with similar error rates (18.42%). The random forest method suggested that phenotypic states (autopodium present and absent) can often be correctly predicted based on Hoxa-13 sequences. Basal, nontetrapod gnat-hostomes that never had an autopodium were consistently classified as limbless together with the snakes, while eu-tetrapods without any history of limb loss in their phylogeny were also consistently classified as having a limb. Misclassifications affected mostly lizards, which, as a group, have a history of limb loss and limb re-evolution, and the urodele and caecilian in our sample. We conclude that a molecular footprint can be detected in Hoxa-13 that is associated with the lack of an autopodium; groups with classification ambiguity (lizards) are characterized by a history of repeated limb loss and possible limb re-evolution.

Mpeg recompression detection based on block artifacts - Luo,W.; Wu,M.; Huang,J. (Proc. of SPIE Electronic Imaging, Security, Steganography, and Watermarking of Multimedia Contents, 2008)
With sophisticated video editing technologies, it is becoming increasingly easy to tamper digital video withoutleaving visual clues. One of the common tampering operations on video is to remove some frames and then re-encode the resulting video. In this paper, we propose a new method for detecting this type of tampering by exploring the temporal patterns of the block artifacts in video sequences. We show that MPEG compression introduces different block artifacts into various types of frames and that the strength of the block artifacts as a function over time has a regular pattern for a given group of pictures (GOP) structure. When some frames are removed from an MPEG video file and the file is then recompressed, the block artifacts introduced by the previous compression would remain and affect the average of block artifact strength of the recompressed one in such a way that depends on the number of deleted frames and the type of GOP used previously. We propose a feature curve to reveal the compression history of an MPEG video file with a given GOP structure, and use it as evidence to detect tampering. Experimental results evaluated on common video benchmark clips demonstrate the effectiveness of the proposed method.

Multi-agent learning with a distributed genetic algorithm - Stonedahl,F.; Rand, William; Wilensky,U. (AAMAS 2008: ALAMAS + ALAg Workshop, 2008)
Lightweight agents distributed in space have the potential to solve many complex problems. In this paper, we examine a model where agents represent individuals in a genetic algorithm (GA) solving a shared problem. We examine two questions: (1) How does the network density of connections between agents affect the performance of the systems? (2) How does the interaction topology aaffect the performance of the system? In our model, agents exist in either a random network topology with long-distance communication, or a location-based topology, where agents only communicate with near neighbors. We examine both fixed and dynamic networks. Within the context of our investigation, our initial results indicate that relatively low network density achievesthe same results as a panmictic, or fully connected, population. Additionally, we find that dynamic networks outperform fixed networks, and that random network topologies outperform proximity-based network topologies. We conclude by showing how this model can be useful not only for multi-agent learning, but also for genetic algorithms, agent-based simulation and models of diffusion of innovation.

Navigating information spaces: A case study of related article search in PubMed - Jimmy Lin; DiCuccio,Michael; Grigoryan,Vahan; Wilbur,W. John (Information Processing & Management, 2008)
The concept of an â€œinformation spaceâ€ provides a powerful metaphor for guiding the design of interactive retrieval systems. We present a case study of related article search, a browsing tool designed to help users navigate the information space defined by results of the PubMedÂ® search engine. This feature leverages content-similarity links that tie MEDLINEÂ® citations together in a vast document network. We examine the effectiveness of related article search from two perspectives: a topological analysis of networks generated from information needs represented in the TREC 2005 genomics track and a query log analysis of real PubMed users. Together, data suggest that related article search is a useful feature and that browsing related articles has become an integral part of how users interact with PubMed.
Keywords: Browsing; Interactive IR; MEDLINE; TREC genomics

Network-Aware Join Processing in Global-Scale Database Federations - Xiaodan Wang; Burns,R.; Terzis,A.; Deshpande, Amol (IEEE 24th International Conference on Data Engineering, 2008. ICDE 2008, 2008)
We introduce join scheduling algorithms that employ a balanced network utilization metric to optimize the use of all network paths in a global-scale database federation. This metric allows algorithms to exploit excess capacity in the network, while avoiding narrow, long-haul paths. We give a two- approximate, polynomial-time algorithm for serial (left-deep) join schedules. We also present extensions to this algorithm that explore parallel schedules, reduce resource usage, and define tradeoffs between computation and network utilization. We evaluate these techniques within the SkyQuery federation of Astronomy databases using spatial-join queries submitted by SkyQuery's users. Experiments show that our algorithms realize near-optimal network utilization with minor computational overhead.
Keywords: Astronomy; Computer networks; Concurrent computing; global-scale database federations; join scheduling algorithms; network utilization; network-aware join processing; parallel schedules; polynomial-time algorithm; Polynomials; Processor scheduling; Query processing; reduce resource usage; Scheduling algorithm; Spatial databases; spatial-join queries; Telecommunication traffic; Throughput

Optimal Cryptographic Hardness of Learning Monotone Functions - Dana Dachman-Soled; Lee, Homin K.; Malkin, Tal; Servedio, Rocco A.; Wan, Andrew; Wee, Hoeteck (Automata, Languages and Programming, 2008)
A wide range of positive and negative results have been established for learning different classes of Boolean functions from uniformly distributed random examples. However, polynomial-time algorithms have thus far been obtained almost exclusively for various classes of monotone functions, while the computational hardness results obtained to date have all been for various classes of general (nonmonotone) functions. Motivated by this disparity between known positive results (for monotone functions) and negative results (for nonmonotone functions), we establish strong computational limitations on the efficient learnability of various classes of monotone functions. We give several such hardness results which are provably almost optimal since they nearly match known positive results. Some of our results show cryptographic hardness of learning polynomial-size monotone circuits to accuracy only slightly greater than 1/2+1/n‾‾√1/2 + 1/\sqrt{n} ; this accuracy bound is close to optimal by known positive results (Blum et al., FOCS ’98). Other results show that under a plausible cryptographic hardness assumption, a class of constant-depth, sub-polynomial-size circuits computing monotone functions is hard to learn; this result is close to optimal in terms of the circuit size parameter by known positive results as well (Servedio, Information and Computation ’04). Our main tool is a complexity-theoretic approach to hardness amplification via noise sensitivity of monotone functions that was pioneered by O’Donnell (JCSS ’04).
Keywords: Data structures; Data Structures, Cryptology and Information Theory; Discrete Mathematics in Computer Science; Numeric Computing; Software Engineering/Programming and Operating Systems; Theory of computation

A pattern classification framework for theoretical analysis of component forensics - Swaminathan,A.; M. Wu; Liu,K. J.R (Acoustics, Speech and Signal Processing, 2008. ICASSP 2008. IEEE International Conference on, 2008)
Component forensics is an emerging methodology for forensic analysis that aims at estimating the algorithms and parameters in each component of a digital device. This paper proposes a theoretical foundation to examine the performance limits of component forensics. Using ideas from pattern classification theory, we define formal notions of identifiability of components in the information processing chain. We show that the parameters of certain device components can be accurately identified only in controlled settings through semi non-intrusive forensics, while the parameters of some others can be computed directly from the available sample data via complete non-intrusive analysis. We then extend the proposed theoretical framework to quantify and improve the accuracies and confidence in component parameter identification for several forensic applications.
Keywords: analysis; information; classification; classification; parameter; component; estimation; pattern; forensics; component; forensics; pattern; identification; forensic; parameter; processing; nonintrusive

Predicate encryption supporting disjunctions, polynomial equations, and inner products - Katz, Jonathan; Sahai,Amit; Waters,Brent (Proceedings of the theory and applications of cryptographic techniques 27th annual international conference on Advances in cryptology, 2008)
Predicate encryption is a new paradigm generalizing, among other things, identity-based encryption. In a predicate encryption scheme, secret keys correspond to predicates and ciphertexts are associated with attributes; the secret key SKf corresponding to a predicate f can be used to decrypt a ciphertext associated with attribute I if and only if f(I) = 1. Constructions of such schemes are currently known for relatively few classes of predicates. We construct such a scheme for predicates corresponding to the evaluation of inner products over ZN (for some large integer N). This, in turn, enables constructions in which predicates correspond to the evaluation of disjunctions, polynomials, CNF/DNF formulae, or threshold predicates (among others). Besides serving as a significant step forward in the theory of predicate encryption, our results lead to a number of applications that are interesting in their own right.

Predictive Modeling-Based Data Collection in Wireless Sensor Networks - Wang,Lidan; Deshpande, Amol (Wireless Sensor NetworksWireless Sensor Networks, 2008)
We address the problem of designing practical, energy-efficient protocols for data collection in wireless sensor networks using predictive modeling. Prior work has suggested several approaches to capture and exploit the rich spatio-temporal correlations prevalent in WSNs during data collection. Although shown to be effective in reducing the data collection cost, those approaches use simplistic corelation models and further, ignore many idiosyncrasies of WSNs, in particular the broadcast nature of communication. Our proposed approach is based on approximating the joint probability distribution over the sensors using undirected graphical models , ideally suited to exploit both the spatial correlations and the broadcast nature of communication. We present algorithms for optimally using such a model for data collection under different communication models, and for identifying an appropriate model to use for a given sensor network. Experiments over synthetic and real-world datasets show that our approach significantly reduces the data collection cost.

The Randomized Coloring Procedure with Symmetry-Breaking - Pemmaraju,Sriram; Srinivasan, Aravind (Automata, Languages and ProgrammingAutomata, Languages and Programming, 2008)
A basic randomized coloring procedure has been used in probabilistic proofs to obtain remarkably strong results on graph coloring. These results include the asymptotic version of the List Coloring Conjecture due to Kahn, the extensions of Brooks’ Theorem to sparse graphs due to Kim and Johansson, and Luby’s fast parallel and distributed algorithms for graph coloring. The most challenging aspect of a typical probabilistic proof is showing adequate concentration bounds for key random variables. In this paper, we present a simple symmetry-breaking augmentation to the randomized coloring procedure that works well in conjunction with Azuma’s Martingale Inequality to easily yield the requisite concentration bounds. We use this approach to obtain a number of results in two areas: frugal coloring and weighted equitable coloring . A β-frugal coloring of a graph G is a proper vertex-coloring of G in which no color appears more than β times in any neighborhood. Let G = ( V , E ) be a vertex-weighted graph with weight function w : V →[0, 1] and let W = ∑ v ∈ V w ( v ). A weighted equitable coloring of G is a proper k -coloring such that the total weight of every color class is “large”, i.e., “not much smaller” than W / k ; this notion is useful in obtaining tail bounds for sums of dependent random variables.

Reciprocity between the cerebellum and the cerebral cortex: Nonlinear dynamics in microscopic modules for generating voluntary motor commands - Wang,Jun; Dam,Gregory; Yildirim,Sule; Rand, William; Wilensky,Uri; Houk,James C. (Complexity, 2008)
The cerebellum and basal ganglia are reciprocally connected with the cerebral cortex, forming many loops that function as distributed processing modules. Here we present a detailed model of one microscopic loop between the motor cortex and the cerebellum, and we show how small arrays of these microscopic loops (CB modules) can be used to generate biologically plausible motor commands for controlling movement. A fundamental feature of CB modules is the presence of positive feedback loops between the cerebellar nucleus and the motor cortex. We use nonlinear dynamics to model one microscopic loop and to investigate its bistable properties. Simulations demonstrate an ability to program a motor command well in advance of command generation and an ability to vary command duration. However, control of command intensity is minimal, which could interfere with the control of movement velocity. To assess these hypotheses, we use a minimal nonlinear model of the neuromuscular (NM) system that translates motor commands into actual movements. Simulations of the combined CB-NM modular model indicate that movement duration is readily controlled, whereas velocity is poorly controlled. We then explore how an array of eight CB-NM modules can be used to control the direction and endpoint of a planar movement. In actuality, thousands of such microscopic loops function together as an array of adjustable pattern generators for programming and regulating the composite motor commands that control limb movements. We discuss the biological plausibility and limitations of the model. We also discuss ways in which an agent-based representation can take advantage of the modularity in order to model this complex system. © 2008 Wiley Periodicals, Inc. Complexity, 2008
Keywords: agent‐based modeling; cerebellum; equilibrium point control; motor command; motor cortex; Movement; neural network; nonlinear dynamics

The role of metacognition in robust AI systems - Schmill,M. D; Oates,T.; Anderson,M.; Fults,S.; Josyula,D.; Perlis, Don; Wilson,S. (AAAI-08 Workshop on Metareasoning,(Chicago, IL), 2008)

Searching the world’s herbaria: A system for visual identification of plant species - Belhumeur,P.; Chen,D.; Feiner,S.; Jacobs, David W.; Kress,W.; Ling,H.; Lopez,I.; Ramamoorthi,R.; Sheorey,S.; White,S. (Computer Vision–ECCV 2008, 2008)
We describe a working computer vision system that aids in the identification of plant species. A user photographs an isolated leaf on a blank background, and the system extracts the leaf shape and matches it to the shape of leaves of known species. In a few seconds, the system displays the top matching species, along with textual descriptions and additional images. This system is currently in use by botanists at the Smithsonian Institution National Museum of Natural History. The primary contributions of this paper are: a description of a working computer vision system and its user interface for an important new application area; the introduction of three new datasets containing thousands of single leaf images, each labeled by species and verified by botanists at the US National Herbarium; recognition results for two of the three leaf datasets; and descriptions throughout of practical lessons learned in constructing this system.

A self-help guide for autonomous systems - Anderson,M. L; Fults,S.; Josyula,D. P; Oates,T.; Perlis, Don; Wilson,S.; Wright,D. (AI Magazine, 2008)

Sparse terrain pyramids - Weiss,Kenneth; De Floriani, Leila (Proceedings of the 16th ACM SIGSPATIAL international conference on Advances in geographic information systems, 2008)
Bintrees based on longest edge bisection and hierarchies of diamonds are popular multiresolution techniques on regularly sampled terrain datasets. In this work, we consider Sparse Terrain Pyramids as a compact multiresolution representation for terrain datasets whose samples are a subset of those lying on a regular grid. While previous diamond-based approaches can efficiently represent meshes built on a complete grid of resolution (2k +1)2, this is not suitable when the field values are uniform in large areas or simply non-existent. We explore properties of diamonds to simplify an encoding of the implicit dependency relationship between diamonds. Additionally, we introduce a diamond clustering technique to further reduce the geometric and topological overhead of such representations. We demonstrate the coherence of our clustering technique as well as the compactness of our representation.
Keywords: diamond hierarchies; longest edge bisection; multiresolution terrain models; nested triangle meshes

Stochastic opponent modeling agents: A case study with Hamas - Mannes,A.; Sliva,A.; V.S. Subrahmanian; Wilkenfeld,J. (Proceedings of ICCCD, 2008)
Stochastic Opponent Modeling Agents (SOMA) have beenproposed as a paradigm for reasoning about cultural groups, terror groups, and other socio-economic-political-military organizations worldwide. In this paper, we describe a case study that shows how SOMA was used to model the behavior of the terrorist organization, Hamas. Our team, consisting of a mix of computer scientists, policy experts, and political scientists, were able to understand new facts about Hamas of which even seasoned Hamas experts may not have been aware. This paper briefly overviews SOMA rules, explains how several thousand SOMA rules for Hamas were automatically derived, and then describes a few key findings about Hamas, enabled by this framework.

Toward automatic facet analysis and need negotiation: Lessons from mediated search - Jimmy Lin; Wu,Philip; Abels,Eileen (ACM Transactions on Information Systems (TOIS), 2008)
This work explores the hypothesis that interactions between a trained human search intermediary and an information seeker can inform the design of interactive IR systems. We discuss results from a controlled Wizard-of-Oz case study, set in the context of the TREC 2005 HARD track evaluation, in which a trained intermediary executed an integrated search and interaction strategy based on conceptual facet analysis and informed by need negotiation techniques common in reference interviews. Having a human “in the loop” yielded large improvements over fully automated systems as measured by standard ranked-retrieval metrics, demonstrating the value of mediated search. We present a detailed analysis of the intermediary's actions to gain a deeper understanding of what worked and why. One contribution is a taxonomy of clarification types informed both by empirical results and existing theories in library and information science. We discuss how these findings can guide the development of future systems. Overall, this work illustrates how studying human information-seeking processes can lead to better information retrieval applications.
Keywords: interactive information retrieval; Reference interview

Upstream and downstream in unsteadiness of STBLI using DNS data in two con gurations - Martin, M.P; Priebe,S.; Wu,M. (46th AIAA Aerospace Sciences Meeting, 2008)
Statistical analysis of the upstream and downstream flow influence on shock unsteadiness in shock and turbulent boundary layer interactions are performed using DNS data of a compression corner Wu & Martin1 and a reflected shock case interaction. For both cases, the scaling proposed by Dussauge et al.2 for the characteristic low frequency applies. The statistical analysis for the compression corner shows that the unsteadiness of the shock is dominated by the downstream flow. The same analysis applied to the reflected shock case also indicates downstream influence. Additional studies are required to fully characterize the reflected shock case DNS data.

Upstream and downstream influence on the unsteadiness of STBLI using DNS data in two configurations - Martin, M.P; Priebe,S.; Wu,M. (AIAA Paper 2008-0719, 46, h, 2008)

User-assisted query translation for interactive cross-language information retrieval - Oard, Douglas; He,Daqing; Wang,Jianqiang (Information Processing & Management, 2008)
Interactive Cross-Language Information Retrieval (CLIR), a process in which searcher and system collaborate to find documents that satisfy an information need regardless of the language in which those documents are written, calls for designs in which synergies between searcher and system can be leveraged so that the strengths of one can cover weaknesses of the other. This paper describes an approach that employs user-assisted query translation to help searchers better understand the system’s operation. Supporting interaction and interface designs are introduced, and results from three user studies are presented. The results indicate that experienced searchers presented with this new system evolve new search strategies that make effective use of the new capabilities, that they achieve retrieval effectiveness comparable to results obtained using fully automatic techniques, and that reported satisfaction with support for cross-language searching increased. The paper concludes with a description of a freely available interactive CLIR system that incorporates lessons learned from this research.
Keywords: Cross-language information retrieval; Machine translation; User studies

VAST 2008 Challenge: Introducing mini-challenges - Grinstein,G.; Plaisant, Catherine; Laskowski,S.; O'Connell,T.; Scholtz,J.; Whiting,M. (Visual Analytics Science and Technology, 2008. VAST '08. IEEE Symposium on, 2008)
Visual analytics experts realize that one effective way to push the field forward and to develop metrics for measuring the performance of various visual analytics components is to hold an annual competition. The VAST 2008 Challenge is the third year that such a competition was held in conjunction with the IEEE Visual Analytics Science and Technology (VAST) symposium. The authors restructured the contest format used in 2006 and 2007 to reduce the barriers to participation and offered four mini-challenges and a Grand Challenge. Mini Challenge participants were to use visual analytic tools to explore one of four heterogeneous data collections to analyze specific activities of a fictitious, controversial movement. Questions asked in the Grand Challenge required the participants to synthesize data from all four data sets. In this paper we give a brief overview of the data sets, the tasks, the participation, the judging, and the results.
Keywords: 2008; analytics; data; Challenge; heterogeneous; collections; visual; data; VAST; visualisation

Adaptive Detection for Group-Based Multimedia Fingerprinting - He,Shan; M. Wu (Signal Processing Letters, IEEE, 2007)
Grouping strategy has been proposed recently to leverage the prior knowledge on collusion pattern to improve collusion resistance in multimedia fingerprinting. However, the improvement is not consistent, as reduced performance of the existing group-based fingerprinting schemes than the non-grouped ones is observed when the grouping does not match the true collusion pattern well. In this letter, we propose a new adaptive detection method, where the threshold for the group detection can be adjusted automatically according to the detection statistics that reflect the underlying collusion pattern. Experimental results show that the proposed adaptive detection outperforms nonadaptive detection and provides consistent performance improvement over non-grouped orthogonal fingerprinting schemes under various collusion scenarios.
Keywords: adaptive; computing; security; data; detection; collusion; detection; group-based; fingerprinting; copy; fingerprinting; grouping; multimedia; of; orthogonal; pattern; detection; protection; multimedia; statistics; group; strategy; nongrouped

Analysis of Nonlinear Collusion Attacks on Fingerprinting Systems for Compressed Multimedia - Varna,A.L.; He,Shan; Swaminathan,A.; M. Wu (Image Processing, 2007. ICIP 2007. IEEE International Conference on, 2007)
In this paper, we analyze the effect of various collusion attacks on fingerprinting systems for compressed multimedia. We evaluate the effectiveness of the collusion attacks in terms of the probability of detection and accuracy in estimating the host signal. Our analysis shows that applying averaging collusion on copies of moderately compressed content gives a highly accurate estimation of the host, and can effectively remove the embedded fingerprints. Averaging is thus the best choice for an attacker as the probability of detection and the distortion introduced are the lowest.
Keywords: attacks; data; coding; multimedia; coding; security; collusion; compressed; compression; image; data; watermarking; fingerprinting; multimedia; data; of; systems; nonlinear

Application of MCL in a dialog agent - Josyula,D. P; Fults,S.; Anderson,M. L; Wilson,S.; Perlis, Don (Third Language and Technology Conference, 2007)

Barrier pointing: using physical edges to assist target acquisition on mobile device touch screens - Jon Froehlich; Wobbrock,J.O.; Kane,S.K. (Proceedings of the 9th international ACM SIGACCESS conference on Computers and accessibility, October, 2007)

Bio-STEER: A Semantic Web workflow tool for Grid computing in the life sciences - Lee,S.; Wang,T. D; Hashmi,N.; Cummings, Michael P. (Future Generation Comp Syst, 2007)
Life science research is becoming evermore computationally intensive. Hence, from a computational resource perspective, Grid computing provides a logical approach to meeting many of the computational needs of life science research. However, there are several barriers to the widespread use of Grid computing in life sciences. In this paper, we attempt to address one particular barrier: the difficulty of using Grid computing by life scientists. Life science research often involves connecting multiple applications together to form a workflow. This process of constructing a workflow is complex. When combined with the difficulty of using Grid services, composing a meaningful workflow using Grid services can present a challenge to life scientists. Our proposed solution is a Semantic Web-enabled computing environment, called Bio-STEER. In BioSTEER, bioinformatics Grid services are mapped to Semantic Web services, described in OWL-S. We also defined an ontology in OWL to model bioinformatics applications. A graphical user interface helps to construct a scientific workflow by showing a list of services that are semantically sound: that is, the output of one service is semantically compatible with the input of the connecting service. Bio-STEER can help users take full advantaue of Grid services through a user-friendly graphical user interface (GUI), which allows them to easily construct the workflows they need. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: client/server; distributed; environments; integrated; interface; management; semantics; services; systems; user; web-base; workflow

Bridging art and science with creativity support tools - Shneiderman, Ben; Rita R Colwell; Diamond,Sara; Greenhalgh,Paul; Wulf,William (Proceedings of the 6th ACM SIGCHI conference on Creativity & cognition, 2007)

CARA: A Cultural-Reasoning Architecture - V.S. Subrahmanian; Albanese,Massimiliano; Martinez,Mar?a Vanina; Nau, Dana S.; Reforgiato,Diego; Simari,Gerardo I.; Sliva,Amy; Udrea,Octavian; Wilkenfeld,Jonathan (IEEE Intelligent Systems, 2007)
The Cognitive Architecture for Reasoning about Adversaries supports methods to gather data about different cultural groups and learn the intensity of those groups' opinions on various topics. It also lets users build and extract models of those groups' behavior and continuously refine those models through shared multiperson learning experiences. Researchers have applied the architecture to develop cultural-reasoning applications for example, a game that teaches soldiers about cultural norms in an Afghan village.
Keywords: cultural reasoning; opinion extraction; opponent modeling

Characterizing RNA Secondary-Structure Features and Their Effects on Splice-Site Prediction - Dogan,R. I; Getoor, Lise; Wilbur,W. J (Data Mining Workshops, 2007. ICDM Workshops 2007. Seventh IEEE International Conference on, 2007)
RNA molecules are distinguished by their sequence composition and by their three-dimensional shape, called the secondary structure. The secondary structure of a pre-mRNA sequence may have a strong influence on gene splicing. In our previous work, we showed that a splice-site model employing sequence features built using our feature generation algorithm was very effective in predicting splice sites. The generated sequence features also contained biologically relevant features. In this paper, we extend the feature generation algorithm to construct secondary-structure features. These features capture the nucleotide pairing tendency in the splice-site neighborhood. We extend the splice-site model to include both pre-mRNA sequence and structure characteristics. The new model significantly outperforms the sequence-based features model. The identified secondary-structure features capture biologically relevant signals such as splicing silencers. We also found these signals to prefer specific regions around the splice-site neighborhood and we detail their preference.
Keywords: algorithm; gene; biophysics; molecular; composition; splice-site; compounds; sequences; computing; genetics; macromolecules; molecular; configurations; organic; features; feature; generation; model; splice-site; molecules; RNA; neighborhood; three-dimensional; pairing; RNA; secondary-structure; sequence; shape; biology; splicing; nucleotide; tendency; pre-mRNA

Children's interests and concerns when using the international children's digital library: a four-country case study - Druin, Allison; Weeks,A.; Massey,S.; Bederson, Benjamin B. (Proceedings of the 7th ACM/IEEE-CS joint conference on Digital libraries, 2007)

CLEF-2006 CL-SR at Maryland: English and Czech - Wang,J.; Oard, Douglas (Evaluation of Multilingual and Multi-modal Information Retrieval, 2007)

Coevolution of Predators and Prey in a Spatial Model - Ottino-Lofler,J.; Rand, William; Wilensky,U. (Genetic and Evolutionary Computation Conference (GECCO), 2007)

Colluding Fingerprinted Video using the Gradient Attack - He,Shan; Kirovski,D.; M. Wu (Acoustics, Speech and Signal Processing, 2007. ICASSP 2007. IEEE International Conference on, 2007)
Digital fingerprinting is an emerging tool to protect multimedia content from unauthorized distribution by embedding a unique fingerprint into each user's copy. Although several fingerprinting schemes have been proposed in related work, disproportional effort has been targeted towards identifying effective collusion attacks on fingerprinting schemes. Recent introduction of the gradient attack has refined the definition of an optimal attack and demonstrated strong effect on direct-sequence, uniformly distributed, and Gaussian spread spectrum fingerprints when applied to synthetic signals. In this paper, we apply the gradient attack on an existing well-engineered video fingerprinting scheme, refine the attack procedure, and demonstrate that the gradient attack is effective on Laplace fingerprints. Finally, we explore an improvement on fingerprint design to thwart the gradient attack. Results suggest that Laplace fingerprint should be avoided. However, we show that a signal mixed of Laplace and Gaussian fingerprints may serve as a design strategy to disable the gradient attack and force pirates into averaging as a form of adversary collusion.
Keywords: attack; multimedia; attacks; digital; content; data; video; distribution; fingerprint; effort; gradient; fingerprinted; fingerprinting; disproportional; fingerprints; colluding; fingerprints; Laplace; Gaussian; identification; multimedia; of; processing; protection; unauthorized; signal; spectrum; spread; systems; security; video; collusion

Collusion-Resistant Dynamic Fingerprinting for Multimedia - He,Shan; M. Wu (Acoustics, Speech and Signal Processing, 2007. ICASSP 2007. IEEE International Conference on, 2007)
This paper considers protecting multimedia content from unauthorized redistribution in subscription based services, where adversaries work together to pirate multiple multimedia programs during a subscription period. Collusion-resistant fingerprinting is an emerging tool for traitor tracing. However, most of the existing fingerprinting works did not consider multiple rounds of interaction between collusion and detection. In this paper, we exploit the temporal dimension and propose a dynamic fingerprinting scheme that adjusts the fingerprint design based on the detection result of previously pirated signal. We also examine colluders' strategies to combat the tracing by dynamic fingerprinting. Both analytical and simulation results show that the proposed dynamic fingerprinting provides better collusion resistance than conventional static fingerprinting
Keywords: based; collusion-resistant; communication; security; data; dimension; traitor; dynamic; fingerprinting; multiple; multimedia; of; piracy; subscription; program; redistribution; multimedia; services; temporal; tracing; unauthorized

Collusion-Resistant Fingerprinting for Compressed Multimedia Signals - Varna,A.L.; He,Shan; Swaminathan,A.; M. Wu; Lu,Haiming; Lu,Zengxiang (Acoustics, Speech and Signal Processing, 2007. ICASSP 2007. IEEE International Conference on, 2007)
Most existing collusion-resistant fingerprinting techniques are for fingerprinting uncompressed signals. In this paper, we first study the performance of the traditional Gaussian based spread spectrum sequences for fingerprinting compressed signals and show that the system can be easily defeated by averaging or taking the median of a few copies. To overcome the collusion problem for compressed multimedia host signals, we propose a technique called anti-collusion dithering to mimic an uncompressed signal. Results show higher probability of catching a colluder using the proposed scheme compared to using Gaussian based fingerprints.
Keywords: based; compression; Gaussian; compression; multimedia; dithering; collusion-resistant; fingerprinting; multimedia; Gaussian; processes; data; sequences; anticollusion; signals; spectrum; spread; systems

Collusion-Resistant Video Fingerprinting for Large User Group - He,Shan; M. Wu (Information Forensics and Security, IEEE Transactions on, 2007)
Digital fingerprinting protects multimedia content from illegal redistribution by uniquely marking copies of the content distributed to users. Most existing multimedia fingerprinting schemes consider a user set on the scale of thousands. However, in such real-world applications as video-on-demand distribution, the number of potential users can be as many as 10-100 million. This large user size demands not only strong collusion resistance but also high efficiency in fingerprint construction, and detection, which makes most existing schemes incapable of being applied to these applications. A recently proposed joint coding and embedding fingerprinting framework provides a promising balance between collusion resistance, efficient construction, and detection, but several issues remain unsolved for applications involving a large group of users. In this paper, we explore how to employ the joint coding and embedding framework and develop practical algorithms to fingerprint video in such challenging settings as to accommodate more than ten million users and resist hundreds of users' collusion. We investigate the proper code structure for large-scale fingerprinting and propose a trimming detection technique that can reduce the decoding computational complexity by more than three orders of magnitude at the cost of less than 0.5% loss in detection probability under moderate to high watermark-to-noise ratios. Both analytic and experimental results show a high potential of joint coding and embedding to meet the needs of real-world large-scale fingerprinting applications.
Keywords: code; coding-embedding; coding; video; communication; video; complexity; decoding; digital; complexity; digital; computational; content; trimming; demand; watermarking; DETECTION; distribution; computational; fingerprinting; fingerprinting; decoding; fingerprinting; joint; framework; large; group; multimedia; identification; multimedia; on; signatures; fingerprint; structure; collusion-resistant; technique; video-on-demand; user; video

Community response grids for older adults: Motivations, usability, and sociability - Wu,P.F.; Preece,J.; Shneiderman, Ben; Jaeger,P. T; Qu,Y. (Proceedings of the 13th Americas Conference on Information Systems, 2007)
This paper discusses the motivation for a Community Response Grid (CRG) to helpolder adults improve their capability for coping with emergency situations. We define and discuss the concept of a CRG, briefly review the limits of current emergency response systems, and identify usability and sociability guidelines for CRGs for older adults based on existing research. The paper ends with a call to action and suggestions for future research directions.

A Component Estimation Framework for Information Forensics - Swaminathan,A.; M. Wu; Liu,K. J.R (Multimedia Signal Processing, 2007. MMSP 2007. IEEE 9th Workshop on, 2007)
With a rapid growth of imaging technologies and an increasingly widespread usage of digital images and videos for a large number of high security and forensic applications, there is a strong need for techniques to verify the source and integrity of digital data. Component forensics is new approach for forensic analysis that aims to estimate the algorithms and parameters in each component of the digital device. In this paper, we develop a novel theoretical foundation to understand the fundamental performance limits of component forensics. We define formal notions of identifiability of components in the information processing chain, and present methods to quantify the accuracies at which the component parameters can be estimated. Building upon the proposed theoretical framework, we devise methods to improve the accuracies of component parameter estimation for a wide range of forensic applications.
Keywords: component; data; data; Estimation; estimation; image; forensics; parameter; framework; digital; integrity; imaging; of; processing; security; technologies; information

COMPUTATIONAL BIOLOGY - Leparc,GG; Mitra,RD; Vardhanabhuti,S.; Wang,J.; Hannenhalli, Sridhar; Smit,S.; Widmann,J.; Knight,R.; Wu,S.; Zhang,Y.; others (Nucleic acids research, 2007)

Confidentiality-preserving rank-ordered search - Swaminathan,Ashwin; Mao,Yinian; Su,Guan-Ming; Gou,Hongmei; Varna,Avinash L.; He,Shan; M. Wu; Oard, Douglas (Proceedings of the 2007 ACM workshop on Storage security and survivability, 2007)
This paper introduces a new framework for confidentiality preserving rank-ordered search and retrieval over large document collections. The proposed framework not only protects document/query confidentiality against an outside intruder, but also prevents an untrusted data center from learning information about the query and the document collection. We present practical techniques for proper integration of relevance scoring methods and cryptographic techniques, such as order preserving encryption, to protect data collections and indices and provide efficient and accurate search capabilities to securely rank-order documents in response to a query. Experimental results on the W3C collection show that these techniques have comparable performance to conventional search systems designed for non-encrypted data in terms of search accuracy. The proposed methods thus form the first steps to bring together advanced information retrieval and secure search capabilities for a wide range of applications including managing data in government and business operations, enabling scholarly study of sensitive data, and facilitating the document discovery process in litigation.
Keywords: encrypted domain search; Ranked retrieval; secure index

Creating a Robust Desktop Grid using Peer-to-Peer Services - Kim,J.-S.; Nam,B.; Marsh,M.; Keleher,P.; Bhattacharjee, Bobby; Richardson,D.; Wellnitz,D.; Sussman, Alan (Parallel and Distributed Processing Symposium, 2007. IPDPS 2007. IEEE International, 2007)
The goal of the work described in this paper is to design and build a scalable infrastructure for executing grid applications on a widely distributed set of resources. Such grid infrastructure must be decentralized, robust, highly available, and scalable, while efficiently mapping application instances to available resources in the system. However, current desktop grid computing platforms are typically based on a client-server architecture, which has inherent shortcomings with respect to robustness, reliability and scalability. Fortunately, these problems can be addressed through the capabilities promised by new techniques and approaches in peer-to-peer (P2P) systems. By employing P2P services, our system allows users to submit jobs to be run in the system and to run jobs submitted by other users on any resources available in the system, essentially allowing a group of users to form an ad-hoc set of shared resources. The initial target application areas for the desktop grid system are in astronomy and space science simulation and data analysis.
Keywords: allocation; architecture; load; balancing; peer-to-peer; client-server; computing; peer-to-peer; computing; resource; desktop; grid; scalable; infrastructure; client-server; system; robust; systems; grid

Crystal Structure and Solution NMR Studies of Lys48-linked Tetraubiquitin at Neutral pH - Eddins,Michael J.; Varadan,Ranjani; Fushman, David; Pickart,Cecile M.; Wolberger,Cynthia (Journal of Molecular Biology, 2007)
Ubiquitin modification of proteins is used as a signal in many cellular processes. Lysine side-chains can be modified by a single ubiquitin or by a polyubiquitin chain, which is defined by an isopeptide bond between the C terminus of one ubiquitin and a specific lysine in a neighboring ubiquitin. Polyubiquitin conformations that result from different lysine linkages presumably differentiate their roles and ability to bind specific targets and enzymes. However, conflicting results have been obtained regarding the precise conformation of Lys48-linked tetraubiquitin. We report the crystal structure of Lys48-linked tetraubiquitin at near-neutral pH. The two tetraubiquitin complexes in the asymmetric unit show the complete connectivity of the chain and the molecular details of the interactions. This tetraubiquitin conformation is consistent with our NMR data as well as with previous studies of diubiquitin and tetraubiquitin in solution at neutral pH. The structure provides a basis for understanding Lys48-linked polyubiquitin recognition under physiological conditions.
Keywords: crystal structure; Lys48-linked; polyubiquitin chains; tetraubiquitin; ubiquitin

Dataflow-based mapping of computer vision algorithms onto FPGAs - Sen,M.; Corretjer,I.; Haim,F.; Saha,S.; Schlessman,J.; Lv,T.; Bhattacharyya, Shuvra S.; Wolf,W. (EURASIP Journal on Embedded Systems, 2007)

Draft Genome of the Filarial Nematode Parasite Brugia Malayi - Ghedin,Elodie; Wang,Shiliang; Spiro,David; Caler,Elisabet; Zhao,Qi; Crabtree,Jonathan; Allen,Jonathan E; Delcher,Arthur L.; Guiliano,David B; Miranda-Saavedra,Diego; Angiuoli,Samuel V; Creasy,Todd; et al. (Science, 2007)
Parasitic nematodes that cause elephantiasis and river blindness threaten hundreds of millions of people in the developing world. We have sequenced the ∼90 megabase (Mb) genome of the human filarial parasite Brugia malayi and predict ∼11,500 protein coding genes in 71 Mb of robustly assembled sequence. Comparative analysis with the free-living, model nematode Caenorhabditis elegans revealed that, despite these genes having maintained little conservation of local synteny during ∼350 million years of evolution, they largely remain in linkage on chromosomal units. More than 100 conserved operons were identified. Analysis of the predicted proteome provides evidence for adaptations of B. malayi to niches in its human and vector hosts and insights into the molecular basis of a mutualistic relationship with its Wolbachia endosymbiont. These findings offer a foundation for rational drug design.

An efficient and scalable parallel algorithm for out-of-core isosurface extraction and rendering - Wang,Qin; JaJa, Joseph F.; Varshney, Amitabh (Journal of Parallel and Distributed Computing, 2007)
We consider the problem of isosurface extraction and rendering for large scale time-varying data. Such data sets have been appearing at an increasing rate especially from physics-based simulations, and can range in size from hundreds of gigabytes to tens of terabytes. Isosurface extraction and rendering is one of the most widely used visualization techniques to explore and analyze such data sets. A common strategy for isosurface extraction involves the determination of the so-called active cells followed by a triangulation of these cells based on linear interpolation, and ending with a rendering of the triangular mesh. We develop a new simple indexing scheme for out-of-core processing of large scale data sets, which enables the identification of the active cells extremely quickly, using more compact indexing structure and more effective bulk data movement than previous schemes. Moreover, our scheme leads to an efficient and scalable implementation on multiprocessor environments in which each processor has access to its own local disk. In particular, our parallel algorithm provably achieves load balancing across the processors independent of the isovalue, with almost no overhead in the total amount of work relative to the sequential algorithm. We conduct a large number of experimental tests on the University of Maryland Visualization Cluster using the Richtmyer–Meshkov instability data set, and obtain results that consistently validate the efficiency and the scalability of our algorithm.
Keywords: Parallel isosurface extraction; scientific visualization

Efficient signature schemes with tight reductions to the Diffie-Hellman problems - Goh,E. J; Jarecki,S.; Katz, Jonathan; Wang,N. (Journal of Cryptology, 2007)
We propose and analyze two efficient signature schemes whose security is tightly related to the Diffie-Hellman problems in the random oracle model. The security of our first scheme relies on the hardness of the computational Diffie-Hellman problem; the security of our second scheme - which is more efficient than the first-is based on the hardness of the decisional Diffie-Hellman problem, a stronger assumption. Given the current state of the art, it is as difficult to solve the Diffie-Hellman problems as it is to solve the discrete logarithm problem in many groups of cryptographic interest. Thus, the signature schemes shown here can currently offer substantially better efficiency (for a given level of provable security) than existing schemes based on the discrete logarithm assumption. The techniques we introduce can also be applied in a wide variety of settings to yield more efficient cryptographic schemes (based on various number-theoretic assumptions) with tight security reductions.

Evolution of genes and genomes on the Drosophila phylogeny - Clark,Andrew G.; Eisen,Michael B.; Smith,Douglas R.; Bergman,Casey M.; Oliver,Brian; Markow,Therese A.; Kaufman,Thomas C.; Kellis,Manolis; Gelbart,William; Iyer,Venky N.; Pollard,Daniel A.; Sackton,Timothy B.; et al. (Nature, 2007)
Comparative analysis of multiple genomes in a phylogenetic framework dramatically improves the precision and sensitivity of evolutionary inference, producing more robust results than single-genome analyses can provide. The genomes of 12 Drosophila species, ten of which are presented here for the first time (sechellia, simulans, yakuba, erecta, ananassae, persimilis, willistoni, mojavensis, virilis and grimshawi), illustrate how rates and patterns of sequence divergence across taxa can illuminate evolutionary processes on a genomic scale. These genome sequences augment the formidable genetic tools that have made Drosophila melanogaster a pre-eminent model for animal genetics, and will further catalyse fundamental research on mechanisms of development, cell biology, genetics, disease, neurobiology, behaviour, physiology and evolution. Despite remarkable similarities among these Drosophila species, we identified many putatively non-neutral changes in protein-coding genes, non-coding RNA genes, and cis-regulatory regions. These may prove to underlie differences in the ecology and behaviour of these diverse species.

Examining Group Behavior and Collaboration using ABM and Robots - Blikstein,P.; Rand, William; Wilensky,Uri (Proc. of Agent, 2007)
Agent-based modeling has been extensively used by scientists to study complex systems.Participatory simulations are similar to agent-based models except that humans play the role of the virtual agents. The Bifocal modeling approach uses sensors to gather data about the real-world phenomena being modeled and uses that information to affect the model. In this work, we are interested in automatically extracting, analyzing and modeling group behaviors in problem solving. Combining these three systems into one unified platform would be useful for those purposes, since it would facilitate a synthesis of their main affordances: understanding the role of locality, mapping human action to emergent behaviors, and controlling embedded physical objects in noisy environments while receiving sensory feedback. We will demonstrate a technological platform based on the NetLogo/HubNet architecture that supports simulated agents, participatory agents and physical agents. We place this platform within a more general framework that we call Human, Embedded and Virtual agents in Mediation (HEV-M). We have run several studies using an instantiation of this platform that consists of a robot-car with four users who navigate a maze. We believe that this tool has potential for three main reasons (1) it facilitates logging of participant’s actions, so as to identify patterns, (2) it offers researchers in the field of computer-supported collaborative learning an easy-to-use tool to design engaging collaborative learning activities and, (3) it foregrounds the role of individual actions within the accomplishment of a collective goal, highlighting the connections between simple individual actions and the resultant macroscopic behaviors of the system.

Features generated for computational splice-site prediction correspond to functional elements - Dogan,Rezarta I.; Getoor,Lise; Wilbur,W. John; Mount, Stephen M. (BMC Bioinformatics, 2007)
Accurate selection of splice sites during the splicing of precursors to messenger RNA requires both relatively well-characterized signals at the splice sites and auxiliary signals in the adjacent exons and introns. We previously described a feature generation algorithm (FGA) that is capable of achieving high classification accuracy on human 3' splice sites. In this paper, we extend the splice-site prediction to 5' splice sites and explore the generated features for biologically meaningful splicing signals.

Full Spectrum Modeling: From Simplicity to Elaboration and Realism in Urban Pattern Formation - Rand, William; Wilensky,U. (North american association computational social and organization sciences conference (NAACSOS), 2007)
There is a dichotomy between researchers who utilize elaborated and realistic agent-basedmodels and those who prefer simple models. Researchers who use realistic agent-based models (ABMs) argue that their realism makes them more useful, while those who utilize simple models claim that they are more general and provide more global knowledge. We believe that it is better to embrace both of these modeling approaches at the same time. Creating richly, detailed, empirically validated models to explore complex systems at a high level, and at the same time extracting general principles to create simplified models that help explore the most important general principles of the phenomena. We call this approach full spectrum modeling and we examine its use through a particular project concerned with understanding urban pattern formation.

Functional connectivity in fMRI: A modeling approach for estimation and for relating to local circuits - Winder,R.; Cortes,C. R; Reggia, James A.; Tagamets,M. A (Neuroimage, 2007)

GATA and Nkx factors synergistically regulate tissue-specific gene expression and development in vivo - Zhang,Yuzhen; Rath,Nibedita; Hannenhalli, Sridhar; Wang,Zhishan; Cappola,Thomas; Kimura,Shioko; Atochina-Vasserman,Elena; Lu,Min Min; Beers,Michael F.; Morrisey,Edward E. (Development, 2007)
In vitro studies have suggested that members of the GATA and Nkx transcription factor families physically interact, and synergistically activate pulmonary epithelial- and cardiac-gene promoters. However, the relevance of this synergy has not been demonstrated in vivo. We show that Gata6-Titf1 (Gata6-Nkx2.1) double heterozygous (G6-Nkx DH) embryos and mice have severe defects in pulmonary epithelial differentiation and distal airway development, as well as reduced phospholipid production. The defects in G6-Nkx DH embryos and mice are similar to those observed in human neonates with respiratory distress syndromes, including bronchopulmonary dysplasia, and differential gene expression analysis reveals essential developmental pathways requiring synergistic regulation by both Gata6 and Titf1 (Nkx2.1). These studies indicate that Gata6 and Nkx2.1 act in a synergistic manner to direct pulmonary epithelial differentiation and development in vivo, providing direct evidence that interactions between these two transcription factor families are crucial for the development of the tissues in which they are co-expressed.

Genome-wide expression profiling and bioinformatics analysis of diurnally regulated genes in the mouse prefrontal cortex - Yang,Shuzhang; Wang,Kai; Valladares,Otto; Hannenhalli, Sridhar; Bucan,Maja (Genome Biology, 2007)
The prefrontal cortex is important in regulating sleep and mood. Diurnally regulated genes in the prefrontal cortex may be controlled by the circadian system, by sleep:wake states, or by cellular metabolism or environmental responses. Bioinformatics analysis of these genes will provide insights into a wide-range of pathways that are involved in the pathophysiology of sleep disorders and psychiatric disorders with sleep disturbances.

Hood College, Master of Business Administration, 2005 Hood College, Master of Science (Computer Science), 2001 Hood College, Bachelor of Science (Computer Science), 1998 Frederick Community College, Associate in Arts (Business Administration), 1993 - Anderson,M. L; Schmill,M.; Oates,T.; Perlis, Don; Josyula,D.; Wright,D.; Human,S. W.T.D.N; Metacognition,L.; Fults,S.; Josyula,D. P (Proceedings of the Workshop on Metareasoning in Agent-Based Systems, 2007)

Improving Embedding Payload in Binary Imageswith "Super-Pixels" - Gou,Hongmei; M. Wu (Image Processing, 2007. ICIP 2007. IEEE International Conference on, 2007)
Hiding data in binary images can facilitate authentication of important documents in the digital domain, which generally requires a high embedding payload. Recently, a steganography framework known as the wet paper coding has been employed in binary image watermarking to achieve high embedding payload. In this paper, we introduce a new concept of super-pixels, and study how to incorporate them in the framework of wet paper coding to further improve the embedding payload in binary images. Using binary text documents as an example, we demonstrate the effectiveness of the proposed super-pixel technique.
Keywords: analysis; watermarking; analysis; wet; authentication; embedding; authentication; text; binary; coding; cryptography; data; coding; message; encapsulation; document; hiding; document; image; paper; payload; steganography; text; processing; image; watermarking; data

In Situ Evaluation of Tracking Algorithms Using Time Reversed Chains - Wu,Hao; Sankaranarayanan,A. C; Chellapa, Rama (Computer Vision and Pattern Recognition, 2007. CVPR '07. IEEE Conference on, 2007)
Automatic evaluation of visual tracking algorithms in the absence of ground truth is a very challenging and important problem. In the context of online appearance modeling, there is an additional ambiguity involving the correctness of the appearance model. In this paper, we propose a novel performance evaluation strategy for tracking systems based on particle filter using a time reversed Markov chain. Starting from the latest observation, the time reversed chain is propagated back till the starting time t = 0 of the tracking algorithm. The posterior density of the time reversed chain is also computed. The distance between the posterior density of the time reversed chain (at t = 0) and the prior density used to initialize the tracking algorithm forms the decision statistic for evaluation. It is postulated that when the data is generated true to the underlying models, the decision statistic takes a low value. We empirically demonstrate the performance of the algorithm against various common failure modes in the generic visual tracking problem. Finally, we derive a small frame approximation that allows for very efficient computation of the decision statistic.
Keywords: (numerical; algorithm; Markov; chain; tracking; decision; density; time; detection; particle; Evaluation; evaluation; object; filter; performance; Filtering; Markov; methods); tracking; visual; processes; decision; reversed; servoing; situ; statistics; in; strategy; posterior; systems; visual; theory; object; tracking; tracking; particle

Intrinsic fingerprints for image authentication and steganalysis - Swaminathan,A.; Wu,M.; Liu,K. J.R (Proc. SPIE Conf. Security, Steganography, Watermarking of Multimedia Contents, 2007)
With growing popularity of digital imaging devices and low-cost image editing software, the integrity of imagecontent can no longer be taken for granted. This paper introduces a methodology for forensic analysis of digital camera images, based on the observation that many in-camera and post-camera processing operations leave distinct traces on digital images. We present methods to identify these intrinsic fingerprint traces of the various processing operations and employ them to verify the authenticity of digital data. We develop an explicit imaging model to characterize the properties that should be satisfied by a direct camera output, and model any further processing applied to the camera captured image by a manipulation filter. Utilizing the manipulation filter coefficients and reference patterns estimated from direct camera outputs using blind deconvolution techniques, the proposed methods are capable of detecting manipulations made by previously unseen operations and steganographic embedding.

Joint Uplink and Downlink Optimization for Real-Time Multiuser Video Streaming Over WLANs - Su,Guan-Ming; Han,Zhu; M. Wu; Liu,K. J.R (Selected Topics in Signal Processing, IEEE Journal of, 2007)
In this paper, a network-aware and source-aware video streaming system is proposed to support interactive multiuser communications within single-cell and multicell IEEE 802.11 networks. Unlike the traditional streaming video services, the strict delay constraints of an interactive video streaming system pose more challenges. These challenges include the heterogeneity of uplink and downlink channel conditions experienced by different users, the multiuser resource allocation of limited radio resources, the incorporation of the cross-layer design, and the diversity of content complexities exhibited by different video sequences. With the awareness of video content and network resources, the proposed system integrates cross-layer error protection mechanism and performs dynamic resource allocation across multiple users. We formulate the proposed system as to minimize the maximal end-to-end expected distortion received by all users, subject to maximal transmission power and delay constraints. To reduce the high dimensionality of the search space, fast multiuser algorithms are proposed to find the near-optimal solutions. Compared to the strategy without dynamically and jointly allocating bandwidth resource for uplinks and downlinks, the proposed framework outperforms by 2.18 7.95 dB in terms of the average received PSNR of all users and by 3.82 11.50 dB in terms of the lowest received PSNR among all users. Furthermore, the proposed scheme can provide more uniform video quality for all users and lower quality fluctuation for each received video sequence.
Keywords: 802.11; allocation; image; allocation; real-time; communications; maximal; distortion; multiuser; end-to-end; error; expected; IEEE; LAN; mechanism; downlink; multiuser; networks; WLAN; cross-layer; optimization; interactive; optimization; video; Protection; quality; video; resource; sequences; video; streaming; streaming; uplink; streaming; wireless; system; bandwidth; video

Just a cog in the machine: participatory robotics as a tool for understanding collaborative learning and decision-making - Blikstein,Paulo; Rand, William; Wilensky,Uri (Proceedings of the 8th iternational conference on Computer supported collaborative learning, 2007)
We will demonstrate the integration of a software-based multi-agent modeling platform with a participatory simulation environment and a real-time control system for a physical robotic agent. Both real and virtual participants will be able to act collaboratively in a simulation that will control a physical agent. The backbone of this demonstration is a widely used, freely available, mature modeling platform (NetLogo). We posit that this technological platform can be of use for researchers interested in investigating collaborative learning and decision-making, as well as to design collaborative learning activities. We will present preliminary findings from pilot studies with the tool.

Learning and visualizing user preferences over sets - Wagstaff,K.; desJardins, Marie; Eaton,E.; Montminy,J. (American Association for Artificial Intelligence (AAAI), 2007)
In previous work, we introduced a representation language,DD-PREF, that balances preferences for particular items with preferences about the properties of the set. Specifically, DD- PREF permits the expression of preferences for depth (i.e., preferences for specific attribute values over others) and di- versity of sets (i.e., preferences for broad vs. narrow distri- butions of attribute values). We have also shown how pref- erences represented in DD-PREF can be learned from training data. In this paper, we present a new experimental method- ology, and give results in a Mars rover image domain. We also provide new visualizations of the learned preferences in this domain. Finally, we describe a Chinese restaurant menu domain for which we are currently gathering user data.

Making models match: Replicating an agent-based model - Wilensky,U.; Rand, William (Journal of Artificial Societies and Social Simulation, 2007)
Scientists have increasingly employed computer models in their work. Recent years have seen a proliferation of agent-based models in the natural and social sciences. But with the exception of a few "classic" models, most of these models have never been replicated by anyone but the original developer. As replication is a critical component of the scientific method and a core practice of scientists, we argue herein for an increased practice of replication in the agent-based modeling community, and for widespread discussion of the issues surrounding replication. We begin by clarifying the concept of replication as it applies to ABM. Furthermore we argue that replication may have even greater benefits when applied to computational models than when applied to physical experiments. Replication of computational models affects model verification and validation and fosters shared understanding about modeling decisions. To facilitate replication, we must create standards for both how to replicate models and how to evaluate the replication. In this paper, we present a case study of our own attempt to replicate a classic agent-based model. We begin by describing an agent-based model from political science that was developed by Axelrod and Hammond. We then detail our effort to replicate that model and the challenges that arose in recreating the model and in determining if the replication was successful. We conclude this paper by discussing issues for (1) researchers attempting to replicate models and (2) researchers developing models in order to facilitate the replication of their results.

Manufacturing multi-material articulated plastic products using in-mold assembly - Priyadarshi,Alok; Gupta, Satyandra K.; Gouker,Regina; Krebs,Florian; Shroeder,Martin; Warth,Stefan (The International Journal of Advanced Manufacturing Technology, 2007)
In-mold assembly can be used to create plastic products with articulated joints. This process eliminates the need for post-molding assembly and reduces the number of parts being used in the product, hence improving the product quality. However, designing both products and molds is significantly more challenging in case of in-mold assembly. Currently, a systematic methodology does not exist for developing product and processes to exploit potential benefits of in-mold assembly for creating articulated joints. This paper is a step towards creating such a methodology and reports the following three results. First, it presents a model for designing assemblies and molding process so that the joint clearances and variation in the joint clearances can meet the performance goals. Second, it describes proven mold design templates for realizing revolute, prismatic, and spherical joints. Third, it describes a mold design methodology for designing molds for products that contain articulated joints and will be produced using in-mold assembly process. Three case studies are also presented to illustrate how in-mold assembly process can be used to create articulated devices.
Keywords: engineering

Measuring the Contributions of Routing Dynamics to Prolonged End-to-End Internet Path Failures - Wang,Feng; Feamster, Nick; Gao,Lixin (Global Telecommunications Conference, 2007. GLOBECOM '07. IEEE, 2007)
This paper studies the contributions of routing dynamics to the duration of long-lived end-to-end Internet path failures. Studies have shown that end-to-end Internet failures (periods of prolonged packet loss) are widespread. These failures are typically attributed to either congestion or routing dynamics. Unfortunately, the extent to which congestion and routing dynamics contribute to long-lasting path failures, and the effect of routing dynamics on end-to-end performance, are not well understood. This paper uses a joint analysis of active measurements and routing data to characterize end-to-end failures observed over one month on a topologically diverse Internet testbed. We find that routing dynamics coincide with most prolonged end-to-end failures, suggesting that routing dynamics contribute significantly to the duration of these failures. We also find that most long-lived end-to-end path failures that coincide with routing dynamics are caused by BGP convergence or instability. Our results provide new insights into the effects of routing instability on end-to-end Internet path performance.
Keywords: diverse Internet topological testbed; Internet; prolonged end-to-end Internet path failure; routing dynamics; telecommunication network reliability; telecommunication network routing; telecommunication network topology

MetaProm: a neural network based meta-predictor for alternative human promoter prediction - Wang,Junwen; Ungar,Lyle; Tseng,Hung; Hannenhalli, Sridhar (BMC Genomics, 2007)
BACKGROUND:De novo eukaryotic promoter prediction is important for discovering novel genes and understanding gene regulation. In spite of the great advances made in the past decade, recent studies revealed that the overall performances of the current promoter prediction programs (PPPs) are still poor, and predictions made by individual PPPs do not overlap each other. Furthermore, most PPPs are trained and tested on the most-upstream promoters; their performances on alternative promoters have not been assessed.RESULTS:In this paper, we evaluate the performances of current major promoter prediction programs (i.e., PSPA, FirstEF, McPromoter, DragonGSF, DragonPF, and FProm) using 42,536 distinct human gene promoters on a genome-wide scale, and with emphasis on alternative promoters. We describe an artificial neural network (ANN) based meta-predictor program that integrates predictions from the current PPPs and the predicted promoters' relation to CpG islands. Our specific analysis of recently discovered alternative promoters reveals that although only 41% of the 3' most promoters overlap a CpG island, 74% of 5' most promoters overlap a CpG island.CONCLUSION:Our assessment of six PPPs on 1.06 x 109 bps of human genome sequence reveals the specific strengths and weaknesses of individual PPPs. Our meta-predictor outperforms any individual PPP in sensitivity and specificity. Furthermore, we discovered that the 5' alternative promoters are more likely to be associated with a CpG island.

Microarray analysis of gene expression induced by sexual contact in Schistosoma mansoni - Waisberg,Michael; Lobo,Francisco; Cerqueira,Gustavo; Passos,Liana; Carvalho,Omar; Franco,Gloria; El‐Sayed, Najib M. (BMC Genomics, 2007)
BACKGROUND:The parasitic trematode Schistosoma mansoni is one of the major causative agents of Schistosomiasis, a disease that affects approximately 200 million people, mostly in developing countries. Since much of the pathology is associated with eggs laid by the female worm, understanding the mechanisms involved in oogenesis and sexual maturation is an important step towards the discovery of new targets for effective drug therapy. It is known that the adult female worm only develops fully in the presence of a male worm and that the rates of oviposition and maturation of eggs are significantly increased by mating. In order to study gene transcripts associated with sexual maturation and oviposition, we compared the gene expression profiles of sexually mature and immature parasites using DNA microarrays.RESULTS:For each experiment, three amplified RNA microarray hybridizations and their dye swaps were analyzed. Our results show that 265 transcripts are differentially expressed in adult females and 53 in adult males when mature and immature worms are compared. Of the genes differentially expressed, 55% are expressed at higher levels in paired females while the remaining 45% are more expressed in unpaired ones and 56.6% are expressed at higher levels in paired male worms while the remaining 43.4% are more expressed in immature parasites. Real-time RT-PCR analysis validated the microarray results. Several new maturation associated transcripts were identified. Genes that were up-regulated in single-sex females were mostly related to energy generation (i.e. carbohydrate and protein metabolism, generation of precursor metabolites and energy, cellular catabolism, and organelle organization and biogenesis) while genes that were down-regulated related to RNA metabolism, reactive oxygen species metabolism, electron transport, organelle organization and biogenesis and protein biosynthesis.CONCLUSION:Our results confirm previous observations related to gene expression induced by sexual maturation in female schistosome worms. They also increase the list of S. mansoni maturation associated transcripts considerably, therefore opening new and exciting avenues for the study of the conjugal biology and development of new drugs against schistosomes.

Noise Features for Image Tampering Detection and Steganalysis - Gou,Hongmei; Swaminathan,A.; M. Wu (Image Processing, 2007. ICIP 2007. IEEE International Conference on, 2007)
With increasing availability of low-cost image editing softwares, the authenticity of digital images can no longer be taken for granted. Digital images have also been used as cover data for transmitting secret information in the field of steganography. In this paper, we introduce a new set of features for multimedia forensics to determine if a digital image is an authentic camera output or if it has been tampered or embedded with hidden data. We perform such image forensic analysis employing three sets of statistical noise features, including those from denoising operations, wavelet analysis, and neighborhood prediction. Our experimental results demonstrate that the proposed method can effectively distinguish digital images from their tampered or stego versions.
Keywords: analysis; cryptography; data; analysis; image; analysis; wavelet; authenticity; hidden; computing; statistical; data; image; denoising; denoising; multimedia; detection; low-cost; editing; encapsulation; feature; extraction; image; features; steganalysis; wavelet; forensic; forensics; neighborhood; image; NOISE; operations; digital; prediction; statistical; softwares; multimedia; tampering; transforms

Nonintrusive component forensics of visual sensors using output images - Swaminathan,A.; M. Wu; Liu,K. J.R (Information Forensics and Security, IEEE Transactions on, 2007)
Rapid technology development and the widespread use of visual sensors have led to a number of new problems related to protecting intellectual property rights, handling patent infringements, authenticating acquisition sources, and identifying content manipulations. This paper introduces nonintrusive component forensics as a new methodology for the forensic analysis of visual sensing information, aiming to identify the algorithms and parameters employed inside various processing modules of a digital device by only using the device output data without breaking the device apart. We propose techniques to estimate the algorithms and parameters employed by important camera components, such as color filter array and color interpolation modules. The estimated interpolation coefficients provide useful features to construct an efficient camera identifier to determine the brand and model from which an image was captured. The results obtained from such component analysis are also useful to examine the similarities between the technologies employed by different camera models to identify potential infringement/licensing and to facilitate studies on technology evolution
Keywords: ACQUISITION; array; color; authenticating; component; filter; forensics; patent; infringements; visual; Interpolation; manipulations; intellectual; modules; content; property; property; protection; nonintrusive; rights; sensors; image; sensors; industrial; sources; color

Ontologies for reasoning about failures in AI systems - Schmill,M.; Josyula,D.; Anderson,M. L; Wilson,S.; Oates,T.; Perlis, Don; Fults,S. (Proceedings from the Workshop on Metareasoning in Agent Based Systems at the Sixth International Joint Conference on Autonomous Agents and Multiagent Sytems, 2007)

Optimal expected-case planar point location - Arya,S.; Malamatos,T.; Mount, Dave; Wong,K.C. (SIAM Journal on Computing, 2007)
Point location is the problem of preprocessing a planar polygonal subdivision S of size ninto a data structure in order to determine efficiently the cell of the subdivision that contains a given query point. We consider this problem from the perspective of expected query time. We are given the probabilities pz that the query point lies within each cell z ∈ S. The entropy H of the resulting discrete probability distribution is the dominant term in the lower bound on the expected-case query time. We show that it is possible to achieve query time H + O( √ H + 1) with space O(n), which is optimal up to lower order terms in the query time. We extend this result to subdivisions with convex cells, assuming a uniform query distribution within each cell. In order to achieve space efficiency, we introduce the concept of entropy-preserving cuttings.

Optimization of nonlinear error for weighted essentially non-oscillatory methods in direct numerical simulations of compressible turbulence - Taylor,Ellen M.; Wu,Minwei; Martin, M.P (Journal of Computational Physics, 2007)
Weighted essentially non-oscillatory (WENO) methods have been developed to simultaneously provide robust shock-capturing in compressible fluid flow and avoid excessive damping of fine-scale flow features such as turbulence. Under certain conditions in compressible turbulence, however, numerical dissipation remains unacceptably high even after optimization of the linear component that dominates in smooth regions. We therefore construct and evaluate WENO schemes that also reduce dissipation due to one source of nonlinear error: the smoothness measurement that governs the application of stencil adaptation away from the linear optimal stencil. Direct numerical simulations (DNS) include a one-dimensional Euler solution and three-dimensional compressible isotropic turbulence. We find that the smoothness measurement modifications that we call the “relative smoothness limiter” and the “relative total variation limiter” each significantly enhance thez grid-convergence properties of WENO schemes while generating, respectively, small and moderate additional computational expense. Moreover, we observe these techniques to be broadly effective regardless of flow configuration.
Keywords: Compressible turbulence; direct numerical simulation; Limiters; Linear dissipation; Non-linear dissipation; Numerical dissipation; Shock capturing

Parameterized st-Orientations of Graphs: Algorithms and Experiments - Charalampos Papamanthou; Tollis, Ioannis G. (Graph Drawing, 2007)
st-orientations (st-numberings) or bipolar orientations of undirected graphs are central to many graph algorithms and applications. Several algorithms have been proposed in the past to compute an st-orientation of a biconnected graph. However, as indicated in [1], the computation of more than one st-orientation is very important for many applications in multiple research areas, such as this of Graph Drawing. In this paper we show how to compute such orientations with certain (parameterized) characteristics in the final st-oriented graph, such as the length of the longest path. Apart from Graph Drawing, this work applies in other areas such as Network Routing and in tackling difficult problems such as Graph Coloring and Longest Path. We present primary approaches to the problem of computing longest path parameterized st-orientations of graphs, an analytical presentation (together with proof of correctness) of a new O(mlog5 n) (O(mlogn) for planar graphs) time algorithm that computes such orientations (and which was used in [1]) and extensive computational results that reveal the robustness of the algorithm.
Keywords: Algorithm Analysis and Problem Complexity; Computer Graphics; Data structures; Discrete Mathematics in Computer Science

Pedestrian detection via periodic motion analysis - Ran, Y.; Weiss, I.; Zheng,Q.; Davis, Larry S. (International Journal of Computer Vision, 2007)
We describe algorithms for detecting pedestrians in videos acquired by infrared (and color) sensors. Two approaches are proposed based on gait. The first employs computationally efficient periodicity measurements. Unlike other methods, it estimates a periodic motion frequency using two cascading hypothesis testing steps to filter out non-cyclic pixels so that it works well for both radial and lateral walking directions. The extraction of the period is efficient and robust with respect to sensor noise and cluttered background. In order to integrate shape and motion, we convert the cyclic pattern into a binary sequence by Maximal Principal Gait Angle (MPGA) fitting in the second method. It does not require alignment and continuously estimates the period using a Phase-locked Loop. Both methods are evaluated by experimental results that measure performance as a function of size, movement direction, frame rate and sequence length.

Portcullis: protecting connection setup from denial-of-capability attacks - Parno, Bryan; Wendlandt, Dan; Elaine Shi; Perrig, Adrian; Maggs, Bruce; Hu, Yih-Chun (ACM, 2007)
Systems using capabilities to provide preferential service to selected flows have been proposed as a defense against large-scale network denial-of-service attacks. While these systems offer strong protection for established network flows, the Denial-of-Capability (DoC) attack, which prevents new capability-setup packets from reaching the destination, limits the value of these systems. Portcullis mitigates DoC attacks by allocating scarce link bandwidth for connection establishment packets based on per-computation fairness. We prove that a legitimate sender can establish a capability with high probability regardless of an attacker's resources or strategy and that no system can improve on our guarantee. We simulate full and partial deployments of Portcullis on an Internet-scale topology to confirm our theoretical results and demonstrate the substantial benefits of using per-computation fairness.
Keywords: network capability; per-computation fairness

Position and distance specificity are important determinants of cis-regulatory motifs in addition to evolutionary conservation - Vardhanabhuti,Saran; Wang,Junwen; Hannenhalli, Sridhar (Nucleic Acids Research, 2007)
Computational discovery of cis-regulatory elements remains challenging. To cope with the high false positives, evolutionary conservation is routinely used. However, conservation is only one of the attributes of cis-regulatory elements and is neither necessary nor sufficient. Here, we assess two additional attributes—positional and inter-motif distance specificity—that are critical for interactions between transcription factors. We first show that for a greater than expected fraction of known motifs, the genes that contain the motifs in their promoters in a position-specific or distance-specific manner are related, both in function and/or in expression pattern. We then use the position and distance specificity to discover novel motifs. Our work highlights the importance of distance and position specificity, in addition to the evolutionary conservation, in discovering cis-regulatory motifs.

A practical approximation algorithm for the LMS line estimator - Mount, Dave; Netanyahu,Nathan S.; Romanik,Kathleen; Silverman,Ruth; Wu,Angela Y. (Computational Statistics & Data Analysis, 2007)
The problem of fitting a straight line to a finite collection of points in the plane is an important problem in statistical estimation. Robust estimators are widely used because of their lack of sensitivity to outlying data points. The least median-of-squares (LMS) regression line estimator is among the best known robust estimators. Given a set of n points in the plane, it is defined to be the line that minimizes the median squared residual or, more generally, the line that minimizes the residual of any given quantile q, where 0 < q ⩽ 1 . This problem is equivalent to finding the strip defined by two parallel lines of minimum vertical separation that encloses at least half of the points.The best known exact algorithm for this problem runs in O ( n 2 ) time. We consider two types of approximations, a residual approximation, which approximates the vertical height of the strip to within a given error bound ε r ⩾ 0 , and a quantile approximation, which approximates the fraction of points that lie within the strip to within a given error bound ε q ⩾ 0 . We present two randomized approximation algorithms for the LMS line estimator. The first is a conceptually simple quantile approximation algorithm, which given fixed q and ε q > 0 runs in O ( n log n ) time. The second is a practical algorithm, which can solve both types of approximation problems or be used as an exact algorithm. We prove that when used as a quantile approximation, this algorithm's expected running time is O ( n log 2 n ) . We present empirical evidence that the latter algorithm is quite efficient for a wide variety of input distributions, even when used as an exact algorithm.
Keywords: Approximation algorithms; least median-of-squares regression; line arrangements; line fitting; randomized algorithms; robust estimation

PRAM-on-chip: first commitment to silicon - Wen,Xingzhi; Vishkin, Uzi (Proceedings of the nineteenth annual ACM symposium on Parallel algorithms and architectures, 2007)
Keywords: ease-of-programming; explicit multi-threading; on-chip parallel processor; Parallel algorithms; PRAM; XMT

Randomized Algorithms and Probabilistic Analysis in Wireless Networking - Srinivasan, Aravind (Stochastic Algorithms: Foundations and ApplicationsStochastic Algorithms: Foundations and Applications, 2007)
Devices connected wirelessly, in various forms including computers, hand-held devices, ad hoc networks, and embedded systems, are expected to become ubiquitous all around us. Wireless networks pose interesting new challenges, some of which do not arise in standard (wired) networks. This survey discusses some key probabilistic notions – both randomized algorithms and probabilistic analysis – in wireless networking.

Robust scanner identification based on noise features - Gou,H.; Swaminathan,A.; Wu,M. (Proc. SPIE, Electronic Imaging, Security, Steganography, and Watermarking of Multimedia Contents IX, 2007)
A large portion of digital image data available today is acquired using digital cameras or scanners. While camerasallow digital reproduction of natural scenes, scanners are often used to capture hardcopy art in more controlled scenarios. This paper proposes a new technique for non-intrusive scanner model identification, which can be further extended to perform tampering detection on scanned images. Using only scanned image samples that contain arbitrary content, we construct a robust scanner identifier to determine the brand/model of the scanner used to capture each scanned image. The proposed scanner identifier is based on statistical features of scanning noise. We first analyze scanning noise from several angles, including through image de-noising, wavelet analysis, and neighborhood prediction, and then obtain statistical features from each characterization. Experimental results demonstrate that the proposed method can effectively identify the correct scanner brands/models with high accuracy.

Robust Visual Tracking Using the Time-Reversibility Constraint - Wu,Hao; Chellapa, Rama; Sankaranarayanan,A. C; Zhou,S. K (Computer Vision, 2007. ICCV 2007. IEEE 11th International Conference on, 2007)
Visual tracking is a very important front-end to many vision applications. We present a new framework for robust visual tracking in this paper. Instead of just looking forward in the time domain, we incorporate both forward and backward processing of video frames using a novel time-reversibility constraint. This leads to a new minimization criterion that combines the forward and backward similarity functions and the distances of the state vectors between the forward and backward states of the tracker. The new framework reduces the possibility of the tracker getting stuck in local minima and significantly improves the tracking robustness and accuracy. Our approach is general enough to be incorporated into most of the current tracking algorithms. We illustrate the improvements due to the proposed approach for the popular KLT tracker and a search based tracker. The experimental results show that the improved KLT tracker significantly outperforms the original KLT tracker. The time-reversibility constraint used for tracking can be incorporated to improve the performance of optical flow, mean shift tracking and other algorithms.
Keywords: backward; constraint; video; criterion; state; forward; frame; KLT; processing; processing; video; processing; visual; signal; tracker; minimization; tracking; minimisation; video; vectors; time-reversibility

A Signal Processing and Randomization Perspective of Robust and Secure Image Hashing - M. Wu; Mao,Yinian; Swaminathan,Ashwin (Statistical Signal Processing, 2007. SSP '07. IEEE/SP 14th Workshop on, 2007)
An image hash is a content-based compact representation of an image and finds applications in image authentication, watermarking, and image similarity comparison. This paper reviews representative approaches developed by the research community in constructing robust and secure image hash. A unified framework and case studies on representative image hash schemes are presented to demonstrate important roles of signal processing and controlled randomization in constructing and evaluating robust and secure hashing for visual data.

Signal Processing Magazine E-Newsletter: Inside Out [From the Editor] - Wu,M. (Signal Processing Magazine, IEEE, 2007)

A spatial model of the red queen effect - Ottino-Loffler,Jules; Rand, William; Wilensky,Uri (Proceedings of the 9th annual conference on Genetic and evolutionary computation, 2007)
Van Valen first discovered the "Red Queen Effect" (RQE), where two species can dramatically co-evolve their phenotypes over time but never gain a relative advantage [2]. In the ideal version of the RQE, regardless of the actual values that the species evolve to obtain, they have not moved in relation to each other. Though previous models of the RQE exist, we developed an agent-based model (ABM) which has a base ontology more similar to real world coevolutionary systems than equation-based models (EBMs). For instance, this model contains spatial information and an individuallevel reproduction mechanism. Yet this model recreates traditional EBM results. For instance Dieckmann et al show that there are three possible outcomes of competitive coevolution: predator dominance, prey dominance and evolutionary cycling (RQE) [1]. By reconceptualizing this EBM using an ABM, we make it easier for students and researchers to understand, manipulate, and modify this model [4]. The model is written in the NetLogo agent-based modeling environment [3]. The model is initialized with 150 predator and 150 prey agents. Predator agents have a resistance level r and prey agents have a poison p. The agents are initially randomly distributed on a toroidal real-valued 35 by 35 grid. The initial resistance and poison values for the predators and prey are drawn from normal distributions with means µr and µp and a standard deviation of 1. During a model timestep, each agent moves one unit at a random heading. If at the end of its move a predator is within 1 unit of a prey, then it will challenge the prey. The predator will compare its resistance value to the prey's poison value and which ever agent has the larger value will win the challenge and the other agent will be killed. At the end of an agent's turn if the total number of agents is less than the maximum carrying capacity the agent will reproduce with a 50% probability. The new agent's initial poison / resistance will be drawn from a normal distribution with the parent's poison / resistance as the mean value and a standard deviation of 1. Our goal was to investigate whether this ABMwould replicate the results of the EBM of [1]. Our parameter of interest was µp; we held µr constant at 25 and varied µp from 0 to 50 at increments of 5. For each value we ran the model 10 times for 5000 timesteps. Figure 1 illustrates the final average values of both the resistance and the poison for the various initial values. If there are no predators or prey then a value of 0 is plotted for the respective final trait. In most cases, one species drives the other to extinction, and there is little change in the initial trait values. However when the value of µp is similar to µr then neither species is completely destroyed, but if there is any significant difference between µr and µp then one species will die off. The highest final trait values are found when µp = µr, in this case we see the results of the RQE since the final trait values are much higher than the initial values. These final values are more than 1.5 orders of magnitude larger than the initial values. This model reproduces classical models of the RQE, but has two different mobile species interacting on a spatial grid over time which is a closer representation of reality than traditional models. This closer representation makes ABMs excellent teaching and experimental tools because their basic assumptions can easily be manipulated and explored. Acknowledgments: We thank the National Science Foundation and NICO for supporting this research.
Keywords: Agent-based modeling; coevolution; red queen effect; spatial modeling

SplicePort--An interactive splice-site analysis tool - Dogan,R. I; Getoor, Lise; Wilbur,W. J; Mount, Stephen M. (Nucleic Acids Research, 2007)
SplicePort is a web-based tool for splice-site analysis that allows the user to make splice-site predictions for submitted sequences. In addition, the user can also browse the rich catalog of features that underlies these predictions, and which we have found capable of providing high classification accuracy on human splice sites. Feature selection is optimized for human splice sites, but the selected features are likely to be predictive for other mammals as well. With our interactive feature browsing and visualization tool, the user can view and explore subsets of features used in splice-site prediction (either the features that account for the classification of a specific input sequence or the complete collection of features). Selected feature sets can be searched, ranked or displayed easily. The user can group features into clusters and frequency plot WebLogos can be generated for each cluster. The user can browse the identified clusters and their contributing elements, looking for new interesting signals, or can validate previously observed signals. The SplicePort web server can be accessed at http://www.cs.umd.edu/projects/SplicePort and http://www.spliceport.org.

Structural Footprinting in Protein Structure Comparison: The Impact of Structural Fragments - Zotenko,Elena; Dogan,Rezarta Islamaj; Wilbur,W. John; O'Leary, Dianne P.; Przytycka,Teresa M. (BMC Structural Biology, 2007)
Abstract Background One approach for speeding-up protein structure comparison is the projection approach, where a protein structure is mapped to a high-dimensional vector and structural similarity is approximated by distance between the corresponding vectors. Structural footprinting methods are projection methods that employ the same general technique to produce the mapping: first select a representative set of structural fragments as models and then map a protein structure to a vector in which each dimension corresponds to a particular model and "counts" the number of times the model appears in the structure. The main difference between any two structural footprinting methods is in the set of models they use; in fact a large number of methods can be generated by varying the type of structural fragments used and the amount of detail in their representation. How do these choices affect the ability of the method to detect various types of structural similarity? Results To answer this question we benchmarked three structural footprinting methods that vary significantly in their selection of models against the CATH database. In the first set of experiments we compared the methods' ability to detect structural similarity characteristic of evolutionarily related structures, i.e., structures within the same CATH superfamily. In the second set of experiments we tested the methods' agreement with the boundaries imposed by classification groups at the Class, Architecture, and Fold levels of the CATH hierarchy. Conclusion In both experiments we found that the method which uses secondary structure information has the best performance on average, but no one method performs consistently the best across all groups at a given classification level. We also found that combining the methods' outputs significantly improves the performance. Moreover, our new techniques to measure and visualize the methods' agreement with the CATH hierarchy, including the threshholded affinity graph, are useful beyond this work. In particular, they can be used to expose a similar composition of different classification groups in terms of structural fragments used by the method and thus provide an alternative demonstration of the continuous nature of the protein structure universe.

Syntactic sentence compression in the biomedical domain: facilitating access to related articles - Jimmy Lin; Wilbur,W. J (Information Retrieval, 2007)
We explore a syntactic approach to sentence compression in the biomedical domain, grounded in the context of result presentation for related article search in the PubMed search engine. By automatically trimming inessential fragments of article titles, a system can effectively display more results in the same amount of space. Our implemented prototype operates by applying a sequence of syntactic trimming rules over the parse trees of article titles. Two separate studies were conducted using a corpus of manually compressed examples from MEDLINE: an automatic evaluation using Bleu and a summative evaluation involving human assessors. Experiments show that a syntactic approach to sentence compression is effective in the biomedical domain and that the presentation of compressed article titles supports accurate “interest judgments”, decisions by users as to whether an article is worth examining in more detail.

Taking Advantage of Collective Operation Semantics for Loosely Coupled Simulations - Wu,Joe Shang-Chieh; Sussman, Alan (Parallel and Distributed Processing Symposium, International, 2007)
Although a loosely coupled component-based framework offers flexibility and versatility for building and deploying large-scale multi-physics simulation systems, the performance of such a system can suffer from excessive buffering of data objects which may or may not be transferred between components. By taking advantages of the collective properties of parallel simulation components, which is common for data-parallel scientific applications, an optimization method, which we call buddy-help, can greatly enhance overall performance. Buddy-Help can reduce the time taken for buffering operations in an exporting component, when there are timing differences across processes in the exporting component. The optimization enables skipping unnecessary buffering operations, once another process, which has already performed the collective export operation, has determined that the buffered data will never be needed. Because an analytical study would be very difficult due to the complexity of the overall coupled simulation system, the performance improvement enabled by buddy-help is investigated via a micro-benchmark specifically designed to illustrate the behavior of coupled simulation scenarios under which buddy-help can provide performance gains.

Time and Space Efficient Algorithms for Two-Party Authenticated Data Structures - Charalampos Papamanthou; Tamassia, Roberto (Information and Communications Security, 2007)
Authentication is increasingly relevant to data management. Data is being outsourced to untrusted servers and clients want to securely update and query their data. For example, in database outsourcing, a client’s database is stored and maintained by an untrusted server. Also, in simple storage systems, clients can store very large amounts of data but at the same time, they want to assure their integrity when they retrieve them. In this paper, we present a model and protocol for two-party authentication of data structures. Namely, a client outsources its data structure and verifies that the answers to the queries have not been tampered with. We provide efficient algorithms to securely outsource a skip list with logarithmic time overhead at the server and client and logarithmic communication cost, thus providing an efficient authentication primitive for outsourced data, both structured (e.g., relational databases) and semi-structured (e.g., XML documents). In our technique, the client stores only a constant amount of space, which is optimal. Our two-party authentication framework can be deployed on top of existing storage applications, thus providing an efficient authentication service. Finally, we present experimental results that demonstrate the practical efficiency and scalability of our scheme.
Keywords: Algorithm Analysis and Problem Complexity; Computer Communication Networks; computers and society; Data Encryption; Management of Computing and Information Systems; Systems and Data Security

Toward domain-neutral human-level metacognition - Anderson,M. L; Schmill,M.; Oates,T.; Perlis, Don; Josyula,D.; Wright,D.; Wilson,S. (AAAI Spring Symposium on Logical Formalizations of Commonsense Reasoning, 2007)

Tracing malicious relays in cooperative wireless communications - Mao,Y.; Wu,M. (Information Forensics and Security, IEEE Transactions on, 2007)

TREMOR—a tool for retrieving transcriptional modules by incorporating motif covariance - Singh,Larry N.; Wang,Li-San; Hannenhalli, Sridhar (Nucleic Acids Research, 2007)
A transcriptional module (TM) is a collection of transcription factors (TF) that as a group, co-regulate multiple, functionally related genes. The task of identifying TMs poses an important biological challenge. Since TFs belong to evolutionarily and structurally related families, TF family members often bind to similar DNA motifs and can confound sequence-based approaches to TM identification. A previous approach to TM detection addresses this issue by pre-selecting a single representative from each TF family. One problem with this approach is that closely related transcription factors can still target sufficiently distinct genes in a biologically meaningful way, and thus, pre-selecting a single family representative may in principle miss certain TMs. Here we report a method—TREMOR (Transcriptional Regulatory Module Retriever). This method uses the Mahalanobis distance to assess the validity of a TM and automatically incorporates the inter-TF binding similarity without resorting to pre-selecting family representatives. The application of TREMOR on human muscle-specific, liver-specific and cell-cycle-related genes reveals TFs and TMs that were validated from literature and also reveals additional related genes.

Unicity Distance of Robust Image Hashing - Mao,Yinian; M. Wu (Information Forensics and Security, IEEE Transactions on, 2007)
An image hash is a randomized compact representation of image content and finds applications in image authentication, image and video watermarking, and image similarity comparison. Usually, an image-hashing scheme is required to be robust and secure, and the security issue is particularly important in applications, such as multimedia authentication, watermarking, and fingerprinting. In this paper, we investigate the security of image hashing from the perspective of unicity distance, a concept pioneered by Shannon in one of his seminal papers. Using two recently proposed image-hashing schemes as representatives, we show that the concept of unicity distance can be adapted to evaluate the security of image hashing. Our analysis shows that the secret hashing key, or its equivalent form, can be estimated with high accuracy when the key is reused several dozen times. The estimated unicity distance determines the maximum number of key reuses in the investigated hashing schemes. A countermeasure of randomized key initialization is discussed to avoid key reuse and strengthen the security of robust image hashing.
Keywords: authentication; image; authentication; randomized; coding; image; compact; comparison; multimedia; content; image; data; distance; watermarking; image; fingerprinting; image; hashing; unicity; image; initialization; robust; key; of; representation; randomized; representation; security; similarity

VAST 2007 Contest - Blue Iguanodon - Grinstein,G.; Plaisant, Catherine; Laskowski,S.; O'Connell,T.; Scholtz,J.; Whiting,M. (Visual Analytics Science and Technology, 2007. VAST 2007. IEEE Symposium on, 2007)
Visual analytics experts realize that one effective way to push the field forward and to develop metrics for measuring the performance of various visual analytics components is to hold an annual competition. The second visual analytics science and technology (VAST) contest was held in conjunction with the 2007 IEEE VAST symposium. In this contest participants were to use visual analytic tools to explore a large heterogeneous data collection to construct a scenario and find evidence buried in the data of illegal and terrorist activities that were occurring. A synthetic data set was made available as well as tasks. In this paper we describe some of the advances we have made from the first competition held in 2006.
Keywords: activities; large; activities; visual; analytic; collection; terrorist; data; heterogeneous; illegal; interfaces; tools; data; user; visualisation; graphical

Viable but nonculturable Vibrio cholerae O1 in biofilms in the aquatic environment and their role in cholera transmission - Alam,M.; Sultana,M.; Nair,G. B.; Siddique,A. K.; Hasan,N. A.; Sack,R. B.; Sack,D. A.; Ahmed,K. U.; Sadique,A.; Watanabe,H.; Rita R Colwell (Proceedings of the National Academy of Sciences, 2007)
Vibrio cholerae persists in aquatic environments predominantly in a nonculturable state. In this study coccoid, nonculturable V. cholerae O1 in biofilms maintained for 495 days in Mathbaria, Bangladesh, pond water became culturable upon animal passage. Culturability, biofilm formation, and the wbe, ctxA, and rstR2 genes were monitored by culture, direct fluorescent antibody (DFA), and multiplex PCR. DFA counts were not possible after formation of biofilm. Furthermore, wbe, but not ctxA, were amplifiable, even after incubation for 54 and 68 days at room temperature (≈25°C) and 4°C, respectively, when no growth was detectable. Slower biofilm formation and extended culturability were observed for cultures incubated at 4°C, compared with ≈25°C, suggesting biofilm production to be temperature dependent and linked to loss of culturability. Small colonies appearing after incubation in microcosms for 54 and 68 days at 25°C and 4°C, respectively, were wbe positive and ctxA and rstR2 negative, indicating loss of bacteriophage CTXΦ. The coccoid V. cholerae O1 observed as free cells in microcosms incubated for 495 days could not be cultured, but biofilms in the same microcosms yielded culturable cells. It is concluded that biofilms can act as a reservoir for V. cholerae O1 between epidemics because of its long-term viability in biofilms. In contrast to biofilms produced in Mathbaria pond water, V. cholerae O1 in biofilms present in cholera stools and incubated under identical conditions as the Mathbaria pond water biofilms could not be cultured after 2 months, indicating that those V. cholerae cells freshly discharged into the environment are significantly less robust than cells adapted to environmental conditions.Bangladesh bacteriophage CTXΦ DFA multiplex-PCR ctxA

Vision Geometry XV - Latecki,L.J.; Mount, Dave; Wu,A. Y (Society of Photo-Optical Instrumentation Engineers (SPIE) Conference Series, 2007)

Adaptive Transformation-based Learning for Improving Dictionary Tagging - Karagol-Ayan,Burcu; Doermann, David; Weinberg, Amy (Proceedings of the 11th Conference on European Chapter of the Association for Computational Linguistics, 2006)
We present an adaptive technique that enables users to produce a high quality dictionary parsed into its lexicographic components (headwords, parts of speech, translations, etc.) using an extremely small amount of user provided training data. We use transformation-based learning (TBL) as a postprocessor at two points in the system to improve performance. The results show that the tagging accuracy is increased from 83% and 91% to 93% and 94% for individual words or tokens , and from 64% and 83% to 90% and 93% for contiguous phrases such as definitions or examples of usage.

Analysis and comparison of geometric and algebraic multigrid for convection-diffusion equations - Wu, C. T; Elman, Howard (ANALYSIS, 2006)

Analysis of Shock Motion in a Compression Ramp Configuration using DNS data - Wu,M.; Martin, M.P (Bulletin of the American Physical Society, 2006)

Annotation compatibility working group report - Meyers,A.; Fang,A. C.; Ferro,L.; Kübler,S.; Jia-Lin,T.; Palmer,M.; Poesio,M.; Dolbey,A.; Schuler,K. K.; Loper,E.; Zinsmeister,H.; Penn,G.; et al. (Proceedings of the Workshop on Frontiers in Linguistically Annotated Corpora 2006, 2006)
This report explores the question of compatibility between annotation projects including translating annotation formalisms to each other or to common forms. Compatibility issues are crucial for systems that use the results of multiple annotation projects. We hope that this report will begin a concerted effort in the field to track the compatibility of annotation schemes for part of speech tagging, time annotation, treebanking, role labeling and other phenomena.

Approximation algorithms for channel allocation problems in broadcast networks - Gandhi,Rajiv; Khuller, Samir; Srinivasan, Aravind; Wang,Nan (Networks, 2006)
We study two packing problems that arise in the area of dissemination-based information systems; a second theme is the study of distributed approximation algorithms. The problems considered have the property that the space occupied by a collection of objects together could be significantly less than the sum of the sizes of the individual objects. In the Channel Allocation Problem, there are requests that are subsets of topics. There are a fixed number of channels that can carry an arbitrary number of topics. All the topics of each request must be broadcast on some channel. The load on any channel is the number of topics that are broadcast on that channel; the objective is to minimize the maximum load on any channel. We present approximation algorithms for this problem, and also show that the problem is MAX-SNP hard. The second problem is the Edge Partitioning Problem addressed by Goldschmidt, Hochbaum, Levin, and Olinick (Networks, 41:13–23, 2003). Each channel here can deliver topics for at most k requests, and we aim to minimize the total load on all channels. We present an O(n1/3)–approximation algorithm, and also show that the algorithm can be made fully distributed with the same approximation guarantee; we also generalize the (nondistributed) Edge Partitioning Problem of graphs to the case of hypergraphs. © 2006 Wiley Periodicals, Inc. NETWORKS, Vol. 47(4), 225–236 2006
Keywords: channel allocation problem; distributed approximation algorithm; edge partitioning problem

An architecture for adaptive intrusion-tolerant applications - Pal,Partha; Rubel,Paul; Atighetchi,Michael; Webber,Franklin; Sanders,William H.; Seri,Mouna; Ramasamy,HariGovind; Lyons,James; Courtney,Tod; Agbaria,Adnan; Michel Cukier; Gossett,Jeanna; et al. (Software: Practice and Experience, 2006)
Applications that are part of a mission-critical information system need to maintain a usable level of key services through ongoing cyber-attacks. In addition to the well-publicized denial of service (DoS) attacks, these networked and distributed applications are increasingly threatened by sophisticated attacks that attempt to corrupt system components and violate service integrity. While various approaches have been explored to deal with DoS attacks, corruption-inducing attacks remain largely unaddressed. We have developed a collection of mechanisms based on redundancy, Byzantine fault tolerance, and adaptive middleware that help distributed, object-based applications tolerate corruption-inducing attacks. In this paper, we present the ITUA architecture, which integrates these mechanisms in a framework for auto-adaptive intrusion-tolerant systems, and we describe our experience in using the technology to defend a critical application that is part of a larger avionics system as an example. We also motivate the adaptive responses that are key to intrusion tolerance, and explain the use of the ITUA architecture to support them in an architectural framework. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: adaptive defense; adaptive middleware; Byzantine fault tolerance; intrusion tolerance; redundancy; survivability architecture

An architecture for specification-based detection of semantic integrity violations in kernel dynamic data - Petroni Jr,N. L; Fraser,T.; Walters,A. A; Arbaugh, William A. (Proceedings of the 15th conference on USENIX Security Symposium, 2006)

Automatic web services composition using Shop2 - Hendler,J.; Nau, Dana S.; Parsia,B.; Sirin,E.; Wu,D. (Department of Computer Science, University of Maryland, College Park, 2006)
Semantic markup of Web services will enable the automation of various kinds of tasks, including discovery, composition, and execution of Web services. We describe how an AI planning system (SHOP2) can be used with DAML-S Web service descriptions to automatically compose Web services.

Characterization of the turbulence structure in supersonic boundary layers using DNS data - Ringuette,M. J; Martin, M.P; Smits,A. J.; Wu,M. (AIAA Paper, 2006)

Classification-based spatial error concealment for visual communications - Chen,Meng; Yefeng Zheng; M. Wu (EURASIP J. Appl. Signal Process., 2006)
In an error-prone transmission environment, error concealment is an effective technique to reconstruct the damaged visual content. Due to large variations of image characteristics, different concealment approaches are necessary to accommodate the different nature of the lost image content. In this paper, we address this issue and propose using classification to integrate the state-of-the-art error concealment techniques. The proposed approach takes advantage of multiple concealment algorithms and adaptively selects the suitable algorithm for each damaged image area. With growing awareness that the design of sender and receiver systems should be jointly considered for efficient and reliable multimedia communications, we proposed a set of classification-based block concealment schemes, including receiver-side classification, sender-side attachment, and sender-side embedding. Our experimental results provide extensive performance comparisons and demonstrate that the proposed classification-based error concealment approaches outperform the conventional approaches.

Clef-2005 cl-sr at maryland: Document and query expansion using side collections and thesauri - Wang,J.; Oard, Douglas (Accessing Multilingual Information Repositories, 2006)

Combining bidirectional translation and synonymy for cross-language information retrieval - Wang,Jianqiang; Oard, Douglas (Proceedings of the 29th annual international ACM SIGIR conference on Research and development in information retrieval, 2006)
This paper introduces a general framework for the use of translation probabilities in cross-language information retrieval based on the notion that information retrieval fundamentally requires matching what the searcher means with what the author of a document meant. That perspective yields a computational formulation that provides a natural way of combining what have been known as query and document translation. Two well-recognized techniques are shown to be a special case of this model under restrictive assumptions. Cross-language search results are reported that are statistically indistinguishable from strong monolingual baselines for both French and Chinese documents.
Keywords: cross-language IR; statistical translation

A Communication Interface for Multiprocessor Signal Processing Systems - Sankalita Saha; Bhattacharyya, Shuvra S.; Wayne Wolf (Proceedings of the 2006 IEEE/ACM/IFIP Workshop on Embedded Systems for Real Time Multimedia, 2006)
Parallelization of embedded software is often desirable for power/performance-related considerations for computation-intensive applications that frequently occur in the signal-processing domain. Although hardware support for parallel computation is increasingly available in embedded processing platforms, there is a distinct lack of effective software support. One of the most widely known efforts in support of parallel software is the message passing interface (MPI). However, MPI suffers from several drawbacks with regards to customization to specialized parallel processing contexts, and performance degradation for communication-intensive applications. In this paper, we propose a new interface, the signal passing interface (SPI), that is targeted toward signal processing applications and addresses the limitations of MPI for this important domain of embedded software by integrating relevant properties of MPI and coarse-grain dataflow modeling. SPI is much easier and more intuitive to use, and due to its careful specialization, more performance-efficient for the targeted application domain. We present our preliminary version of SPI, along with experiments using SPI on a practical face detection system that demonstrate the capabilities of SPI
Keywords: application program interfaces; Application software; coarse-grain dataflow modeling; Computer applications; Concurrent computing; Context; data flow graphs; Embedded computing; Embedded software; face detection system; Hardware; Message passing; message passing interface; MPI; Multiprocessing systems; multiprocessor signal processing system; PARALLEL PROCESSING; signal passing interface; Signal processing; SPI

Component Forensics of Digital Cameras: A Non-Intrusive Approach - Swaminathan,A.; Wu,M.; Liu,K. J.R (Information Sciences and Systems, 2006 40th Annual Conference on, 2006)
This paper considers the problem of component forensics and proposes a methodology to identify the algorithms and parameters employed by various processing modules inside a digital camera. The proposed analysis techniques are non-intrusive, using only sample output images collected from the camera to find the color filter array pattern; and the algorithm and parameters of color interpolation employed in cameras. As demonstrated by various case studies in the paper, the features obtained from component forensic analysis provide useful evidence for such applications as detecting technology infringement, protecting intellectual property rights, determining camera source, and identifying image tampering.
Keywords: analysis; image; approach; processing; array; camera; image; Color; colour; detection; optical; filter; filters; forensics; detecting; identification; intellectual; infringement; digital; interpolation; component; intrusive; module; cameras; image; pattern; color; property; protection; non; right; sensors; interpolation; object; tampering; technology

Cross-Path PDMA-Based Error Protection for Streaming Multiuser Video over Multiple Paths - Su,Guan-Ming; Chen,Meng; M. Wu (Image Processing, 2006 IEEE International Conference on, 2006)
In this paper, we consider aggregating multiple video streams and transmitting the merged stream over multiple error-prone paths. We propose a novel multi-stream error protection scheme based on packet division multiplexing access (PDMA) and cross-path forward error coding. Compared with the traditional time division multiplexing access (TDMA)-based error protection scheme, the proposed scheme outperforms 1.43 1.88 dB for the averaged PSNR of all received streams
Keywords: access; error; codes; forward; coding; multiple; coding; video; correction; correction; multi-access; division; error; error-prone; forward; multiplexing; path; multistream; PDMA; cross-path; Protection; scheme; multiuser; streaming; streaming; packet; systems; video; video

Dense Subgraph Computation Via Stochastic Search: Application to Detect Transcriptional Modules - Everett,Logan; Wang,Li-San; Hannenhalli, Sridhar (BioinformaticsBioinformatics, 2006)
Motivation: In a tri-partite biological network of transcription factors, their putative target genes, and the tissues in which the target genes are differentially expressed, a tightly inter-connected (dense) subgraph may reveal knowledge about tissue specific transcription regulation mediated by a specific set of transcription factors—a tissue-specific transcriptional module. This is just one context in which an efficient computation of dense subgraphs in a multi-partite graph is needed.Result: Here we report a generic stochastic search based method to compute dense subgraphs in a graph with an arbitrary number of partitions and an arbitrary connectivity among the partitions. We then use the tool to explore tissue-specific transcriptional regulation in the human genome. We validate our findings in Skeletal muscle based on literature. We could accurately deduce biological processes for transcription factors via the tri-partite clusters of transcription factors, genes, and the functional annotation of genes. Additionally, we propose a few previously unknown TF-pathway associations and tissue-specific roles for certain pathways. Finally, our combined analysis of Cardiac, Skeletal, and Smooth muscle data recapitulates the evolutionary relationship among the three tissues. Contact:sridharh@pcbi.upenn.edu

Development of a Large-Scale Integrated Neurocognitive Architecture Part 1: Conceptual Framework - Reggia, James A.; Tagamets,Malle; Contreras-Vidal,Jose; Weems,Scott; Jacobs, David W.; Winder,Ransom; Chabuk,Timur (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2006)
The idea of creating a general purpose machine intelligence that capturesmany of the features of human cognition goes back at least to the earliest days of artificial intelligence and neural computation. In spite of more than a half-century of research on this issue, there is currently no existing approach to machine intelligence that comes close to providing a powerful, general-purpose human-level intelligence. However, substantial progress made during recent years in neural computation, high performance computing, neuroscience and cognitive science suggests that a renewed effort to produce a general purpose and adaptive machine intelligence is timely, likely to yield qualitatively more powerful approaches to machine intelligence than those currently existing, and certain to lead to substantial progress in cognitive science, AI and neural computation. In this report, we outline a conceptual framework for the long-term development of a large-scale machine intelligence that is based on the modular organization, dynamics and plasticity of the human brain. Some basic design principles are presented along with a review of some of the relevant existing knowledge about the neurobiological basis of cognition. Three intermediate-scale prototypes for parts of a larger system are successfully implemented, providing support for the effectiveness of several of the principles in our framework. We conclude that a human-competitive neuromorphic system for machine intelligence is a viable long- term goal, but that for the short term, substantial integration with more standard symbolic methods as well as substantial research will be needed to make this goal achievable.
Keywords: Technical Report

Development of a Large-Scale Integrated Neurocognitive Architecture - Part 2: Design and Architecture - Reggia, James A.; Tagamets,M.; Contreras-Vidal,J.; Jacobs, David W.; Weems,S.; Naqvi,W.; Winder,R.; Chabuk,T.; Jung,J.; Yang,C. (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2006)
In Part 1 of this report, we outlined a framework for creating an intelligent agentbased upon modeling the large-scale functionality of the human brain. Building on those results, we begin Part 2 by specifying the behavioral requirements of a large-scale neurocognitive architecture. The core of our long-term approach remains focused on creating a network of neuromorphic regions that provide the mechanisms needed to meet these requirements. However, for the short term of the next few years, it is likely that optimal results will be obtained by using a hybrid design that also includes symbolic methods from AI/cognitive science and control processes from the field of artificial life. We accordingly propose a three-tiered architecture that integrates these different methods, and describe an ongoing computational study of a prototype 'mini-Roboscout' based on this architecture. We also examine the implications of some non-standard computational methods for developing a neurocognitive agent. This examination included computational experiments assessing the effectiveness of genetic programming as a design tool for recurrent neural networks for sequence processing, and experiments measuring the speed-up obtained for adaptive neural networks when they are executed on a graphical processing unit (GPU) rather than a conventional CPU. We conclude that the implementation of a large-scale neurocognitive architecture is feasible, and outline a roadmap for achieving this goal.
Keywords: Technical Report

Differential Transcriptional Response to Nonassociative and Associative Components of Classical Fear Conditioning in the Amygdala and Hippocampus - Keeley,Michael B; Wood,Marcelo A; Isiegas,Carolina; Stein,Joel; Hellman,Kevin; Hannenhalli, Sridhar; Abel,Ted (Learning & MemoryLearn. Mem., 2006)
Classical fear conditioning requires the recognition of conditioned stimuli (CS) and the association of the CS with an aversive stimulus. We used Affymetrix oligonucleotide microarrays to characterize changes in gene expression compared to naive mice in both the amygdala and the hippocampus 30 min after classical fear conditioning and 30 min after exposure to the CS in the absence of an aversive stimulus. We found that in the hippocampus, levels of gene regulation induced by classical fear conditioning were not significantly greater than those induced by CS alone, whereas in the amygdala, classical fear conditioning did induce significantly greater levels of gene regulation compared to the CS. Computational studies suggest that transcriptional changes in the hippocampus and amygdala are mediated by large and overlapping but distinct combinations of molecular events. Our results demonstrate that an increase in gene regulation in the amygdala was partially correlated to associative learning and partially correlated to nonassociative components of the task, while gene regulation in the hippocampus was correlated to nonassociative components of classical fear conditioning, including configural learning.

An exploratory study of the W3C mailing list test collection for retrieval of emails with pro/con arguments - Wu,Y.; Oard, Douglas; Soboroff,I. (Proceedings of the Third Conference on Email and Anti-Spam, Mountain View, CA, July, 2006)

Exploring QIM-based anti-collusion fingerprinting for multimedia - Swaminathan,A.; He,S.; Wu,M. (Proceedings of SPIE, 2006)
Digital fingerprinting is an emerging technology to protect multimedia from unauthorizeduse by embedding a unique fingerprint signal into each user’s copy. A robust embedding algorithm is an important building block in order to make the fingerprint resilient to vari- ous distortions and collusion attacks. Spread spectrum embedding has been widely used for multimedia fingerprinting. In this paper, we explore another class of embedding methods – Quantization Index Modulation (QIM) for fingerprinting applications. We first employ Dither Modulation (DM) technique and extend it for embedding multiple symbols through a basic dither sequence design. We then develop a theoretical model and propose a new algorithm to improve the collusion resistance of the basic scheme. Simulation results show that the improvement algorithm enhances the collusion resistance, while there is still a performance gap with the existing spread spectrum based fingerprinting. We then explore coded fingerprinting based on spread transform dither modulation (STDM) embedding. Simulation results show that this coded STDM based fingerprinting has significant advantages over spread spectrum based fingerprinting under blind detection.

Exploring the limits of single-iteration clarification dialogs - Jimmy Lin; Wu,Philip; Demner-Fushman,Dina; Abels,Eileen (Proceedings of the 29th annual international ACM SIGIR conference on Research and development in information retrieval, 2006)
Single-iteration clarification dialogs, as implemented in the TREC HARD track, represent an attempt to introduce interaction into ad hoc retrieval, while preserving the many benefits of large-scale evaluations. Although previous experiments have not conclusively demonstrated performance gains resulting from such interactions, it is unclear whether these findings speak to the nature of clarification dialogs, or simply the limitations of current systems. To probe the limits of such interactions, we employed a human intermediary to formulate clarification questions and exploit user responses. In addition to establishing a plausible upper bound on performance, we were also able to induce an "ontology of clarifications" to characterize human behavior. This ontology, in turn, serves as the input to a regression model that attempts to determine which types of clarification questions are most helpful. Our work can serve to inform the design of interactive systems that initiate user dialogs.
Keywords: interactive retrieval; intermediated search; TREC HARD

Extending the SAND Spatial Database System for the Visualization of Three-Dimensional Scientific Data - Samet, Hanan; Webber,R. E (Geographical Analysis, 2006)
The three-dimensional extension of the SAND (Spatial and Nonspatial Data) spatial database system is described as is its use for data found in scientific visualization applications. The focus is on surface data. Some of the principal operations supported by SAND involve locating spatial objects in the order of their distance from other spatial objects in an incremental manner so that the number of objects that are needed is not known a priori. These techniques are shown to be useful in enabling users to visualize the results of certain proximity queries without having to execute algorithms to completion as is the case when performing a nearest-neighbor query where a Voronoi diagram (i.e., Thiessen polygon) would be computed as a preprocessing step before any attempt to respond to the query could be made. This is achieved by making use of operations such as the spatial join and the distance semijoin. Examples of the utility of such operations is demonstrated in the context of posing meteorological queries to a spatial database with a visualization component.

A feature generation algorithm for sequences with application to splice-site prediction - Islamaj,R.; Getoor, Lise; Wilbur,W. (Knowledge Discovery in Databases: PKDD 2006, 2006)
In this paper we present a new approach to feature selection for sequence data. We identify general feature categories and give construction algorithms for each of them. We show how they can be integrated in a system that tightly couples feature construction and feature selection. This integrated process, which we refer to as feature generation, allows us to systematically search a large space of potential features. We demonstrate the effectiveness of our approach for an important component of the gene finding problem, splice-site prediction. We show that predictive models built using our feature generation algorithm achieve a significant improvement in accuracy over existing, state-of-the-art approaches.

Fingerprinting digital elevation maps - Gou,H.; Wu,M. (Proceedings of SPIE, 2006)
Digital elevation maps (DEMs) provide a digital representation of 3-D terrain information. In civilian appli-cations, high-precision DEMs carry a high commercial value owing to the large amount of effort in acquiring them; and in military applications, DEMs are often used to represent critical geospatial information in sensitive operations. These call for new technologies to prevent unauthorized distribution and to trace traitors in the event of information leak related to DEMs. In this paper, we propose a new digital fingerprinting technique to protect DEM data from illegal re-distribution. The proposed method enables reliable detection of fingerprints from both 3-D DEM data set and its 2-D rendering, whichever format that is available to a detector. Our method starts with extracting from a DEM a set of critical contours either corresponding to important topographic features of the terrain or having application-dependent importance. Fingerprints are then embedded into these critical contours by employing parametric curve modeling and spread spectrum embedding. Finally, a fingerprinted DEM is constructed to incorporate the marked 2-D contours. Through experimental results, we demonstrate the robustness of the proposed method against a number of challenging attacks applied to either DEMs or their contour representations.

First Steps Toward an Electronic Field Guide for Plants - Haibin,Gaurav Agarwal; Agarwal,Gaurav; Ling,Haibin; Jacobs, David W.; Shirdhonkar,Sameer; Kress,W. John; Russell,Rusty; Belhumeur,Peter; Dixit,An; Feiner,Steve; Mahajan,Dhruv; Sunkavalli,Kalyan; et al. (Taxon, 2006)
this paper, we will describe our progress towards building a digital collection of the Smithsonian's type specimens, developing recognition algorithms that can match an image of a leaf to the species of plant from which it comes, and designing user interfaces for interacting with an electronic field guide. To start, we are developing a prototype electronic field guide for the flora of Plummers Island, a small, well-studied island in the Potomac River. This prototype system contains multiple images for each of about 130 species of plants on the island, and should soon grow to cover all 200+ species currently recorded (Shetler et al., 2005). Images of full specimens are available, as well as images of isolated leaves of each species. A zoomable user interface allows a user to browse these images, zooming in on ones of interest. Visual recognition algorithms assist a botanist in locating the specimens that are most relevant to identify the species of a plant. The system currently runs on a small hand-held computer. We will describe the components of this prototype, and also describe some of the future challenges we anticipate if we are to provide botanists in the field with all the resources that are now currently available in the world's museums and herbaria. Type Specimen Digital Collection The first challenge in producing our electronic field guide is to create a digital collection covering all of the Smithsonian's 85,000 vascular plant type specimens. For each type specimen, the database should eventually include systematically acquired high-resolution digital images of the specimen, textual descriptions, links to decision trees, images of live plants, and 3D models. Figure 1: On the left, our set-up at the Smithsonian for digitally photographing type specimens. On the...

Flow algorithms for two pipelined filter ordering problems - Condon,Anne; Deshpande, Amol; Hellerstein,Lisa; Wu,Ning (Proceedings of the twenty-fifth ACM SIGMOD-SIGACT-SIGART symposium on Principles of database systems, 2006)
Pipelined filter ordering is a central problem in database query optimization, and has received renewed attention recently in the context of environments such as the web, continuous high-speed data streams and sensor networks. We present algorithms for two natural extensions of the classical pipelined filter ordering problem: (1) a distributional type problem where the filters run in parallel and the goal is to maximize throughput, and (2) an adversarial type problem where the goal is to minimize the expected value of multiplicative regret. We show that both problems can be solved using similar flow algorithms, which find an optimal ordering scheme in time O(n2), where n is the number of filters. Our algorithm for (1) improves on an earlier O(n3 log n) algorithm of Kodialam.
Keywords: flow algorithms; Pipelined filter ordering; Query optimization; selection ordering

How Multirobot Systems Research will Accelerate our Understanding of Social Animal Behavior - Balch, T.; Dellaert, F.; Feldman, A.; Guillory, A.; Isbell, C.L.; Zia Khan; Pratt, S.C.; Stein, A.N.; Wilde, H. (Proceedings of the IEEE, 2006)
Our understanding of social insect behavior has significantly influenced artificial intelligence (AI) and multirobot systems' research (e.g., ant algorithms and swarm robotics). In this work, however, we focus on the opposite question: "How can multirobot systems research contribute to the understanding of social animal behavior?" As we show, we are able to contribute at several levels. First, using algorithms that originated in the robotics community, we can track animals under observation to provide essential quantitative data for animal behavior research. Second, by developing and applying algorithms originating in speech recognition and computer vision, we can automatically label the behavior of animals under observation. In some cases the automatic labeling is more accurate and consistent than manual behavior identification. Our ultimate goal, however, is to automatically create, from observation, executable models of behavior. An executable model is a control program for an agent that can run in simulation (or on a robot). The representation for these executable models is drawn from research in multirobot systems programming. In this paper we present the algorithms we have developed for tracking, recognizing, and learning models of social animal behavior, details of their implementation, and quantitative experimental results using them to study social insects
Keywords: Acceleration; Animal behavior; ant movement tracking; Artificial intelligence; biology computing; Computer vision; control engineering computing; Insects; Intelligent robots; Labeling; monkey movement tracking; multi-robot systems; multirobot systems; robotics algorithms; Robotics and automation; social animal behavior; social animals; social insect behavior; Speech recognition; tracking

Image Tampering Identification using Blind Deconvolution - Swaminathan,A.; M. Wu; Liu,K. J.R (Image Processing, 2006 IEEE International Conference on, 2006)
Digital images have been used in growing number of applications from law enforcement and surveillance, to medical diagnosis and consumer photography. With such widespread popularity and the presence of low-cost image editing softwares, the integrity of image content can no longer be taken for granted. In this paper, we propose a novel technique based on blind deconvolution to verify image authenticity. We consider the direct output images of a camera as authentic, and introduce algorithms to detect further processing such as tampering applied to the image. Our proposed method is based on the observation that many tampering operations can be approximated as a combination of linear and non-linear components. We model the linear part of the tampering process as a filter, and obtain its coefficients using blind deconvolution. These estimated coefficients are then used to identify possible manipulations. We demonstrate the effectiveness of the proposed image authentication technique and compare our results with existing works
Keywords: (access; approximation; blind; authentication; image; coding; compression; deconvolution; filtering; control); data; deconvolution; camera; consumer; diagnosis; surveillance; tampering; editing; identification; approximation; images; filter; photography; digital; process; image; softwares; medical; theory; biometrics; theory; image

Initial findings from a three-year international case study exploring children's responses to literature in a digital library - Druin, Allison; Massey,S.; Weeks,A. C (Library trends, 2006)

An Interaction-Dependent Model for Transcription Factor Binding - Wang,Li-San; Jensen,Shane; Hannenhalli, Sridhar (Systems Biology and Regulatory GenomicsSystems Biology and Regulatory Genomics, 2006)
Transcriptional regulation is accomplished by several transcription factor proteins that bind to specific DNA elements in the relative vicinity of the gene, and interact with each other and with Polymerase enzyme. Thus the determination of transcription factor-DNA binding is an important step toward understanding transcriptional regulation. An effective way to experimentally determine the genomic regions bound by a transcription factor is by a ChIP-on-chip assay. Then, given the putative genomic regions, computational motif finding algorithms are applied to estimate the DNA binding motif or positional weight matrix for the TF. The a priori expectation is that the presence or absence of the estimated motif in a promoter should be a good indicator of the binding of the TF to that promoter. This association between the presence of the transcription factor motif and its binding is however weak in a majority of cases where the whole genome ChIP experiments have been performed. One possible reason for this is that the DNA binding of a particular transcription factor depends not only on its own motif, but also on synergistic or antagonistic action of neighboring motifs for other transcription factors. We believe that modeling this interaction-dependent binding with linear regression can better explain the observed binding data. We assess this hypothesis based on the whole genome ChIP-on-chip data for Yeast. The derived interactions are largely consistent with previous results that combine ChIP-on-chip data with expression data. We additionally apply our method to determine interacting partners for CREB and validate our findings based on published experimental results.

JET: dynamic join-exit-tree amortization and scheduling for contributory key management - Mao,Yinian; Sun,Yan; M. Wu; Liu,K. J.R (IEEE/ACM Trans. Netw., 2006)
In secure group communications, the time cost associated with key updates in the events of member join and departure is an important aspect of quality of service, especially in large groups with highly dynamic membership. To achieve better time efficiency, we propose a join-exit-tree (JET) key management framework. First, a special key tree topology with join and exit subtrees is introduced to handle key updates for dynamic membership. Then, optimization techniques are employed to determine the capacities of join and exit subtrees for achieving the best time efficiency, and algorithms are designed to dynamically update the join and exit trees. We show that, on average, the asymptotic time cost for each member join/departure event is reduced to O(log (log n)) from the previous cost of O(log n), where n is the group size. Our experimental results based on simulated user activities as well as the real MBone data demonstrate that the proposed JET scheme can significantly improve the time efficiency, while maintaining low communication and computation cost, of tree-based contributory key management.
Keywords: contributory key management; dynamic tree topology; secure group communications; time efficiency

Joint coding and embedding techniques for MultimediaFingerprinting - He,Shan; M. Wu (Information Forensics and Security, IEEE Transactions on, 2006)
Digital fingerprinting protects multimedia content from illegal redistribution by uniquely marking every copy of the content distributed to each user. The collusion attack is a powerful attack where several different fingerprinted copies of the same content are combined together to attenuate or even remove the fingerprints. One major category of collusion-resistant fingerprinting employs an explicit step of coding. Most existing works on coded fingerprinting mainly focus on the code-level issues and treat the embedding issues through abstract assumptions without examining the overall performance. In this paper, we jointly consider the coding and embedding issues for coded fingerprinting systems and examine their performance in terms of collusion resistance, detection computational complexity, and distribution efficiency. Our studies show that coded fingerprinting has efficient detection but rather low collusion resistance. Taking advantage of joint coding and embedding, we propose a permuted subsegment embedding technique and a group-based joint coding and embedding technique to improve the collusion resistance of coded fingerprinting while maintaining its efficient detection. Experimental results show that the number of colluders that the proposed methods can resist is more than three times as many as that of the conventional coded fingerprinting approaches.
Keywords: coding-embedding; coding; collusion-resistant; complexity; computational; data; DETECTION; embedded; EMBEDDING; fingerprinting; group-based; image; joint; multimedia; of; Security; subsegment; systems; technique; techniques

A joint signal processing and cryptographic approach to multimedia encryption - Mao,Yinian; M. Wu (Image Processing, IEEE Transactions on, 2006)
In recent years, there has been an increasing trend for multimedia applications to use delegate service providers for content distribution, archiving, search, and retrieval. These delegate services have brought new challenges to the protection of multimedia content confidentiality. This paper discusses the importance and feasibility of applying a joint signal processing and cryptographic approach to multimedia encryption, in order to address the access control issues unique to multimedia applications. We propose two atomic encryption operations that can preserve standard compliance and are friendly to delegate processing. Quantitative analysis for these operations is presented to demonstrate that a good tradeoff can be made between security and bitrate overhead. In assisting the design and evaluation of media security systems, we also propose a set of multimedia-oriented security scores to quantify the security against approximation attacks and to complement the existing notion of generic data security. Using video as an example, we present a systematic study on how to strategically integrate different atomic operations to build a video encryption system. The resulting system can provide superior performance over both generic encryption and its simple adaptation to video in terms of a joint consideration of security, bitrate overhead, and friendliness to delegate processing.
Keywords: access control; approximation attacks; atomic encryption operations; bitrate overhead; content distribution; cryptographic approach; delegate processing; delegate service providers; generic data security; media security systems; multimedia content confidentiality; m; Computer-Assisted; Computer-Assisted; Information Storage and Retrieval; Multimedia; Signal Processing

Learning user preferences for sets of objects - desJardins, Marie; Eaton,Eric; Wagstaff,Kiri L (Proceedings of the 23rd international conference on Machine learning, 2006)
Most work on preference learning has focused on pairwise preferences or rankings over individual items. In this paper, we present a method for learning preferences over sets of items. Our learning method takes as input a collection of positive examples---that is, one or more sets that have been identified by a user as desirable. Kernel density estimation is used to estimate the value function for individual items, and the desired set diversity is estimated from the average set diversity observed in the collection. Since this is a new learning problem, we introduce a new evaluation methodology and evaluate the learning method on two data collections: synthetic blocks-world data and a new real-world music data collection that we have gathered.

A mammalian promoter model links cis elements to genetic networks - Wang,Junwen; Hannenhalli, Sridhar (Biochemical and Biophysical Research Communications, 2006)
An accurate identification of gene promoters remains an important challenge. Computational approaches for this problem rely on promoter sequence attributes that are believed to be critical for transcription initiation. Here we report a probabilistic model that captures two important properties of promoters, not used by previous methods, viz., the location preference and co-occurrence of promoter elements. Additionally, we found that many of the position-specific DNA elements are strongly linked with the function of the gene product. For instance, a highly conserved motif CCTTT at -1 position is strongly associated with protein synthesis, cellular and tissue development. Our comparative analysis of promoter classes reveals that the promoters devoid of CpG islands are more conserved and have fewer alternative transcription start sites. The discovered links between promoter elements and gene function allows us to infer genetic networks from promoter elements. The web server for the PSPA promoter predictor is available at http://cagr.pcbi.upenn.edu/PSPA.
Keywords: conservation; Core promoter prediction; CpG island; Genetic networks; Position-specific motif; Propensity; Transcription factor binding site (TFBS)

Mapping Multimedia Applications Onto Configurable Hardware With Parameterized Cyclo-Static Dataflow Graphs - Haim,F.; Sen,M.; Ko,Dong-Ik; Bhattacharyya, Shuvra S.; Wolf,W. (Acoustics, Speech and Signal Processing, 2006. ICASSP 2006 Proceedings. 2006 IEEE International Conference on, 2006)
This paper develops methods for model-based design and implementation of image processing applications. We apply our previously developed meta-modeling technique of homogeneous parameterized dataflow (HPDF) (M. Sen et al., 2005) to the framework of cyclostatic dataflow (CSDF) (G. Bilsen et al., 1996), and demonstrate this integrated modeling methodology through hardware mapping of a gesture recognition application. We also provide a comparative study between HPDF/CSDF-based representation of the gesture recognition application, and a previously developed version based on applying HPDF in conjunction with conventional synchronous dataflow (SDF) semantics (M. Sen et al., 2005)
Keywords: configurable hardware; Data communication; Gesture recognition; gesture recognition application; graph theory; hardware mapping; image processing applications; mapping multimedia applications; meta-modeling technique; model-based design; Multimedia communication; parameterized cyclo-static dataflow graphs

Morphology Induction from Limited Noisy Data Using Approximate String Matching - Karagol-Ayan,Burcu; David Doermann; Weinberg, Amy (Proceedings of the Eighth Meeting of the ACL Special Interest Group in Computational Phonology (SIGPHON 2006), 2006)
For a language with limited resources, a dictionary may be one of the few available electronic resources. To make effective use of the dictionary for translation, however, users must be able to access it using the root form of morphologically deformed variant found in the text. Stemming and data driven methods, however, are not suitable when data is sparse. We present algorithms for discovering morphemes from limited, noisy data obtained by scanning a hard copy dictionary. Our approach is based on the novel application of the longest common substring and string edit distance metrics. Results show that these algorithms can in fact segment words into roots and affixes from the limited data contained in a dictionary, and extract affixes. This in turn allows non native speakers to perform multilingual tasks for applications where response must be rapid, and their knowledge is limited. In addition, this analysis can feed other NLP tools requiring lexicons.

Multiuser cross-layer resource allocation for video transmission over wireless networks - Su,Guan-Ming; Man,Zhu; M. Wu; Liu,K. J.R (Network, IEEE, 2006)
With the advancement of video-compression technology and the wide deployment of wireless networks, there is an increasing demand for wireless video communication services, and many design challenges remain to be overcome. In this article, we discuss how to dynamically allocate resources according to the changing environments and requirements, so as to improve the overall system performance and ensure individual quality of service (QoS). Specifically, we consider two aspects with regard to design issues: cross-layer design, which jointly optimizes resource utilization from the physical layer to the application layer, and multiuser diversity, which explores source and channel heterogeneity for different users. We study how to efficiently transmit multiple video streams, encoded by current and future video codecs, over resource-limited wireless networks such as 3G/4G cellular system and future wireless local/metropolitan area networks (WLANs/WMANs)
Keywords: 3G; allocation; multiuser; allocation; video; cellular; channels; quality; codecs; video; coding; video; communication; 4G; communication; data; compression; diversity; cross-layer; diversity; physical; layer; multiple; layer; quality; mobile; networks; 3G; of; reception; multiuser; resource; service; resource; service; video; streaming; streams; multiuser; system; 4G; system; QoS; application; technology; wireless; transmission; video-compression; video

Multiuser distortion management of layered video over resource limited downlink multicode-CDMA - Han,Z.; Su,Guan-Ming; Kwasinski,A.; M. Wu; Liu,K. J.R (Wireless Communications, IEEE Transactions on, 2006)
Transmitting multiple real-time encoded videos to multiple users over wireless cellular networks is a key driving force for developing broadband technology. We propose a new framework to transmit multiple users' video programs encoded by MPEG-4 FGS codec over downlink multicode CDMA networks in real time. The proposed framework jointly manages the rate adaptation of source and channel coding, CDMA code allocation, and power control. Subject to the limited system resources, such as the number of pseudo-random codes and the maximal power for CDMA transmission, we develop an adaptive scheme of distortion management to ensure baseline video quality for each user and further reduce the overall distortion received by all users. To efficiently utilize system resources, the proposed scheme maintains a balanced ratio between the power and code usages. We also investigate three special scenarios where demand, power, or code is limited, respectively. Compared with existing methods in the literature, the proposed algorithm can reduce the overall system's distortion by 14% to 26%. In the demand-limited case and the code-limited but power-unlimited case, the proposed scheme achieves the optimal solutions. In the power-limited but code-unlimited case, the proposed scheme has a performance very close to a performance upper bound
Keywords: (mobile; access; combined; allocation; broadband; case; layered; CDMA; cellular; code; codes; radio; codes; real-time; codes; telecommunication; coding; mobility; coding; video; coding; wireless; communication; control; pseudo-random; control; pseudonoise; control; video; distortion; division; downlink; encoded; limited; links; random; management; management; power; multicode-CDMA; source-channel; multiple; networks; broadband; networks; cellular; radio); power; radio; code; source-channel; technology; code-unlimited; video; multiuser; videos; resource

New DNS results of shockwave/turbulent boundary layer interaction - Wu,M.; Martin, M.P (3rd AIAA Flow Control Conference, 2006)

Non-Intrusive Forensic Analysis of Visual Sensors Using Output Images - Swaminathan,A.; M. Wu; Liu,K. J.R (Acoustics, Speech and Signal Processing, 2006. ICASSP 2006 Proceedings. 2006 IEEE International Conference on, 2006)
This paper considers the problem of non-intrusive forensic analysis of the individual components in visual sensors and its implementation. As a new addition to the emerging area of forensic engineering, we present a framework for analyzing technologies employed inside digital cameras based on output images, and develop a set of forensic signal processing algorithms for visual sensors based on color array sensor and interpolation methods. We show through simulations that the proposed method is robust against compression and noise, and can help identify various processing components inside the camera. Such a non-intrusive forensic framework would provide useful evidence for analyzing technology infringement and evolution for visual sensors
Keywords: algorithms; interpolation; analysis; image; analysis; output; array; cameras; forensic; Color; colour; engineering; forensic; forensic; images; visual; methods; nonintrusive; PROCESSING; sensor; digital; sensors; cameras; image; sensors; interpolation; signal

Nuclear Envelope Dystrophies Show a Transcriptional Fingerprint Suggesting Disruption of Rb–MyoD Pathways in Muscle Regeneration - Bakay,Marina; Wang,Zuyi; Melcon,Gisela; Schiltz,Louis; Xuan,Jianhua; Zhao,Po; Sartorelli,Vittorio; Seo,Jinwook; Pegoraro,Elena; Angelini,Corrado; Shneiderman, Ben; Escolar,Diana; et al. (BrainBrain, 2006)
Mutations of lamin A/C (LMNA) cause a wide range of human disorders, including progeria, lipodystrophy, neuropathies and autosomal dominant Emery–Dreifuss muscular dystrophy (EDMD). EDMD is also caused by X-linked recessive loss-of-function mutations of emerin, another component of the inner nuclear lamina that directly interacts with LMNA. One model for disease pathogenesis of LMNA and emerin mutations is cell-specific perturbations of the mRNA transcriptome in terminally differentiated cells. To test this model, we studied 125 human muscle biopsies from 13 diagnostic groups (125 U133A, 125 U133B microarrays), including EDMD patients with LMNA and emerin mutations. A Visual and Statistical Data Analyzer (VISDA) algorithm was used to statistically model cluster hierarchy, resulting in a tree of phenotypic classifications. Validations of the diagnostic tree included permutations of U133A and U133B arrays, and use of two probe set algorithms (MAS5.0 and MBEI). This showed that the two nuclear envelope defects (EDMD LMNA, EDMD emerin) were highly related disorders and were also related to fascioscapulohumeral muscular dystrophy (FSHD). FSHD has recently been hypothesized to involve abnormal interactions of chromatin with the nuclear envelope. To identify disease-specific transcripts for EDMD, we applied a leave-one-out (LOO) cross-validation approach using LMNA patient muscle as a test data set, with reverse transcription–polymerase chain reaction (RT–PCR) validations in both LMNA and emerin patient muscle. A high proportion of top-ranked and validated transcripts were components of the same transcriptional regulatory pathway involving Rb1 and MyoD during muscle regeneration (CRI-1, CREBBP, Nap1L1, ECREBBP/p300), where each was specifically upregulated in EDMD. Using a muscle regeneration time series (27 time points) we develop a transcriptional model for downstream consequences of LMNA and emerin mutations. We propose that key interactions between the nuclear envelope and Rb and MyoD fail in EDMD at the point of myoblast exit from the cell cycle, leading to poorly coordinated phosphorylation and acetylation steps. Our data is consistent with mutations of nuclear lamina components leading to destabilization of the transcriptome in differentiated cells.
Keywords: EDMD = Emery–Dreifuss muscular dystrophy; emerin; Emery-Dreifuss muscular dystrophy; FSHD = fascioscapulohumeral muscular dystrophy; IDG = individual discriminatory genes; JDG = jointly discriminatory genes; lamin A/C; LGMD = limb-girdle muscular dystrophy; LOO = leave-one-out; RT–PCR = reverse transcription–polymerase chain reaction; VISDA = Visual and Statistical Data Analyzer; Skeletal muscle; wFC = weighted Fisher criterion

Participatory, embodied, multi-agent simulation - Blikstein,Paulo; Rand, William; Wilensky,Uri (Proceedings of the fifth international joint conference on Autonomous agents and multiagent systems, 2006)
We will demonstrate the integration of a software-based multi-agent modeling platform with a participatory simulation environment and real-time control over a physical agent (robot). Both real and virtual participants will be able to act as agents in a simulation that will control a physical agent. The backbone of this demonstration is a widely used, freely available, mature modeling platform known as NetLogo.
Keywords: embedded agents; multi-agent simulation; participatory simulation; ROBOTICS; Sensors

Quantifying the effects of routing dynamics on end-to-end Internet path failures - Wang,F.; Feamster, Nick; Gao,L. (University of Massachusetts, 2006)

Query planning in the presence of overlapping sources - Bleiholder,J.; Khuller, Samir; Naumann,F.; Raschid, Louiqa; Wu,Y. (Advances in Database Technology-EDBT 2006, 2006)
Navigational queries on Web-accessible life science sources pose unique query optimization challenges. The objects in these sources are interconnected to objects in other sources, forming a large and complex graph, and there is an overlap of objects in the sources. Answering a query requires the traversal of multiple alternate paths through these sources. Each path can be associated with the benefit or the cardinality of the target object set (TOS) of objects reached in the result. There is also an evaluation cost of reaching the TOS.We present dual problems in selecting the best set of paths. The first problem is to select a set of paths that satisfy a constraint on the evaluation cost while maximizing the benefit (number of distinct objects in the TOS). The dual problem is to select a set of paths that satisfies a threshold of the TOS benefit with minimal evaluation cost. The two problems can be mapped to the budgeted maximum coverage problem and the maximal set cover with a threshold. To solve these problems, we explore several solutions including greedy heuristics, a randomized search, and a traditional IP/LP formulation with bounds. We perform experiments on a real-world graph of life sciences objects from NCBI and report on the computational overhead of our solutions and their performance compared to the optimal solution.

Query planning in the presence of overlapping sources - Bleiholder,J.; Khuller, Samir; Naumann,F.; Raschid, Louiqa; Wu,Y. (Advances in Database Technology-EDBT 2006, 2006)

Query Rewriting in the Semantic Web7 - Vidal,Maria Esther; Raschid, Louiqa; Marquez,Natalia; Cardenas,Marelis; Yao Wu (Data Engineering Workshops, 22nd International Conference on, 2006)
The widespread explosion of Web accessible resources has lead to a new challenge of locating all relevant resources and identifying the best ones to answer a query. This challenge has to address the difficult task of ranking the resources based on user needs, as well as the more expensive computational task of determining all the solutions to answer a query. In this paper, we define a Top K problem for query rewriting on the Semantic Web. We first introduce a three level data model composed of the ontology level, the physical level of the physical resources, and the data level composed of the entries in the different resources. We present a query language for Top K navigational queries over ontology concepts. We then sketch the outline of an efficient search algorithm to compute an approximation of the Top K rewriting options to produce source paths among the physical resources. We briefly discuss the results of an experimental study

Revisiting Internet addressing: Back to the future - Vutukuru,M.; Feamster, Nick; Walfish,M.; Balakrishnan,H.; Shenker,S. (Massachusetts Institute of Technology Computer Science and Artificial Intelligence Laboratory, 2006)
IP prefixes undermine three goals of Internet routing:accurate reflection of network-layer reachability, secure routing messages, and effective traffic control. This pa- per presents Atomic IP (AIP), a simple change to Inter- net addressing (which in fact reverts to how addressing once worked), that allows Internet routing to achieve these goals.

Robust and secure image hashing - Swaminathan,A.; Mao,Yinian; M. Wu (Information Forensics and Security, IEEE Transactions on, 2006)
Image hash functions find extensive applications in content authentication, database search, and watermarking. This paper develops a novel algorithm for generating an image hash based on Fourier transform features and controlled randomization. We formulate the robustness of image hashing as a hypothesis testing problem and evaluate the performance under various image processing operations. We show that the proposed hash function is resilient to content-preserving modifications, such as moderate geometric and filtering distortions. We introduce a general framework to study and evaluate the security of image hashing systems. Under this new framework, we model the hash values as random variables and quantify its uncertainty in terms of differential entropy. Using this security framework, we analyze the security of the proposed schemes and several existing representative methods for image hashing. We then examine the security versus robustness tradeoff and show that the proposed hashing methods can provide excellent security and robustness.
Keywords: content-preserving; cryptography; differential; distortions; entropy; Filtering; Fourier; functions; hash; hashing; image; modifications; processing; secure; theory; transform; transforms

A Scalable Multiuser Framework for Video Over OFDM Networks: Fairness and Efficiency - Su,Guan-Ming; Han,Zhu; M. Wu; Liu,K. J.R (Circuits and Systems for Video Technology, IEEE Transactions on, 2006)
In this paper, we propose a framework to transmit multiple scalable video programs over downlink multiuser orthogonal frequency division multiplex (OFDM) networks in real time. The framework explores the scalability of the video codec and multidimensional diversity of multiuser OFDM systems to achieve the optimal service objectives subject to constraints on delay and limited system resources. We consider two essential service objectives, namely, the fairness and efficiency. Fairness concerns the video quality deviation among users who subscribe the same quality of service, and efficiency relates to how to attain the highest overall video quality using the available system resources. We formulate the fairness problem as minimizing the maximal end-to-end distortion received among all users and the efficiency problem as minimizing total end-to-end distortion of all users. Fast suboptimal algorithms are proposed to solve the above two optimization problems. The simulation results demonstrated that the proposed fairness algorithm outperforms a time division multiple (TDM) algorithm by 0.5 3 dB in terms of the worst received video quality among all users. In addition, the proposed framework can achieve a desired tradeoff between fairness and efficiency. For achieving the same average video quality among all users, the proposed framework can provide fairer video quality with 1 1.8 dB lower PSNR deviation than a TDM algorithm
Keywords: algorithm; video; codec; video; coding; video; communication; deviation; downlink; deviation; OFDM; distortion; multidimensional; diversity; multiple; division; end-to-end; framework; time; Frequency; modulation; diversity; multiple; multiplex; multiuser; network; efficiency; networks; video; objectives; optimization; of; OFDM; orthogonal; over; problem; fairness; problem; maximal; problems; quality; programs; multiuser; PSNR; QUALITY; reception; image; resolution; optimisation; quality; scalable; service; service; scalable; service; video; systems; optimal; video

Schistosoma mansoni (Platyhelminthes, Trematoda) nuclear receptors: Sixteen new members and a novel subfamily - Wu,Wenjie; Niles,Edward G.; El‐Sayed, Najib M.; Berriman,Matthew; LoVerde,Philip T. (Gene, 2006)
Nuclear receptors (NRs) are important transcriptional modulators in metazoans. Sixteen new NRs were identified in the Platyhelminth trematode, Schistosoma mansoni. Three were found to possess novel tandem DNA-binding domains that identify a new subfamily of NR. Two NRs are homologues of the thyroid hormone receptor that previously were thought to be restricted to chordates. This study brings the total number of identified NR in S. mansoni to 21. Phylogenetic and comparative genomic analyses demonstrate that S. mansoni NRs share an evolutionary lineage with that of arthropods and vertebrates. Phylogenic analysis shows that more than half of the S. mansoni nuclear receptors evolved from a second gene duplication. As the second gene duplication of NRs was thought to be specific to vertebrates, our data challenge the current theory of NR evolution.
Keywords: Nuclear receptors; Schistosoma mansoni

Security Issues in Cooperative Communications: Tracing Adversarial Relays - Mao,Yinian; M. Wu (Acoustics, Speech and Signal Processing, 2006. ICASSP 2006 Proceedings. 2006 IEEE International Conference on, 2006)
Cooperative communication system explores a new dimension of diversity in wireless communications to combat unfriendly wireless environment through strategic relays. While this emerging technology is promising in improving communication quality, some security problems inherent to cooperative relay also arise. In this paper we investigate the security issues in cooperative communications that consist of multiple relay nodes using decode-and-forward strategy. In particular, we consider the situation where one of the relay nodes is adversarial and tries to corrupt the communications by sending garbled signals. We show that the conventional physical-layer signal detection will not be effective in such a scenario, and the application-layer cryptography alone is not sufficient to identify the adversarial relay. To combat adversarial relay, we propose a cross-layer scheme that uses pseudo-random tracing symbols, with an adaptive signal detection rule at the physical layer, and direct sequence spread spectrum symbol construction at the application layer for tracing and identifying adversarial relay. Our experimental simulations show that the proposed tracing scheme is effective and efficient
Keywords: adaptive; Communication; communications; adaptive; construction; multiple; detection; adversarial; detection; decoding; radiocommunication; telecommunication; issues; strategic; nodes; pseudo-random; relay; relay; decode-and-forward; relays; cooperative; relays; wireless; security; sequence; signal; spectrum; spread; strategy; direct; symbol; symbols; security; system; cooperative; tracing

Structure of social contact networks and their impact on epidemics - Eubank,S.; Kumar,V. S.A; Marathe,M. V; Srinivasan, Aravind; Wang,N. (DIMACS Series in Discrete Mathematics and Theoretical Computer Science, 2006)
Traditional epidemiological research has focused on rate-based differential-equation models on completely mixing populations. In this paper, we outline an approach based on a combination of net- work theory and discrete-event simulations to study epidemics in large urban areas. We survey some of our results published in Nature (2004) and the Proc. ACM-SIAM Symposium on Discrete Algorithms (2004), and present some new results on: (i) mathematical properties of large social contact networks, as well as (ii) simulation-based dynamic anal- ysis of disease-spread in such networks. We identify a number of new measures that are significant for understanding epidemics and for devel- oping new strategies in policy planning. We also perform a very detailed structural analysis of the social contact networks produced by TRAN- SIMS, a simulator for detailed transportation/traffic studies, and study two random graph models to generate realistic social networks: Chung- Lu’s model and the configuration model. We also develop combinatorial formulations and approximation algorithms for quarantining, vaccina- tion and sensor placement, as aids to decision-making.

System and method for locating a closest server in response to a client ... - Andrews,Matthew; Hofmann,Markus; Shepherd,Bruce; Srinivasan, Aravind; Winkler,Peter; Zane,Francis (2006)
A scalable system and method for locating a closest server in response to a client request via an interactive distribution network, such as the Internet, are provided. A closest content server is defined as having the least round trip time for responding to a client request. The system including a plurality of content servers; and a local server in communication with a plurality of clients, the local server acting as a proxy for communicating client requests from clients to a redirection server. Client network distance and load information is periodically collected at each content server in the network from clients communicating with each of the respective content servers. The redirection server periodically aggregates the network distance and load information from each content server to create client clusters from both current and previously aggregated network distance and load information. Each client cluster represents a division or partition of the total IP address space. Each...

Transcriptional Genomics Associates FOX Transcription Factors With Human Heart Failure - Hannenhalli, Sridhar; Putt,Mary E.; Gilmore,Joan M.; Wang,Junwen; Parmacek,Michael S.; Epstein,Jonathan A.; Morrisey,Edward E.; Margulies,Kenneth B.; Cappola,Thomas P. (Circulation, 2006)
Background— Specific transcription factors (TFs) modulate cardiac gene expression in murine models of heart failure, but their relevance in human subjects remains untested. We developed and applied a computational approach called transcriptional genomics to test the hypothesis that a discrete set of cardiac TFs is associated with human heart failure.Methods and Results— RNA isolates from failing (n=196) and nonfailing (n=16) human hearts were hybridized with Affymetrix HU133A arrays, and differentially expressed heart failure genes were determined. TF binding sites overrepresented in the −5-kb promoter sequences of these heart failure genes were then determined with the use of public genome sequence databases. Binding sites for TFs identified in murine heart failure models (MEF2, NKX, NF-AT, and GATA) were significantly overrepresented in promoters of human heart failure genes (P<0.002; false discovery rate 2% to 4%). In addition, binding sites for FOX TFs showed substantial overrepresentation in both advanced human and early murine heart failure (P<0.002 and false discovery rate <4% for each). A role for FOX TFs was supported further by expression of FOXC1, C2, P1, P4, and O1A in failing human cardiac myocytes at levels similar to established hypertrophic TFs and by abundant FOXP1 protein in failing human cardiac myocyte nuclei.Conclusions— Our results provide the first evidence that specific TFs identified in murine models (MEF2, NKX, NFAT, and GATA) are associated with human heart failure. Moreover, these data implicate specific members of the FOX family of TFs (FOXC1, C2, P1, P4, and O1A) not previously suggested in heart failure pathogenesis. These findings provide a crucial link between animal models and human disease and suggest a specific role for FOX signaling in modulating the hypertrophic response of the heart to stress in humans.

Trypanosoma cruzi mitochondrial maxicircles display species- and strain-specific variation and a conserved element in the non-coding region - Westenberger,Scott; Cerqueira,Gustavo; El‐Sayed, Najib M.; Zingales,Bianca; Campbell,David; Sturm,Nancy (BMC Genomics, 2006)
BACKGROUND:The mitochondrial DNA of kinetoplastid flagellates is distinctive in the eukaryotic world due to its massive size, complex form and large sequence content. Comprised of catenated maxicircles that contain rRNA and protein-coding genes and thousands of heterogeneous minicircles encoding small guide RNAs, the kinetoplast network has evolved along with an extreme form of mRNA processing in the form of uridine insertion and deletion RNA editing. Many maxicircle-encoded mRNAs cannot be translated without this post-transcriptional sequence modification.RESULTS:We present the complete sequence and annotation of the Trypanosoma cruzi maxicircles for the CL Brener and Esmeraldo strains. Gene order is syntenic with Trypanosoma brucei and Leishmania tarentolae maxicircles. The non-coding components have strain-specific repetitive regions and a variable region that is unique for each strain with the exception of a conserved sequence element that may serve as an origin of replication, but shows no sequence identity with L. tarentolae or T. brucei. Alternative assemblies of the variable region demonstrate intra-strain heterogeneity of the maxicircle population. The extent of mRNA editing required for particular genes approximates that seen in T. brucei. Extensively edited genes were more divergent among the genera than non-edited and rRNA genes. Esmeraldo contains a unique 236-bp deletion that removes the 5'-ends of ND4 and CR4 and the intergenic region. Esmeraldo shows additional insertions and deletions outside of areas edited in other species in ND5, MURF1, and MURF2, while CL Brener has a distinct insertion in MURF2.CONCLUSION:The CL Brener and Esmeraldo maxicircles represent two of three previously defined maxicircle clades and promise utility as taxonomic markers. Restoration of the disrupted reading frames might be accomplished by strain-specific RNA editing. Elements in the non-coding region may be important for replication, transcription, and anchoring of the maxicircle within the kinetoplast network.

The turbulence structure of shockwave and boundary layer interaction in a compression corner - Martin, M.P; Smits,A.; Wu,M.; Ringuette,M. (44th AIAA Aerospace Meeting and Exhibit, 2006)
Shockwave and turbulent boundary layer interactions (STBLI) result in intense localizedheating rates and pressure loads, making them extremely important flow features that must be identified for engineering design. The absence of detailed and complete experimental and numerical data at the same flow and boundary conditions is one of the major stumbling blocks in the development of accurate turbulence models for the prediction of STBLI. We use a set of direct numerical simulation data (Wu & Martin, 2006) that has been validated against experiments (Bookey et al., 2005) at the same conditions to present detailed flow features of the STBLI over a compression corner at Mach 3 and low Reynolds number with Reθ=2100. Details regarding the evolution of the turbulence structure angle, characteristic streamwise length scales, and hairpin packets through the interaction are presented. The three-dimensionality of the turbulence field and main shock are illustrated and the strength of shocks and shocklets through the interaction are considered.

VAST 2006 Contest - A Tale of Alderwood - Grinstein,G.; O'Connell,T.; Laskowski,S.; Plaisant, Catherine; Scholtz,J.; Whiting,M. (Visual Analytics Science And Technology, 2006 IEEE Symposium On, 2006)
Visual analytics experts realize that one effective way to push the field forward and to develop metrics for measuring the performance of various visual analytics components is to hold an annual competition. The first visual analytics science and technology (VAST) contest was held in conjunction with the 2006 IEEE VAST Symposium. The competition entailed the identification of possible political shenanigans in the fictitious town of Alderwood. A synthetic data set was made available as well as tasks. We summarize how we prepared and advertised the contest, developed some initial metrics for evaluation, and selected the winners. The winners were invited to participate at an additional live competition at the symposium to provide them with feedback from senior analysts
Keywords: Alderwood; human; analysis; data; analytics; and; contest; data; information; interaction; sense; making; visual; Science; technology; visualisation

Verification and Validation through Replication: A Case Study Using Axelrod and Hammond’s Ethnocentrism Model - Rand, William; Wilensky,U. (North American Association for Computational Social and Organization Sciences (NAACSOS), 2006)
Recent years have seen a proliferation of agent-based models (ABMs), but with the exceptionof a few "classic" models, most of these models have never been replicated. We argue that replication has even greater benefits when applied to computational models than when applied to physical experiments. Replication affects model verification, in that it aids in determining if the implemented model reflects the conceptual model. It affects model validation, since a replication of a conceptual model may change the output from an implemented model and thus alter the correspondence between the model and the real world. Replication also affects validation by forcing the model developer and replicator to re-examine assumptions made in the original model. In addition replication fosters shared understanding of the details of modeling decisions within the research community. To facilitate the practice of replication, we argue for the creation of standards for both how to replicate models and how to evaluate the replication. In this paper, we present a case study of our attempt to replicate an ABM developed by Axelrod and Hammond. We detail our effort to replicate that model and the challenges that arose in recreating the model and in determining if the replication was successful.

Widgets, Planets, and Demons: the Case for the Integration of Human, Embedded, and Virtual Agents via Mediation - Rand, William; Blikstein,P.; Wilensky,U. (Proceedings of Swarmfest, 2006)

Active Constrained Clustering by Examining Spectral Eigenvectors - Xu,Qianjun; desJardins, Marie; Wagstaff,Kiri (Discovery ScienceDiscovery Science, 2005)
This work focuses on the active selection of pairwise constraints for spectral clustering. We develop and analyze a technique for Active Constrained Clustering by Examining Spectral eigenvectorS (ACCESS) derived from a similarity matrix. The ACCESS method uses an analysis based on the theoretical properties of spectral decomposition to identify data items that are likely to be located on the boundaries of clusters, and for which providing constraints can resolve ambiguity in the cluster descriptions. Empirical results on three synthetic and five real data sets show that ACCESS significantly outperforms constrained spectral clustering using randomly selected constraints.

Anti-collusion forensics of multimedia fingerprinting using orthogonal modulation - Wang,Z.J.; M. Wu; Zhao,H.V.; Trappe,W.; Liu,K. J.R (Image Processing, IEEE Transactions on, 2005)
Digital fingerprinting is a method for protecting digital data in which fingerprints that are embedded in multimedia are capable of identifying unauthorized use of digital content. A powerful attack that can be employed to reduce this tracing capability is collusion, where several users combine their copies of the same content to attenuate/remove the original fingerprints. In this paper, we study the collusion resistance of a fingerprinting system employing Gaussian distributed fingerprints and orthogonal modulation. We introduce the maximum detector and the thresholding detector for colluder identification. We then analyze the collusion resistance of a system to the averaging collusion attack for the performance criteria represented by the probability of a false negative and the probability of a false positive. Lower and upper bounds for the maximum number of colluders Kmax are derived. We then show that the detectors are robust to different collusion attacks. We further study different sets of performance criteria, and our results indicate that attacks based on a few dozen independent copies can confound such a fingerprinting system. We also propose a likelihood-based approach to estimate the number of colluders. Finally, we demonstrate the performance for detecting colluders through experiments using real images.
Keywords: Automated; Product Labeling; Signal Processing; Computer-Assisted; Computer-Assisted; Multimedia; Patents as Topic; Pattern Recognition; Gaussian distribution; anticollusion forensic; colluder identification; collusion resistance; digital fingerprinting; false probability; likelihood-based approach; multimedia fingerprinting; orthogonal modulation; spread spectrum embedding; Gaussian distribution; fi

Applications of SHOP and SHOP2 - Nau, Dana S.; Au,T.-C.; Ilghami,O.; Kuter,U.; Wu,D.; Yaman,F.; Munoz-Avila,H.; Murdock,J. W. (Intelligent Systems, IEEE, 2005)
We design the simple hierarchical ordered planner (SHOP) and its successor, SHOP2, with two goals in mind: to investigate research issues in automated planning and to provide some simple, practical planning tools. SHOP and SHOP2 are based on a planning formalism called hierarchical task network planning. SHOP and SHOP2 use a search-control strategy called ordered task decomposition, which breaks tasks into subtasks and generates the plan's actions in the same order that the plan executor executes them. So, throughout the planning process, the planner can tell what the state of the world at each step of the plan.
Keywords: automated planning; hierarchical task network planning; ordered task decomposition; planning (artificial intelligence); problem solving; search-control strategy; simple hierarchical ordered planner; trees (mathematics); uncertainty handling

An architectural level design methodology for embedded face detection - Kianzad,V.; Saha,S.; Schlessman,J.; Aggarwal,G.; Bhattacharyya, Shuvra S.; Wolf,W.; Chellapa, Rama (Proceedings of the 3rd IEEE/ACM/IFIP international conference on Hardware/software codesign and system synthesis, 2005)
Face detection and recognition research has attracted great attention in recent years. Automatic face detection has great potential in a large array of application areas, including banking and security system access control, video surveillance, and multimedia information retrieval. In this paper, we discuss an architectural level design methodology for implementation of an embedded face detection system on a reconfigurable system on chip. We present models for performance estimation and validate these models with experimental values obtained from implementing our system on an FPGA platform. This modeling approach is shown to be efficient, accurate, and intuitive for designers to work with. Using this approach, we present several design options that trade-off various architectural features.
Keywords: design space exploration; Face detection; platforms; reconfigurable; system-level models

Assessment of STBLI DNS data and comparison against experiments - Wu,M.; Taylor,E. M; Martin, M.P (AIAA paper, 2005)

Automated checking for Windows host vulnerabilities - Tamizi,M.; Weinstein,M.; Michel Cukier (2005)
Evaluation of computing system security requires knowledge of the vulnerabilities present in the system and of potential attacks against the system. Vulnerabilities can be classified based on their location as application vulnerabilities, network vulnerabilities, or host vulnerabilities. This paper describes Ferret-Windows, a new software tool for checking host vulnerabilities on the Windows platforms. This tool helps system administrators by quickly finding vulnerabilities that are present on a host. It is designed and implemented in a modular way: a plug-in module is used for each vulnerability checked, and each possible output format is specified by a plug-in module. Moreover, several vulnerability fixing plug-in modules exist to help users remove specific vulnerabilities. As a result, Ferret-Windows is extensible, and can easily be kept up-to-date through the addition of checks for new vulnerabilities as they are identified. Finally, Ferret-Windows is a freely available open-source software
Keywords: application vulnerabilities; computing system security; Ferret-Windows software tool; host vulnerabilities; network vulnerabilities; open-source software; operating systems (computers); plug-in module; program diagnostics; security of data; software reliability; software tools; system attacks; Windows host vulnerability checking; Windows platforms

Automatic Mining of Source Code Repositories to Improve Bug Finding Techniques - Williams, Chadd C; Hollingsworth, Jeffrey K (IEEE Transactions on Software Engineering, 2005)
We describe a method to use the source code change history of a software project to drive and help to refine the search for bugs. Based on the data retrieved from the source code repository, we implement a static source code checker that searches for a commonly fixed bug and uses information automatically mined from the source code repository to refine its results. By applying our tool, we have identified a total of 178 warnings that are likely bugs in the Apache Web server source code and a total of 546 warnings that are likely bugs in Wine, an open-source implementation of the Windows API. We show that our technique is more effective than the same static analysis that does not use historical data from the source code repository.
Keywords: configuration control; debugging aids.; index terms- testing tools; version control

Bootstrapping parsers via syntactic projection across parallel texts - Hwa,Rebecca; Resnik, Philip; Weinberg, Amy; Cabezas,Clara; Kolak,Okan (Nat. Lang. Eng., 2005)
Broad coverage, high quality parsers are available for only a handful of languages. A prerequisite for developing broad coverage parsers for more languages is the annotation of text with the desired linguistic representations (also known as “treebanking”). However, syntactic annotation is a labor intensive and time-consuming process, and it is difficult to find linguistically annotated text in sufficient quantities. In this article, we explore using parallel text to help solving the problem of creating syntactic annotation in more languages. The central idea is to annotate the English side of a parallel corpus, project the analysis to the second language, and then train a stochastic analyzer on the resulting noisy annotations. We discuss our background assumptions, describe an initial study on the “projectability” of syntactic relations, and then present two experiments in which stochastic parsers are developed with minimal human intervention via projection from English.

Breaking the resource bottleneck for multilingual parsing - Hwa,R.; Resnik, Philip; Weinberg, Amy (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2005)
We propose a framework that enables the acquisition of annotation-heavy resources such as syntacfic dependency tree corpora for low-resource languages by importing linguistic annotations from high-quality English resources. We present a large-scale experiment showing that Chinese dependency trees can be induced by using an English parser, a word alignment package, and a large corpus of sentence-aligned bilingual text. As a part of the experiment, we evaluate the quality of a Chinese parser trained on the induced dependency treebank. We find that a parser trained in this manner out-performs some simple baselines inspite of the noise in the induced treebank. The results suggest that projecting syntactic structures from English is a viable option for acquiring annotated syntactic structures quickly and cheaply. We expect the quality of the induced treebank to improve when more sophisticated filtering and error-correction techniques are applied.

Broadcasting on networks of workstations - Khuller, Samir; Kim,Yoo-Ah; Wan,Yung-Chun Justin (Proceedings of the seventeenth annual ACM symposium on Parallelism in algorithms and architectures, 2005)
Broadcasting and multicasting are fundamental operations. In this work we develop algorithms for performing broadcast and multicast in clusters of workstations. In this model, sending a message from one machine to another machine in the same cluster takes 1 time unit, and sending a message to a machine in a different cluster takes C time units. Lowekamp and Beguelin proposed heuristics for this model, but their algorithms may produce broadcast times that are arbitrarily worse than optimal. We develop the first constant factor approximation algorithms for this model. Algorithm LCF (Largest Cluster First) for the basic model is simple, efficient and has a worst case approximation guarantee of 2. We then extend these models to more complex models where we remove the assumption that an unbounded amount of simultaneous communication may happen using the global network. The algorithms for these models build on the LCF method developed for the basic problem. Finally, we develop broadcasting algorithms for the postal model where the sending processor does not block for C time units when the message is in transit. Moreover, we assume that the messages are small and so the bottleneck is the latency.
Keywords: Approximation algorithms; Broadcasting; multicasting

Building efficient and effective multimedia fingerprints via joint coding and embedding - He,Shan; M. Wu (Proceedings of the 7th workshop on Multimedia and security, 2005)
Digital fingerprinting protects multimedia content from illegal redistribution by uniquely marking every copy of the content distributed to each user. One major category of collusion-resistant fingerprinting employs an explicit step of coding. Most existing works on coded fingerprinting mainly focus on the code-level issues and treat the embedding issues through abstract assumptions without examining the overall performance. In this paper, we jointly consider the coding and embedding issues for coded fingerprinting systems and examine their performance in terms of collusion resistance, detection computational complexity, and distribution efficiency. Our studies show that coded fingerprinting has efficient detection but rather low collusion resistance. Taking advantage of joint coding and embedding, we propose two new techniques, namely, a Permuted Subsegment Embedding technique and a Group-based Joint Coding and Embedding (GRACE) technique, to improve the collusion resistance of coded fingerprinting while maintaining its efficient detection. Experimental results show that the number of colluders that the proposed methods can resist is more than three times as many as that of the conventional coded fingerprinting approaches.
Keywords: collusion resistance; error correcting code; multimedia fingerprinting

Collusion resistance analysis of multimedia fingerprinting systems - Wang,Z.J.; Wu,M.; Zhao,H.V.; Trappe,W.; Liu,K. J.R (IEEE Tran. on Image Processing, 2005)

Comparative Genomics of Trypanosomatid Parasitic Protozoa - El‐Sayed, Najib M.; Myler,Peter J.; Blandin,Gaëlle; Berriman,Matthew; Crabtree,Jonathan; Aggarwal,Gautam; Caler,Elisabet; Renauld,Hubert; Worthey,Elizabeth A.; Hertz-Fowler,Christiane; Ghedin,Elodie; Peacock,Christopher; et al. (Science, 2005)
A comparison of gene content and genome architecture of Trypanosoma brucei, Trypanosoma cruzi, and Leishmania major, three related pathogens with different life cycles and disease pathology, revealed a conserved core proteome of about 6200 genes in large syntenic polycistronic gene clusters. Many species-specific genes, especially large surface antigen families, occur at nonsyntenic chromosome-internal and subtelomeric regions. Retroelements, structural RNAs, and gene family expansion are often associated with syntenic discontinuities that—along with gene divergence, acquisition and loss, and rearrangement within the syntenic regions—have shaped the genomes of each parasite. Contrary to recent reports, our analyses reveal no evidence that these species are descended from an ancestor that contained a photosynthetic endosymbiont.

Computer vision on FPGAs: Design methodology and its application to gesture recognition - Sen,M.; Corretjer,I.; Haim,F.; Saha,S.; Bhattacharyya, Shuvra S.; Schlessman,J.; Wolf,W. (Computer Vision and Pattern Recognition-Workshops, 2005. CVPR Workshops. IEEE Computer Society Conference on, 2005)

Coordinated sensor deployment for improving secure communications and sensing coverage - Mao,Yinian; M. Wu (Proceedings of the 3rd ACM workshop on Security of ad hoc and sensor networks, 2005)
Sensor network has a great potential in applications such as habitat monitoring, wildlife tracking, building surveillance, and military combat. The design of a sensor network system involves several important issues, including the sensing coverage, node-to-node or node-to-base-station communications, and the security in information gathering and relay by the sensors. In this paper, we show that the system performance on these aspects depends closely on how the sensors are deployed in the field, and on how the sensor locations can be adjusted after the initial deployment. For static sensor deployment, we investigate the hexagon and square lattice topology and analyze their impact on secure connectivity and sensing coverage. For advanced sensing devices that allow for location adjustment after deployment, we have established a new framework for coordinated updates of sensor locations. We propose two new sensor location updating algorithms, the VFSec and the Weighted Centroid algorithm, to jointly optimize sensing coverage and secure connectivity. Simulation results show that these new algorithms provide superior tradeoff over the existing approaches that do not take security into considerations.
Keywords: key pre-distribution; location adjustment; secure communications; sensing coverage; sensor deployment

Data hiding in compiled program binaries for enhancing computer system performance - Swaminathan,A.; Mao,Y.; Wu,M.; Kailas,K. (Information Hiding, 2005)
Information hiding has been studied in many security applications such as authentication, copyright management and digital forensics. In this work, we introduce a new application where successful information hiding in compiled program binaries could bring system-wide performance improvements. Our goal is to enhance computer system performance by providing additional information to the processor, without changing the instruction set architecture. We first analyze the statistics of typical programs to demonstrate the feasibility of hiding data in them. We then propose several techniques to hide a large amount of data in the operand fields with very low computation and storage requirements during the extraction process. The data embedding is made reversible to recover the original instructions and to ensure the correct execution of the computer program. Our experiments on the SPEC CPU2000 benchmark programs show that up to 110K bits of information can be embedded in large programs with as little as 3K bits of additional run-time memory in the form of a simple look-up table.

Data hiding in curves with application to fingerprinting maps - Gou,Hongmei; M. Wu (Signal Processing, IEEE Transactions on, 2005)
This paper presents a new data hiding method for curves. The proposed algorithm parameterizes a curve using the B-spline model and adds a spread spectrum sequence to the coordinates of the B-spline control points. In order to achieve robust fingerprint detection, an iterative alignment-minimization algorithm is proposed to perform curve registration and to deal with the nonuniqueness of B-spline control points. Through experiments, we demonstrate the robustness of the proposed data-hiding algorithm against various attacks, such as collusion, cropping, geometric transformations, vector/raster-raster/vector conversions, printing-and-scanning, and some of their combinations. We also show the feasibility of our method for fingerprinting topographic maps as well as writings and drawings.
Keywords: (mathematics); algorithm; alignment-minimization; B-spline; CONTROL; curve; data; detection; edge; embedding; encapsulation; fingerprint; geospatial; hiding; identification; image; iterative; method; methods; minimisation; point; protection; registration; sequence; spectrum; splines; spread; watermarking

Dynamic Layout Management in a Multimedia Bulletin Board (2002) - Kang,Hyunmo; Shneiderman, Ben; Wolff,Gregory J (Institute for Systems Research Technical Reports, 2005)
This paper proposes a novel user interface to manage the dynamic layout of multimedia objects in the Multimedia Bulletin Board (MBB) system. The MBB has been designed and implemented as a prototype of an asynchronous communication system that enables rich communication and collaboration among users of multimedia objects such as text, image, moving picture, sound, voice, web, office document, and other files. The layout properties of the multimedia objects on a board (e.g. x-y position, size, z-order, partial occlusion, explicit and implicit links, etc.) show important and useful information on the user dynamics occurring within a board. However, a fixed layout created and edited by multiple users may prevent users from recognizing and identifying useful information. This paper resolves this problem with a novel user-controlled layout strategy made visible with dynamic layout templates (DLT). Users can reorganize the objects to extract meaningful information related to time, source, geographic location, or topic.
Keywords: Technical Report

Dynamic network resource allocation using multimedia content features and ... - M. Wu; Joyce,Robert A.; Vetro,Anthony; Wong,Hau-San; Guan,Ling; Kung,Sun-Yuan (2005)
A method for dynamically allocating network resources while transferring multimedia at variable bit-rates in a network extracts first content features from the multimedia to determine renegotiation points and observation periods. Second content features and traffic features are extracted from the multimedia bit stream during the observation periods. The second content features and the traffic features are combined in a neural network to predict the network resources to be allocated at the renegotiation points.

Efficient bandwidth resource allocation for low-delay multiuser video streaming - Su,Guan-Ming; M. Wu (Circuits and Systems for Video Technology, IEEE Transactions on, 2005)
This paper studies efficient bandwidth resource allocation for streaming multiple MPEG-4 fine granularity scalability (FGS) video programs to multiple users. We begin with a simple single-user scenario and propose a rate-control algorithm that has low delay and achieves an excellent tradeoff between the average visual distortion and the quality fluctuation. The proposed algorithm employs two weight factors for adjusting the tradeoff, and the optimal choice of these factors is derived. We then extend to the multiuser case and propose a dynamic resource allocation algorithm with low delay and low computational complexity. By exploring the variations in the scene complexity of video programs as well as dynamically and jointly distributing the available system resources among users, our proposed algorithm provides low fluctuation of quality for each user, and can support consistent or differentiated quality among all users to meet applications' needs. Experimental results show that compared to traditional look-ahead sliding-window approaches, our algorithm can achieve comparable visual quality and channel utilization at a much lower cost of delay, computation, and storage.
Keywords: algorithm; allocation; allocation; approaches; average; Bandwidth; channel; channels; coding; complexity; computational; control; distortion; dynamic; efficient; fine; fluctuation; granularity; look-ahead; low-delay; MPEG-4; multiple; multiuser; QUALITY; quality; rate-control; resource; scalability; scenario; single-user; sliding-window; streaming; Telecommunication; utilization; video; visual

Enhanced position weight matrices using mixture models - Hannenhalli, Sridhar; Wang,L.-S. (Bioinformatics, 2005)
Motivation: Positional weight matrix (PWM) is derived from a set of experimentally determined binding sites. Here we explore whether there exist subclasses of binding sites and if the mixture of these subclass-PWMs can improve the binding site prediction. Intuitively, the subclasses correspond to either distinct binding preference of the same transcription factor in different contexts or distinct subtypes of the transcription factor.Result: We report an Expectation Maximization algorithm adapting the mixture model of Baily and Elkan. We assessed the relative merit of using two subclass-PWMs. The resulting PWMs were evaluated with respect to preferred conservation (relative to mouse) of potential sites in human promoters and expression coherence of the potential target genes. Based on 64 JASPAR vertebrate PWMs, 61–81% of the cases resulted in a higher conservation using the mixture model. Also in 98% of the cases the expression coherence was higher for the target genes of one of the subclass-PWMs. Our analysis of Reb1 sites is consistent with previously discovered subtypes using independent methods. Additionally application of our method to mutated sites for transcription factor LEU3 reveals subclasses that segregate into strongly binding and weakly binding sites with P-value of 0.008. This is the first study which attempts to quantify the subtly different binding specificities of a transcription factor on a large scale and suggests the use of a mixture of PWMs, instead of the current practice of using a single PWM, for a transcription factor.

Fingerprinting curves - Gou,H.; Wu,M. (Digital Watermarking, 2005)
This paper presents a new method for robust data hiding in curves and highlights potential applications including digital fingerprinting of map document for trace and track purposes. We parameterize a curve using the B-spline model and add a spread spectrum sequence to the coordinates of the B-spline control points. In order to achieve robust fingerprint detection, we propose an iterative alignment-minimization algorithm to perform curve registration and deal with the non-uniqueness of B-spline control points. We show through experiments the robustness of our method against various attacks such as collusion, geometric transformations and perturbation, printing-and-scanning, and some of their combinations. We demonstrate the feasibility of our method for fingerprinting topographic maps as well as writings and drawings. The extension from hiding data in 2D topographic maps to 3D elevation data sets is also discussed.

Finite Elements and Fast Iterative Solvers : with Applications in Incompressible Fluid Dynamics - Elman, Howard; Silvester, David J; Wathen, Andrew J (Oxford University Press, 2005)
The subject of this book is the efficient solution of partial differential equations (PDEs) that arise when modelling incompressible fluid flow. The material is organized into four groups of two chapters each, covering the Poisson equation (chapters 1 & 2); the convection-diffucion equation (chapters 3 & 4); the Stokes equations (chapters 5 & 6); and the Navier-Stokes equations (chapters 7 & 8). These equations represent important models within the domain of computational fluid dynamics, but they also arise in many other settings. For each PDE model, there is a chapter concerned with finite element discretization. For each problem and associated solvers there is a description of how to compute along with theoretical analysis which guides the choice of approaches. Illustrative numerical results occur throughout the book, which have been computed with the freely downloadable IFISS software. All numerical results should be reproducible by readers who have access to MATLAB and there is considerable scope for experimentation in the 'computational laboratory' provided by the software. This book provides an excellent introduction to finite elements, iterative linear solvers and scientific computing aimed at graduates in engineering, numerical analysis, applied mathematics and interdisciplinary scientific computing. Including theoretical problems and practical exercises closely tied with freely downloadable MATLAB software, this book is an ideal teaching and learning resource.
Keywords: Computers / Computer Science; Mathematics / Numerical Analysis; Science / Mechanics / Fluids; Science / Physics / General; Technology & Engineering / Mechanical

Forensic analysis of nonlinear collusion attacks for multimedia fingerprinting - Zhao,H.V.; M. Wu; Wang,Z.J.; Liu,K. J.R (Image Processing, IEEE Transactions on, 2005)
Digital fingerprinting is a technology for tracing the distribution of multimedia content and protecting them from unauthorized redistribution. Unique identification information is embedded into each distributed copy of multimedia signal and serves as a digital fingerprint. Collusion attack is a cost-effective attack against digital fingerprinting, where colluders combine several copies with the same content but different fingerprints to remove or attenuate the original fingerprints. In this paper, we investigate the average collusion attack and several basic nonlinear collusions on independent Gaussian fingerprints, and study their effectiveness and the impact on the perceptual quality. With unbounded Gaussian fingerprints, perceivable distortion may exist in the fingerprinted copies as well as the copies after the collusion attacks. In order to remove this perceptual distortion, we introduce bounded Gaussian-like fingerprints and study their performance under collusion attacks. We also study several commonly used detection statistics and analyze their performance under collusion attacks. We further propose a preprocessing technique of the extracted fingerprints specifically for collusion scenarios to improve the detection performance.
Keywords: Automated; Product Labeling; Reproducibility of Results; Sensitivity and Specificity; Signal Processing; bounded Gaussian-like fingerprint; detection statistics; digital fingerprinting; forensic analysis; independent Gaussian fingerprint; multimedia content; multimedia fingerprinting; nonlinear collusion attack; perceptual distortion; perceptual quality; preprocessing; Computer-Assisted; Computer-Assisted; Models; Statistical; Nonlinear Dynamics; Patents as Topic; Pattern Recognition

Generalizations of Markov model to characterize biological sequences - Wang,Junwen; Hannenhalli, Sridhar (BMC Bioinformatics, 2005)
BACKGROUND:The currently used kth order Markov models estimate the probability of generating a single nucleotide conditional upon the immediately preceding (gap = 0) k units. However, this neither takes into account the joint dependency of multiple neighboring nucleotides, nor does it consider the long range dependency with gap>0.RESULT:We describe a configurable tool to explore generalizations of the standard Markov model. We evaluated whether the sequence classification accuracy can be improved by using an alternative set of model parameters. The evaluation was done on four classes of biological sequences - CpG-poor promoters, all promoters, exons and nucleosome positioning sequences. Using di- and tri-nucleotide as the model unit significantly improved the sequence classification accuracy relative to the standard single nucleotide model. In the case of nucleosome positioning sequences, optimal accuracy was achieved at a gap length of 4. Furthermore in the plot of classification accuracy versus the gap, a periodicity of 10-11 bps was observed which might indicate structural preferences in the nucleosome positioning sequence. The tool is implemented in Java and is available for download at ftp://ftp.pcbi.upenn.edu/GMM/.CONCLUSION:Markov modeling is an important component of many sequence analysis tools. We have extended the standard Markov model to incorporate joint and long range dependencies between the sequence elements. The proposed generalizations of the Markov model are likely to improve the overall accuracy of sequence analysis tools.

The Genome Sequence of Trypanosoma Cruzi, Etiologic Agent of Chagas Disease - El‐Sayed, Najib M.; Myler,Peter J.; Bartholomeu,Daniella C.; Nilsson,Daniel; Aggarwal,Gautam; Tran,Anh-Nhi; Ghedin,Elodie; Worthey,Elizabeth A.; Delcher,Arthur L.; Blandin,Gaëlle; Westenberger,Scott J.; Caler,Elisabet; et al. (ScienceScience, 2005)
Whole-genome sequencing of the protozoan pathogen Trypanosoma cruzi revealed that the diploid genome contains a predicted 22,570 proteins encoded by genes, of which 12,570 represent allelic pairs. Over 50% of the genome consists of repeated sequences, such as retrotransposons and genes for large families of surface molecules, which include trans-sialidases, mucins, gp63s, and a large novel family (>1300 copies) of mucin-associated surface protein (MASP) genes. Analyses of the T. cruzi, T. brucei, and Leishmania major (Tritryp) genomes imply differences from other eukaryotes in DNA repair and initiation of replication and reflect their unusual mitochondrial DNA. Although the Tritryp lack several classes of signaling molecules, their kinomes contain a large and diverse set of protein kinases and phosphatases; their size and diversity imply previously unknown interactions and regulatory processes, which may be targets for intervention.

The Genome Sequence of Trypanosoma cruzi, Etiologic Agent of Chagas Disease - El‐Sayed, Najib M.; Myler,Peter J.; Bartholomeu,Daniella C.; Nilsson,Daniel; Aggarwal,Gautam; Tran,Anh-Nhi; Ghedin,Elodie; Worthey,Elizabeth A.; Delcher,Arthur L.; Blandin,Gaëlle; Westenberger,Scott J.; Caler,Elisabet; et al. (Science, 2005)
Whole-genome sequencing of the protozoan pathogen Trypanosoma cruzi revealed that the diploid genome contains a predicted 22,570 proteins encoded by genes, of which 12,570 represent allelic pairs. Over 50% of the genome consists of repeated sequences, such as retrotransposons and genes for large families of surface molecules, which include trans-sialidases, mucins, gp63s, and a large novel family (>1300 copies) of mucin-associated surface protein (MASP) genes. Analyses of the T. cruzi, T. brucei, and Leishmania major (Tritryp) genomes imply differences from other eukaryotes in DNA repair and initiation of replication and reflect their unusual mitochondrial DNA. Although the Tritryp lack several classes of signaling molecules, their kinomes contain a large and diverse set of protein kinases and phosphatases; their size and diversity imply previously unknown interactions and regulatory processes, which may be targets for intervention.

The genome sequence of Trypanosoma cruzi, etiologic agent of Chagas disease - El-Sayed, N.M.; Myler,P. J; Bartholomeu,D. C; Nilsson,D.; Aggarwal,G.; Tran,A. N; Ghedin,E.; Worthey,E. A; Delcher,A. L; Blandin,G.; others (Science, 2005)

Group-based joint coding and embedding technique for multimedia fingerprinting - He,S.; Wu,M. (Proc. SPIE, 2005)
This paper proposes a group-based fingerprinting scheme employing a joint coding and embedding strategy totrace multimedia distribution and proactively prevent the leak of multimedia information. Taking advantage of the prior knowledge on the collusion pattern, we construct compact fingerprints that consist of user sub-codeword and group sub-codeword and are embedded in host signal via spread spectrum technique. The detection is done in two levels, which identifies guilty groups through correlation and then narrows down to specific colluders through minimum distance decoding. Experimental results show that the proposed method provides higher collusion resistance than the existing non-grouped fingerprint codes.

Handling uneven embedding capacity in binary images: a revisit - M. Wu; Fridrich,Jessica; Goljan,Miroslav; Gou,Hongmei (Proceedings of SPIE, 2005)
Hiding data in binary images can facilitate the authentication and annotation of important document images in digital domain. A representative approach is to first identify pixels whose binary color can be flipped without introducing noticeable artifacts, and then embed one bit in each non-overlapping block by adjusting the flippable pixel values to obtain the desired block parity. The distribution of these flippable pixels is highly uneven across the image, which is handled by random shuffling in the literature. In this paper, we revisit the problem of data embedding for binary images and investigate the incorporation of a most recent steganography framework known as the wet paper coding to improve the embedding capacity. The wet paper codes naturally handle the uneven embedding capacity through randomized projections. In contrast to the previous approach, where only a small portion of the flippable pixels are actually utilized in the embedding, the wet paper codes allow for a high utilization of pixels that have high flippability score for embedding, thus giving a significantly improved embedding capacity than the previous approach. The performance of the proposed technique is demonstrated on several representative images. We also analyze the perceptual impact and capacity-robustness relation of the new approach.

How do I find blue books about dogs? The errors and frustrations of young digital library users - Hutchinson,H.; Druin, Allison; Bederson, Benjamin B.; Reuter,K.; Rose,A.; Weeks,A. C (Proceedings of HCII 2005, 2005)

Improving collusion resistance of error correcting code based multimedia fingerprinting - He,Shan; M. Wu (Acoustics, Speech, and Signal Processing, 2005. Proceedings. (ICASSP '05). IEEE International Conference on, 2005)
Digital fingerprinting protects multimedia content from illegal redistribution by uniquely marking copies of the content distributed to each user. Collusion is a powerful attack whereby several differently fingerprinted copies of the same content are combined together to attenuate or remove the fingerprints. Focusing on the error correction code (ECC) based fingerprinting, we explore in this paper new avenues that can substantially improve its collusion resistance, and in the mean time retain its advantages in detection complexity and fast distribution. Our analysis suggests a great need of jointly considering the coding, embedding, and detection issues, and inspires the proposed technique of permuted subsegment embedding that is able to substantially improve the collusion resistance of ECC based fingerprinting.
Keywords: based; code; codes; coding; collusion; correcting; correction; data; detection; digital; ECC; embedding; error; fingerprint; fingerprinting; fingerprinting; multimedia; of; permuted; resistance; Security; signatures; subsegment; systems

An interactive and team approach to multimedia design curriculum - M. Wu; Liu,K. J.R (Signal Processing Magazine, IEEE, 2005)
Over the past decade, increasingly powerful technologies have made it easier to compress, distribute, and store multimedia content. The merger of computing and communications has created a ubiquitous infrastructure that brings digital multimedia closer to the users and opens up tremendous educational and commercial opportunities in multimedia content creation, delivery, rendering, and archiving for millions of users worldwide. Multimedia has become a basic skill demanded by an increasing number of potential jobs for electrical engineering/computer science graduates. In this article, the authors intend to share their experiences and new ways of thinking about curriculum development. It is beneficial for colleagues in the multimedia signal processing areas for use in developing or revising the curriculum to fit the needs and resources of their own programs.
Keywords: approach; communication; courses; curriculum; curriculum; design; development; digital; education; educational; interactive; learning; multimedia; multimedia; processing; signal; team

The International Children’s Digital Library: A Case Study in Designing for a MultiLingual - Hutchinson,H.B.; Rose,A.; Bederson, Benjamin B.; Weeks,A. C; Druin, Allison (Multi-Cultural, Multi-Generational Audience. Information Technology and Libraries, 2005)

Joint uplink and downlink optimization for video conferencing over wireless LAN - Su,Guan-Ming; Han,Zhu; M. Wu; Liu,K. J.R (Acoustics, Speech, and Signal Processing, 2005. Proceedings. (ICASSP '05). IEEE International Conference on, 2005)
A real-time video conferencing framework is proposed for multiple conferencing pairs by jointly considering the uplink and downlink conditions within IEEE 802.11 networks. We formulate this system so as to minimize the maximal end-to-end expected distortion received by all users by selecting the PHY modes and transmission time. Compared with the strategy of individually optimizing uplink and downlink, the proposed framework outperforms by 3.67-8.65 dB for the average received PSNR among all users.
Keywords: 802.11; conferencing; conferencing; distortion; end-to-end; expected; IEEE; joint; LAN; maximal; minimisation; modes; multiple; networks; optimization; pairs; PHY; PSNR; real-time; teleconferencing; time; transmission; uplink-downlink; video; wireless

Modeling image processing systems with homogeneous parameterized dataflow graphs - Sen,Mainak; Bhattacharyya, Shuvra S.; Lv,Tiehan; Wolf,W. (Acoustics, Speech, and Signal Processing, 2005. Proceedings. (ICASSP '05). IEEE International Conference on, 2005)
We describe a new dataflow model called homogeneous parameterized dataflow (HPDF). This form of dynamic dataflow graph takes advantage of the fact that in a large number of image processing applications, data production and consumption rates, though dynamic, are equal across graph edges for any particular iteration, which leads to a homogeneous rate of actor execution, even though data production and consumption values are dynamic and vary across graph edges. We discuss existing dataflow models and formulate in detail the HPDF model. We develop examples of applications that are described naturally in terms of HPDF semantics and present experimental results that demonstrate the efficacy of the HPDF approach.
Keywords: data consumption; data flow graphs; data production; dynamic dataflow graph; graph edges; homogeneous parameterized dataflow graphs; IMAGE PROCESSING; image processing system modeling; iteration; iterative methods

New experimental data of STBLI at DNS/LES accessible Reynolds numbers - Bookey,P.; Wyckham,C.; Smits,A. J.; Martin, M.P (AIAA paper, 2005)

Ordered and Quantum Treemaps: Making Effective Use of 2D Space to Display Hierarchies (2001) - Bederson, Benjamin B.; Shneiderman, Ben; Wattenberg,Martin (Institute for Systems Research Technical Reports, 2005)
Treemaps, a space- filling method of visualizing large hierarchical data sets, are receiving increasing attention. Several algorithms have been proposed to create more useful displays by controlling the aspect ratios of the rectangles that make up a treemap. While these algorithms do improve visibility of small items in a single layout, they introduce instability over time in the display of dynamically changing data, fail to preserve order of the underlying data, and create layouts that are difficult to visually search. In addition, continuous treemap algorithms are not suitable for displaying quantum-sized objects within them, such as images. This paper introduces several new treemap algorithms, which address these shortcomings. In addition, we show a new application of these treemaps, using them to present groups of images. The ordered treemap algorithms ensure that items near each other in the given order will be near each other in the treemap layout. Using experimental evidence from Monte Carlo trials, we show that compared to other layout algorithms ordered treemaps are more stable while maintaining relatively favorable aspect ratios of the constituent rectangles. A second test set uses stock market data. The quantum treemap algorithms modify the layout of the continuous treemap algorithms to generate rectangles that are integral multiples of an input object size. The quantum treemap algorithm has been applied to PhotoMesa, an application that supports browsing of large numbers of images.
Keywords: Technical Report

Ordered Treemap Layouts (2001) - Shneiderman, Ben; Wattenberg,Martin (Institute for Systems Research Technical Reports, 2005)
Treemaps, a space-filling method of visualizing large hierarchical data sets, are receiving increasing attention. Several algorithms have been proposed to create more useful displays by controlling the aspect ratios of the rectangles that make up a treemap. While these algorithms do improve visibility of small items in a single layout, they introduce instability over time in the display of dynamically changing data, and fail to preserve an ordering of the underlying data. This paper introduces the ordered treemap, which addresses these two shortcomings. The ordered treemap algorithm ensures that items near each other in the given order will be near each other in the treemap layout. Using experimental evidence from Monte Carlo trials, we show that compared to other layout algorithms ordered treemaps are more stable while maintaining relatively low aspect ratios of the constituent rectangles. A second test set uses stock market data.
Keywords: Technical Report

An outdoor 3-D visual tracking system for the study of spatial navigation and memory in rhesus monkeys - Zia Khan; Herman, Rebecca A.; Wallen, Kim; Balch, Tucker (Behavior Research Methods, 2005)
Previous studies of the navigational abilities of nonhuman primates have largely been limited to what could be described by a human observer with a pen and paper. Consequently, we have developed a system that uses a pair of cameras to automatically obtain the three-dimensional trajectory of rhesus monkeys performing an outdoor spatial navigation and memory task. The system provides trajectories, path length, speed, and other variables that would be impossible for an unaided observer to note. From trajectory data, we computed and validated a path-length measurement. We use this measurement to compare the navigation abilities of several animals. In addition, we provide quantitative data on the accuracy of a method for automatic behavior detection. Currently, the system is being used to examine the sex differences in spatial navigation of rhesus monkeys. We expect that measures derived from the trajectory data will reveal strategies used by animals to solve spatial problems.
Keywords: cognitive psychology

Pedestrian classification from moving platforms using cyclic motion pattern - Yang Ran; Qinfen Zheng; Weiss, I.; Davis, Larry S.; Abd-Almageed, Wael; Liang Zhao (Image Processing, 2005. ICIP 2005. IEEE International Conference on, 2005)
This paper describes an efficient pedestrian detection system for videos acquired from moving platforms. Given a detected and tracked object as a sequence of images within a bounding box, we describe the periodic signature of its motion pattern using a twin-pendulum model. Then a principle gait angle is extracted in every frame providing gait phase information. By estimating the periodicity from the phase data using a digital phase locked loop (dPLL), we quantify the cyclic pattern of the object, which helps us to continuously classify it as a pedestrian. Past approaches have used shape detectors applied to a single image or classifiers based on human body pixel oscillations, but ours is the first to integrate a global cyclic motion model and periodicity analysis. Novel contributions of this paper include: i) development of a compact shape representation of cyclic motion as a signature for a pedestrian, ii) estimation of gait period via a feedback loop module, and iii) implementation of a fast online pedestrian classification system which operates on videos acquired from moving platforms.
Keywords: analysis; angle; body; classification; compact; cyclic; DETECTION; detection; digital; Feedback; Gait; human; image; information; locked; loop; loop; loops; module; MOTION; object; oscillations; pattern; pedestrian; phase; Pixel; principle; representation; sequence; sequences; SHAPE; system

Pedestrian classification from moving platforms using cyclic motion pattern - Yang Ran; Qinfen Zheng; Weiss, I.; Davis, Larry S.; Abd-Almageed, Wael; Liang Zhao (IEEE International Conference on Image Processing, 2005. ICIP 2005, 2005)
This paper describes an efficient pedestrian detection system for videos acquired from moving platforms. Given a detected and tracked object as a sequence of images within a bounding box, we describe the periodic signature of its motion pattern using a twin-pendulum model. Then a principle gait angle is extracted in every frame providing gait phase information. By estimating the periodicity from the phase data using a digital phase locked loop (dPLL), we quantify the cyclic pattern of the object, which helps us to continuously classify it as a pedestrian. Past approaches have used shape detectors applied to a single image or classifiers based on human body pixel oscillations, but ours is the first to integrate a global cyclic motion model and periodicity analysis. Novel contributions of this paper include: i) development of a compact shape representation of cyclic motion as a signature for a pedestrian, ii) estimation of gait period via a feedback loop module, and iii) implementation of a fast online pedestrian classification system which operates on videos acquired from moving platforms.
Keywords: compact shape representation; cyclic motion pattern; data mining; Detectors; digital phase locked loop; digital phase locked loops; feedback loop module; gait analysis; gait phase information; human body pixel oscillations; HUMANS; image classification; Image motion analysis; image representation; image sequence; Image sequences; Motion detection; Object detection; pedestrian classification; pedestrian detection system; Phase estimation; Phase locked loops; principle gait angle; SHAPE; tracking; Videos

Performance study on multimedia fingerprinting employing traceability codes - He,S.; Wu,M. (Digital Watermarking, 2005)
Digital fingerprinting is a tool to protect multimedia content from illegal redistribution by uniquely marking copies of the content distributed to each user. Collusion attack is a powerful attack whereby several differently-fingerprinted copies of the same content are combined together to attenuate or even remove the fingerprint. Coded fingerprinting is one major category of fingerprinting techniques against collusion. Many fingerprinting codes are proposed with tracing capability and collusion resistance, such as Traceability (TA) codes and Identifiable Parent Property (IPP) codes. Most of these works treat the important embedding issue in terms of a set of simplified and abstract assumptions, and they do not examine the end-to-end performance of the coded multimedia fingerprinting. In this paper we jointly consider the coding and embedding issues and examine the collusion resistance of coded fingerprinting systems with various code parameters. Our results show that TA codes generally offer better collusion resistance than IPP codes, and a TA code with a larger alphabet size and a longer code length is preferred.

Recovering system specific rules from software repositories - Williams, Chadd C; Hollingsworth, Jeffrey K (SIGSOFT Softw. Eng. Notes, 2005)
One of the most successful applications of static analysis based bug finding tools is to search the source code for violations of system-specific rules. These rules may describe how functions interact in the code, how data is to be validated or how an API is to be used. To apply these tools, the developer must encode a rule that must be followed in the source code. The difficulty is that many of these system-specific rules are undocumented and "grow" over time as the source code changes. Most research in this area relies on expert programmers to document these little-known rules. In this paper we discuss a method to automatically recover a subset of these rules, function usage patterns, by mining the software repository. We present a preliminary study that applies our work to a large open source software project.
Keywords: data warehouse and repository; debugging aids; design; experimentation; measurement; performance

Reliable Segmentation of Pedestrians in Moving Scenes - Ran, Y.; Zheng,Q.; Weiss, I.; Davis, Larry S. (The 2005 International Conference on Acoustics, Speech, and Signal Processing (ICASSP2005), 2005)
This paper describes a periodic motion based pedestriansegmentation algorithm for videos acquired from moving platforms. Given a sequence of bounding boxes containing the detected and tracked walking human, the goal is to analyze the low dimension structure by considering every object sample as a point in the high dimensional manifold space and use the learned structure for segmentation. In this work, unlike the traditional top- down dimension reduction (manifold learning) methods such as Isomap and locally linear embedding (LLE) [9], we introduce a novel bottom-up learning approach. We represent the human stride as a cascade of models with increasing parameter numbers. These parameters describe the dynamics of pedestrians from coarse to fine. By applying the learned manifold structure, we can predict the location of body parts, especially legs, with high accuracy at every frame. The segmentation in consecutive images is done by EM clustering. With the accuracy for prediction using twin-pendulum model, EM is more likely to converge to global maximums. Experimental results for real videos are presented. The algorithm has demonstrated a reliable performance for videos acquired from moving platforms.

Robust digital fingerprinting for curves - Gou,H.; Wu,M. (Proc. of IEEE Int. Conf. on Acoustics, Speech, and Signal Processing (ICASSP'05), 2005)
Hiding data in curves can be achieved by parameterizing acurve using the B-spline model and adding spread spectrum sequences in B-spline control points. In this paper, we pro- pose an iterative alignment-minimization algorithm to per- form curve registration and deal with the non-uniqueness of B-spline control points. We demonstrate through experi- ments the robustness of our method against various attacks such as collusion, geometric transformation, and printing- and-scanning. We also show the feasibility of our method for fingerprinting topographic maps and detecting finger- prints from printed copies.

Robust routing in malicious environment for ad hoc networks - Yu,Z.; Seng,C. Y; Jiang,T.; Wu,X.; Arbaugh, William A. (Information Security Practice and Experience, 2005)

ROMER: resilient opportunistic mesh routing for wireless mesh networks - Yuan,Y.; Yang,H.; Wong,S. H.Y; Lu,S.; Arbaugh, William A. (Proc. of IEEE WiMesh, 2005)

Security of feature extraction in image hashing - Swaminathan,A.; Mao,Yinian; M. Wu (Acoustics, Speech, and Signal Processing, 2005. Proceedings. (ICASSP '05). IEEE International Conference on, 2005)
Security and robustness are two important requirements for image hash functions. We introduce "differential entropy" as a metric to quantify the amount of randomness in image hash functions and to study their security. We present a mathematical framework and derive expressions for the proposed security metric for various common image hashing schemes. Using the proposed security metric, we discuss the trade-offs between security and robustness in image hashing.
Keywords: cryptography; differential; digital; entropy; extraction; feature; functions; hash; hashing; image; metric; processing; randomness; robustness; Security; signature; signatures

A simulation and data analysis system for large-scale, data-driven oil reservoir simulation studies - Kurc, T.; Catalyurek,U.; Zhang,X.; Saltz, J.; Martino,R.; Wheeler,M.; Peszyńska,M.; Sussman, Alan; Hansen,C.; Sen,M.; others (Concurrency and Computation: Practice and Experience, 2005)

Transcriptional profiling of the hyperthermophilic methanarchaeon Methanococcus jannaschii in response to lethal heat and non‐lethal cold shock - Boonyaratanakornkit,Boonchai B; Simpson,Anjana J.; Whitehead,Timothy A; Fraser,Claire M.; El‐Sayed, Najib M.; Clark,Douglas S (Environmental Microbiology, 2005)
Temperature shock of the hyperthermophilic methanarchaeon Methanococcus jannaschii from its optimal growth temperature of 85°C to 65°C and 95°C resulted in different transcriptional responses characteristic of both the direction of shock (heat or cold shock) and whether the shock was lethal. Specific outcomes of lethal heat shock to 95°C included upregulation of genes encoding chaperones, and downregulation of genes encoding subunits of the H+ transporting ATP synthase. A gene encoding an α subunit of a putative prefoldin was also upregulated, which may comprise a novel element in the protein processing pathway in M. jannaschii. Very different responses were observed upon cold shock to 65°C. These included upregulation of a gene encoding an RNA helicase and other genes involved in transcription and translation, and upregulation of genes coding for proteases and transport proteins. Also upregulated was a gene that codes for an 18 kDa FKBP-type PPIase, which may facilitate protein folding at low temperatures. Transcriptional profiling also revealed several hypothetical proteins that respond to temperature stress conditions.

Vision geometry XIII(San Jose CA, 18-19 January 2005) - Latecki,L.J.; Mount, Dave; Wu,A. Y (SPIE proceedings series, 2005)

Bug driven bug finders - Williams, C. C; Hollingsworth, Jeffrey K (Proceedings of the International Workshop on Mining Software Repositories, 2004)

Building an information retrieval test collection for spontaneous conversational speech - Oard, Douglas; Soergel,Dagobert; David Doermann; Huang,Xiaoli; Murray,G. Craig; Wang,Jianqiang; Ramabhadran,Bhuvana; Franz,Martin; Gustman,Samuel; Mayfield,James; Kharevych,Liliya; Strassel,Stephanie (Proceedings of the 27th annual international ACM SIGIR conference on Research and development in information retrieval, 2004)
Test collections model use cases in ways that facilitate evaluation of information retrieval systems. This paper describes the use of search-guided relevance assessment to create a test collection for retrieval of spontaneous conversational speech. Approximately 10,000 thematically coherent segments were manually identified in 625 hours of oral history interviews with 246 individuals. Automatic speech recognition results, manually prepared summaries, controlled vocabulary indexing, and name authority control are available for every segment. Those features were leveraged by a team of four relevance assessors to identify topically relevant segments for 28 topics developed from actual user requests. Search-guided assessment yielded sufficient inter-annotator agreement to support formative evaluation during system development. Baseline results for ranked retrieval are presented to illustrate use of the collection.
Keywords: assessment; Automatic speech recognition; oral history; search-guided relevance

CHARACTERIZATION OF Ath17, A QUANTITATIVE TRAIT LOCUS FOR ATHEROSCLEROSIS SUSCEPTIBILITY BETWEEN C57BL/6J AND 129S1/SvImJ; SINGLE-NUCLEOTIDE POLYMORPHISMS HAVE IMPORTANT IMPLICATIONS ON IDENTIFYING ATHEROSCLEROSIS MODIFIER GENES - Ishimori,Naoki; Walsh,Kenneth; Zheng,Xiangqun; Lu,Fu; Hannenhalli, Sridhar; Nusskern,Deborah; Mural,Richard; Paigen,Beverly (Cardiovascular Pathology, 2004)
Although identifying quantitative trait loci (QTL) for atherosclerosis susceptibility in experimental murine models has helped us better understand the pathophysiology of atherosclerosis, identifying the genes underlying these QTL has been a slow and difficult process. We are currently in the process of identifying the gene that underlies Ath17, an atherosclerosis-susceptibility QTL we discovered in a (C57BL/6J×129S1/SvImJ)F2 intercross. Ath17 maps to a 6 cM interval region on chromosome 10 (D10Mit31, LOD score 6.6) and contains 46 annotated and 133 predicted genes. We searched the Celera Discovery System database for single nucleotide polymorphisms (SNPs) between C57BL/6J (B6) and 129S1/SvImJ in the Ath17 region and found defined blocks of high and low diversity and one polymorphic region of over 4 Mb surrounded by nonpolymorphic regions. Four of the genes, including the annotated Desrt, in the polymorphic region contained mis-sense mutations. The Desrt coding region contained four mis-sense mutations: B6 lysine to 129 glutamic acid at aa382, B6 asparagine to 129 serine at aa388, B6 threonine to 129 alanine at aa836, and B6 glycine to 129 serine at aa964. In addition, intron 5 of Desrt contained a SNP which co-localized with a putative transcription factor binding site. Desrt is a DNA binding protein, widely expressed in adult tissues, and likely plays a role in cell proliferation, differentiation, and development, making Dsert a strong candidate gene for Ath17. The murine SNP database dramatically reduced the percentage of the murine genome we had to search to find viable candidate genes for Ath17.

Characterization of the Overall Rotational Diffusion of a Protein From 15N Relaxation Measurements and Hydrodynamic Calculations - Blake-Hall,Jennifer; Walker,Olivier; Fushman, David (Protein NMR Techniques, 2004)
In this chapter, we discuss experimental and theoretical methods for characterizing the overall rotational diffusion of molecules in solution. The methods are illustrated for the B3 domain of protein G, a small protein with rotational anisotropy of D par / D perp = 1.4. The rotational diffusion tensor of the protein is determined directly from 15 N relaxation measurements. The experimental data are treated assuming various possible models for the overall tumbling: isotropic, axially symmetric, and fully anisotropic, and the results of these analyses are compared to determine an adequate diffusion model for the protein. These experimentally derived characteristics of the protein are compared with the results of theoretical calculations of the diffusion tensor using various hydrodynamic models, to find optimal models and parameter sets for theoretical predictions. We also derive model-free characteristics of internal backbone motions in the protein, to show that different models for the overall motion can result in significantly different pictures of motion. This emphasizes the necessity of accurately characterizing the overall tumbling of a molecule to determine its local dynamics.
Keywords: Biomedical and Life Sciences

Collusion resistant multimedia fingerprinting: A unified framework - Wu,M.; Trappe,W.; Wang,Z.J.; Liu,K. J.R (Electronic Imaging Symposium: Security, Steganography, and Watermarking of Multimedia Contents VI, San Jose, CA, Proc. of SPIE, 2004)
Digital fingerprints are unique labels inserted in different copies of the same content before distribution. Eachdigital fingerprint is assigned to an intended recipient, and can be used to trace the culprits who use their content for unintended purposes. Attacks mounted by multiple users, known as collusion attacks, provide a cost-effective method for attenuating the identifying fingerprint from each colluder, thus collusion poses a real challenge to protect the digital media data and enforce usage policies. This paper examines a few major design methodologies for collusion-resistant fingerprinting of multimedia, and presents a unified framework that helps highlight the common issues and the uniqueness of different fingerprinting techniques.

Collusion-resistant fingerprinting for multimedia - M. Wu; Trappe,W.; Wang,Z.J.; Liu,K. J.R (Signal Processing Magazine, IEEE, 2004)
Digital fingerprinting is a technology for enforcing digital rights policies whereby unique labels, known as digital fingerprints, are inserted into content prior to distribution. For multimedia content, fingerprints can be embedded using conventional watermarking techniques that are typically concerned with robustness against a variety of attacks mounted by an individual. These attacks, known as multiuser collusion attacks, provide a cost-effective method for attenuating each of the colluder's fingerprints and poses a real threat to protecting media data and enforcing usage policies. In this article, we review some major design methodologies for collusion-resistant fingerprinting of multimedia and highlight common and unique issues of different fingerprinting techniques. It also provides detailed discussions on the two major classes of fingerprinting strategies, namely, orthogonal fingerprinting and correlated fingerprinting.
Keywords: attacks; colluder; collusion; collusion-resistant; content; correlated; data; digital; fingerprinting; identification; multimedia; multiuser; of; orthogonal; policies; rights; Security; systems; techniques; tracing; watermarking; watermarking

A computational framework for incremental motion - Mount, Dave; Netanyahu,Nathan S.; Piatko,Christine D.; Silverman,Ruth; Wu,Angela Y. (Proceedings of the twentieth annual symposium on Computational geometry, 2004)
We propose a generic computational framework for maintaining a discrete geometric structure defined by a collection of static and mobile objects. We assume that the mobile objects move incrementally, that is, in discrete time steps. We assume that the structure to be maintained is a function of the current locations of the mobile and static objects (independent of their prior motion). Unlike other models for kinetic computation, we place no restrictions on the motion nor on its predictability.In order to handle unrestricted incremental motion, our framework is based on the coordination of two computational entities. The first is the incremental motion algorithm. It is responsible for maintaining the structure and a set of certificates, or conditions, that prove the structure's correctness. The other entity, called the motion processor, is responsible for handling all the low-level aspects of motion, including computing and/or tracking the motion of the mobile objects, answering queries about their current positions and velocities, and validating that the object motions satisfy simple motion estimates, which are generated by the incremental motion algorithm. Computational efficiency is measured in terms of the number of interactions between these two entities.
Keywords: competitive analysis; incremental motion; kinetic data structures

Data hiding in binary image for authentication and annotation - M. Wu; Liu,Bede (Multimedia, IEEE Transactions on, 2004)
This paper proposes a new method to embed data in binary images, including scanned text, figures, and signatures. The method manipulates "flippable" pixels to enforce specific block-based relationship in order to embed a significant amount of data without causing noticeable artifacts. Shuffling is applied before embedding to equalize the uneven embedding capacity from region to region. The hidden data can be extracted without using the original image, and can also be accurately extracted after high quality printing and scanning with the help of a few registration marks. The proposed data embedding method can be used to detect unauthorized use of a digitized signature, and annotate or authenticate binary documents. The paper also presents analysis and discussions on robustness and security issues.
Keywords: annotation; authentication; binary; coding; data; digital; digitized; document; EMBEDDING; encapsulation; extraction; feature; hiding; image; image; method; signature; unauthorized; user; watermarking

Data hiding in curves for collusion-resistant digital fingerprinting - Gou,Hongmei; M. Wu (Image Processing, 2004. ICIP '04. 2004 International Conference on, 2004)
This paper presents a new data hiding method for curves. The proposed algorithm parameterizes a curve using the B-spline model and adds a spread spectrum sequence in the coordinates of the B-spline control points. We demonstrate through experiments the robustness of the proposed data hiding algorithm against printing-and-scanning and collusions, and show its feasibility for collusion-resistant fingerprinting of topographic maps as well as writings/drawings from pen-based input devices.
Keywords: (mathematics); B-spline; coding; collusion-resistant; CONTROL; data; devices; digital; document; encapsulation; extraction; feature; fingerprinting; hiding; image; INPUT; maps; model; pen-based; points; printing-and-scanning; processing; robustness; sequence; spectrum; splines; spread; topographic; watermarking

Data migration on parallel disks - Golubchik,L.; Khuller, Samir; Kim,Y. A; Shargorodskaya,S.; Wan,Y. C (Algorithms–ESA 2004, 2004)
Our work is motivated by the problem of managing data on storage devices, typically a set of disks. Such storage servers are used as web servers or multimedia servers, for handling high demand for data. As the system is running, it needs to dynamically respond to changes in demand for different data items. There are known algorithms for mapping demand to a layout. When the demand changes, a new layout is computed. In this work we study the data migration problem, which arises when we need to quickly change one layout to another. This problem has been studied earlier when for each disk the new layout has been prescribed. However, to apply these algorithms effectively, we identify another problem that we refer to as the correspondence problem, whose solution has a significant impact on the solution for the data migration problem. We study algorithms for the data migration problem in more detail and identify variations of the basic algorithm that seem to improve performance in practice, even though some of the variations have poor worst case behavior.

Distortion compensated lookup-table embedding: Joint security and robustness enhancement for quantization based data hiding - Wu,M. (Electronic Imaging Symposium: Security, Steganography, and Watermarking of Multimedia Contents VI, San Jose, CA, Proc. of SPIE, 2004)
Data embedding mechanism used for authentication applications should be secure in order to prevent an adversaryfrom forging the embedded data at his/her will. Meanwhile, semi-fragileness is often preferred to allow for distinguishing content changes versus non-content changes. In this paper, we focus on jointly enhancing the robustness and security of the embedding mechanism, which can be used as a building block for authentication. The paper presents analysis showing that embedding through a look-up table (LUT) of non-trivial run that maps quantized multimedia features randomly to binary data offers a probability of detection error considerably smaller than that of the traditional quantization embedding. We quantify the security strength of LUT embedding and enhance its robustness through distortion compensation. We introduce a combined security and capacity measure and show that the proposed distortion compensated LUT embedding provides joint enhancement of security and robustness over the traditional quantization embedding.

Distortion management of real-time MPEG-4 video over downlink multicode CDMA networks - Su,Guan-Ming; Han,Zhu; Kwasinski,A.; M. Wu; Liu,K. J.R; Farvardin,N. (Communications, 2004 IEEE International Conference on, 2004)
In this paper, a protocol is designed to manage source rate/channel coding rate adaptation, code allocation, and power control to transmit real-time MPEG-4 FGS video over downlink multicode CDMA networks. We develop a fast adaptive scheme of distortion management to reduce the overall distortion received by all users subject, to the limited number of codes and maximal transmitted power. Compared with a modified greedy method in literature, our proposed algorithm can reduce the overall system's distortion by at least 45%.
Keywords: access; adaptation; allocation; CDMA; channel; code; coding; coding; combined; communication; compression; control; data; distortion; division; downlink; links; management; MPEG-4; multicode; multiple; networks; power; radio; rate; real-time; resource; source; source-channel; video; video; visual

Divergent Gene Copies in the Asexual Class Bdelloidea (Rotifera) Separated Before the Bdelloid Radiation or Within Bdelloid Families - Welch,David B. Mark; Cummings, Michael P.; Hillis,David M; Meselson,Matthew (Proceedings of the National Academy of Sciences of the United States of AmericaPNAS, 2004)
Rotifers of the asexual class Bdelloidea are unusual in possessing two or more divergent copies of every gene that has been examined. Phylogenetic analysis of the heat-shock gene hsp82 and the TATA-box-binding protein gene tbp in multiple bdelloid species suggested that for each gene, each copy belonged to one of two lineages that began to diverge before the bdelloid radiation. Such gene trees are consistent with the two lineages having descended from former alleles that began to diverge after meiotic segregation ceased or from subgenomes of an alloploid ancestor of the bdelloids. However, the original analyses of bdelloid gene-copy divergence used only a single outgroup species and were based on parsimony and neighbor joining. We have now used maximum likelihood and Bayesian inference methods and, for hsp82, multiple outgroups in an attempt to produce more robust gene trees. Here we report that the available data do not unambiguously discriminate between gene trees that root the origin of hsp82 and tbp copy divergence before the bdelloid radiation and those which indicate that the gene copies began to diverge within bdelloid families. The remarkable presence of multiple diverged gene copies in individual genomes is nevertheless consistent with the loss of sex in an ancient ancestor of bdelloids.

Dynamic distortion control for 3-D embedded wavelet video over multiuser OFDM networks - Su,Guan-Ming; Han,Zhu; M. Wu; Liu,K. J.R (Global Telecommunications Conference, 2004. GLOBECOM '04. IEEE, 2004)
In this paper, we propose a system to transmit multiple 3D embedded wavelet video programs over downlink multiuser OFDM. We consider the fairness among users and formulate the problem as minimizing the users' maximal distortion subject to power, rate, and subcarrier constraints. By exploring frequency, time, and multiuser diversity in OFDM and flexibility of the 3D embedded wavelet video codec, the proposed algorithm can achieve fair video qualities among all users. Compared to a scheme similar to the current multiuser OFDM standard (IEEE 802.11a), the proposed scheme outperforms it by 1-5 dB on the worst received PSNR among all users and has much smaller PSNR deviation.
Keywords: 3D; 802.11a; channels; codec; codecs; communication; control; deviation; distortion; diversity; diversity; downlink; dynamic; embedded; fairness; Frequency; IEEE; LAN; maximal; minimax; minimization; modulation; multimedia; multiuser; OFDM; OFDM; PSNR; rate; reception; streaming; systems; techniques; theory; TIME; transforms; video; video; wavelet; wireless

Dynamic join-exit amortization and scheduling for time-efficient group key agreement - Mao,Yinian; Sun,Yan; M. Wu; Liu,K. J.R (INFOCOM 2004. Twenty-third AnnualJoint Conference of the IEEE Computer and Communications Societies, 2004)
We propose a time-efficient contributory key agreement framework for secure communications in dynamic groups. The proposed scheme employs a special join-tree/exit-tree topology in the logical key tree and effectively exploits the efficiency of amortized operations. We derive the optimal parameters and design an activation algorithm for the join and exit trees. We also show that the asymptotic average time cost per user join and leave event is theta;(log (log n)), where n is the group size. Our experiment results on both simulated user activities and the real MBone data have shown that the proposed scheme outperforms the existing tree-based schemes.
Keywords: agreement; asymptotic; average; communication; complexity; computational; cost; cryptography; dynamic; group; join-tree/exit-tree; key; logical; Multicast; network; secure; security; special; Telecommunication; TIME; time-efficient; topology; tree

An Efficient and Robust Human Classification Algorithm using Finite Frequencies Probing - Yang Ran; Weiss, I.; Qinfen Zheng; Davis, Larry S. (Computer Vision and Pattern Recognition Workshop, 2004. CVPRW '04. Conference on, 2004)
This paper describes a periodicity motion detection based object classification algorithm for infrared videos. Given a detected and tracked object, the goal is to analyze the periodic signature of its motion pattern. We propose an efficient and robust solution, which is related to the frequency estimation in speech recognition. Periodic reference functions are correlated with the video signal. Experimental results for both infrared and visible videos acquired by ground-based as well as airborne moving sensors are presented.

Efficient bandwidth resource allocation for low-delay multiuser MPEG-4 video transmission - Su,Guan-Ming; M. Wu (Communications, 2004 IEEE International Conference on, 2004)
An efficient bandwidth resource allocation algorithm with low delay and low fluctuation of quality to transmit multiple MPEG-4 fine granularity scalability (FGS) video programs to multiple users is proposed in this paper. By exploring the variation in the scene complexity of each video program and jointly redistributing available system resources among users, our proposed algorithm provides low fluctuation of quality for each user and consistent quality among all users. Experimental results show that compared to a traditional look-ahead sliding-window approach, our scheme can achieve comparable perceptual quality and channel utilization at a much lower cost of delay, computation, and storage.
Keywords: algorithm; allocation; allocation; approach; Bandwidth; broadband; channel; channels; coding; delays; expert; FGS; fine; granularity; group; look-ahead; moving; MPEG-4; multiuser; networks; of; picture; program; QUALITY; resource; scalability; service; sliding-window; transmission; utilization; video

Efficient Serial and Parallel Algorithms for Querying Large Scale Multidimensional Time Series Data - JaJa, Joseph F.; Kim,J.; Wang,Q. (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2004)
We consider the problem of querying large scale multidimensional time series data to discover events of interest,test and validate hypotheses, or to associate temporal patterns with specific events. Multidimensional time series data is growing at an extremely fast rate due to a number of trends including a recent strong interest in collecting and analyzing time series of business, scientific, demographic, and simulation data. The ability to explore such collections interactively, even at a coarse level, will be critical to the process of extracting some of the information and knowledge embedded in such collections. We develop indexing techniques and search algorithms to efficiently handle temporal range value querying of multidimensional time series data. Our indexing uses linear space data structures that enable the handling of queries very efficiently, invoking in the worst case a logarithmic number of queries to single time steps. We also show that our algorithm is ideally suited for parallel implementation on clusters of processors achieving a linear speedup in the number of available processors. A particularly simple data structure with provably good bounds is also presented for the case when the number of multidimensional objects is relatively small. These techniques improve significantly over previous techniques for either the serial or the parallel case, and are evaluated by extensive experimental results that confirm their superior performance. In particular, we achieve query times in the order of hundreds of milliseconds on a (relatively outdated) cluster of 16 processors for 140GB of data consisting of 160, 000 distinct time series of 16-dimensional points, each time series being of length 10, 000.

Flexible Control of Data Transfers between Parallel Programs - Wu,Joe Shang-Chieh; Sussman, Alan (Proceedings of the 5th IEEE/ACM International Workshop on Grid Computing, 2004)
Allowing loose coupling between complex e-Science applications has many advantages, such as being able to easily incorporate new applications and to flexibly specify how the applications are connected to transfer data between them. To facilitate efficient, flexible data transfers between applications, in this paper we describe methods for making decisions at runtime about when such transfers will occur, and for flexibly specifying when data transfers are desired. We also present preliminary experimental results that measure the overheads incurred by our approach.

Group-oriented fingerprinting for multimedia forensics - Wang,Z. Jane; M. Wu; Trappe,Wade; Liu,K. J.R (EURASIP J. Appl. Signal Process., 2004)
Digital fingerprinting of multimedia data involves embedding information in the content signal and offers protection to the digital rights of the content by allowing illegitimate usage of the content to be identified by authorized parties. One potential threat to fingerprinting is collusion, whereby a group of adversaries combine their individual copies in an attempt to remove the underlying fingerprints. Former studies indicate that collusion attacks based on a few dozen independent copies can confound a fingerprinting system that employs orthogonal modulation. However, in practice an adversary is more likely to collude with some users than with other users due to geographic or social circumstances. To take advantage of prior knowledge of the collusion pattern, we propose a two-tier group-oriented fingerprinting scheme where users likely to collude with each other are assigned correlated fingerprints. Additionally, we extend our construction to represent the natural social and geographic hierarchical relationships between users by developing a more flexible tree-structure-based fingerprinting system. We also propose a multistage colluder identification scheme by taking advantage of the hierarchial nature of the fingerprints. We evaluate the performance of the proposed fingerprinting scheme by studying the collusion resistance of a fingerprinting system employing Gaussian-distributed fingerprints. Our results show that the group-oriented fingerprinting system provides the superior collusion resistance over a system employing orthogonal modulation when knowledge of the potential collusion pattern is available.
Keywords: collusion resistance; group-oriented fingerprinting; multimedia fingerprinting; multimedia forensics; multistage colluder identification

HTN planning for Web Service composition using SHOP2 - Sirin,Evren; Parsia,Bijan; Wu,Dan; Hendler,James; Nau, Dana S. (Web Semantics: Science, Services and Agents on the World Wide Web, 2004)
Automated composition of Web Services can be achieved by using AI planning techniques. Hierarchical Task Network (HTN) planning is especially well-suited for this task. In this paper, we describe how HTN planning system SHOP2 can be used with OWL-S Web Service descriptions. We provide a sound and complete algorithm to translate OWL-S service descriptions to a SHOP2 domain. We prove the correctness of the algorithm by showing the correspondence to the situation calculus semantics of OWL-S. We implemented a system that plans over sets of OWL-S descriptions using SHOP2 and then executes the resulting plans over the Web. The system is also capable of executing information-providing Web Services during the planning process. We discuss the challenges and difficulties of using planning in the information-rich and human-oriented context of Web Services.
Keywords: HTN planning; OWL-S; SHOP2; Web Service composition; Web services

iCLEF 2003 at Maryland: Translation selection and document selection - Dorr, Bonnie J; He,D.; Luo,J.; Oard, Douglas; Schwartz,R.; Wang,J.; Zajic, David (Comparative Evaluation of Multilingual Information Access Systems, 2004)

iCLEF 2003 at Maryland: Translation Selection and Document Selection - Dorr, Bonnie J; He,Daqing; Luo,Jun; Oard, Douglas; Schwartz,Richard; Wang,Jianqiang; Zajic, David (Comparative Evaluation of Multilingual Information Access SystemsComparative Evaluation of Multilingual Information Access Systems, 2004)
Maryland performed two sets of experiments for the 2003 Cross-Language Evaluation Forum’s interactive track, one focused on interactive selection of appropriate translations for query terms, the second focused on interactive selection of relevant documents. Translation selection was supported using possible synonyms discovered through back translation and two techniques for generating KeyWord In Context (KWIC) examples of usage. The results indicate that searchers typically achieved a similar search effectiveness using fewer query iterations when interactive translation selection was available. For document selection, a complete extract of the first 40 words of each news story was compared to a compressed extract generated using an automated parse-and-trim approach that approximates one way in which people can produce headlines. The results indicate that compressed “headlines” result in faster assessment, but with a 20% relative reduction in the F α = 0.8 search effectiveness measure.

iCLEF 2004 at Maryland: Summarization design for interactive cross-language question answering - He,D.; Wang,J.; Luo,J.; Oard, Douglas (Proceeding of Cross Language Evaluation Forum (CLEF2004), 2004)

Image hashing resilient to geometric and filtering operations - Swaminathan,A.; Mao,Yinian; M. Wu (Multimedia Signal Processing, 2004 IEEE 6th Workshop on, 2004)
Image hash functions provide compact representations of images, which is useful for search and authentication applications. In this work, we have identified a general three step framework and proposed a new image hashing scheme that achieves a better overall performance than the existing approaches under various kinds of image processing distortions. By exploiting the properties of discrete polar Fourier transform and incorporating cryptographic keys, the proposed image hash is resilient to geometric and filtering operations, and is secure against guessing and forgery attacks.
Keywords: compact; cryptographic; cryptography; discrete; distortion; Filtering; Fourier; function; geometric; hash; image; key; key; operation; polar; PROCESSING; public; representation; theory; transform; transforms

Interactive binary instrumentation - Williams, C. C; Hollingsworth, Jeffrey K (Second International Workshop on Remote Analysis and Measurement of Software Systems (RAMSS), 2004)

Interactive cross-language document selection - Oard, Douglas; Gonzalo,J.; Sanderson,M.; López-Ostenero,F.; Wang,J. (information retrieval, 2004)

Local Adaption and Dissipation Properties of a Weighted Essentially Non-Oscillatory Scheme - Taylor,E. M; Martin, M.P; Weirs,V. G (34th AIAA Fluid Dynamics Conference and Exhibit, 2004)
We perform several direct numerical simulations (DNS) of decaying isotropic turbulencewith various initial turbulent mach numbers Mt using a modifiedi weighted essentially non-oscillatory (WENO) method. We then present a procedure for the identification of shock-containing and smooth regions where the WENO scheme should respectively engage its adaption mechanism and revert to its linear optimal stencil. Weirsi has previously proposed the centrality index CI and nonlinearity index NI as two quantitative measures of stencil adaption, and we analyze these values within the regions of interest in the DNS flow fields. Our preliminary results indicate that these indices are suitable for assessments of the local adaption and dissipation properties of the WENO method; however, further studies must be conducted over a wider range of compressible flow conditions.

Mandarin-English Information (MEI): investigating translingual speech retrieval - Meng,Helen M.; Chen,Berlin; Khudanpur,Sanjeev; Levow,Gina-Anne; Lo,Wai-Kit; Oard, Douglas; Schone,Patrick; Tang,Karen; Wang,Hsin-Min; Wang,Jianqiang (Computer Speech & Language, 2004)
This paper describes the Mandarin–English Information (MEI) project, where we investigated the problem of cross-language spoken document retrieval (CL-SDR), and developed one of the first English–Chinese CL-SDR systems. Our system accepts an entire English news story (text) as query, and retrieves relevant Chinese broadcast news stories (audio) from the document collection. Hence, this is a cross-language and cross-media retrieval task. We applied a multi-scale approach to our problem, which unifies the use of phrases, words and subwords in retrieval. The English queries are translated into Chinese by means of a dictionary-based approach, where we have integrated phrase-based translation with word-by-word translation. Untranslatable named entities are transliterated by a novel subword translation technique. The multi-scale approach can be divided into three subtasks – multi-scale query formulation, multi-scale audio indexing (by speech recognition) and multi-scale retrieval. Experimental results demonstrate that the use of phrase-based translation and subword translation gave performance gains, and multi-scale retrieval outperforms word-based retrieval.
Keywords: English–Chinese cross-language spoken document retrieval; Multi-scale spoken document retrieval

A model of BGP routing for network engineering - Feamster, Nick; Winick,Jared; Rexford,Jennifer (SIGMETRICS Perform. Eval. Rev., 2004)
The performance of IP networks depends on a wide variety of dynamic conditions. Traffic shifts, equipment failures, planned maintenance, and topology changes in other parts of the Internet can all degrade performance. To maintain good performance, network operators must continually reconfigure the routing protocols. Operators configure BGP to control how traffic flows to neighboring Autonomous Systems (ASes), as well as how traffic traverses their networks. However, because BGP route selection is distributed, indirectly controlled by configurable policies, and influenced by complex interactions with intradomain routing protocols, operators cannot predict how a particular BGP configuration would behave in practice. To avoid inadvertently degrading network performance, operators need to evaluate the effects of configuration changes before deploying them on a live network. We propose an algorithm that computes the outcome of the BGP route selection process for each router in a single AS, given only a static snapshot of the network state, without simulating the complex details of BGP message passing. We describe a BGP emulator based on this algorithm; the emulator exploits the unique characteristics of routing data to reduce computational overhead. Using data from a large ISP, we show that the emulator correctly computes BGP routing decisions and has a running time that is acceptable for many tasks, such as traffic engineering and capacity planning.
Keywords: BGP; modeling; Routing; traffic engineering

Modelling disease outbreaks in realistic urban social networks - Eubank,Stephen; Guclu,Hasan; Kumar,V. S. Anil; Marathe,Madhav V.; Srinivasan, Aravind; Toroczkai,Zolt|[aacute]|n; Wang,Nan (Nature, 2004)
Most mathematical models for the spread of disease use differential equations based on uniform mixing assumptions1 or ad hoc models for the contact process2, 3, 4. Here we explore the use of dynamic bipartite graphs to model the physical contact patterns that result from movements of individuals between specific locations. The graphs are generated by large-scale individual-based urban traffic simulations built on actual census, land-use and population-mobility data. We find that the contact network among people is a strongly connected small-world-like5 graph with a well-defined scale for the degree distribution. However, the locations graph is scale-free6, which allows highly efficient outbreak detection by placing sensors in the hubs of the locations network. Within this large-scale simulation framework, we then analyse the relative merits of several proposed mitigation strategies for smallpox spread. Our results suggest that outbreaks can be contained by a strategy of targeted vaccination combined with early detection without resorting to mass vaccination of a population.

New directions in design for manufacturing - Herrmann,J.W.; Cooper,J.; Gupta,S.K.; Hayes,C. C.; Ishii,K.; Kazmer,D.; Sandborn,P. A.; Wood,W. H. (2004)
This paper gives an overview of research that is expandingthe domain of design for manufacturing (DFM) into new and important areas. This paper covers DFM and concurrent engineering, DFM for conceptual design, DFM for embodiment design, DFM for detailed design, design for production, platform design for reducing time-to-market, design for system quality, design for life cycle costs, and design for environment. The paper concludes with some general guidelines that suggest how manufacturing firms can develop useful, effective DFM tools.

New year’s resolutions for software quality - Basili, Victor R.; Boehm,B.; Davis,A.; Humphrey,W. S; Leveson,N.; Mead,N. R; Musa,J. D; Parnas,D. L; Pfleeger,S. L; Weyuker,E. (IEEE Software, 2004)
In the spirit of making resolutions for betterment in the New Year, ten distinguished individuals in the software quality field offer their recommendations on how organizations can improve software quality In the spirit of making resolutions for betterment in the New Year, ten distinguished individuals in the software quality field offer their recommendations on how organizations can improve software quality.

PAWN: Producer-Archive Workflow Network in support of digital preservation - Smorul,M.; JaJa, Joseph F.; Wang, Y.; McCall,F. (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2004)
We describe the design and the implementation of the PAWN (Producer – ArchiveWorkflow Network) environment to enable secure and distributed ingestion of digital objects into a persistent archive. PAWN was developed to capture the core elements required for long term preservation of digital objects as identified by previous research in the digital library and archiving communities. In fact, PAWN can be viewed as an implementation of the Ingest Process as defined by the Open Archival Information System (OAIS) Reference Model, and is currently being used to ingest significant collections into a pilot persistent archive developed through a collaboration between the San Diego Supercomputer Center, the University of Maryland, and the National Archives and Records Administration. We make use of METS (Metadata Encoding and Transmission Standards) to encapsulate content, structural, descriptive, and preservation metadata. The basic software components are based on open standards and web technologies, and hence are platform independent.

Performance study of ECC-based collusion-resistant multimedia fingerprinting - He,S.; Wu,M. (Proceedings of the 38th CISS, 2004)
Digital fingerprinting is a tool to protect multimediacontent from illegal redistribution by uniquely marking copies of the content distributed to each user. Fingerprinting based on error correction coding (ECC) handle the important issue of how to embed the fingerprint into host data in an abstract way known as the marking assumptions, which often do not fully account for multimedia specific issues. In this paper, we examine the performance of ECC based fingerprinting by considering both coding and embedding issues. We provide performance comparison of ECC-based scheme and a major alternative of orthogonal fingerprinting. As averaging is a feasible and cost-effective collusion attack against multimedia fingerprints yet is generally not considered in the ECC-based system, we also investigate the resistance against averaging collusion and identify avenues for improving collusion resistance.

Security evaluation for communication-friendly encryption of multimedia - Mao,Yinian; M. Wu (Image Processing, 2004. ICIP '04. 2004 International Conference on, 2004)
This paper addresses the access control issues unique to multimedia, by using a joint signal processing and cryptographic approach to multimedia encryption. Based on three atomic encryption primitives, we present a systematic study on how to strategically integrate different atomic operations to build a video encryption system. We also propose a set of multimedia-specific security metrics to quantify the security against approximation attacks and to complement the existing notion of generic data security. The resulting system can provide superior performance to both generic encryption and its simple adaptation to video in terms of a joint consideration of security, bitrate overhead, and communication friendliness.
Keywords: access; approximation; atomic; attacks; bitrate; coding; communication-friendly; communication; control; cryptography; data; encryption; encryption; generic; joint; method; metrics; multimedia; multimedia-specific; overhead; primitives; processing/cryptographic; Security; security; signal; system; Telecommunication; video

Structural and algorithmic aspects of massive social networks - Eubank,Stephen; Kumar,V. S. Anil; Marathe,Madhav V.; Srinivasan, Aravind; Wang,Nan (Proceedings of the fifteenth annual ACM-SIAM symposium on Discrete algorithms, 2004)
We study the algorithmic and structural properties of very large, realistic social contact networks. We consider the social network for the city of Portland, Oregon, USA, developed as a part of the TRANSIMS/EpiSims project at the Los Alamos National Laboratory. The most expressive social contact network is a bipartite graph, with two types of nodes: people and locations; edges represent people visiting locations on a typical day. Three types of results are presented. (i) Our empirical results show that many basic characteristics of the dataset are well-modeled by a random graph approach suggested by Fan Chung Graham and Lincoln Lu (the CL-model), with a power-law degree distribution. (ii) We obtain fast approximation algorithms for computing basic structural properties such as clustering coefficients and shortest paths distribution. We also study the dominating set problem for such networks; this problem arose in connection with optimal sensor-placement for disease-detection. We present a fast approximation algorithm for computing near-optimal dominating sets. (iii) Given the close approximations provided by the CL-model to our original dataset and the large data-volume, we investigate fast methods for generating such random graphs. We present methods that can generate such a random network in near-linear time, and show that these variants asymptotically share many key features of the CL-model, and also match the Portland social network.The structural results have been used to study the impact of policy decisions for controlling large-scale epidemics in urban environments.

Temporal range exploration of large scale multidimensional time series data - JaJa, Joseph F.; Kim,J.; Wang,Q. (Proceedings of SSDBM, 2004)
We consider the problem of querying largescale multidimensional time series data to discover events of interest, test and validate hypotheses, or to associate temporal patterns with specific events. This type of data currently dominate most other types of available data, and will very likely become even more prevalent in the future given the current trends in collecting time series of business, scientific, demographic, and simulation data. The ability to explore such collections interactively, even at a coarse level, will be critical in discovering the information and knowledge embedded in such collections. We develop indexing techniques and search algorithms to efficiently handle temporal range value querying of multidimensional time series data. Our indexing uses linear space data structures that enable the handling of queries in I/O time that is essentially the same as that of handling a single time slice, assuming the availability of a logarithmic number of processors as a function of size of the temporal window. A data structure with provably good bounds is also presented for the case when the number of multidimensional objects is relatively small. These techniques improve significantly over standard techniques for either serial or parallel processing, and are evaluated by extensive experimental results that confirm their superior performance.

Using distributed partial memories to improve self-organizing collective movements - Winder,R.; Reggia, James A. (Systems, Man, and Cybernetics, Part B: Cybernetics, IEEE Transactions on, 2004)

Video-Based Automatic Target Recognition - Zhou,S. K; Chellapa, Rama; Mei,Xue; Wu,Hao; Qinfen Zheng (MARYLAND UNIV COLLEGE PARK CENTER FOR AUTOMATION RESEARCH, 2004)
We present an approach for vehicle classification in IR video sequences by integrating detection, tracking and recognition. The method has two steps. First, the moving target is automatically detected using a detection algorithm. Next, we perform simultaneous tracking and recognition using an appearance-model based particle filter. The tracking result is evaluated at each frame. Low confidence in tracking performance initiates a new cycle of detection, tracking and classification. We demonstrate the robustness of the proposed method using outdoor IR video sequences.
Keywords: *SEQUENCES(MATHEMATICS); *TARGET RECOGNITION; *VEHICLES; *VIDEO RECORDING; algorithms; AUTOMATIC TRACKING.; COMPONENT REPORTS; MOVING TARGETS; SURFACE TRANSPORTATION AND EQUIPMENT; SYMPOSIA; TARGET CLASSIFICATION; TARGET DIRECTION, RANGE AND POSITION FINDING; tracking; VIDEO SIGNALS

Visibility Planning: Predicting Continuous Period of Unobstructed Views - Lim,Ser-Nam; Davis, Larry S.; Wan,Yung-Chun (Justin) (Technical Reports from UMIACS, 2004)
To perform surveillance tasks effectively, unobstructed views ofobjects are required e.g. unobstructed video of objects are often needed for gait recognition. As a result, we need to determine intervals for video collection during which a desired object is visible w.r.t. a given sensor. In addition, these intervals are in the future so that the system can effectively plan and schedule sensors for collecting these videos. We describe an approach to determine these visibility intervals. A Kalman filter is first used to predict the trajectories of the objects. The trajectories are converted to polar coordinate representations w.r.t. a given sensor. Trajectories with the same angular displacement w.r.t. the sensor over time can be found by determining intersection points of functions representing these trajectories. Intervals between these intersection points are suitable for video collection. We also address the efficiency issue of finding these intersection points. An obvious brute force approach of $O(N^2)$ exists, where $N$ is the number of objects. This approach suffices when $N$ is small. When $N$ is large, we introduce an optimal segment intersection algorithm of $O(N\log^2N+I)$, $I$ being the number of intersection points. Finally, we model the prediction errors associated with the Kalman filter using a circular object representation. Experimental results that compare the performance of the brute force and the optimal segment intersection algorithms are shown. (UMIACS-TR-2004-22)
Keywords: Technical Report

Vision Geometry XII - Latecki,L.J.; Mount, Dave; Wu,A. Y (Society of Photo-Optical Instrumentation Engineers (SPIE) Conference Series, 2004)

Vision geometry XII:(San Jose CA, 19-20 January 2004) - Latecki,L.J.; Mount, Dave; Wu,A. Y (SPIE proceedings series, 2004)

Whole-genome shotgun assembly and comparison of human genome assemblies - Istrail,S.; Sutton,G. G; Florea,L.; Halpern,A. L; Mobarry,C. M; Lippert,R.; Walenz,B.; Shatkay,H.; Dew,I.; Miller,J. R; others (Proceedings of the National Academy of Sciences of the United States of America, 2004)

Anti-collusion fingerprinting for multimedia - Trappe,W.; M. Wu; Wang,Z.J.; Liu,K. J.R (Signal Processing, IEEE Transactions on, 2003)
Digital fingerprinting is a technique for identifying users who use multimedia content for unintended purposes, such as redistribution. These fingerprints are typically embedded into the content using watermarking techniques that are designed to be robust to a variety of attacks. A cost-effective attack against such digital fingerprints is collusion, where several differently marked copies of the same content are combined to disrupt the underlying fingerprints. We investigate the problem of designing fingerprints that can withstand collusion and allow for the identification of colluders. We begin by introducing the collusion problem for additive embedding. We then study the effect that averaging collusion has on orthogonal modulation. We introduce a tree-structured detection algorithm for identifying the fingerprints associated with K colluders that requires O(Klog(n/K)) correlations for a group of n users. We next develop a fingerprinting scheme based on code modulation that does not require as many basis signals as orthogonal modulation. We propose a new class of codes, called anti-collusion codes (ACCs), which have the property that the composition of any subset of K or fewer codevectors is unique. Using this property, we can therefore identify groups of K or fewer colluders. We present a construction of binary-valued ACC under the logical AND operation that uses the theory of combinatorial designs and is suitable for both the on-off keying and antipodal form of binary code modulation. In order to accommodate n users, our code construction requires only O( radic;n) orthogonal signals for a given number of colluders. We introduce three different detection strategies that can be used with our ACC for identifying a suspect set of colluders. We demonstrate the performance of our ACC for fingerprinting multimedia and identifying colluders through experiments using Gaussian signals and real images.
Keywords: (mathematics); additive; algorithm; and; anti-collusion; attack; averaging; binary; code; codes; codevectors; coding; colluders; collusion; combinatorial; communication; compression; correlation; cost-effective; data; data; design; DETECTION; detection; digital; embedding; fingerprinting; Gaussian; identification; image; images; keying; logical; mathematics; Modulation; modulation; multimedia; multimedia; of; on-off; operation; orthogonal; processes; real; redistribution; Security; signal; signals; theory; tree-structured; TREES; watermarking

Anti-collusion of group-oriented fingerprinting - Wang,Z.J.; M. Wu; Trappe,W.; Liu,K. J.R (Multimedia and Expo, 2003. ICME '03. Proceedings. 2003 International Conference on, 2003)
Digital fingerprinting of multimedia data involves embedding information in the content, and offers protection to the digital rights of the content by allowing illegitimate usage of the content to be identified by authorized parties. One potential threat to fingerprints is collusion, whereby a group of adversaries combine their individual copies in an attempt to remove the underlying fingerprints. Former studies indicate that collusion attacks based on a few dozen independent copies can confound a fingerprinting system that employs orthogonal modulation. However, since an adversary is more likely to collude with some users than other users, we propose a group-based fingerprinting scheme where users likely to collude with each other are assigned correlated fingerprints. We evaluate the performance of our group-based fingerprints by studying the collusion resistance of a fingerprinting system employing Gaussian distributed fingerprints. We compare the results to those of fingerprinting systems employing orthogonal modulation.
Keywords: anticollusion; attacks; collusion; communication; data; digital; distributed; distribution; fingerprinting; fingerprints; Gaussian; group-oriented; Internet; method; modulation; multimedia; orthogonal; security; Telecommunication; watermarking

Approximation Algorithms for Channel Allocation Problems in Broadcast Networks - Gandhi,Rajiv; Khuller, Samir; Srinivasan, Aravind; Wang,Nan (Approximation, Randomization, and Combinatorial Optimization: Algorithms and Techniques, 2003)
We study two packing problems that arise in the area of dissemination-based information systems; a second theme is the study of distributed approximation algorithms. The problems considered have the property that the space occupied by a collection of objects together could be significantly less than the sum of the sizes of the individual objects. In the Channel Allocation Problem , there are users who request subsets of items. There are a fixed number of channels that can carry an arbitrary amount of information. Each user must get all of the requested items from one channel, i.e., all the data items of each request must be broadcast on some channel. The load on any channel is the number of items that are broadcast on that channel; the objective is to minimize the maximum load on any channel. We present approximation algorithms for this problem and also show that the problem is MAX-SNP hard. The second problem is the Edge Partitioning Problem addressed by Goldschmidt, Hochbaum, Levin, and Olinick ( Networks, 41:13-23, 2003 ). Each channel here can deliver information to at most k users, and we aim to minimize the total load on all channels. We present an O ( n⅓ )–approximation algorithm and also show that the algorithm can be made fully distributed with the same approximation guarantee; we also generalize to the case of hypergraphs.

Automating DAML-S Web Services Composition Using SHOP2 - Wu,Dan; Parsia,Bijan; Sirin,Evren; Hendler,James; Nau, Dana S. (The Semantic Web - ISWC 2003, 2003)
The DAML-S Process Model is designed to support the application of AI planning techniques to the automated composition of Web services. SHOP2 is an Hierarchical Task Network (HTN) planner well-suited for working with the Process Model. We have proven the correspondence between the semantics of SHOP2 and the situation calculus semantics of the Process Model. We have also implemented a system which soundly and completely plans over sets of DAML-S descriptions using a SHOP2 planner, and then executes the resulting plans over the Web. We discuss the challenges and difficulties of using SHOP2 in the information-rich and human-oriented context of Web services.
Keywords: Computer science

Bistro: a scalable and secure data transfer service for digital government applications - Golubchik,Leana; Cheng,William C.; Chou,Cheng-Fu; Khuller, Samir; Samet, Hanan; Wan,C. Justin (Commun. ACM, 2003)
Government at all levels is a major collector and provider of data.Our project focuses on the collection of data over wide-area networks (WANs) and addresses the scalability issues that arise in the context of Internet-based massive data collection applications. Furthermore, security, due to the need for privacy and integrity of the data, is a central issue for data collection applications that use a public infrastructure such as the Internet. Numerous digital government applications require data collection over WANs [5].One compelling example of such an application is the Internal Revenue Service's electronic submission of income tax forms. Other digital government applications include collecting census data, federal statistics, and surveys; gathering and tallying of electronic votes; collecting crime data for the U.S. Justice department; collecting data from sensors for disaster response applications; collecting data from geological surveys; collecting electronic filings of patents, permits, and securities (for SEC) applications; grant proposals and contract bids submissions; and so on. All these applications have scalability and security needs in common.The poor performance that may be experienced by current digital government users, given the existing state of technology (as in Figure 1a), is largely due to how (independent) data transfers using TCP/IP work over the Internet. TCP/IP is good at equally sharing bandwidth between data streams, which in large-scale applications can lead to poor performance for individual clients (as they receive only a very small share of this bandwidth). Given that TCP/IP is here to stay for the foreseeable future, what is needed is a scalable yet cost- effective solution that can be easily deployed over the existing Internet technology.We are designing and developing a system called Bistro, which addresses the scalability needs of digital government data collection applications while allowing them to share the same infrastructure and resources efficiently, cost-effectively, and securely [1]. Bistro's basic approach is to introduce intermediate hosts---bistros---which allow replacement of a traditionally "synchronized client push" approach with a "nonsynchronized combination of client-push and server-pull" approach (as depicted in Figure 1b). This in turn allows spreading of the workload on the destination server and the network over time, with subsequent elimination of hot spots as well as significant improvements in performance for both clients and servers. Our ongoing research [2, 4] indicates that orders of magnitude of improvement can be achieved with the Bistro architecture and the corresponding data collection algorithms it affords.Bistro's design allows for a gradual deployment and experimentation over the Internet (by simply downloading Bistro server software and installing it on public servers). Bistro's security protocol and trust structure [3] are designed such that only encrypted data travels through (not necessarily trusted) bistros. This means a government agency does not need to trust bistros installed by other agencies or commercial institutions. At the same time, these (untrusted) bistros can significantly improve the agency's data collection performance. Each application (within each agency) can have its own scalability, security, fault tolerance, and other data collection needs, and these applications and agencies can still share available resources, if so desired, across all Bistro servers.We believe an appropriately designed single infrastructure such as Bistro can address all digital government wide-area data collection needs in a scalable, secure, and cost-effective manner. (For more information, see bourbon.usc.edu/iml/bistro/.

Bistro: a scalable and secure data transfer service for digital government applications - Golubchik,Leana; Cheng,William C.; Chou,Cheng-Fu; Khuller, Samir; Samet, Hanan; Wan,C. Justin (Communications of the ACM, 2003)
Government at all levels is a major collector and provider of data.Our project focuses on the collection of data over wide-area networks (WANs) and addresses the scalability issues that arise in the context of Internet-based massive data collection applications. Furthermore, security, due to the need for privacy and integrity of the data, is a central issue for data collection applications that use a public infrastructure such as the Internet. Numerous digital government applications require data collection over WANs [5].One compelling example of such an application is the Internal Revenue Service's electronic submission of income tax forms. Other digital government applications include collecting census data, federal statistics, and surveys; gathering and tallying of electronic votes; collecting crime data for the U.S. Justice department; collecting data from sensors for disaster response applications; collecting data from geological surveys; collecting electronic filings of patents, permits, and securities (for SEC) applications; grant proposals and contract bids submissions; and so on. All these applications have scalability and security needs in common.The poor performance that may be experienced by current digital government users, given the existing state of technology (as in Figure 1a), is largely due to how (independent) data transfers using TCP/IP work over the Internet. TCP/IP is good at equally sharing bandwidth between data streams, which in large-scale applications can lead to poor performance for individual clients (as they receive only a very small share of this bandwidth). Given that TCP/IP is here to stay for the foreseeable future, what is needed is a scalable yet cost- effective solution that can be easily deployed over the existing Internet technology.We are designing and developing a system called Bistro, which addresses the scalability needs of digital government data collection applications while allowing them to share the same infrastructure and resources efficiently, cost-effectively, and securely [1]. Bistro's basic approach is to introduce intermediate hosts---bistros---which allow replacement of a traditionally "synchronized client push" approach with a "nonsynchronized combination of client-push and server-pull" approach (as depicted in Figure 1b). This in turn allows spreading of the workload on the destination server and the network over time, with subsequent elimination of hot spots as well as significant improvements in performance for both clients and servers. Our ongoing research [2, 4] indicates that orders of magnitude of improvement can be achieved with the Bistro architecture and the corresponding data collection algorithms it affords.Bistro's design allows for a gradual deployment and experimentation over the Internet (by simply downloading Bistro server software and installing it on public servers). Bistro's security protocol and trust structure [3] are designed such that only encrypted data travels through (not necessarily trusted) bistros. This means a government agency does not need to trust bistros installed by other agencies or commercial institutions. At the same time, these (untrusted) bistros can significantly improve the agency's data collection performance. Each application (within each agency) can have its own scalability, security, fault tolerance, and other data collection needs, and these applications and agencies can still share available resources, if so desired, across all Bistro servers.We believe an appropriately designed single infrastructure such as Bistro can address all digital government wide-area data collection needs in a scalable, secure, and cost-effective manner. (For more information, see bourbon.usc.edu/iml/bistro/.

Classification-based spatial error concealment for images - Chen,M.; Wu,M.; Zheng,Y. (Image Processing, 2003. ICIP 2003. Proceedings. 2003 International Conference on, 2003)
This paper presents a new, classification-based spatial error concealment algorithm for images. The proposed scheme takes advantage of two state-of-the-art concealment schemes and adaptively selects a better suitable concealment scheme for each corrupted block. Using a support vector machine (SVM) classifier, our proposed approach outperforms the prior art in terms of the concealment quality and has moderate computational complexity.
Keywords: algorithm; classification-based; classification; classifier; complexity; computational; concealment; error; image; Machine; machines; moderate; scheme; spatial; state-of-the-art; Support; SVM; vector

Comparing bootstrap and posterior probability values in the four-taxon case - Cummings, Michael P.; Handley,S. A; Myers,D. S; Reed,D. L; Rokas,A.; Winka,K. (Syst Biol, 2003)
Assessment of the reliability of a given phylogenetic hypothesis is an important step in phylogenetic analysis. Historically, the nonparametric bootstrap procedure has been the most frequently used method for assessing the support for specific phylogenetic relationships. The recent employment of Bayesian methods for phylogenetic inference problems has resulted in clade support being expressed in terms of posterior probabilities. We used simulated data and the four-taxon case to explore the relationship between nonparametric bootstrap values (as inferred by maximum likelihood) and posterior probabilities (as inferred by Bayesian analysis). The results suggest a complex association between the two measures. Three general regions of tree space can be identified: (1) the neutral zone, where differences between mean bootstrap and mean posterior probability values are not significant, (2) near the two-branch corner, and (3) deep in the two-branch corner. In the last two regions, significant differences occur between mean bootstrap and mean posterior probability values. Whether bootstrap or posterior probability values are higher depends on the data in support of alternative topologies. Examination of star topologies revealed that both bootstrap and posterior probability values differ significantly from theoretical expectations; in particular, there are more posterior probability values in the range 0.85-1 than expected by theory. Therefore, our results corroborate the findings of others that posterior probability values are excessively high. Our results also suggest that extrapolations from single topology branch-length studies are unlikely to provide any general conclusions regarding the relationship between bootstrap and posterior probability values.

Comparing user-assisted and automatic query translation - He,D.; Wang,J.; Oard, Douglas; Nossal,M. (Advances in cross-language information retrieval, 2003)

Data hiding in image and video .I. Fundamental issues and solutions - M. Wu; Liu,Bede (Image Processing, IEEE Transactions on, 2003)
We address a number of fundamental issues of data hiding in image and video and propose general solutions to them. We begin with a review of two major types of embedding, based on which we propose a new multilevel embedding framework to allow the amount of extractable data to be adaptive according to the actual noise condition. We then study the issues of hiding multiple bits through a comparison of various modulation and multiplexing techniques. Finally, the nonstationary nature of visual signals leads to highly uneven distribution of embedding capacity and causes difficulty in data hiding. We propose an adaptive solution switching between using constant embedding rate with shuffling and using variable embedding rate with embedded control bits. We verify the effectiveness of our proposed solutions through analysis and simulation.
Keywords: adaptive; analysis; bits; colour; condition; constant; CONTROL; data; embedded; EMBEDDING; embedding; encapsulation; extractable; hiding; image; Modulation; modulation; multilevel; multiplexing; multiplexing; NOISE; nonstationary; processing; rate; reviews; shuffling; signal; signals; simulation; solution; techniques; variable; video; visual

Data hiding in image and video .II. Designs and applications - M. Wu; Yu,H.; Liu,Bede (Image Processing, IEEE Transactions on, 2003)
For pt. I see ibid., vol.12, no.6, p.685-95 (2003). This paper applies the solutions to the fundamental issues addressed in Part I to specific design problems of embedding data in image and video. We apply multilevel embedding to allow the amount of embedded information that can be reliably extracted to be adaptive with respect to the actual noise conditions. When extending the multilevel embedding to video, we propose strategies for handling uneven embedding capacity from region to region within a frame as well as from frame to frame. We also embed control information to facilitate the accurate extraction of the user data payload and to combat such distortions as frame jitter. The proposed algorithm can be used for a variety of applications such as copy control, access control, robust annotation, and content-based authentication.
Keywords: access; annotation; authentication; capacity; conditions; content-based; CONTROL; control; copy; data; distortions; EMBEDDING; embedding; encapsulation; extraction; frame; hiding; image; information; jitter; message; multilevel; NOISE; noise; payload; processing; robust; signal; uneven; user; video

Defeating Web censorship with untrusted messenger discovery - Feamster, Nick; Balazinska,M.; Wang,W.; Balakrishnan,H.; Karger,D. (Workshop on Privacy Enhancing Technologies, 2003)

Designing a digital library for young children: An intergenerational partnership - Druin, Allison; Bederson, Benjamin B.; Hourcade,J. P; Sherman,L.; Revelle,G.; Platner,M.; Weng,S. (The craft of information visualization: readings and reflections, 2003)

Desparately seeking cebuano - Oard, Douglas; David Doermann; Dorr, Bonnie J; He,D.; Resnik, Philip; Weinberg, Amy; Byrne,W.; Khudanpur,S.; Yarowsky,D.; Leuski,A.; others (Third Conference on Human Language Technologies, 2003)
This paper describes an effort to rapidly de-velop language resources and component tech- nology to support searching Cebuano news sto- ries using English queries. Results from the first 60 hours of the exercise are presented.

Digital Government-Bistro: A Scalable and Secure Data Transfer Service for Digital Government Applications - Golubchik,L.; Cheng,W. C; Chou,C. F; Khuller, Samir; Samet, Hanan; Wan,Y. C.J (Communications of the ACM-Association for Computing Machinery-CACM, 2003)

The dog genome: survey sequencing and comparative analysis - Kirkness,E. F; Bafna,V.; Halpern,A. L; Levy,S.; Remington,K.; Rusch,D. B; Delcher,A. L; Pop, Mihai; Wang,W.; Fraser,C. M; others (Science, 2003)

The Dog Genome: Survey Sequencing and Comparative Analysis - Kirkness,Ewen F.; Bafna,Vineet; Halpern,Aaron L.; Levy,Samuel; Remington,Karin; Rusch,Douglas B; Delcher,Arthur L.; Pop, Mihai; Wang,Wei; Fraser,Claire M.; Venter,J. Craig (ScienceScience, 2003)
A survey of the dog genome sequence (6.22 million sequence reads; 1.5× coverage) demonstrates the power of sample sequencing for comparative analysis of mammalian genomes and the generation of species-specific resources. More than 650 million base pairs (>25%) of dog sequence align uniquely to the human genome, including fragments of putative orthologs for 18,473 of 24,567 annotated human genes. Mutation rates, conserved synteny, repeat content, and phylogeny can be compared among human, mouse, and dog. A variety of polymorphic elements are identified that will be valuable for mapping the genetic basis of diseases and traits in the dog.

Dynamic rebinding for marshalling and update, with destruct-time ? - Bierman,Gavin; Hicks, Michael W.; Sewell,Peter; Stoyle,Gareth; Wansbrough,Keith (Proceedings of the eighth ACM SIGPLAN international conference on Functional programming, 2003)
Most programming languages adopt static binding, but for distributed programming an exclusive reliance on static binding is too restrictive: dynamic binding is required in various guises, for example when a marshalled value is received from the network, containing identifiers that must be rebound to local resources. Typically it is provided only by ad-hoc mechanisms that lack clean semantics.In this paper we adopt a foundational approach, developing core dynamic rebinding mechanisms as extensions to simply-typed call-by-value ? -calculus. To do so we must first explore refinements of the call-by-value reduction strategy that delay instantiation, to ensure computations make use of the most recent versions of rebound definitions. We introduce redex-time and destruct-time strategies. The latter forms the basis for a ?marsh calculus that supports dynamic rebinding of marshalled values, while remaining as far as possible statically-typed. We sketch an extension of ? marsh with concurrency and communication, giving examples showing how wrappers for encapsulating untrusted code can be expressed. Finally, we show that a high-level semantics for dynamic updating can also be based on the destruct-time strategy, defining a ?marsh calculus with simple primitives to provide type-safe updating of running code. We thereby establish primitives and a common semantic foundation for a variety of real-world dynamic rebinding requirements.
Keywords: distributed programming; dynamic binding; dynamic update; lambda calculus; marshalling; programming languages; serialisation

Efficiency improvements for signature schemes with tight security reductions - Katz, Jonathan; Wang,Nan (Proceedings of the 10th ACM conference on Computer and communications security, 2003)
Much recent work has focused on constructing efficient digital signature schemes whose security is tightly related to the hardness of some underlying cryptographic assumption. With this motivation in mind, we show here two approaches which improve both the computational efficiency and signature length of some recently-proposed schemes:Diffie-Hellman signatures. Goh and Jarecki [18] recently analyzed a signature scheme which has a tight security reduction to the computational Diffie-Hellman problem. Unfortunately, their scheme is less efficient in both computation and bandwidth than previous schemes relying on the (related) discrete logarithm assumption. We present a modification of their scheme in which signing is 33% more efficient and signatures are 75% shorter; the security of this scheme is tightly related to the decisional Diffie-Hellman problem.PSS. The probabilistic signature scheme (PSS) designed by Bellare and Rogaway [3] uses a random salt to enable a tight security reduction to, e.g., the RSA problem. Coron [12] subsequently showed that a shorter random salt can be used without impacting the security of the scheme. We show a variant of PSS which avoids the random salt altogether yet has an equally-tight security reduction. This furthermore yields a version of PSS-R (PSS with message recovery) with optimal message length. Our technique may also be used to improve the efficiency of a number of other schemes.
Keywords: digital; SIGNATURES

Evaluating Translational Correspondence using Annotation Projection - Hwa,R.; Resnik, Philip; Weinberg, Amy; Kolak,O. (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2003)
Recently, statistical machine translation models have begun to take advantage of higherlevel linguistic structures such as syntactic dependencies. Underlying these models is an assumption about the directness of translational correspondence between sentences in the two languages; however, the extent to which this assumption is valid and useful is not well understood. In this paper, we present an empirical study that quantifies the degree to which syntactic dependencies are preserved when parses are projected directly from En- glish to Chinese. Our results show that although the direct correspondence assumption is often too restrictive, a small set of principled, elementary linguistic transformations can boost the quality of the projected Chinese parses by 76% relative to the unimproved baseline.

Experimental validation of new software technology - Zelkowitz, Marvin V; Wallace,D. R; Binkley,D. W (SERIES ON SOFTWARE ENGINEERING AND KNOWLEDGE ENGINEERING, 2003)
When to apply a new technology in an organization is acritical decision for every software development organization. Earlier work defines a set of methods that the research community uses when a new technology is developed. This chapter presents a discussion of the set of methods that industrial organizations use before adopting a new technology. First there is a brief definition of the earlier research methods and then a definition of the set of industrial methods. A comparison of the two sets leads into the perspectives of these methods of experts in the research and industrial community via surveys made to those communities.

The genome sequence of Bacillus anthracis Ames and comparison to closely related bacteria - Read,Timothy D.; Peterson,Scott N.; Tourasse,Nicolas; Baillie,Les W.; Paulsen,Ian T.; Nelson,Karen E.; Tettelin,Herv|[eacute]|; Fouts,Derrick E.; Eisen,Jonathan A.; Gill,Steven R.; Holtzapple,Erik K.; |[Oslash]|kstad,Ole Andreas; et al. (Nature, 2003)
Bacillus anthracis is an endospore-forming bacterium that causes inhalational anthrax1. Key virulence genes are found on plasmids (extra-chromosomal, circular, double-stranded DNA molecules) pXO1 (ref. 2) and pXO2 (ref. 3). To identify additional genes that might contribute to virulence, we analysed the complete sequence of the chromosome of B. anthracis Ames (about 5.23 megabases). We found several chromosomally encoded proteins that may contribute to pathogenicity—including haemolysins, phospholipases and iron acquisition functions—and identified numerous surface proteins that might be important targets for vaccines and drugs. Almost all these putative chromosomal virulence and surface proteins have homologues in Bacillus cereus, highlighting the similarity of B. anthracis to near-neighbours that are not associated with anthrax4. By performing a comparative genome hybridization of 19 B. cereus and Bacillus thuringiensis strains against a B. anthracis DNA microarray, we confirmed the general similarity of chromosomal genes among this group of close relatives. However, we found that the gene sequences of pXO1 and pXO2 were more variable between strains, suggesting plasmid mobility in the group. The complete sequence of B. anthracis is a step towards a better understanding of anthrax pathogenesis.

HCIL Technical Report Listing (1993-2002) - Ceaparu,I.; Druin, Allison; Guimbretiere,F.; Manipulation,D.; Shneiderman, Ben; Westerlurid,B.; Keogh,E.; Hochheiser,H.; Shrieidemian,B.; Shneidemiari,B.; others (The craft of information visualization: readings and reflections, 2003)

Human visual model for data hiding - M. Wu; Yu,Hong Heather (2003)
A method and apparatus of hiding identification data in visual media. When image or video data is received, frequency masking is performed to divide the image or video data into blocks of smooth regions and blocks of non-smooth regions and to obtain preliminary just-noticeable-difference. Edge detection is performed to divide the non-smooth region of the image or video data into texture blocks and edge blocks. Then blocks of regions that are substantially proximate to blocks of smooth regions of the image or video data are determined. The image or video data is then adjusted by applying different strength of watermark in association with the type of each block.

Improving the Arabidopsis genome annotation using maximal transcript alignment assemblies - Haas,Brian J.; Delcher,Arthur L.; Mount, Stephen M.; Wortman,Jennifer R.; Jr,Roger K. Smith; Hannick,Linda I.; Maiti,Rama; Ronning,Catherine M.; Rusch,Douglas B; Town,Christopher D.; Salzberg,Steven L.; White,Owen (Nucleic Acids ResearchNucl. Acids Res., 2003)
The spliced alignment of expressed sequence data to genomic sequence has proven a key tool in the comprehensive annotation of genes in eukaryotic genomes. A novel algorithm was developed to assemble clusters of overlapping transcript alignments (ESTs and full‐length cDNAs) into maximal alignment assemblies, thereby comprehensively incorporating all available transcript data and capturing subtle splicing variations. Complete and partial gene structures identified by this method were used to improve The Institute for Genomic Research Arabidopsis genome annotation (TIGR release v.4.0). The alignment assemblies permitted the automated modeling of several novel genes and >1000 alternative splicing variations as well as updates (including UTR annotations) to nearly half of the ∼27 000 annotated protein coding genes. The algorithm of the Program to Assemble Spliced Alignments (PASA) tool is described, as well as the results of automated updates to Arabidopsis gene annotations.

In vivo filtering of in vitro expression data reveals MyoD targets - Zhao,Po; Seo,Jinwook; Wang,Zuyi; Wang,Yue; Shneiderman, Ben; Hoffman,Eric P (Comptes Rendus Biologies, 2003)
A published set of downstream targets of MyoD defined in a well-controlled in vitro experiment was filtered for relevance to muscle regeneration using a 27-time-point in vivo murine regeneration series. Using interactive hierarchical and Bayes soft clustering, only a minority of the targets defined in vitro can be confirmed in vivo (∼50% of induced transcripts, and none of repressed transcripts). This approach provided strong support that 18 targets including of MyoD are biologically relevant during myoblast differentiation. To cite this article: P. Zhao et al., C. R. Biologies 326 (2003).
Keywords: clustering; expression profiling; Microarray; microréseaux; muscle regeneration; MyoD; profil d'expression; régénération musculaire; regroupement

Integrality ratio for group Steiner trees and directed steiner trees - Halperin,Eran; Kortsarz,Guy; Krauthgamer,Robert; Srinivasan, Aravind; Wang,Nan (Proceedings of the fourteenth annual ACM-SIAM symposium on Discrete algorithms, 2003)
We present an Ω(log2k) lower bound on the integrality ratio of the flow-based relaxation for the Group Steiner Tree problem, where k denotes the number of groups; this holds even for input graphs that are Hierarchically Well-Separated Trees, introduced by Bartal [Symp. Foundations of Computer Science, pp. 184--193, 1996], in which case this lower bound is tight. This relaxation appears to be the only one that have been studied for the problem, as well as for its generalization, the Directed Steiner Tree problem. For the latter problem, our results imply an Ω(log2n/(log logn)2) integrality ratio, where n is the number of vertices in the graph. For both problems, this is the first known lower bound on the integrality ratio that is superlogarithmic in the input size. We also show algorithmically that the integrality ratio for Group Steiner Tree is much better for certain families of instances, which helps pinpoint the types of instances that appear to be most difficult to approximate.

The International Children's Digital Library - Druin, Allison; Bederson, Benjamin B.; Weeks,A.; Farber,A.; Grosjean,J.; Guha,M.L.; Hourcade,J. P; Lee,J.; Liao,S.; Reuter,K.; others (First Monday, 2003)

The International Children's Digital Library: Description and analysis of first use - Druin, Allison; Bederson, Benjamin B.; Weeks,A.; Farber,A.; Grosjean,J.; Guha,M.L.; Hourcade,J. P; Lee,J.; Liao,S.; Reuter,K.; others (First Monday, 2003)

Joint security and robustness enhancement for quantization based data embedding - Wu,M. (Circuits and Systems for Video Technology, IEEE Transactions on, 2003)
The paper studies joint security and robustness enhancement of quantization-based data embedding for multimedia authentication applications. We present an analysis showing that through a nontrivial run lookup table (LUT) that maps quantized multimedia features randomly to binary data, the probability of detection error can be considerably smaller than the traditional quantization embedding. We quantify the security strength of LUT embedding and enhance its robustness through distortion compensation. Introducing a joint security and capacity measure, we show that the proposed distortion-compensated LUT embedding provides joint enhancement of security and robustness over the traditional quantization embedding.
Keywords: (signal); authentication; binary; compensation; data; data; DETECTION; digital; distortion; distortion; embedding; encapsulation; enhancement; error; features; hiding; lookup; lookup; LUT; message; multimedia; nontrivial; probability; quantisation; quantization; quantized; Robustness; run; Security; statistics; systems; table; table; watermarking

Joint security robustness enhancement for quantization embedding - Wu,M. (Image Processing, 2003. ICIP 2003. Proceedings. 2003 International Conference on, 2003)
This paper studies joint security and robustness enhancement of quantization based data embedding for multimedia authentication applications. We present analysis showing that through a lookup table (LUT) of nontrivial run that maps quantized multimedia features randomly to binary data, the detection error probability can be considerably smaller than the traditional quantization embedding. We quantify the security strength of LUT embedding and enhance its robustness through distortion compensation. Introducing a joint security and capacity measure, we show that the proposed distortion compensated LUT embedding provides joint enhancement of security and robustness over the traditional quantization embedding.
Keywords: applications; Authentication; authentication; binary; communication; data; data; embedding; error; joint; lookup; lookup; message; multimedia; probability; security; statistics; table; table; watermarking

Latency Profiles: Performance Monitoring for Wide Area Applications - Raschid, Louiqa; Wen,Hui-Fang; Gal,Avigdor; Zadorozhny,Vladimir (Internet Applications, IEEE Workshop on, 2003)
Recent technological advances have enabled the deployment of wide area applications against Internet accessible sources. A performance challenge to applications in such a setting is the unpredictable end-to-end latency of accessing these sources. We use passive information gathering mechanisms to learn end-to-end latency distributions and construct Latency Profiles (LPs). We hypothesize that a group of clients, within an autonomous system (AS), that are accessing a content server, in another AS, may be represented by (one or more) LPs. Related networking research on IDMaps, points of congestion, and BGP routes support such hypothesis. We develop aggregate LPs to provide coverage of groups (clusters) of client-server pairs. Using data gathered from a (limited) experiment we demonstrate the feasibility of constructing LPs.

Making miracles: Interactive translingual search for cebuano and hindi - He,D.; Oard, Douglas; Wang,J.; Luo,J.; Demner-Fushman,D.; Darwish,K.; Resnik, Philip; Khudanpur,S.; Nossal,M.; Subotin,M.; others (ACM Transactions on Asian Language Information Processing (TALIP), 2003)

Multimedia Data Hiding - M. Wu; Liu,Bede (Springer, 2003)
With the advances of the digital information revolution and the societal changes they have prompted, it has become critical to facilitate secure management of content usage and delivery across communication networks. Data hiding and digital watermarking are promising new technologies for multimedia information protection and rights management. Multimedia Data Hiding addresses the theory, methods, and design of multimedia data hiding and its application to multimedia rights management, information security, and communication. It offers theoretical and practical aspects, and both design and attack problems. Applications discussed include: annotation, tamper detection, copy/access control, fingerprinting, and ownership protection. Countermeasures for attacks on data hiding are discussed, and a chapter assesses attack problems on digital music protection under a unique competitive environment. Topics and features: * Comprehensive and practical coverage of data hiding for various media types, including binary image, grayscale and color images and video, and audio * Provides unique analysis of problems and solutions, such as data hiding in binary signature and generic binary documents, block concealment attacks, and attacks on audio watermarking * Authoritative discussion and analysis of data hiding and effective countermeasures, supported by concrete application examples * Accessible, well-organized progression from the fundamentals to specific approaches to various data-hiding problems This work offers a state-of-the-art presentation covering theoretical, algorithmic, and design topics for digital content/data security protection, and rights management. It is an essential resource for multimedia security researchers and professionals in electrical engineering, computer science, IT, and digital rights management.
Keywords: computer security; Computers / Computer Engineering; Computers / Computer Science; Computers / Database Management / General; Computers / Information Technology; Computers / Information Theory; Computers / Interactive & Multimedia; Computers / Networking / General; Computers / Security / Cryptography; Computers / Security / General; Computers / System Administration / Storage & Retrieval; Data encryption (Computer science); multimedia systems; Technology & Engineering / Electrical; Technology & Engineering / Engineering (General)

Nonlinear collusion attacks on independent fingerprints for multimedia - Zhao,Hong; M. Wu; Wang,Z.J.; Liu,K. J.R (Acoustics, Speech, and Signal Processing, 2003. Proceedings. (ICASSP '03). 2003 IEEE International Conference on, 2003)
Digital fingerprinting is a technology for tracing the distribution of multimedia content and protecting them from unauthorized redistribution. Collusion attack is a cost effective attack against digital fingerprinting where several copies with the same content but different fingerprints are combined to remove the original fingerprints. In this paper, we investigate average and nonlinear collusion attacks of independent Gaussian fingerprints and study both their effectiveness and the perceptual quality. We also propose the bounded Gaussian fingerprints to improve the perceptual quality of the fingerprinted copies. We further discuss the tradeoff between the robustness against collusion attacks and the perceptual quality of a fingerprinting system.
Keywords: attacks; average; bounded; collusion; computing; content; copies; digital; distribution; fingerprinted; fingerprinting; fingerprints; Gaussian; independent; multimedia; nonlinear; perceptual; quality; robustness; watermarking

On-line computation of two types of structural relations in Japanese - Aoshima,S.; Phillips,C.; Weinberg, Amy (2003)

Overlaying graph links on treemaps - Fekete,J. D; Wang,D.; Dang,N.; Aris,A.; Plaisant, Catherine (IEEE Symposium on Information Visualization Conference Compendium (demonstration), 2003)
Every graph can be decomposed into a tree structure plus a set ofremaining edges. We describe a visualization technique that displays the tree structure as a Treemap and the remaining edges as curved links overlaid on the Treemap. Link curves are designed to show where the link starts and where it ends without requiring an explicit arrow that would clutter the already dense visualization. This technique is effective for visualizing structures where the underlying tree has some meaning, such as Web sites or XML documents with cross-references. Graphic attributes of the links – such as color or thickness – can be used to represent attributes of the edges. Users can choose to see all links at once or only the links to and from the node or branch under the cursor.

Parsing and Tagging of Bilingual Dictionaries - Ma,Huanfeng; Karagol-Ayan,Burcu; David Doermann; Oard, Douglas; Wang,Jianqiang (TALTraitement Automatique Des Langues, 2003)
Bilingual dictionaries hold great potential as a source of lexical resources for training and testing automated systems for optical character recognition, machine translation, and cross-language information retrieval. In this paper, we describe a system for extracting term lexicons from printed bilingual dictionaries. Our work was divided into three phases - dictionary segmentation, entry tagging, and generation. In segmentation, pages are divided into logical entries based on structural features learned from selected examples. The extracted entries are associated with functional labels and passed to a tagging module which associates linguistic labels with each word or phrase in the entry. The output of the system is a structure that represents the entries from the dictionary. We have used this approach to parse a variety of dictionaries with both Latin and non-Latin alphabets, and demonstrate the results of term lexicon generation for retrieval from a collection of French news stories using English queries.

Performance of detection statistics under collusion attacks on independent multimedia fingerprints - Zhao,Hong; M. Wu; Wang,Z.J.; Liu,K. J.R (Multimedia and Expo, 2003. ICME '03. Proceedings. 2003 International Conference on, 2003)
Digital fingerprinting is a technology for tracing the distribution of multimedia content and protecting them from unauthorized redistribution. Collusion attack is a cost effective attack against digital fingerprinting where several copies with the same content but different fingerprints are combined to remove the original fingerprints. In this paper, we consider average attack and several nonlinear collusion attacks on independent Gaussian based fingerprints, and study the detection performance of several commonly used detection statistics in the literature under collusion attacks. Observing that these detection statistics are not specifically designed for collusion scenarios and do not take into account the characteristics of the newly generated fingerprints under collusion attacks, we propose pre-processing techniques to improve the detection performance of the detection statistics under collusion attacks.
Keywords: analysis; attacks; based; collusion; content; DETECTION; digital; fingerprint; fingerprinting; fingerprints; Gaussian; identification; independent; multimedia; performance; preprocessing; processes; redistribution; security; statistical; statistics; systems; techniques; Telecommunication; unauthorized

Resistance of orthogonal Gaussian fingerprints to collusion attacks - Wang,Z.J.; M. Wu; Zhao,Hong; Liu,K. J.R; Trappe,W. (Multimedia and Expo, 2003. ICME '03. Proceedings. 2003 International Conference on, 2003)
Digital fingerprinting is a means to offer protection to digital data by which fingerprints embedded in the multimedia are capable of identifying unauthorized use of digital content. A powerful attack that can be employed to reduce this tracing capability is collusion. In this paper, we study the collusion resistance of a fingerprinting system employing Gaussian distributed fingerprints and orthogonal modulation. We propose a likelihood-based approach to estimate the number of colluders, and introduce the thresholding detector for colluder identification. We first analyze the collusion resistance of a system to the average attack by considering the probability of a false negative and the probability of a false positive when identifying colluders. Lower and upper bounds for the maximum number of colluders Kmax are derived. We then show that the detectors are robust to different attacks. We further study different sets of performance criteria.
Keywords: approach; attacks; capability; collusion; data; data; digital; distributed; embedded; fingerprinting; fingerprints; Gaussian; likelihood-based; modulation; multimedia; of; orthogonal; probability; processes; protection; Security; systems; tracing

Scriptroute: A public Internet measurement facility - Spring, Neil; Wetherall,D.; Anderson,T. (Proceedings of the 4th conference on USENIX Symposium on Internet Technologies and Systems-Volume 4, 2003)

The sequence and analysis of Trypanosoma brucei chromosome II - El‐Sayed, Najib M.; Ghedin,E.; Song,J.; MacLeod,A.; Bringaud,F.; Larkin,C.; Wanless,D.; Peterson,J.; Hou,L.; Taylor,S.; others (Nucleic acids research, 2003)

SHOP2: An HTN planning system - Nau, Dana S.; Au,T. C; Ilghami,O.; Kuter,U.; Murdock,J. W.; Wu,D.; Yaman,F. (J. Artif. Intell. Res. (JAIR), 2003)
The SHOP2 planning system received one of the awards for distinguished performance in the 2002 International Planning Competition. This paper describes the features of SHOP2 which enabled it to excel in the competition, especially those aspects of SHOP2 that deal with temporal and metric planning domains.

Starting an intergenerational technology design team: a case study - Knudtzon,Kendra; Druin, Allison; Kaplan,Nancy; Summers,Kathryn; Chisik,Yoram; Kulkarni,Rahul; Moulthrop,Stuart; Weeks,Holly; Bederson, Benjamin B. (Proceedings of the 2003 conference on Interaction design and children, 2003)
This paper presents a case study of the first three months of a new intergenerational design team with children ages 10--13. It discusses the research and design methods used for working with children of this age group, the challenges and opportunities of starting a new team, and the lessons learned.
Keywords: children; cooperative inquiry; design methods; educational applications; intergenerational design teams; participatory design

Tagging and Parsing of Bilingual Dictionary - Ma,Huanfeng; Karagol-Ayan,Burcu; David Doermann; Oard, Douglas; Wang,Jianqiang (University of Maryland, College Park, 2003)
Bilingual dictionaries hold great potential as a source of lexical resources for training and testing automated systems for optical character recognition, machine translation, and cross-language information retrieval. In this paper, we describe a system for extracting term lexicons from printed bilingual dictionaries. Our work was divided into three phases - dictionary segmentation, entry tagging, and generation. In segmentation, pages are divided into logical entries based on structural features learned from selected examples. The extracted entries are associated with functional labels and passed to a tagging module which associates linguistic labels with each word or phrase in the entry. The output of the system is a structure that represents the entries from the dictionary. We have used this approach to parse a variety of dictionaries with both Latin and non-Latin alphabets, and demonstrate the results of term lexicon generation for retrieval from a collection of French news stories using English queries.

Technology probes: inspiring design for and with families - Hutchinson,Hilary; Mackay,Wendy; Westerlund,Bo; Bederson, Benjamin B.; Druin, Allison; Plaisant, Catherine; Beaudouin-Lafon,Michel; Conversy,Stéphane; Evans,Helen; Hansen,Heiko; Roussel,Nicolas; Eiderbäck,Björn (Proceedings of the SIGCHI conference on Human factors in computing systems, 2003)
We describe a new method for use in the process of co-designing technologies with users called technology probes. Technology probes are simple, flexible, adaptable technologies with three interdisciplinary goals: the social science goal of understanding the needs and desires of users in a real-world setting, the engineering goal of field-testing the technology, and the design goal of inspiring users and researchers to think about new technologies. We present the results of designing and deploying two technology probes, the messageProbe and the videoProbe, with diverse families in France, Sweden, and the U.S. We conclude with our plans for creating new technologies for and with families based on our experiences.
Keywords: computer mediated communication; ethnography; Home; participatory design and cooperative design

Thwarting Web Censorship with Untrusted Messenger Discovery - Feamster, Nick; Balazinska,Magdalena; Wang,Winston; Balakrishnan,Hari; Karger,David (Privacy Enhancing TechnologiesPrivacy Enhancing Technologies, 2003)
All existing anti-censorship systems for the Web rely on proxies to grant clients access to censored information. Therefore, they face the proxy discovery problem : how can clients discover the proxies without having the censor discover and block these proxies? To avoid widespread discovery and blocking, proxies must not be widely published and should be discovered in-band. In this paper, we present a proxy discovery mechanism called keyspace hopping that meets this goal. Similar in spirit to frequency hopping in wireless networks, keyspace hopping ensures that each client discovers only a small fraction of the total number of proxies. However, requiring clients to independently discover proxies from a large set makes it practically impossible to verify the trustworthiness of every proxy and creates the possibility of having untrusted proxies. To address this, we propose separating the proxy into two distinct components—the messenger , which the client discovers using keyspace hopping and which simply acts as a gateway to the Internet; and the portal , whose identity is widely-published and whose responsibility it is to interpret and serve the client’s requests for censored content. We show how this separation, as well as in-band proxy discovery, can be applied to a variety of anti-censorship systems.
Keywords: Computer science

User-level internet path diagnosis - Mahajan,R.; Spring, Neil; Wetherall,D.; Anderson,T. (ACM SIGOPS Operating Systems Review, 2003)

AAAI 2002 Workshops - Blake,Brian; Haigh,Karen; Hexmoor,Henry; Falcone,Rino; Soh,Leen-Kiat; Baral,Chitta; McIlraith,Sheila; Gmytrasiewicz,Piotr; Parsons,Simon; Malaka,Rainer; Krueger,Antonio; Bouquet,Paolo; et al. (AI Magazine, 2002)

Algorithmic issues in modeling motion - Agarwal,Pankaj K.; Guibas,Leonidas J.; Edelsbrunner,Herbert; Erickson,Jeff; Isard,Michael; Har-Peled,Sariel; Hershberger,John; Jensen,Christian; Kavraki,Lydia; Koehl,Patrice; Lin,Ming; Manocha,Dinesh; et al. (ACM Comput. Surv., 2002)
This article is a survey of research areas in which motion plays a pivotal role. The aim of the article is to review current approaches to modeling motion together with related data structures and algorithms, and to summarize the challenges that lie ahead in producing a more unified theory of motion representation that would be useful across several disciplines.
Keywords: computational geometry; Computer vision; mobile networks; modeling; molecular biology; motion modeling; physical simulation; robotoics; spatio-temporal databases

Anti-collusion codes: multi-user and multimedia perspectives - Trappe,W.; M. Wu; Liu,K. J.R (Image Processing. 2002. Proceedings. 2002 International Conference on, 2002)
Digital fingerprinting is an effective method to identify users who might try to redistribute multimedia content, such as images and video. These fingerprints are typically embedded into the content using watermarking techniques that are designed to be robust to a variety of attacks. A cheap and effective attack against such digital fingerprints is collusion, where several differently marked copies of the same content are averaged or combined to disrupt the underlying fingerprint. We present a construction of collusion-resistant fingerprints based upon anti-collusion codes (ACC) and binary code modulation. ACC have the property that the composition of any subset of K or fewer codevectors is unique. Using this property, we build fingerprints that allow for the identification of groups of K or less colluders. We present a construction of binary-valued ACC under the logical AND operation using the theory of combinatorial designs. Our code construction requires only Oscr;( radic;n) orthogonal signals to accommodate n users. We demonstrate the performance of our ACC for fingerprinting multimedia by identifying colluders through experiments using real images.
Keywords: and; anti-collusion; authentication; binary; code; codes; coding; combinatorial; computing; content; data; designs; digital; embedding; encapsulation; fingerprinting; image; images; logical; mathematics; message; Modulation; modulation; multimedia; operation; performance; watermarking

Argument structure saturation in a constraint based model - Drury,J.; Resnik, Philip; Weinberg, Amy; Gennari,S.; Aoshima,S. (2002)

Binarization of low quality text using a Markov random field model - Wolf,C.; David Doermann (Pattern Recognition, 2002. Proceedings. 16th International Conference on, 2002)
Binarization techniques have been developed in the document analysis community for over 30 years and many algorithms have been used successfully. On the other hand, document analysis tasks are more and more frequently being applied to multimedia documents such as video sequences. Due to low resolution and lossy compression, the binarization of text included in the frames is a non-trivial task. Existing techniques work without a model of the spatial relationships in the image, which makes them less powerful. We introduce a new technique based on a Markov random field model of the document. The model parameters (clique potentials) are learned from training data and the binary image is estimated in a Bayesian framework. The performance is evaluated using commercial OCR software.
Keywords: analysis; annealing; Bayes; Bayesian; binarization; computing; distributions; document; documents; field; Gibbs; image; low; Markov; method; methods; multimedia; optimization; probability; processes; processing; QUALITY; random; simulated; text

Block preconditioners for the discrete incompressible Navier–Stokes equations - Elman, Howard; Silvester, David J; Wathen, Andrew J (International Journal for Numerical Methods in Fluids, 2002)
We examine the convergence characteristics of iterative methods based on a new preconditioning operator for solving the linear systems arising from discretization and linearization of the steady-state Navier–Stokes equations. For steady-state problems, we show that the preconditioned problem has an eigenvalue distribution consisting of a tightly clustered set together with a small number of outliers. These characteristics are directly correlated with the convergence properties of iterative solvers, with convergence rates independent of mesh size and only mildly dependent on viscosity. For evolutionary problems, we show that implicit treatment of the time derivatives leads to systems for which convergence is essentially independent of viscosity. Copyright © 2002 John Wiley & Sons, Ltd.
Keywords: Iterative algorithms; Navier–Stokes equations; preconditioning

Breaking the resource bottleneck for multilingual applications - Hwa,R.; Resnik, Philip; Weinberg, Amy (2002)

CHI@20: fighting our way from marginality to power - Shneiderman, Ben; Card,Stuart; Norman,Donald A.; Tremaine,Marilyn; Waldrop,M. Mitchell (CHI '02 extended abstracts on Human factors in computing systems, 2002)
The Special Interest Group on Computer Human Interaction (SIGCHI) has had a successful history of 20 years of growth in its numbers and influence. To help guide the continued evolution of the academic discipline and professional community, we invite several senior members to offer their visions for what the field of CHI actually accomplished over the past several decades, and what do we still need to accomplish? What do we need to do differently/ better/smarter? What haven't we tried because the technology, the money or the will wasn't there in the past, but perhaps is now.The CHI field is more than just technology. We understand that our work can have a profound effect on individuals, families, neighborhoods, corporations, and countries. We know that we can influence education, commerce, healthcare, and government. How can we contribute to bridging the digital divides in developed and developing countries? What agendas can we offer for the academic, research, industrial, and civic spheres for the next 20 years? How can we be more ambitious? How can we truly serve human needs.
Keywords: education; future vision; Human-computer interaction; practice; professional; THEORY; usability engineering

Clustering and server selection using passive monitoring - Andrews,M.; Shepherd,B.; Srinivasan, Aravind; Winkler,P.; Zane,F. (IEEE INFOCOM 2002. Twenty-First Annual Joint Conference of the IEEE Computer and Communications Societies. Proceedings, 2002)
We consider the problem of client assignment in a distributed system of content servers. We present a system called Webmapper for clustering IP addresses and assigning each cluster to an optimal content server. The system is passive in that the only information it uses comes from monitoring the TCP connections between the clients and the servers. It is also flexible in that it makes no a priori assumptions about network topology and server placement and it can react quickly to changing network conditions. We present experimental results to evaluate the performance of Webmapper.
Keywords: client assignment; client-server systems; clustering; content servers; Delay; distributed system; Educational institutions; Internet; IP addresses; Monitoring; network conditions; Network servers; Network topology; optimal content server; passive monitoring; server selection; Space technology; TCPIP; Transport protocols; Web pages; Web server; Webmapper

Collusion-resistant fingerprinting for multimedia - Trappe,Wade; M. Wu; Liu,K. J.R (Acoustics, Speech, and Signal Processing (ICASSP), 2002 IEEE International Conference on, 2002)
Digital fingerprinting is an effective method to identify users who might try to redistribute multimedia content, such as images and video. These fingerprints are typically embedded into the content using watermarking techniques that are designed to be robust to a variety of attacks. A cheap and effective attack against such digital fingerprints is collusion, where several differently marked copies of the same content are averaged or combined to disrupt the underlying fingerprint. In this paper, we study the problem of designing fingerprints that can withstand collusion, yet trace colluders. Since, in antipodal CDMA-type watermarking, the correlation contributions only decrease where watermarks differ, by constructing binary code vectors where any subset of k or fewer of these vectors have unique overlap, we may identify groups of k or less colluders. Our construction of such anti-collusion codes (ACC) uses the theory of combinatorial designs, and for n users requires O( #x221A;n) bits. Further, we explore a block matrix structure for the ACC that reduces the computational complexity for identifying colluders and improves the detection capability when colluders belong to the same subgroup.

Combinatorial Algorithms for Design of DNA Arrays - Hannenhalli, Sridhar; Hubbell,Earl; Lipshutz,Robert; Pevzner,Pavel (Chip TechnologyChip Technology, 2002)
Optimal design of DNA arrays requires the development of algorithms with two-fold goals: reducing the effects caused by unintended illumination ( border length minimization problem ) and reducing the complexity of masks ( mask decomposition problem ). We describe algorithms that reduce the number of rectangles in mask decomposition by 20–30% as compared to a standard array design under the assumption that the arrangement of oligonucleotides on the array is fixed. This algorithm produces provably optimal solution for all studied real instances of array design. We also address the difficult problem of finding an arrangement which minimizes the border length and come up with a new idea of threading that significantly reduces the border length as compared to standard designs.

Communication-friendly encryption of multimedia - M. Wu; Mao,Yinian (Multimedia Signal Processing, 2002 IEEE Workshop on, 2002)
This paper discusses encryption operations that selectively encrypt content-carrying segments of multimedia data stream. We propose and analyze three techniques that work in different domains, namely, a syntax-aware selective bitstream encryption tool with bit stuffing, a generalized index mapping encryption tool with controlled overhead and an intra-bitplane encryption tool compatible with fine granularity scalable coding. The designs of these proposed encryption operations take into consideration the inherent structure and syntax of multimedia sources and have improved friendliness to communications, compression and computation.
Keywords: bit; bitstream; coding; Communication; communication; compression; compression; COMPUTATION; controlled; cryptography; data; encryption; encryption; fine; friendliness; granularity; image; index; intrabitplane; MAPPING; multimedia; operation; overhead; scalable; selective; sources; stream; stuffing; syntax-aware; syntax; tool

Complete genome sequence and comparative analysis of the metabolically versatile Pseudomonas putida KT2440 - Nelson,K. E; Weinel,C.; Paulsen,IT; Dodson,RJ; Hilbert,H.; Martins dos Santos,VAP; Fouts,DE; Gill,S. R; Pop, Mihai; Holmes,M.; others (Environmental microbiology, 2002)
Pseudomonas putida is a metabolically versatile saprophytic soil bacterium that has been certified as a biosafety host for the cloning of foreign genes. The bacterium also has considerable potential for biotechnological applications. Sequence analysis of the 6.18 Mb genome of strain KT2440 reveals diverse transport and metabolic systems. Although there is a high level of genome conservation with the pathogenic Pseudomonad Pseudomonas aeruginosa (85% of the predicted coding regions are shared), key virulence factors including exotoxin A and type III secretion systems are absent. Analysis of the genome gives insight into the non-pathogenic nature of P. putida and points to potential new applications in agriculture, biocatalysis, bioremediation and bioplastic production.

Cyclone: A safe dialect of C - Jim,T.; Morrisett,G.; Grossman,D.; Hicks, Michael W.; Cheney,J.; Wang, Y. (USENIX Annual Technical Conference, 2002)
Cyclone is a safe dialect of C. It has been designed from the ground up to prevent the buffer overflows, format string attacks, and memory management errors that are common in C programs, while retaining C's syntax and semantics. This paper examines safety violations enabled by C's design, and shows how Cyclone avoids them, without giving up C's hallmark control over low-level details such as data representation and memory management.

Dynamic layout management in a multimedia bulletin board - Kang,Hyunmo; Shneiderman, Ben; Wolff,G. J (IEEE 2002 Symposia on Human Centric Computing Languages and Environments, 2002. Proceedings, 2002)
This paper proposes a novel user interface to manage the dynamic layout of multimedia objects in the Multimedia Bulletin Board (MBB) system. The MBB has been designed and implemented as a prototype of an asynchronous communication system that enables rich communication and collaboration among users of multimedia objects such as text, image, moving picture, sound, voice, Web, office document, and other files. The layout properties of the multimedia objects on a board (e.g. x-y position, size, z-order, explicit and implicit links, etc.) show important and useful information on the user dynamics occurring within a board. However, a fixed layout created and edited by multiple users may prevent users from recognizing and identifying other information. This paper resolves this problem with a novel user-controlled layout strategy made visible with dynamic layout templates (DLT). Users can reorganize the objects to extract meaningful information related to time, source, geographic location, or topic.
Keywords: Asynchronous communication; asynchronous communication system; Collaboration; data mining; dynamic layout management; dynamic layout templates; groupware; Human computer interaction; image; Information services; Laboratories; moving picture; Multimedia Bulletin Board system; multimedia computing; Multimedia databases; multimedia objects; multimedia systems; office document; Prototypes; sound; text; user interface; User interfaces; user-controlled layout strategy; voice; Web; Web pages

An efficient k-means clustering algorithm: analysis and implementation - Kanungo,T.; Mount, Dave; Netanyahu,N. S; Piatko,C. D; Silverman,R.; Wu,A. Y (Pattern Analysis and Machine Intelligence, IEEE Transactions on, 2002)
In k-means clustering, we are given a set of n data points in d-dimensional space Rd and an integer k and the problem is to determine a set of k points in Rd, called centers, so as to minimize the mean squared distance from each data point to its nearest center. A popular heuristic for k-means clustering is Lloyd's (1982) algorithm. We present a simple and efficient implementation of Lloyd's k-means clustering algorithm, which we call the filtering algorithm. This algorithm is easy to implement, requiring a kd-tree as the only major data structure. We establish the practical efficiency of the filtering algorithm in two ways. First, we present a data-sensitive analysis of the algorithm's running time, which shows that the algorithm runs faster as the separation between clusters increases. Second, we present a number of empirical studies both on synthetically generated data and on real data sets from applications in color quantization, data compression, and image segmentation
Keywords: algorithm; color; algorithm; image; algorithm; kd-tree; mean; analysis; filtering; clustering; clustering; compression; data; distance; covariance; Lloyd; matrices; filtering; quantization; data; segmentation; k-means; squared; structure; data-sensitive; theory; pattern

Empirical findings in agile methods - Lindvall,M.; Basili, Victor R.; Boehm,B.; Costa,P.; Dangle,K.; Shull, F.; Tesoriero,R.; Williams,L.; Zelkowitz, Marvin V (Extreme Programming and Agile Methods—XP/Agile Universe 2002, 2002)
In recent years, the use of, interest in, and controversy about Agile methodologies have realized dramatic growth. Anecdotal evidence is rising regarding the effectiveness of agile methodologies in certain environments and for specified projects. However, collection and analysis of empirical evidence of this effectiveness and classification of appropriate environments for Agile projects has not been conducted. Researchers from four institutions organized an eWorkshop to synchronously and virtually discuss and gather experiences and knowledge from eighteen Agile experts spread across the globe. These experts characterized Agile Methods and communicated experiences using these methods on small to very large teams. They discussed the importance of staffing Agile teams with highly skilled developers. They shared common success factors and identified warning signs of problems in Agile projects. These and other findings and heuristics gathered through this valuable exchange can be useful to researchers and to practitioners as they establish an experience base for better decision making.

Evaluating translational correspondence using annotation projection - Hwa,Rebecca; Resnik, Philip; Weinberg, Amy; Kolak,Okan (Association for Computational Linguistics, 2002)
Recently, statistical machine translation models have begun to take advantage of higher level linguistic structures such as syntactic dependencies. Underlying these models is an assumption about the directness of translational correspondence between sentences in the two languages; however, the extent to which this assumption is valid and useful is not well understood. In this paper, we present an empirical study that quantifies the degree to which syntactic dependencies are preserved when parses are projected directly from English to Chinese. Our results show that although the direct correspondence assumption is often too restrictive, a small set of principled, elementary linguistic transformations can boost the quality of the projected Chinese parses by 76% relative to the unimproved baseline.

Evaluating translational correspondence using annotation projection - Hwa,R.; Resnik, Philip; Weinberg, Amy; Kolak,O. (Proceedings of the 40th Annual Meeting on Association for Computational Linguistics, 2002)

Experiences with capsule-based active networking - Hicks, Michael W.; Moore,J. T; Wetherall,D.; Nettles,S. (DARPA Active NEtworks Conference and Exposition, 2002. Proceedings, 2002)
Active networking adds programmability to the elements of the network, most aggressively by using programmable packets, or capsules. ANTS [22, 21] and PLANet [10, 8] are the most mature examples of capsule-based systems, both having been publicly available for several years. This paper presents our experience with these systems and the lessons they hold for the future of capsule-based active networking. The paper focuses on four key issues: flexibility, performance, security, and usability. We consider how ANTS and PLANet address these issues, noting that despite substantial surface differences, both systems identify similar key problems and use closely related solutions. Based on our experience with these systems we conclude that capsule-based systems can achieve useful levels of flexibility, performance, and usability. Many aspects of security can also be adequately addressed, but some important problems related to denial of service remain as open problems
Keywords: active networking; ANTS; application-specific routing; capsule architecture; capsule-based systems; computer crime; Computer network management; Computer networks; Computer science; Contracts; Electronic switching systems; INFORMATION SCIENCE; Internet; internetworking; network management; PLANet; Planets; programmability; programmable packets; Programming; Security; Standards development; telecommunication network routing; usability

Experimental Construction of Very Large Scale DNA Databases with Associative Search - Reif,J. H; LaBean,T. H; Pirrung,M.; Rana,V. S; Guo,B.; Kingsford, Carl; Wickham,G. S (DNA computing: 7th International Workshop on DNA-Based Computers, DNA 7, Tampa, FL, USA, June 10-13, 2001: revised papers, 2002)

Genome sequence and comparative analysis of the model rodent malaria parasite Plasmodium yoelii yoelii - Carlton,Jane M.; Angiuoli,Samuel V; Suh,Bernard B.; Kooij,Taco W.; Pertea,Mihaela; Silva,Joana C.; Ermolaeva,Maria D.; Allen,Jonathan E; Jeremy D Selengut; Koo,Hean L.; Peterson,Jeremy D.; Pop, Mihai; et al. (Nature, 2002)
Species of malaria parasite that infect rodents have long been used as models for malaria disease research. Here we report the whole-genome shotgun sequence of one species, Plasmodium yoelii yoelii, and comparative studies with the genome of the human malaria parasite Plasmodium falciparum clone 3D7. A synteny map of 2,212 P. y. yoelii contiguous DNA sequences (contigs) aligned to 14 P. falciparum chromosomes reveals marked conservation of gene synteny within the body of each chromosome. Of about 5,300 P. falciparum genes, more than 3,300 P. y. yoelii orthologues of predominantly metabolic function were identified. Over 800 copies of a variant antigen gene located in subtelomeric regions were found. This is the first genome sequence of a model eukaryotic parasite, and it provides insight into the use of such systems in the modelling of Plasmodium biology and disease.

iCLEF 2001 at Maryland: comparing term-for-term gloss and MT - Wang,J.; Oard, Douglas (Evaluation of Cross-Language Information Retrieval Systems, 2002)

Impediments to software engineering technology transfer - Zelkowitz, Marvin V; Wallace,D. R; Binkley,D. W (Journal of Systems and Software. Forthcoming, 2002)

Inferring link weights using end-to-end measurements - Mahajan,Ratul; Spring, Neil; Wetherall,David; Anderson,Tom (Proceedings of the 2nd ACM SIGCOMM Workshop on Internet measurment, 2002)
We describe a novel constraint-based approach to approximate ISP link weights using only end-to-end measurements. Common routing protocols such as OSPF and IS-IS choose least-cost paths using link weights, so inferred weights provide a simple, concise, and useful model of intradomain routing. Our approach extends router-level ISP maps, which include only connectivity, with link weights that are consistent with routing. Our inferred weights agree well with observed routing: while our inferred weights fully characterize the set of shortest paths between 84--99% of the router-pairs, alternative models based on hop count and latency do so for only 47--81% of the pairs.

Interacting with identification technology: can it make us more secure? - Scholtz,Jean; Johnson,Jeff; Shneiderman, Ben; Hope-Tindall,Peter; Gosling,Marcus; Phillips,Jonathon; Wexelblat,Alan (CHI '02 extended abstracts on Human factors in computing systems, 2002)
Keywords: Biometrics; civil liberties; face recognition; national id card; privacy; Security

Joint coding and embedding for collusion-resistant fingerprinting - Trappe,W.; Wu,M.; Liu,K. J.R (Proceedings of the European Signal Processing Conference, EUSIPCO, 2002)
An effective attack against fingerprints for multimedia is collusion,where several differently marked copies of the same content are av- eraged or combined to disrupt the underlying fingerprint. In this paper, we investigate the problem of designing fingerprints that can withstand collusion and allow for the identification of colluders. We begin by introducing the collusion problem for additive embedding, and introduce an efficient detection algorithm for orthogonal mod- ulation that identifies the fingerprints associated with K colluders and requires O(K log(n/K)) correlations for a group of n users. We present a construction of collusion-resistant fingerprints based upon anti-collusion codes (ACC) and binary code modulation. Us- ing ACC, we build fingerprints that identify groups of K or less colluders. We present a construction of binary-valued ACC un- der the logical AND operation using the theory of combinatorial designs. Our code construction requires only O(√n) orthogonal signals to accommodate n users. We demonstrate the performance of our ACC for fingerprinting multimedia and identifying colluders through experiments using Gaussian signals.

Level of Detail for 3D Graphics - Luebke, David; Watson, Benjamin; Cohen, Jonathan D.; Reddy, Martin; Varshney, Amitabh (Elsevier Science Inc., 2002)
Level of detail (LOD) techniques are increasingly used by professional real-time developers to strike the balance between breathtaking virtual worlds and smooth, flowing animation. Level of Detail for 3D Graphics brings together, for the first time, the mechanisms, principles, practices, and theory needed by every graphics developer seeking to apply LOD methods.Continuing advances in level of detail management have brought this powerful technology to the forefront of 3D graphics optimization research. This book, written by the very researchers and developers who have built LOD technology, is both a state-of-the-art chronicle of LOD advances and a practical sourcebook, which will enable graphics developers from all disciplines to apply these formidable techniques to their own work.

A local search approximation algorithm for k-means clustering - Kanungo,Tapas; Mount, Dave; Netanyahu,Nathan S.; Piatko,Christine D.; Silverman,Ruth; Wu,Angela Y. (Proceedings of the eighteenth annual symposium on Computational geometry, 2002)
In k-means clustering we are given a set of n data points in d-dimensional space Rd and an integer k, and the problem is to determine a set of k points in ÓC;d, called centers, to minimize the mean squared distance from each data point to its nearest center. No exact polynomial-time algorithms are known for this problem. Although asymptotically efficient approximation algorithms exist, these algorithms are not practical due to the extremely high constant factors involved. There are many heuristics that are used in practice, but we know of no bounds on their performance.We consider the question of whether there exists a simple and practical approximation algorithm for k-means clustering. We present a local improvement heuristic based on swapping centers in and out. We prove that this yields a (9+&egr;)-approximation algorithm. We show that the approximation factor is almost tight, by giving an example for which the algorithm achieves an approximation factor of (9-&egr;). To establish the practical value of the heuristic, we present an empirical study that shows that, when combined with Lloyd's algorithm, this heuristic performs quite well in practice.
Keywords: Approximation algorithms; clustering; computational geometry; k-means; local search

Measuring ISP topologies with Rocketfuel - Spring, Neil; Mahajan,R.; Wetherall,D. (ACM SIGCOMM Computer Communication Review, 2002)

Methods and apparatus for multi-layer data hiding - Yu,Hong Heather; M. Wu; Li,Xin; Gelman,Alexander D. (2002)
A data hiding system and method for providing a method of embedding multiple layers of hidden data into multimedia data. First, a media unit of the multimedia data is evaluated to determine an appropriate embedding procedure. Next during a first embedding pass, a ruling layer of primary hidden data is embedded into the media unit. In another embedding pass, a governing layer of secondary hidden data is embedded on top of the ruling layer. The secondary hidden data provides control information for controlling the primary hidden data and the host data. Control information such as error correction data, synchronization data, decoding data, and authentication data is embedded in the governing layer. Embedding schemes such as base domain and spectrum domain embedding are employed.

M-Translog-2: A Planning Domain Designed for AIPS-2002 - Wu,Dan; Nau, Dana S. (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2002)
This document describes UM-Translog-2, which is an extended version of theUM Translog planning domain. The extensions include some numerical-computation features to make the domain a more realistic model of transportation-logistics problems. We are proposing UM- Translog-2 as a candidate domain for AIPS-2002 planning competition. (Also UMIACS-TR-2002-82)
Keywords: Technical Report

Nonlinear collusion attacks on independent multimedia fingerprints - Zhao,H.; Wu,M.; Wang,Z.J.; Liu,K. J.R (submitted to IEEE Trans. on Image Proc, 2002)

Ordered and quantum treemaps: Making effective use of 2D space to display hierarchies - Bederson, Benjamin B.; Shneiderman, Ben; Wattenberg,Martin (ACM Transactions on Graphics (TOG), 2002)
Treemaps, a space-filling method for visualizing large hierarchical data sets, are receiving increasing attention. Several algorithms have been previously proposed to create more useful displays by controlling the aspect ratios of the rectangles that make up a treemap. While these algorithms do improve visibility of small items in a single layout, they introduce instability over time in the display of dynamically changing data, fail to preserve order of the underlying data, and create layouts that are difficult to visually search. In addition, continuous treemap algorithms are not suitable for displaying fixed-sized objects within them, such as images.This paper introduces a new "strip" treemap algorithm which addresses these shortcomings, and analyzes other "pivot" algorithms we recently developed showing the trade-offs between them. These ordered treemap algorithms ensure that items near each other in the given order will be near each other in the treemap layout. Using experimental evidence from Monte Carlo trials and from actual stock market data, we show that, compared to other layout algorithms, ordered treemaps are more stable, while maintaining relatively favorable aspect ratios of the constituent rectangles. A user study with 20 participants clarifies the human performance benefits of the new algorithms. Finally, we present quantum treemap algorithms, which modify the layout of the continuous treemap algorithms to generate rectangles that are integral multiples of an input object size. The quantum treemap algorithm has been applied to PhotoMesa, an application that supports browsing of large numbers of images.
Keywords: hierarchies; Human-computer interaction; image browsers; Information Visualization; jazz; ordered treemaps; treemaps; TREES; zoomable user interfaces (ZUIs).

PASSAT: A user-centric planning framework - Myers,K.L.; Tyson,W.M.; Wolverton,M.J.; Jarvis,P.A.; Lee,T.J.; desJardins, Marie (Proceedings of the 3rd International NASA Workshop on Planning and Scheduling for Space, 2002)
We describe a plan-authoring system called PASSAT (Plan-Authoring System based on Sketches, Advice, and Templates) that combines interactive tools for constructing plans with a suite of automated and mixed-initiative capabilities designed to complement human planning skills. PASSAT is organized around a library of predefined templates that encode task networks describing standard operating procedures and previous cases. Users can select from these templates to apply during plan development, with the system providing various forms of automated assistance. A mixed-initiative plan sketch facility helps users refine outlines for plans to complete solutions, by detecting problems and proposing possible fixes. An advice capability enables user specification of high-level guidelines for plans that the system helps to enforce. Finally, PASSAT includes process facilitation mechanisms designed to help a user track and manage outstanding planning tasks and information requirements, as a means of improving the efficiency and effectiveness of the planning process. PASSAT is designed for applications for which a core of planning knowledge can be captured in predefined action models but where significant user control of the planning process is required.

Performance and analysis of saddle point preconditioners for the discrete steady-state Navier-Stokes equations - Elman, Howard; Silvester, D. J; Wathen, A. J (Numerische Mathematik, 2002)

Probabilistic validation of intrusion tolerance - Sanders,W. H.; Michel Cukier; Webber,F.; Pal,P.; Watro,R. (2002)

A recognition algorithm for Chinese characters in diverse fonts - Wu,Xianli; M. Wu (Image Processing. 2002. Proceedings. 2002 International Conference on, 2002)
The paper proposes an algorithm for recognizing Chinese characters in many diverse fonts including Song, Fang, Kai, Hei, Yuan, Lishu, Weibei and Xingkai. The algorithm is based on features derived from peripheral direction contributions and utilizes a set of dictionaries. A 3-level matching is first performed with respect to each dictionary. The distance measures associated with these matches are then fed into a central discriminator to output the final recognition result. We propose a new multi-dictionary matching algorithm for use in the central discriminator that utilizes estimated information of neighborhood fonts. Experiments have been performed on a practical OCR software system whose recognition kernel is based on the proposed algorithm. Fast and accurate recognition has been accomplished both in title recognition, involving all of the 8 fonts, and in main-body recognition, that usually involves only the first 4 most commonly used fonts.
Keywords: algorithm; central; character; Chinese; contributions; direction; discriminator; diverse; fonts; image; interfaces; LANGUAGE; MATCHING; matching; multi-dictionary; natural; OCR; optical; peripheral; recognition; recognition; sets; software; system

RECOMB '02: Proceedings of the sixth annual international conference on Computational biology - Myers,Gene; Hannenhalli, Sridhar; Sankoff,David; Istrail,Sorin; Pevzner,Pavel; Waterman,Michael (ACM, 2002)
The papers in this volume were presented at the Sixth Annual International Conference on Computational Biology RECOMB 2002, held in Washington, D.C. on April 18-21, 2002. The RECOMB series was started in 1997 by Sorin Istrail, Pavel Pevzner and Michael Waterman. RECOMB '99 took place in Lyon, France, RECOMB 2000 was held in Tokyo, Japan, and RECOMB 2001 was held in Montreal, Quebec, Canada.This year's call for papers gave rise to 118 submissions, out of which the program committee selected 35 papers to be presented at the conference and included in the proceedings. Each submission was refereed by at least three members of the program committee. After the completion of the referees' reports, an extensive web-based discussion took place.RECOMB 2002 had 8 invited speakers: Ruben Abagyan (The Scripps Research Institute), Ali H. Brivanlou (Rockefeller University), Evan Eichler (Case Western Reserve University), Harold "Skip" Garner (University of Texas Southwestern Medical Center at Dallas), David Ho (Rockefeller University), Gerry Rubin (Howard Hughes Medical Institute), J. Craig Venter (Celera) and Marc Vidal (Dana-Farber Cancer Institute). The Stanislaw Ulam Memorial Lecture was given by J. Craig Venter. The Distinguished Biology Lecture was given by David Ho. The Distinguished New Technologies Lecture was given by Harold Garner.Complete final versions of many of the papers presented in the conference will appear in a special issue of the Journal of Computational Biology, which is closely affiliated with the conference.

Region-based memory management in cyclone - Grossman,Dan; Morrisett,Greg; Jim,Trevor; Hicks, Michael W.; Wang,Yanling; Cheney,James (SIGPLAN Not., 2002)
Cyclone is a type-safe programming language derived from C. The primary design goal of Cyclone is to let programmers control data representation and memory management without sacrificing type-safety. In this paper, we focus on the region-based memory management of Cyclone and its static typing discipline. The design incorporates several advancements, including support for region subtyping and a coherent integration with stack allocation and a garbage collector. To support separate compilation, Cyclone requires programmers to write some explicit region annotations, but a combination of default annotations, local type inference, and a novel treatment of region effects reduces this burden. As a result, we integrate C idioms in a region-based framework. In our experience, porting legacy C to Cyclone has required altering about 8% of the code; of the changes, only 6% (of the 8%) were region annotations.

A robust error resilient approach for MPEG video transmission over internet - Yin,P.; Wu,M.; Liu,B. (Visual Communication and Image Processing, SPIE, 2002)
In network delivery of compressed video, packets may be lost if the channel is unreliable. Such losses tend to occur inburst. In this paper, we develop an error resilient video encoding approach to help error concealment at the decoder. We introduce a new block shuffling scheme to isolate erroneous blocks caused by packet losses. And we apply data hiding to add additional protection for motion vectors. The incorporation of these scheme adds little complexity to the standard encoder. Experimental results suggest that our approach can achieve a reasonable quality for packet loss up to 30% over a wide range of video materials.

Semantics in the spin cycle Competence and performance criteria for the creation of lexical entries - Weinberg, Amy (The lexical basis of sentence processing: formal, computational, and experimental issues, 2002)

Structural Properties of Polyubiquitin Chains in Solution - Varadan,Ranjani; Walker,Olivier; Pickart,Cecile; Fushman, David (Journal of Molecular Biology, 2002)
Because polyubiquitin chain structure modulates Ub-mediated signaling, knowledge of the physiological conformations of chain signals should provide insights into specific recognition. Here, we characterized the solution conformations of K48-linked Ub2 and Ub4 using a combination of NMR techniques, including chemical shift mapping of the interdomain interface, domain orientation measurements on the basis of 15N relaxation and residual dipolar couplings, and the solvent accessibility studies. Our data indicate a switch in the conformation of Ub2, from open to closed, with increasing pH. The closed conformation features a well-defined interface that is related to, but distinguishable from, that observed in the Ub2 crystal structure. This interface is dynamic in solution, such that important hydrophobic residues (L8, I44, V70) that are sequestered at the interface in the closed conformation may be accessible for direct interactions with recognition factors. Our results suggest that the distal two units of Ub4, which is the minimum signal for efficient proteasomal degradation, may adopt the closed Ub2 conformation.
Keywords: chemical shift mapping; domain orientation measurements; polyubiquitin chains; spin relaxation; ubiquitin

Understanding Machine Performance in the Context of Human Performance for Multi-document Summarization - Schlesinger,J.D.; Okurowski,M. E.; Conroy,J.M.; O'Leary, Dianne P.; Taylor,A.; Hobbs,J.; Wilson,H. T. (DUC 02 Conference ProceedingsDUC 02 Conference Proceedings, 2002)
We present a discussion of our summarization algorithm -- both single and multi-document -- along with a discussion of the evaluation experiments we have undertaken, what we have learned from them, and how we intend to utilize this information.

Vision geometry XI(Seattle WA, 7-8 July 2002) - Latecki,L.J.; Mount, Dave; Wu,A. Y (SPIE proceedings series, 2002)

Analysis of a donor gene region for a variant surface glycoprotein and its expression site in African trypanosomes - LaCount,D. J; El‐Sayed, Najib M.; Kaul,S.; Wanless,D.; Turner,C. M.R; Donelson,J. E (Nucleic acids research, 2001)

Analysis of attacks on SDMI audio watermarks - M. Wu; Craver,S.; Felten,E.W.; Liu,B. (Acoustics, Speech, and Signal Processing, 2001. Proceedings. (ICASSP '01). 2001 IEEE International Conference on, 2001)
This paper explains and analyzes the successful attacks submitted by the authors on four audio watermark proposals during a 3-week SDMI public challenge. Our analysis points out some weaknesses in the watermark techniques currently under SDMI consideration and suggests directions for further improvement. The paper also discusses the framework and strategies for analyzing the robustness and security of watermarking systems as well as the difficulty, uniqueness, and unrealistic expectations of the attack setup
Keywords: attacks; watermark; audio; coding; copy; digital; encapsulation; Initiative; attack; Music; protection; data; SDMI; setup; robustness; security; successful; watermarks; Secure; weaknesses; audio

Approximating large convolutions in digital images - Mount, Dave; Kanungo,T.; Netanyahu,N. S; Piatko,C.; Silverman,R.; Wu,A. Y (Image Processing, IEEE Transactions on, 2001)
Computing discrete two-dimensional (2-D) convolutions is an important problem in image processing. In mathematical morphology, an important variant is that of computing binary convolutions, where the kernel of the convolution is a 0-1 valued function. This operation can be quite costly, especially when large kernels are involved. We present an algorithm for computing convolutions of this form, where the kernel of the binary convolution is derived from a convex polygon. Because the kernel is a geometric object, we allow the algorithm some flexibility in how it elects to digitize the convex kernel at each placement, as long as the digitization satisfies certain reasonable requirements. We say that such a convolution is valid. Given this flexibility we show that it is possible to compute binary convolutions more efficiently than would normally be possible for large kernels. Our main result is an algorithm which, given an m times;n image and a k-sided convex polygonal kernel K, computes a valid convolution in O(kmn) time. Unlike standard algorithms for computing correlations and convolutions, the running time is independent of the area or perimeter of K, and our techniques do not rely on computing fast Fourier transforms. Our algorithm is based on a novel use of Bresenham's (1965) line-drawing algorithm and prefix-sums to update the convolution incrementally as the kernel is moved from one position to another across the image
Keywords: 2D; algorithm; binary; approximation; mathematical; convolution; convolution; binary; convolutions; Bresenham's; convolutions; convex; convolutions; geometric; images; discrete; kernel; convex; kernel; digital; line-drawing; morphology; morphology; approximation; object; image; polygonal; processing; large; processing; mathematical; theory; convolution; image; two-dimensional

A Calculus for Dynamic Loading - Hicks, Michael W.; Weirich,Stephanie (Technical Reports (CIS), 2001)
We present the load-calculus, used to model dynamic loading, and prove it sound. The calculus extends the polymorphic λ-calculus with a load primitive that dynamically loads terms that are closed, with respect to values. The calculus is meant to approximate the process of dynamic loading in TAL/Load [4], a version of Typed Assembly Language [7] extending with dynamic linking. To model the key aspects of TAL, the calculus contains references and facilities for named types. Loadable programs may refer to named types defined by the running program, and may export new types to code loaded later. Our approach follows the framework initially outlined by Glew et. al [3]. This calculus has been implemented in the TALx86 [6] version of Typed Assembly Language, and is used to implement a full-featured dynamic linking library, DLpop [4].

A Call for Knowledge-Based Planning - Wilkins,David E; desJardins, Marie (AI Magazine, 2001)

Compiling PLAN to SNAP - Hicks, Michael W.; Moore,Jonathan; Nettles,Scott (Active NetworksActive Networks, 2001)
PLAN (Packet Language for Active Networks) [ 3 ] is a highly flexible and usable active packet language, whereas SNAP (Safe and Nimble Active Packets) [ 12 ] offers significant resource usage safety and achieves much higher performance compared to PLAN, but at the cost of flexibility and usability. Ideally, we would like to combine the good properties of PLAN with those of SNAP. We have achieved this end by developing a compiler that translates PLANi nto SNAP. The compiler allows us to achieve the flexibility and usability of PLAN, but with the safety and efficiency of SNAP. In this paper, we describe both languages, highlighting the features that require special compilation techniques. We then present the details of our compiler and experimental results to evaluate our compiler with respect to code size.

Conditions enabling the emergence of inter-agent signalling in an artificial world - Reggia, James A.; Schulz,R.; Wilkinson,G. S; Uriagereka,J. (Artificial Life, 2001)

Cyclone User's Manual, Version 0.1. 3 - Grossman,D.; Morrisett,G.; Jim,T.; Hicks, Michael W.; Wang, Y.; Cheney,J. (Computer Science Technical Reports, 2001)
The current version of this manual should be available at http://www.cs.cornell.edu/projects/cyclone/ and http://www.research.att.com/projects/cyclone/. The version here describes Cyclone Version 0.1.3, although minor changes may have occurred before the release.

Detecting format string vulnerabilities with type qualifiers - Shankar,U.; Talwar,K.; Foster, Jeffrey S.; Wagner,D. (Proceedings of the 10th conference on USENIX Security Symposium-Volume 10, 2001)

Dynamic resource allocation via video content and short-term traffic statistics - M. Wu; Joyce,R.A.; Wong,Hau-San; Guan,Long; Kung,Sun-Yuan (Multimedia, IEEE Transactions on, 2001)
The reliable and efficient transmission of high-quality variable bit rate (VBR) video through the Internet generally requires network resources be allocated in a dynamic fashion. This includes the determination of when to renegotiate for network resources, as well as how much to request at a given time. The accuracy of any resource request method depends critically on its prediction of future traffic patterns. Such a prediction can be performed using the content and traffic information of short video segments. This paper presents a systematic approach to select the best features for prediction, indicating that while content is important in predicting the bandwidth of a video hit stream, the use of both content and available short-term bandwidth statistics can yield significant improvements. A new framework for traffic prediction is proposed in this paper; experimental results show a smaller mean-square resource prediction error and higher overall link utilization
Keywords: allocation; link; allocation; multimedia; allocation; variable; bit; codes; content; bandwidth; error; short; Internet; dynamic; patterns; variable; prediction; rate; resource; segments; short-term; statistics; traffic; systems; resource; traffic; utilization; mean-square; video; video; video

Efficient algorithms for location and sizing problems in network design - Kumaran,K.; Srinivasan, Aravind; Qiong Wang; Lanning,S.; Ramakrishnan,K. G (IEEE Global Telecommunications Conference, 2001. GLOBECOM '01, 2001)
Large-scale location, sizing and homing problems of distributed network elements, have received much attention recently due to the massive deployment of broadband communication networks for services like Internet telephony and Web caching. Key considerations in designing these networks include modularity of capacity, economies of scale in cost, and reliability. We formulate a general class of such network design problems as Mixed-Integer Programs. These problems are computationally intractable in general; under various asymptotic conditions, we show how to compute near-optimal solutions. To deal with arbitrary instances, we develop new algorithms based on linear programming, as well as greedy randomized adaptive search. These algorithms achieved near-optimal solutions with reasonable computation time for our experiments
Keywords: Algorithm design and analysis; Broadband communication; broadband communication networks; broadband networks; capacity modularity; Communication networks; computer network reliability; distributed network elements; Economies of scale; greedy randomized adaptive search; homing; integer programming; Intelligent networks; Internet telephony; large-scale location problems; Large-scale systems; Linear programming; mixed-integer programs; near-optimal solutions; network design; Optical switches; randomised algorithms; reliability; search problems; sizing; Technological innovation; telecommunication network planning; Web caching

Enrichment of Regulatory Signals in Conserved Non-Coding Genomic Sequence - Levy,Samuel; Hannenhalli, Sridhar; Workman,Christopher (BioinformaticsBioinformatics, 2001)
Motivation: Whole genome shotgun sequencing strategies generate sequence data prior to the application of assembly methodologies that result in contiguous sequence. Sequence reads can be employed to indicate regions of conservation between closely related species for which only one genome has been assembled. Consequently, by using pairwise sequence alignments methods it is possible to identify novel, non-repetitive, conserved segments in non-coding sequence that exist between the assembled human genome and mouse whole genome shotgun sequencing fragments. Conserved non-coding regions identify potentially functional DNA that could be involved in transcriptional regulation.Results: Local sequence alignment methods were applied employing mouse fragments and the assembled human genome. In addition, transcription factor binding sites were detected by aligning their corresponding positional weight matrices to the sequence regions. These methods were applied to a set of transcripts corresponding to 502 genes associated with a variety of different human diseases taken from the Online Mendelian Inheritance in Man database. Using statistical arguments we have shown that conserved non-coding segments contain an enrichment of transcription factor binding sites when compared to the sequence background in which the conserved segments are located. This enrichment of binding sites was not observed in coding sequence. Conserved non-coding segments are not extensively repeated in the genome and therefore their identification provides a rapid means of finding genes with related conserved regions, and consequently potentially related regulatory mechanism. Conserved segments in upstream regions are found to contain binding sites that are co-localized in a manner consistent with experimentally known transcription factor pairwise co-occurrences and afford the identification of novel co-occurring Transcription Factor (TF) pairs. This study provides a methodology and more evidence to suggest that conserved non-coding regions are biologically significant since they contain a statistical enrichment of regulatory signals and pairs of signals that enable the construction of regulatory models for human genes. Contact: samuel.levy@celera.com

Integrating distributed scientific data sources with MOCHA and XRoaster - Rodriguez-Martinez,M.; Roussopoulos, Nick; McGann,J. M; Kelley,S.; Mokwa,J.; White,B.; Jala,J. (Thirteenth International Conference on Scientific and Statistical Database Management, 2001. SSDBM 2001. Proceedings, 2001)
MOCHA is a novel middleware system for integrating distributed data sources that we have developed at the University of Maryland. MOCHA is based on the idea that the code that implements user-defined types and functions should be automatically deployed to remote sites by the middleware system itself. To this end, we have developed an XML-based framework to specify metadata about data sites, data sets, and user-defined types and functions. XRoaster is a graphical tool that we have developed to help the user create all the XML metadata elements to be used in MOCHA
Keywords: client-server systems; data sets; data sites; Databases; Distributed computing; distributed databases; distributed scientific data source integration; Educational institutions; graphical tool; hypermedia markup languages; IP networks; java; Large-scale systems; Maintenance engineering; meta data; metadata; Middleware; middleware system; MOCHA; Query processing; remote sites; scientific information systems; user-defined types; visual programming; XML; XML metadata elements; XML-based framework; XRoaster

Intrusion tolerance approaches in ITUA - Michel Cukier; Lyons,J.; Pandey,P.; Ramasamy,H. V.; Sanders,W. H.; Pal,P.; Webber,F.; Schantz,R.; Loyall,J.; Watro,R. (2001)

Mandarin-English Information (MEI): investigating translingual speech retrieval - Meng,Helen; Chen,Berlin; Khudanpur,Sanjeev; Levow,Gina-Anne; Lo,Wai-Kit; Oard, Douglas; Schone,Patrick; Tang,Karen; Wang,Hsin-Min; Wang,Jianqiang (Proceedings of the first international conference on Human language technology research, 2001)
This paper describes the Mandarin-English Information (MEI) project, where we investigated the problem of cross-language spoken document retrieval (CL-SDR), and developed one of the first English-Chinese CL-SDR systems. Our system accepts an entire English news story (text) as query, and retrieves relevant Chinese broadcast news stories (audio) from the document collection. Hence this is a cross-language and cross-media retrieval task. We applied a multi-scale approach to our problem, which unifies the use of phrases, words and subwords in retrieval. The English queries are translated into Chinese by means of a dictionary-based approach, where we have integrated phrase-based translation with word-by-word translation. Untranslatable named entities are transliterated by a novel subword translation technique. The multi-scale approach can be divided into three subtasks -- multi-scale query formulation, multi-scale audio indexing (by speech recognition) and multi-scale retrieval. Experimental results demonstrate that the use of phrase-based translation and subword translation gave performance gains, and multi-scale retrieval outperforms word-based retrieval.
Keywords: cross-language; English-Chinese; spoken document retrieval

Modulation and multiplexing techniques for multimedia data hiding - Wu,M.; Liu,B. (Proc. of SPIE ITcom’01, SPIE vol, 2001)
Many multimedia data hiding systems demand either multiple bits or multiple sets of data to be embedded. Thispaper examines the modulation and multiplexing techniques for accomplishing the task of extending the basic single- bit embedding to multiple-bit embedding. Amplitude modulo modulation, orthogonal/bi-orthogonal modulation, and TDMA or CDMA type modulation/multiplexing are discussed and compared. Several examples are included to demonstrate the use of such techniques in practical designs.

Ordered treemap layouts - Shneiderman, Ben; Wattenberg,M. (IEEE Symposium on Information Visualization, 2001. INFOVIS 2001, 2001)
Keywords: Clustering algorithms; Computer science; Data visualization; Displays; Electronic switching systems; Filling; Monte Carlo methods; Read only memory; Testing

Reading between the lines: Lessons from the SDMI challenge - Craver,S.A.; Wu,M.; Liu,B.; Stubblefield,A.; Swartzlander,B.; Wallach,D.S.; Dean,D.; Felten,E.W. (Proceedings of the 10th USENIX Security Symposium, 2001)
The Secure Digital Music Initiative is a consortium ofparties interested in preventing piracy of digital music, and to this end they are developing architectures for con- tent protection on untrusted platforms. SDMI recently held a challenge to test the strength of four watermark- ing technologies, and two other security technologies. No documentation explained the implementations of the technologies, and neither watermark embedding nor de- tecting software was directly accessible to challenge par- ticipants. We nevertheless accepted the challenge, and explored the inner workings of the technologies. We re- port on our results here.

The role of a natural language conversational interface in online sales: A case study - Chai,J.; Jimmy Lin; Zadrozny,W.; Ye,Y.; Stys-Budzikowska,M.; Horvath,V.; Kambhatla,N.; Wolf,C. (International Journal of Speech Technology, 2001)
This paper describes the evaluation of a natural language dialog-based navigation system (HappyAssistant) that helps users access e-commerce sites to find relevant information about products and services. The prototype system leverages technologies in natural language processing and human-computer interaction to create a faster and more intuitive way of interacting with websites, especially for less experienced users. The result of a comparative study shows that users prefer the natural language-enabled navigation two to one over the menu driven navigation. In addition, the study confirmed the efficiency of using natural language dialog in terms of the number of clicks and the amount of time required to obtain the relevant information. In the case study, as compared to the menu driven system, the average number of clicks used in the natural language system was reduced by 63.2% and the average time was reduced by 33.3%.

Rotation, scale, and translation resilient public watermarking for images using a log-polar fourier transform - Bloom,Jeffrey A.; Cox,Ingemar J.; Miller,Matthew L.; M. Wu; Lin,Ching-Yung; Lui,Yui Man (2001)
A method for detecting a watermark signal in digital image data. The detecting method includes the steps of: computing a log-polar Fourier transform of the image data to obtain a log-polar Fourier spectrum; projecting the log-polar Fourier spectrum down to a lower dimensional space to obtain an extracted signal; comparing the extracted signal to a target watermark signal; and declaring the presence or absence of the target watermark signal in the image data based on the comparison. Also provided is a method for inserting a watermark signal in digital image data to obtain a watermarked image. The inserting method includes the steps of: computing a log-polar Fourier transform of the image data to obtain a log-polar Fourier spectrum; projecting the log-polar Fourier spectrum down to a lower dimensional space to obtain an extracted signal; modifying the extracted signal such that it is similar to a target watermark; performing a one-to-many mapping of the modified signal back to...

Rotation, scale, and translation resilient watermarking for images - Lin,C.-Y.; Wu,M.; Bloom,J.A.; Cox,I.J.; Miller,M.L.; Lui,Y.M. (Image Processing, IEEE Transactions on, 2001)
Many electronic watermarks for still images and video content are sensitive to geometric distortions. For example, simple rotation, scaling, and/or translation (RST) of an image can prevent blind detection of a public watermark. In this paper, we propose a watermarking algorithm that is robust to RST distortions. The watermark is embedded into a one-dimensional (1-D) signal obtained by taking the Fourier transform of the image, resampling the Fourier magnitudes into log-polar coordinates, and then summing a function of those magnitudes along the log-radius axis. Rotation of the image results in a cyclical shift of the extracted signal. Scaling of the image results in amplification of the extracted signal, and translation of the image has no effect on the extracted signal. We can therefore compensate for rotation with a simple search, and compensate for scaling by using the correlation coefficient as the detection measure. False positive results on a database of 10 000 images are reported. Robustness results on a database of 2000 images are described. It is shown that the watermark is robust to rotation, scale, and translation. In addition, we describe tests examining the watermarks resistance to cropping and JPEG compression
Keywords: axis; one-dimensional; coding; security; coefficient; cropping; cyclical; compression; RST; coordinates; log-radius; data; detection; correlation; distortions; blind; distortions; images; log-polar; encapsulation; image; Fourier; images; translation; magnitudes; Fourier; measure; geometric; of; protection; data; resilient; shift; detection; signal; public; transform; JPEG; transforms; copy; watermark; resampling; rotation; scale; search; still; watermarking; video; Fourier

Safe and Flexible Dynamic Linking of Native Code - Hicks, Michael W.; Weirich,Stephanie; Crary,Karl (Types in Compilation, 2001)
We present the design and implementation of the first complete framework for flexible and safe dynamic linking of native code. Our approach extends Typed Assembly Language with a primitive for loading and typechecking code, which is flexible enough to support a variety of linking strategies, but simple enough that it does not significantly expand the trusted computing base. Using this primitive, along with the ability to compute with types, we show that we can program many existing dynamic linking approaches. As a concrete demonstration, we have used our framework to implement dynamic linking for a type-safe dialect of C, closely modeled after the standard linking facility for Unix C programs. Aside from the unavoidable cost of verification, our implementation performs comparably with the standard, untyped approach.

Secure Health Information Sharing System: SHARE - M. Wu; Mui,Lik; Mohtashemi,Mojdeh; Szolovits,Peter (Proceedings of the AMIA SymposiumProc AMIA Symp, 2001)

Vision Geometry X - Latecki,L.J.; Mount, Dave; Wu,A. Y; Melter,R.A. (Society of Photo-Optical Instrumentation Engineers (SPIE) Conference Series, 2001)

Watermarking scheme for image authentication - M. Wu; Liu,Bede (2001)
A digital watermarking process whereby an invisible watermark inserted into a host image is utilized to determine whether or not the image has been altered and, if so, where in the image such alteration occurred. The watermarking method includes the steps of providing a look-up table containing a plurality of coefficients and corresponding values; transforming the image into a plurality of blocks, wherein each block contains coefficients matching coefficients in the look-up table; and embedding the watermark in the image by performing the following substeps for at least some of the blocks: First, a coefficient is selected for insertion of a marking value representative of a corresponding portion of the watermark. Next, the value of the selected coefficient to used to identify a corresponding value in the look-up table. Finally, the identified coefficient is left unchanged if the corresponding value is the same as the marking value, and is changed if the corresponding value is...

What can we reasonably expect from watermarks? - Craver,S.A.; M. Wu; Liu,B. (Applications of Signal Processing to Audio and Acoustics, 2001 IEEE Workshop on the, 2001)
Digital watermarking has been positioned as a solution to copyright protection of digital music, and some doubt exists about its ability to perform in this regard. A survey of watermarking applications assesses the technology's potential for copy protection, as well as other digital audio applications
Keywords: applications; audio; applications; digital; audio; coding; copy; data; databases; music; hashing; steganography; watermarking; music; digital; of; protection; copyright; protection; copyright; music; security; protection; digital; watermarking; copy; watermarking; forensic; watermarking; music

Adaptive Use of Iterative Methods in Predictor-Corrector Interior Point Methods for Linear Programming - Wang,Weichung; O'Leary, Dianne P. (Numerical Algorithms, 2000)
In this work we devise efficient algorithms for finding the search directions for interior point methods applied to linear programming problems. There are two innovations. The first is the use of updating of preconditioners computed for previous barrier parameters. The second is an adaptive automated procedure for determining whether to use a direct or iterative solver, whether to reinitialize or update the preconditioner, and how many updates to apply. These decisions are based on predictions of the cost of using the different solvers to determine the next search direction, given costs in determining earlier directions. We summarize earlier results using a modified version of the OB1-R code of Lustig, Marsten, and Shanno, and we present results from a predictor–corrector code PCx modified to use adaptive iteration. If a direct method is appropriate for the problem, then our procedure chooses it, but when an iterative procedure is helpful, substantial gains in efficiency can be obtained.

The analysis of a simple k-means clustering algorithm - Kanungo,Tapas; Mount, Dave; Netanyahu,Nathan S.; Piatko,Christine; Silverman,Ruth; Wu,Angela Y. (Proceedings of the sixteenth annual symposium on Computational geometry, 2000)

Building a Chinese-English Mapping Between Verb Concepts for Multilingual Applications - Dorr, Bonnie J; Levow,Gina-Anne; Lin,Dekang (Envisioning Machine Translation in the Information FutureEnvisioning Machine Translation in the Information Future, 2000)
This paper addresses the problem of building conceptual resources for multilingual applications. We describe new techniques for large-scale construction of a Chinese-English lexicon for verbs, using thematic-role information to create links between Chinese and English conceptual information. We then present an approach to compensating for gaps in the existing resources. The resulting lexicon is used for multilingual applications such as machine translation and cross-language information retrieval.

Centers of sets of pixels - Khuller, Samir; Rosenfeld,Azriel; Wu,Angela (Discrete Applied Mathematics, 2000)
The center of a connected graph G is the set of nodes of G for which the maximum distance to any other node of G is as small as possible. If G is a simply connected set of lattice points (“pixels”) with graph structure defined by 4-neighbor adjacency, we show that the center of G is either a 2×2 square block, a diagonal staircase, or a (dotted) diagonal line with no gaps.
Keywords: Center; Chessboard distance; City block distance; Intrinsic distance; Simply connected set

Chromatic nearest neighbor searching: A query sensitive approach - Mount, Dave; Netanyahu,Nathan S.; Silverman,Ruth; Wu,Angela Y. (Computational Geometry, 2000)
The nearest neighbor problem is that of preprocessing a set P of n data points in Rd so that, given any query point q, the closest point in P to q can be determined efficiently. In the chromatic nearest neighbor problem, each point of P is assigned a color, and the problem is to determine the color of the nearest point to the query point. More generally, given k⩾1, the problem is to determine the color occurring most frequently among the k nearest neighbors. The chromatic version of the nearest neighbor problem is used in many applications in pattern recognition and learning. In this paper we present a simple algorithm for solving the chromatic k nearest neighbor problem. We provide a query sensitive analysis, which shows that if the color classes form spatially well separated clusters (as often happens in practice), then queries can be answered quite efficiently. We also allow the user to specify an error bound ε⩾0, and consider the same problem in the context of approximate nearest neighbor searching. We present empirical evidence that for well clustered data sets, this approach leads to significant improvements in efficiency.
Keywords: BBD trees; Branch-and-bound search; Chromatic nearest neighbors; Classification algorithms; Multidimensional searching; pattern recognition; Query sensitive analysis

Class representation and image retrieval with non-metric distances - Jacobs, David W.; Weinshall,D.; Gdalyahu,Y. (IEEE Transactions on Pattern Analysis and Machine Intelligence (TPAMI), 2000)
One of the key problems in appearance-based vision is understanding how to use a set oflabeled images to classify new images. Classification systems that can model human perfor- mance, or that use robust image matching methods, often make use of similarity judgments that are non-metric; but when the triangle inequality is not obeyed, most existing pattern recogni- tion techniques are not applicable. We note that exemplar-based (or nearest-neighbor) methods can be applied naturally when using a wide class of non-metric similarity functions. The key issue, however, is to find methods for choosing good representatives of a class that accurately characterize it. We show that existing condensing techniques for finding class representatives are ill-suited to deal with non-metric dataspaces. We then focus on developing techniques for solving this problem, emphasizing two points: First, we show that the distance between two images is not a good measure of how well one image can represent another in non-metric spaces. Instead, we use the vector correlation between the distances from each image to other previously seen images. Second, we show that in non-metric spaces, boundary points are less significant for capturing the structure of a class than they are in Euclidean spaces. We suggest that atypical points may be more important in describing classes. We demonstrate the importance of these ideas to learning that generalizes from experience by improving performance using both synthetic and real images.

Classification with nonmetric distances: image retrieval and class representation - Jacobs, David W.; Weinshall,D.; Gdalyahu,Y. (Pattern Analysis and Machine Intelligence, IEEE Transactions on, 2000)
A key problem in appearance-based vision is understanding how to use a set of labeled images to classify new images. Systems that model human performance, or that use robust image matching methods, often use nonmetric similarity judgments; but when the triangle inequality is not obeyed, most pattern recognition techniques are not applicable. Exemplar-based (nearest-neighbor) methods can be applied to a wide class of nonmetric similarity functions. The key issue, however, is to find methods for choosing good representatives of a class that accurately characterize it. We show that existing condensing techniques are ill-suited to deal with nonmetric dataspaces. We develop techniques for solving this problem, emphasizing two points: First, we show that the distance between images is not a good measure of how well one image can represent another in nonmetric spaces. Instead, we use the vector correlation between the distances from each image to other previously seen images. Second, we show that in nonmetric spaces, boundary points are less significant for capturing the structure of a class than in Euclidean spaces. We suggest that atypical points may be more important in describing classes. We demonstrate the importance of these ideas to learning that generalizes from experience by improving performance. We also suggest ways of applying parametric techniques to supervised learning problems that involve a specific nonmetric distance functions, showing how to generalize the idea of linear discriminant functions in a way that may be more useful in nonmetric spaces
Keywords: appearance-based; by; classification; image; correlation; correlation; dataspaces; nonmetric; distances; nonmetric; example; functions; nonmetric; image; inequality; vector; judgments; robust; MATCHING; methods; image; methods; nonmetric; methods; triangle; points; boundary; points; class; representation; exemplar-based; representation; image; retrieval; learning; retrieval; nearest-neighbor; similarity; vision; atypical

Comparative Evaluation of a Natural Language Dialog Based System and a Menu-Driven System for Information Access: A Case Study - Chai,J.; Jimmy Lin; Zadrozny,W.; Ye,Y.; Budzikowska,M.; Horvath,V.; Kambhatla,N.; Wolf,C. (In Proceedings of the International Conference on Multimedia Information Retrieval (RIAO 2000), 2000)
This paper describes the evaluation of a natural language dialog based navigation system (HappyAssistant) thathelps users access e-commerce sites to find relevant information about products and services. The prototype system leverages technologies in natural language processing and human computer interaction to create a faster and more intuitive way of interacting with websites, especially for the less experienced users. The result of a comparative study shows that users prefer the natural language enabled navigation two to one over the menu driven navigation. In addition, the study confirmed the efficiency of using natural language dialog in terms of the number of clicks and the amount of time required to obtain the relevant information. In the case study, comparing to the menu driven system, the average number of clicks used in the natural language system was reduced by 63.2% and the average time was reduced by 33.3%.

Data hiding in digital binary image - M. Wu; Tang,E.; Lin, B. (Multimedia and Expo, 2000. ICME 2000. 2000 IEEE International Conference on, 2000)
This paper proposes a new method to embed data in binary images, including scanned text, figures and signatures. The method manipulates ldquo;flippable rdquo; pixels and uses shuffling to embed a significant amount of data without causing noticeable artifacts. The extraction of the hidden data does not require the original image. Potential applications include detecting unauthorized use of a digitized signature and authenticating binary documents
Keywords: authentication; data; binary; data; document; encapsulation; image; hiding; digital; image; digital; of; pixels; multimedia; scanned; processing; multimedia; signature; flippable; systems; security; text; shuffling; data; watermarking; digitized

A first step towards automated detection of buffer overrun vulnerabilities - Wagner,D.; Foster, Jeffrey S.; Brewer,E.A.; Aiken,A. (The 2000 Network and Distributed Systems Security Conference. San Diego, CA, 2000)

The Interface of Three Areas of Computer Science with the Mathematical Sciences - O'Leary, Dianne P.; Weidman,Scott T. (National Academy Press, 2000)

A Neural Network Approach for Predicting Network Resource Requirements in Video Transmission Systems - Wong,H.S.; Wu,M.; Joyce,R.A.; Guan,L.; Kung, S.Y. (Proc. IEEE Pacific RIM Conference on Multimedia, Sydney, Australia, 2000)
Dynamic resource allocation is important for ensuring ef-ficient network utilization in Internet-based multimedia content delivery system. To allow accurate network traf- fic prediction in the case of video delivery, relevant infor- mation based on video contents and the short term traffic pattern has to be taken into account, while the inclusion of non-relevant features will deterioriate the prediction per- formance due to the "curse of dimensionality" problem. In this work, we propose a neural network-based predic- tion system and specifically address the determination of relevant input features for the system. Experiments have shown that the current system is capable of identifying a highly relevant subset of features for traffic prediction given a large number of video content and short-term net- work traffic descriptors.

A protocol-independent technique for eliminating redundant network traffic - Spring, Neil; Wetherall,D. (ACM SIGCOMM Computer Communication Review, 2000)

Quantile approximation for robust statistical estimation and k-enclosing problems - Mount, Dave; Netanyahu,N. S; Piatko,C. D; Silverman,R.; Wu,A. Y (International Journal of Computational Geometry and Applications, 2000)
Given a set P of n points in Rd, a fundamental problem in computational geometryis concerned with finding the smallest shape of some type that encloses all the points of P. Well-known instances of this problem include finding the smallest enclosing box, minimum volume ball, and minimum volume annulus. In this paper we consider the following variant: Given a set of n points in Rd, find the smallest shape in question that contains at least k points or a certain quantile of the data. This type of problem is known as a k-enclosing problem. We present a simple algorithmic framework for computing quantile approximations for the minimum strip, ellipsoid, and annulus containing a given quantile of the points. The algorithms run in O(n log n) time.

Review of "Architectures and mechanisms for language processing" by Matthew W. Crocker, Martin Pickering, and Charles Clifton. Cambridge University Press 2000. - Weinberg, Amy (Computational Linguistics, 2000)

Rotation, scale, and translation resilient public watermarking for images - Lin,C.Y.; Wu,M.; Bloom,J.A.; Cox,I.J.; Miller,M.L.; Lui,Y.M. (PROC SPIE INT SOC OPT ENG, 2000)
Many electronic watermarks for still images and video content are sensitive to geometric distortions. For example,simple rotation, scaling, and/or translation (RST) of an image can prevent detection of a public watermark. In this paper, we propose a watermarking algorithm that is robust to RST distortions. The watermark is embedded into a 1-dimensional signal obtained by first taking the Fourier transform of the image, resampling the Fourier magnitudes into log-polar coordinates, and then summing a function of those magnitudes along the log-radius axis. If the image is rotated, the resulting signal is cyclically shifted. If it is scaled, the signal is multiplied by some value. And if the image is translated, the signal is unaffected. We can therefore compensate for rotation with a simple search, and for scaling by using the correlation coefficient for the detection metric. False positive results on a database of 10,000 images are reported. Robustness results on a database of 2,000 images are described. It is shown that the watermark is robust to rotation, scale and translation. In addition, the algorithm shows resistance to cropping.

Safe and Flexible Dynamic Linking of Native Code - Crary,Karl; Hicks, Michael W.; Weirich,Stephanie (Technical Reports (CIS), 2000)
We present the design and implementation of a framework for flexible and safe dynamic linking of native code. Our approach extends Typed Assembly Language with a primitive for loading and typechecking code, which is flexible enough to support a variety of linking strategies, but simple enough that it does not significantly expand the trusted computing base. Using this primitive, along with the ability to compute with types, we show that we can program many existing dynamic linking approaches. As a concrete demonstration, we have used our framework to implement dynamic linking for a type-safe dialect of C, closely modeled after the standard linking facility for Unix C programs. Aside from the unavoidable cost of verification, our implementation performs comparably with the standard, untyped approach.

A SIMULATION ENVIRONMENT FOR EVOLVING MULTIAGENT COMMUNICATION - Reggia, James A.; Schultz,Reiner; Uriagereka,Juan; Wilkinson,Jerry (Instititue for Advanced Computer Studies, Univ of Maryland, College Park, 2000)
A simulation environment has been created to support study of emergentcommunication. Multiple agents exist in a two-dimensional world where they must find food and avoid predators. While non-communicating agents may survive, the world is configured so that survival and fitness can be enhanced through the use of inter-agent communication. The goal with this version of the simulator is to determine conditions under which simple communication (signaling) emerges and persists during an evolutionary process. (Also cross-referenced as UMIACS-TR-2000-64)
Keywords: Technical Report

Telicity as a cue to temporal and discourse structure in Chinese-English machine translation - Olsen,Mari; Traum,David; Van Ess-Dykema,Carol; Weinberg, Amy; Dolan,Ron (Association for Computational Linguistics, 2000)
Machine translation between any two languages requires the generation of information that is implicit in the source language. In translating from Chinese to English, tense and other temporal information must be inferred from other grammatical and lexical cues. Moreover, Chinese multiple-clause sentences may contain inter-clausal relations (temporal or otherwise) that must be explicit in English (e.g., by means of a discourse marker). Perfective and imperfective grammatical aspect markers can provide cues to temporal structure, but such information is not present in every sentence. We report on a project to use the lexical aspect features of (a)telicity reflected in the Lexical Conceptual Structure of the input text to suggest tense and discourse structure in the English translation of a Chinese newspaper corpus.

Toward the large-eddy simulation over a hypersonic elliptical cross-section cone - Martin, M.P; Weirs,G.; Candler,G. V; Piomelli,U.; Johnson,H.; Nompelis,I. (AIAA Paper No. 00-2311, 2000)

Using Feature Hierarchies in Bayesian Network Learning - desJardins, Marie; Getoor,Lise; Koller,Daphne (Abstraction, Reformulation, and Approximation, 2000)
In recent years, researchers in statistics and the UAI community have developed an impressive body of theory and algorithmic machinery for learning Bayesian networks from data. Learned Bayesian networks can be used for pattern discovery, prediction, diagnosis, and density estimation tasks. Early pioneering work in this area includes [ 5 , 9 , 10 , 13 ]. The algorithm that has emerged as the current most popular approach is a simple greedy hill-climbing algorithm that searches the space of candidate structures, guided by a network scoring function (either Bayesian or Minimum Description Length (MDL)-based). The search begins with an initial candidate network (typically the empty network, which has no edges), and then considers making small local changes such as adding, deleting, or reversing an edge in the network.

Video access control via multi-level data hiding - M. Wu; Yu,Hong Heather (Multimedia and Expo, 2000. ICME 2000. 2000 IEEE International Conference on, 2000)
The paper proposes novel data hiding algorithms and system design for high quality digital video. Instead of targeting on a single degree of robustness, which results in overestimation and/or underestimation of the noise conditions, we apply multi-level embedding to digital video to achieve more than one level of robustness-capacity tradeoff. In addition, an adaptive technique is proposed to determine how many bits are embedded in each part of the video. Besides user data, control information such as synchronization and the number of hidden user bits are embedded as well. The algorithm can be used for applications such as access control
Keywords: access; adaptive; algorithms; hidden; bits; high; conditions; robustness; robustness-capacity; control; adaptive; data; data; video; design; user; digital; embedding; noise; encapsulation; multimedia; hiding; hiding; multi-level; information; data; processing; QUALITY; signal; systems; authorisation; data; systems; video; technique; control; tradeoff; system; user; video; multi-level

Video transcoding by reducing spatial resolution - Yin,Peng; M. Wu; Liu,Bede (Image Processing, 2000. Proceedings. 2000 International Conference on, 2000)
In network delivery of digital video, if the bandwidth required for a video is not available, the video has to be recoded at a reduced bit rate. It is highly desirable that the transcoding is carried out in real time while maintaining reasonable image quality. In this paper, we propose a fast approach to derive from an MPEG stream a new MPEG stream with half the spatial resolution. For the downsized video, we first generate from the original compressed video an improved estimate of the motion vectors. We then propose a compressed domain approach with data hiding to produce DCT residues by an open-loop method. The computational complexity is significantly lower than a number of previous approaches. Simulation suggests that our approach produces reasonable image quality
Keywords: approach; computational; coding; coding; video; complexity; data; compression; data; cosine; DCT; delivery; open-loop; domain; encapsulation; discrete; estimation; network; estimation; transform; hiding; digital; method; spatial; quality; motion; reduction; video; residues; MPEG; resolution; resolution; motion; stream; compressed; transcoding; computational; transforms; image; vectors; video; downsized; video; image

Visibility stabs and depth-first spiralling on line segments in output sensitive time - Keil,M.; Mount, Dave; Wismath,S.K. (International Journal of Computational Geometry and Applications, 2000)
Given a set S of n non-intersecting line segments in the plane, we present a newtechnique for e ciently traversing the endpoint visibility graph of S to solve a variety of visibility problems in output sensitive time. In particular, we develop two techniques to compute the 2n visibility polygons of the endpoints of S, in output sensitive time. Depth- rst spiralling is a technique that relies on the ordered endpoint visibility graph information to traverse the endpoints of S in a spiral-like manner using a combination of Jarvis' March and depth- rst search. It is a practical method and has been implemented in C++ using LEDA.

Vision geometry IX:(San Diego CA, 30-31 July 2000) - Latecki,L.J.; Mount, Dave; Wu,A. Y (SPIE proceedings series, 2000)

Attacks on digital watermarks - M. Wu; Liu,Bede (Signals, Systems, and Computers, 1999. Conference Record of the Thirty-Third Asilomar Conference on, 1999)
Two methods for attacking watermarks in images and videos have been proposed. The first attack is to remove robust watermarks by iterative block dropping and concealment. Our study suggests that the block size chosen by a robust watermark embedding system should be large enough to circumventing concealment based attacks. The second attacking method is to forge valid watermarks for authentication systems based on fragile-watermarking. Double watermarking is then proposed as one possible countermeasure.
Keywords: attacks; copy; Authentication; authentication; video; based; block; coding; coding; iterative; control; digital; countermeasure; fragile-watermarking; images; iterative; dropping; ownership; EMBEDDING; forging; copyright; image; methods; message; protection; robust; removal; videos; watermarks; size; concealment; system; robust; systems; block; watermark; watermarking; watermarks; watermarks; double

Classification in non-metric spaces - Weinshall,Daphna; Jacobs, David W.; Gdalyahu,Yoram (Proceedings of the 1998 conference on Advances in neural information processing systems II, 1999)

Computing nearest neighbors for moving points and applications to clustering - Kanungo,Tapas; Mount, Dave; Netanyahu,Nathan S.; Piatko,Christine; Silverman,Ruth; Wu,Angela Y. (Proceedings of the tenth annual ACM-SIAM symposium on Discrete algorithms, 1999)

Coordinating a Distributed Planning System - desJardins, Marie; Wolverton,Michael (AI Magazine, 1999)
Distributed SIPE (DSIPE) is a distributed planning system that provides decision support to human planners in a collaborative planning environment. The key contributions of our research on DSIPE are (1) constraint-based, consistent local views of the global plan that give each planner a view of how other planners' subplans relate to their local planning decisions; (2) methods for automatically identifying and sharing potentially relevant information among distributed planning agents; and (3) techniques for merging subplans that leverage the shared subplan structure to generate a complete, final plan. DSIPE is a fully implemented system and has been demonstrated to end users in the maritime (United States Navy and United States Marine Corps) planning community.

Designing PETS: a personal electronic teller of stories - Druin, Allison; Montemayor,Jamie; Hendler,Jim; McAlister,Britt; Boltman,Angela; Fiterman,Eric; Plaisant,Aurelie; Kruskal,Alex; Olsen,Hanne; Revett,Isabella; Schwenn,Thomas Plaisant; Sumida,Lauren; et al. (Proceedings of the SIGCHI conference on Human factors in computing systems: the CHI is the limit, 1999)
We have begun the development of a new robotic pet that cansupport children in the storytelling process. Children can build their own pet by snapping together the modular animal parts of the PETS robot. After their pet is built, children can tell stories using the My Pets software. These stories can then be acted out by their robotic pet. This video paper describes the motivation for this research and the design process of our intergenerational design team in building the first PETS prototypes. We will discuss our progress to date and our focus for the future.
Keywords: children; cooperative inquiry; design techniques; educational applications; intergenerational design team; PETS; ROBOTICS

Digital watermarking using shuffling - M. Wu; Liu,B. (Image Processing, 1999. ICIP 99. Proceedings. 1999 International Conference on, 1999)
This paper applies shuffling to digital watermarking and data hiding. The data embedding capacity in the multimedia source generally varies significantly from one part of the source to another. Sequential embedding is very sensitive to noise which may cause synchronization problem; the common but conservative solution via partitioning an image into large segments and embedding only one bit per segment is wasteful of the data embedding capacity. This paper shows how random shuffling can be used to equalize the uneven distribution of embedding capacity. The effectiveness of random shuffling is demonstrated by analysis and experiments
Keywords: coding; data; embeddin; data; encapsulation; document; hiding; digital; image; processing; image; shuffling; shuffling; synchronization; data; source; random; watermarking; multimedia

The dynamic homefinder: evaluating dynamic queries in a real-estate information exploration system - Williamson,C.; Shneiderman, Ben (Materialized views, 1999)

Effects of term segmentation on Chinese/English cross-language information retrieval - Oard, Douglas; Wang,Jianqiang (String Processing and Information Retrieval Symposium, 1999 and International Workshop on Groupware, 1999)
The majority of recent Cross-Language Information Retrieval (CLIR) research has focused on European languages. CLIR problems that involve East Asian languages such as Chinese introduce additional challenges, because written Chinese texts lack boundaries between terms. The paper examines three Chinese segmentation techniques in combination with two variants of dictionary-based Chinese to English query translation. The results indicate that failure to segment terms, particularly technical terms and names, can have a cascading effect that reduces retrieval effectiveness. Task-tuned segmentation algorithms and alternative term weighting strategies are suggested as productive directions for future work
Keywords: alternative term weighting strategies; cascading effect; Chinese segmentation techniques; Chinese/English cross-language information retrieval; Chromium; CLIR problems; Cross-Language Information Retrieval research; data mining; Dictionaries; dictionary-based Chinese; East Asian languages; English query translation; European languages; future work; Information retrieval; language translation; linguistics; natural language processing; natural languages; productive directions; Reactive power; retrieval effectiveness; task-tuned segmentation algorithms; technical terms; term segmentation; text analysis; written Chinese texts

Efficient preconditioning of the linearized Navier-Stokes equations - Silvester, D.; Elman, Howard; Kay, D.; Wathen, A. (Citeseer, 1999)

Field-to-frame transcoding with spatial and temporal downsampling - Wee,S.J.; Apostolopoulos,J.G.; Feamster, Nick (Image Processing, 1999. ICIP 99. Proceedings. 1999 International Conference on, 1999)
We present an algorithm for transcoding high-rate compressed bitstreams containing field-coded interlaced video to lower-rate compressed bitstreams containing frame-coded progressive video. We focus on MPEG-2 to H.263 transcoding, however these results can be extended to other lower-rate video compression standards including MPEG-4 simple profile and MPEG-1. A conventional approach to the transcoding problem involves decoding the input bitstream, spatially and temporally downsampling the decoded frames, and re-encoding the result. The proposed transcoder achieves improved performance by exploiting the details of the MPEG-2 and H.263 compression standards when performing interlaced to progressive (or field to frame) conversion with spatial downsampling and frame-rate reduction. The transcoder reduces the MPEG-2 decoding requirements by temporally downsampling the data at the bitstream level and reduces the H.263 encoding requirements by largely bypassing H.263 motion estimation by reusing the motion vectors and coding modes given in the input bitstream. In software implementations, the proposed approach achieved a 5 times; speedup over the conventional approach with only a 0.3 and 0.5 dB loss in PSNR for the Carousel and Bus sequences
Keywords: data compression; decoding; Encoding; field-coded interlaced video; field-to-frame transcoding; frame-coded progressive video; H.263 motion estimation; H.263 transcoding; high-rate compressed bitstreams; lower-rate compressed bitstreams; Motion estimation; MPEG-1; MPEG-2; MPEG-4; spatial downsampling; standards; temporal downsampling; transcoder; video coding; video compression standards

Genes and other samples of DNA sequence data for phylogenetic inference - Cummings, Michael P.; Otto,S. P; Wakeley,J. (The Biological Bulletin, 1999)

An international SIGCHI research agenda - Scholtz,Jean C.; Muller,Michael; Novick,David; Olsen,Jr.,Dan R.; Shneiderman, Ben; Wharton,Cathleen (CHI '99 extended abstracts on Human factors in computing systems, 1999)
The goal of this workshop is to articulate an HCI research agenda statement, along with plans for continued refinement with the greater CHI community and plans for disseminating the information beyond the CHI community. There are been several similar prior efforts, including:• 1998 Universal Access program [2]• European community report, "Building the European Information Society for Us All" [1];• CHI 97 workshop [5] and paper [6], "HCI Research and Practice Agenda based on Human Needs …";• CHI 96 Workshop, "CHI Ten-Year View…" [3];• 1995 US National Science Foundation report, "New Directions in Human-Computer Interaction …" [9];• 1995 report from the US National Research Council [7];• 1991 report, "…HCI… Serving Human Needs" [4]
Keywords: agenda; human-computer; interaction; research

Machine Translation - Bel,N.; Dorr, Bonnie J; Hovy,E.; Knight,K.; Iida,H.; Boitet,C.; Maegaard,B.; Wilks,Y. (Multilingual Information Management: Current Levels and Future Abilities, 1999)

An MPEG-2 to H. 263 transcoder - Feamster, Nick; Wee,S. (SPIE Voice, Video, and Data Communications Conference, 1999)
We present an MPEG-2 to H.263 transcoder that accepts an interlaced MPEG-2 bitstream as the input and producesa lower-bitrate progressive H.263 bitstream as the output. As both DVD and digital television may use MPEG-2 interlaced sequences, a potential application of such a transcoder is the transmission of a digital television signal over a wireless medium. Another application is transcoding interlaced DVD content for use on lower-resolution thin clients with progressive displays. The proposed algorithm exploits the properties of the MPEG-2 and H.263 compression standards to perform interlaced to progressive ( eld to frame) conversion with spatial downsampling and frame-rate reduction in a CPU and memory e cient manner, while additionally minimizing picture quality degradation as measured by PSNR. This is the rst algorithm to our knowledge that e ectively uses both spatial and temporal downsampling in an MPEG-2 to H.263 eld to frame transcoder in order to achieve substantial bitrate reduction. This paper discusses recoding experiments used to determine appropriate source and target coding parameters for the transcoder, provides a detailed description of the transcoding algorithm, and describes the performance of a software implementation of the transcoder.

Multi-level data hiding for digital image and video - Wu,M.; Yu,H.; Gelman,A. (SPIE Photonics East’99, 1999)
Previous works on data hiding generally targeted on a specific tradeoff between capacity and robustness. This results inoverestimation of the processing noise under some situations and/or underestimation under some other situations, hence limits the overall performance. In this paper, we propose a multi-level data hiding scheme which is able to convey secondary data in high rate when noise is not severe and can also convey some data reliably under heavy distortion. The proposed scheme is motivated by a two-category classification of embedding schemes and by a study on detection performance of spread spectrum watermarking. The multi-level data hiding has been successfully applied to both digital image and video, and can be used for applications such as copy control.

Predicting the CPU availability of time-shared Unix systems on the computational grid - Wolski,R.; Spring, Neil; Hayes,J. (The Eighth International Symposium on High Performance Distributed Computing, 1999. Proceedings, 1999)
Focuses on the problem of making short- and medium-term forecasts of CPU availability on time-shared Unix systems. We evaluate the accuracy with which availability can be measured using the Unix load average, the Unix utility “vmstat” and the Network Weather Service (NWS) CPU sensor that uses both. We also examine the autocorrelation between successive CPU measurements to determine their degree of self-similarity. While our observations show a long-range autocorrelation dependence, we demonstrate how this dependence manifests itself in the short- and medium-term predictability of the CPU resources in our study
Keywords: accuracy; Application software; Autocorrelation; Availability; Central Processing Unit; computational grid; correlation methods; CPU availability prediction; CPU resources predictability; CPU sensor; Dynamic scheduling; grid computing; Load forecasting; long-range autocorrelation dependence; medium-term forecasts; network operating systems; Network Weather Service; NWS; performance evaluation; self-similarity degree; short-term forecasts; successive CPU measurements; Time measurement; Time sharing computer systems; time-shared Unix systems; time-sharing systems; Unix; Unix load average; vmstat utility; Weather forecasting

Reports on the AAAI Fall Symposia - De Giacomo,Giuseppe; desJardins, Marie; Canamero,Dolores; Wasson,Glenn; Littman,Michael; Allwein,Gerard; Marriott,Kim; Meyer,Bernd; Webb,Barbara; Consi,Tom (AI Magazine, 1999)
The Association for the Advancement of Artificial Intelligence (AAAI) held its 1998 Fall Symposium Series on 23 to 25 October at the Omni Rosen Hotel in Orlando, Florida. This article contains summaries of seven of the symposia that were conducted: (1) Cognitive Robotics; (2) Distributed, Continual Planning; (3) Emotional and Intelligent: The Tangled Knot of Cognition; (4) Integrated Planning for Autonomous Agent Architectures; (5) Planning with Partially Observable Markov Decision Processes; (6) Reasoning with Visual and Diagrammatic Representations; and (7) Robotics and Biology: Developing Connections.

The RNA World - Woodson,Sarah A.; Mount, Stephen M. (Cold Spring Harbor Laboratory Press, 1999)

A rotation, scale and translation resilient public watermark - Wu,M.; Miller,M.L.; Bloom,J.A.; Cox,I.J. (Acoustics, Speech, and Signal Processing, 1999. Proceedings., 1999 IEEE International Conference on, 1999)
Summary form only given. Watermarking algorithms that are robust to the common geometric transformations of rotation, scale and translation (RST) have been reported for cases in which the original unwatermarked content is available at the detector so as to allow the transformations to be inverted. However, for public watermarks the problem is significantly more difficult since there is no original content to register with. Two classes of solution have been proposed. The first embeds a registration pattern into the content while the second seeks to apply detection methods that are invariant to these geometric transformations. This paper describes a public watermarking method which is invariant (or bares a simple relation) to the common geometric transforms of rotation, scale, and translation. It is based on the Fourier-Mellin transform which has previously been suggested. We extend this work, using a variation based on the Radon transform. The watermark is inserted into a projection of the image. The properties of this projection are such that RST transforms produce simple or no effects on the projection waveform. When a watermark is inserted into a projection, the signal must eventually be back projected to the original image dimensions. This is a one to many mapping that allows for considerable flexibility in the watermark insertion process. We highlight some theoretical and practical issues that affect the implementation of an RST invariant watermark. Finally, we describe preliminary experimental results
Keywords: algorithms; Fourier; coding; coding; image; data; transform; dimensions; projection; Fourier-Mellin; image; invariant; methods; detector; experimental; of; pattern; rotation; projection; mapping; original; public; registration; security; resilient; results; geometric; transform; detection; transform; RST; transformations; image; transforms; image; transforms; Radon; watermark; RST; watermark; scale; watermark; translation; watermark; watermarking; waveform; registration

Running EveryWare on the computational grid - Wolski,R.; Brevik,J.; Krintz,C.; Obertelli,G.; Spring, Neil; Su,A. (Proceedings of the 1999 ACM/IEEE conference on Supercomputing (CDROM), 1999)

A Survey of Research in Distributed, Continual Planning - desJardins, Marie; Durfee,Edmund H; Ortiz,Jr.; Wolverton,Michael J (AI Magazine, 1999)

Vision geometry VIII(Denver CO, 19-20 July 1999) - Latecki,L.J.; Melter,R.A.; Mount, Dave; Wu,A. Y (SPIE proceedings series, 1999)

An algorithm for wipe detection - M. Wu; Wolf,W.; Liu,B. (Image Processing, 1998. ICIP 98. Proceedings. 1998 International Conference on, 1998)
The detection of transitions between shots in video programs is an important first step in analyzing video content. The wipe is a frequently used transitional form between shots. Wipe detection is more involved than the detection of abrupt and other gradual transitions because a wipe may take various patterns and because of the difficulty in discriminating a wipe from object and camera motion. In this paper, we propose an algorithm for detecting wipes using both structural and statistical information. The algorithm can effectively detect most wipes used in current TV programs. It uses the DC sequence which can be easily extracted from the MPEG stream without full decompression
Keywords: algorithm; image; analysis; video; content; video; DC; DETECTION; detection; statistical; domain; object; information; structural; information; video; motion; compressed; motion; shot; processing; programs; camera; programs; wipe; sequence; MPEG; sequences; signal; signal; stream; TV; transitions

Application level scheduling of gene sequence comparison on metacomputers - Spring, Neil; Wolski,R. (Proceedings of the 12th international conference on Supercomputing, 1998)

Approximating large convolutions in digital images - Kanungo,T.; Mount, Dave; Netanyahu,N. S; Piatko,C.; Silverman,R.; Wu,A. Y (PROCEEDINGS-SPIE THE INTERNATIONAL SOCIETY FOR OPTICAL ENGINEERING, 1998)
Computing discrete two-dimensional convolutions is an important problem in image processing. In mathematicalmorphology, an important variant is that of computing binary convolutions, where the kernel of the convolution is a 0{1 valued function. This operation can be quite costly, especially when large kernels are involved. In this paper, we present an algorithm for computing convolutions of this form, where the kernel of the binary convolution is derived from a convex polygon. Because the kernel is a geometric object, we allow the algorithm some exibility in how it elects to digitize the convex kernel at each placement, as long as the digitization satis es certain reasonable requirements. We say that such a convolution is valid. Given this exibility we show that it is possible to compute binary convolutions more e ciently than would normally be possible for large kernels. Our main result is an algorithm, which given an m n image and a k-sided convex polygonal kernel, computes a valid convolution in time O(kmn) time. Unlike standard algorithms for computing correlations and convolutions, the running time is independent of the area or perimeter of K, and our techniques do not rely on computing fast Fourier transforms. Our algorithm is based on a novel use of Bresenham's line-drawing algorithm and pre x-sums to update the convolution e ciently as the kernel is moved from one position to another across the image.

On the Area of Overlap of Translated Polygons - Mount, Dave; Silverman,Ruth; Wu,Angela Y. (Department of Computer Science, University of Maryland, College Park, 1998)
(Also cross-referenced as CAR-TR-699) Given two simple polygons P and Q in the plane and a translation vector t E R2, the area-oJ-overlap function of P and Q is the function Ar(t) = Area(P n (t + Q)), where t + Q denotes Q translated by t. This function has a number of applications in areas such as motion planning and object recognition. We present a number of mathematical results regarding this function. We also provide efficient algorithms for computing a representation of this function, and for tracing contour curves of constant area of o verlap.
Keywords: Technical Report

Condensing image databases when retrieval is based on non-metric distances - Jacobs, David W.; Weinshall,D.; Gdalyahu,Y. (Computer Vision, 1998. Sixth International Conference on, 1998)
One of the key problems in appearance-based vision is understanding how to use a set of labeled images to classify new images. Classification systems that can model human performance, or that use robust image matching methods, often make use of similarity judgments that are non-metric but when the triangle inequality is not obeyed, most existing pattern recognition techniques are not applicable. We note that exemplar-based (or nearest-neighbor) methods can be applied naturally when using a wide class of non-metric similarity functions. The key issue, however, is to find methods for choosing good representatives of a class that accurately characterize it. We note that existing condensing techniques for finding class representatives are ill-suited to deal with non-metric dataspaces. We then focus on developing techniques for solving this problem, emphasizing two points: First, we show that the distance between two images is not a good measure of how well one image can represent another in non-metric spaces. Instead, we use the vector correlation between the distances from each image to other previously seen images. Second, we show that in non-metric spaces, boundary points are less significant for capturing the structure of a class than they are in Euclidean spaces. We suggest that atypical points may be more important in describing classes. We demonstrate the importance of these ideas to learning that generalizes from experience by improving performance using both synthetic and real images
Keywords: appearance-based; databases; databases; image; dataspaces; pattern; MATCHING; methods; non-metric; processing; visual; recognition; query; systems; image; vision; classification

Constraint-based array dependence analysis - Pugh, William; Wonnacott,David (ACM Transactions on Programming Languages and SystemsACM Trans. Program. Lang. Syst., 1998)

Controlling communication in distributed planning using irrelevance reasoning - Wolverton,Michael; desJardins, Marie (Proceedings of the fifteenth national/tenth conference on Artificial intelligence/Innovative applications of artificial intelligence, 1998)
Efficient and effective distributed planning requires careful control over how much information the planning agents broadcast to one another. Sending too little information could result in incorrect plans, while sending too much information could overtax the distributed planning system's resources (bandwidth and computational power). Ideally, distributed planning systems would have an efficient technique for filtering a large amount of irrelevant information from the message stream while retaining all the relevant messages. This paper describes an approach to controlling information distribution among planning agents using irrelevance reasoning (Levy & Sagiv 1993). In this approach, each planning agent maintains a data structure encoding the planning effects that could potentially be relevant to each of the other agents, and uses this structure to decide which of the planning effects that it generates will be sent to other agents. We describe an implementation of this approach within a distributed version of the SIPE-2 planner. Our experiments with this implementation show two important benefits of the approach: first, a noticeable speedup of the distributed planners; second--and, we argue, more importantly--a substantial reduction in message traffic.

Culture conflicts in software engineering technology transfer - Zelkowitz, Marvin V; Wallace,D. R; Binkley,D. (NASA Goddard Software Engineering Workshop, 1998)
Although the need to transition new technology to improve the process of developing quality software products is well understood, the computer software industry has done a poor job of carrying out that need. All too often new software technology is touted as the next "silver bullet" to be adopted, only to fail and disappear within a very short period. New technologies are often adopted without any convincing evidence that they will be effective, yet other technologies are ignored despite the published data that they will be useful. It is cClearly there is a clash between those developing new technologies and those responsible for developing quality products. In this paper we discuss a study conducted among a large group of computer software professionals in order to understand what techniques can be used to support the introduction of new technologies, and to understand the biases and opinions of those charged with researching, developing or implementing those new technologies. This study indicates which evaluation techniques are viewed as most successful under various conditions. We show that the research and industrial communities do indeed have different perspectives, which leads to a clash between the goals of the technology developers researchers and the needs of the technology users.

Designing to facilitate browsing: A look back at the Hyperties workstation browser - Shneiderman, Ben; Plaisant, Catherine; Botafogo,Rodrigo; Hopkins,Don; Weiland,William (Technical Reports of the Computer Science Department, University of Maryland, 1998)
Since browsing hypertext can present a formidable cognitivechallenge, user interface design plays a major role in determining acceptability. In the Unix workstation version of Hyperties, a research-oriented prototype, we focussed on design features that facilitate browsing. We first give a general overview of Hyperties and its markup language. Customizable documents can be generated by the conditional text feature that enables dynamic and selective display of text and graphics. In addition we present: - an innovative solution to link identification: pop-out graphical buttons of arbitrary shape. - application of pie menus to permit low cognitive load actions that reduce the distraction of common actions, such as page turning or window selection. - multiple window selection strategies that reduce clutter and housekeeping effort. We preferred piles-of-tiles, in which standard-sized windows were arranged in a consistent pattern on the display and actions could be done rapidly, allowing users to concentrate on the contents. (Also cross-referenced as CAR-TR-494)
Keywords: Technical Report

Distance learning: is it the end of education as most of us know it? - Laurillard,Diana; Preece,Jenny; Shneiderman, Ben; Neal,Lisa; Wærn,Yvonne (CHI 98 conference summary on Human factors in computing systems, 1998)
Keywords: distance learning; education; Internet; Web

Drawing of Two-Dimensional Irregular Meshes - Aggarwal,Alok; Rao Kosaraju,S.; Pop, Mihai (Graph DrawingGraph Drawing, 1998)
We present a method for transforming two-dimensional irregular meshes into square meshes with only a constant blow up in area. We also explore context invariant transformations of irregular meshes into square meshes and provide a lower bound for the transformation of down-staircases.

Experimental models for validating technology - Zelkowitz, Marvin V; Wallace,D. R (Computer, 1998)
Experimentation helps determine the effectiveness of proposed theories and methods. However, computer science has not developed a concise taxonomy of methods for demonstrating the validity of new techniques. Experimentation is a crucial part of attribute evaluation and can help determine whether methods used in accordance with some theory during product development will result in software being as effective as necessary. By looking at multiple examples of technology validation, the authors develop a taxonomy for software engineering experimentation that describes twelve different experimental approaches
Keywords: attribute; development; software; engineering; engineering; evaluation; computer; experimentation; technology; models; product; science; experimental; validation; product

Hybrid planning: An approach to integrating generative and case-based planning - desJardins, Marie; Francis,A.; Wolverton,M. (Working Notes of the AAAI-98 Workshop on Case-Based Reasoning Integrations, 1998)

An intelligent environment for simulating mechanical assembly operations - Gupta,S.K.; Paredis,C. J. J.; Sinha,R.; Wang,C. H.; Brown,P. F. (1998)
Rapid technical advances in many different areas of scientificcomputing provide the enabling technologies for creating a com- prehensive simulation and visualization environment for assembly design and planning. We have built an intelligent environment in which simple simulations can be composed together to create com- plex simulations for detecting potential assembly problems. Our goal in this project is to develop high fidelity assembly simulation and visualization tools that can detect assembly related problems without going through physical mock-ups. In addition, these tools can be used to create easy-to-visualize instructions for performing assembly and service operations.

Low-bandwidth routing and electrical power networks - Cook,Doug; Faber,Vance; Marathe,Madhav; Srinivasan, Aravind; Sussmann,Yoram (Automata, Languages and ProgrammingAutomata, Languages and Programming, 1998)
Given a graph G and a (multi-)set of pairs of vertices in it, the classical NP-hard maximum edge-disjoint-paths problem (MDP) is to connect as many of the given pairs as possible using pairwise edge-disjoint paths in G . We study a relative of this problem: we have a network with fixed link capacities that may have to service large demands when necessary. In particular, individual demands are allowed to exceed capacities, and thus flows for some request pairs necessarily have to be split into different flow-paths. This is the framework for computational problems arising from: (i) electrical power networks due to the proposed deregulation of the electric utility industry in the USA, and (ii) applications such as real-time Internet services (e.g., telephone, fax, video). We show that these problems come in a few variants, some efficiently solvable and many NP -hard; we also present approximation algorithms for many of the NP -hard variants presented. Some of our approximation algorithms benefit from certain improved tail estimates that we derive; the latter also yield improved approximations for a family of packing integer programs.

Modeling and evaluating design alternatives for an on-line instrumentation system: a case study - Waheed, A.; Rover, D. T; Hollingsworth, Jeffrey K (IEEE Transactions on Software Engineering, 1998)
This paper demonstrates the use of a model-based evaluation approach for instrumentation systems (ISs). The overall objective of this study is to provide early feedback to tool developers regarding IS overhead and performance; such feedback helps developers make appropriate design decisions about alternative system configurations and task scheduling policies. We consider three types of system architectures: network of workstations (NOW), symmetric multiprocessors (SMP), and massively parallel processing (MPP) systems. We develop a Resource OCCupancy (ROCC) model for an on-line IS for an existing tool and parameterize it for an IBM SP-2 platform. This model is simulated to answer several “what if” questions regarding two policies to schedule instrumentation data forwarding: collect-and-forward (CF) and batch-and-forward (BF). In addition, this study investigates two alternatives for forwarding the instrumentation data: direct and binary tree forwarding for an MPP system. Simulation results indicate that the BF policy can significantly reduce the overhead and that the tree forwarding configuration exhibits desirable scalability characteristics for MPP systems. Initial measurement-based testing results indicate more than 60 percent reduction in the direct IS overhead when the BF policy was added to Paradyn parallel performance measurement tool
Keywords: alternative system configurations; Application software; batch-and-forward; collect-and-forward; Computer aided software engineering; design alternatives; design decisions; Feedback; IBM SP-2 platform; Instruments; massively parallel processing; model-based evaluation approach; Monitoring; multiprocessing programs; on-line instrumentation system; Paradyn parallel performance measurement tool; PARALLEL PROCESSING; Real time systems; scalability characteristics; software metrics; software tools; Space technology; symmetric multiprocessors; system architectures; system monitoring; System testing; task scheduling policies; tool developers; tree forwarding configuration; Workstations

An optimal algorithm for approximate nearest neighbor searching fixed dimensions - Arya,Sunil; Mount, Dave; Netanyahu,Nathan S.; Silverman,Ruth; Wu,Angela Y. (Journal of the ACM (JACM), 1998)
Consider a set of S of n data points in real d-dimensional space, Rd, where distances are measured using any Minkowski metric. In nearest neighbor searching, we preprocess S into a data structure, so that given any query point q ∈ Rd, is the closest point of S to q can be reported quickly. Given any positive real &egr;, data point p is a (1 +&egr;)-approximate nearest neighbor of q if its distance from q is within a factor of (1 + &egr;) of the distance to the true nearest neighbor. We show that it is possible to preprocess a set of n points in Rd in O(dn log n) time and O(dn) space, so that given a query point q ∈ Rd, and &egr; > 0, a (1 + &egr;)-approximate nearest neighbor of q can be computed in O(cd, &egr; log n) time, where cd,&egr;≤d 1 + 6d/e;d is a factor depending only on dimension and &egr;. In general, we show that given an integer k ≥ 1, (1 + &egr;)-approximations to the k nearest neighbors of q can be computed in additional O(kd log n) time.
Keywords: Approximation algorithms; Box-decomposition trees; closet-point queries; nearest neighbor searching; post-office problem; priority search

Pigment composition of putatively achlorophyllous angiosperms - Cummings, Michael P.; Welschmeyer,N. A (Plant Syst Evol, 1998)
Chlorophyll and carotenoid pigment composition was determined for ten species of putatively achlorophyllous angiosperms using high-performance liquid chromatography. Four families were represented: Lennoaceae (Pholisma arenarium); Monotropaceae (Allotropa virgata, Monotropa uniflora, Pterospora andromedea, Sarcodes sanguinea); Orobanchaceae (Epifagus virginiana, Orobanche cooperi, O. uniflora); Orchidaceae (Cephalanthera austinae, Corallorhiza maculata). Chlorophyll a was detected in all tars, but chlorophyll b was only detected in Corallorhiza maculata. The relative amount of chlorophyll and chlorophyll-related pigments in these plants is greatly reduced compared to fully autotrophic angiosperms.
Keywords: Angiospermae; Lennoaceae; Monotropaceae; Orchidaceae; Lennoaceae; Monotropaceae; Orobanchaceae; Orchidaceae; chlorophyll; carotenoid; pigment; high-performance liquid chromatography; Orobanchaceae

Solution structure and dynamics of the bioactive retroviral M domain from rous sarcoma virus - McDonnell,James M; Fushman, David; Cahill,Sean M.; Zhou,Wenjun; Wolven,Amy; Wilson,Carol B; Nelle,Timothy D; Resh,Marilyn D; Wills,John; Cowburn,David (Journal of Molecular Biology, 1998)
A biologically active construct of the retroviral M domain from the avian Rous sarcoma virus is defined and its solution structure described. This M domain is fully active in budding and infectivity without myristylation. In spite of a sequence homology level that suggests no relationship among M domains and the family of matrix proteins in mammalian retroviruses, the conserved structural elements of a central core allow an M domain sequence motif to be described for all retroviruses. The surface of the M domain has a highly clustered positive patch comprised of sequentially distant residues. An analysis of the backbone dynamics, incorporating rotational anisotropy, is used to estimate the thermodynamics of proposed domain oligomerization.
Keywords: heteronuclear NMR spectroscopy; protein dynamics; RSV matrix protein; sequence homology; three-dimensional structure

Validating the Benefit of New Software Technology - Zelkowitz, Marvin V; Wallace,D. (Software Quality Practitioner, 1998)
The software engineering research community has developed methodsfor showing that new development technologies are effective and the corporate world investigates various techniques before applying them on new developments. Unfortunately, these two communities do not often work together to make technology transfer a smooth process. In this paper, methods for validating research claims in the software development domain are described and methods used by industry to investigate new technologies are given. Guidelines that allow research papers to address the needs for industrial investigations are proposed that should greatly improve the transfer of new technology to industry.

Watermarking for image authentication - M. Wu; Liu,Bede (Image Processing, 1998. ICIP 98. Proceedings. 1998 International Conference on, 1998)
A data embedding method is proposed for image authentication based on table look-up in frequency domain. A visually meaningful watermark and a set of simple features are embedded invisibly in the marked image, which can be stored in the compressed form. The scheme can detect and localize alterations of the original image, such as the tampering of images exported from a digital camera
Keywords: alterations; analysis; image; analysis; message; authentication; image; authentication; table; camera; frequency; coding; image; colour; compression; frequency-domain; detection; alterations; domain; image; EMBEDDING; image; image; compressed; image; ownership; localisation; color; look-up; watermarking; data; lookup; method; digital; protection; table; storage; data; tampering; marked

Anywhere, Anytime Code Inspections: Using the Web to Remove Inspection Bottlenecks in Large-Scale Software Development - Perpich,J. M.; Perry,D. E.; Porter, Adam; Votta,L. G.; Wade,M. W. (Software Engineering, International Conference on, 1997)
The dissemination of critical information and the synchronization of coordinated activities are critical problems in geographically separated, large-scale, software development. While these problems are not insurmountable, their solutions have varying trade-offs in terms of time, cost and effectiveness. Our previous studies have shown that the inspection interval is typically lengthened because of schedule conflicts among inspectors which delay the (usually) required inspection collection meeting.We present and justify a solution using an intranet web that is both timely in its dissemination of information and effective in its coordination of distributed inspectors. First, exploiting a naturally occurring experiment (reported here), we conclude that the asynchronous collection of inspection results is at least as effective as the synchronous collection of those results. Second, exploiting the information dissemination qualities and the on-demand nature of information retrieval of the web, and the platform independence of browsers, we built an inexpensive tool that integrates seamlessly into the current development process. By seamless we mean an identical paper flow that results in an almost identical inspection process.The acceptance of the inspection tool has been excellent. The cost savings just from the reduction in paper work and the time savings from the reduction in distribution interval of the inspection package (sometimes involving international mailings) have been substantial. These savings together with the seamless integration into the existing environment are the major factors for this acceptance. From our viewpoint as experimentalists, the acceptance came too readily. Therefore we lost our op portunity to explore this tool using a series of controlled experiments to isolate the underlying factors or its effectiveness. Nevertheless, by using historical data we can show that the new process is less expensive in terms of cost and at least as effective in terms of quality (defect detection effectiveness).
Keywords: asynchronous; natural occurring inspection experiment; automated support for inspections; code inspections: web-based; meetingless

Comments on "Towards a framework for software measurement validation" - Morasca,S.; Briand,L.C.; Basili, Victor R.; Weyuker,E.J.; Zelkowitz, Marvin V; Kitchenham,B.; Lawrence Pfleeger,S.; Fenton,N. (Software Engineering, IEEE Transactions on, 1997)
A view of software measurement that disagrees with the model presented by Kitchenham, Pfleeger, and Fenton (1995), is given. Whereas Kitchenham et al. argue that properties used to define measures should not constrain the scale type of measures, the authors contend that that is an inappropriate restriction. In addition, a misinterpretation of Weyuker's (1988) properties is noted.
Keywords: measurement; metrics; software; testing; program; validation; program; verification; software

A computational model of acute focal cortical lesions - Goodall,S.; Reggia, James A.; Chen,Y.; Ruppin,E.; Whitney,C. (Stroke, 1997)

Editorial: Evaluation and assessment in software engineering - Kitchenham,B.; Brereton,P.; Budgen,D.; Linkman,S.; Almstrum,V. L; Pfleeger,S. L; Zelkowitz, Marvin V; Wallace,D. (Information and Software Technology, 1997)

Experimental validation in software engineering - Zelkowitz, Marvin V; Wallace,Dolores (Information and Software Technology, 1997)
Although experimentation is an accepted approach toward scientific validation in most scientific disciplines, it only recently has gained acceptance within the software development community. In this paper we discuss a 12-model classification scheme for performing experimentation within the software development domain. We evaluate over 600 published papers in the computer science literature and over one hundred papers from other scientific disciplines in order to determine: (1) how well the computer science community is succeeding at validating its theories, and (2) how computer science compares to other scientific disciplines.
Keywords: data collection; Evaluation; experimentation; measurement

Implementing a performance forecasting system for metacomputing: the Network Weather Service - Wolski,Rich; Spring, Neil; Peterson,Chris (Proceedings of the 1997 ACM/IEEE conference on Supercomputing (CDROM), 1997)
In this paper we describe the design and implementation of a system called the Network Weather Service (NWS) that takes periodic measurements of deliverable resource performance from distributed networked resources, and uses numerical models to dynamically generate forecasts of future performance levels. These performance forecasts, along with measures of performance fluctuation (e.g. the mean square prediction error) and forecast lifetime that the NWS generates, are made available to schedulers and other resource management mechanisms at runtime so that they may determine the quality-of-service that will be available from each resource.We describe the architecture of the NWS and implementations that we have developed and are currently deploying for the Legion [13] and Globus/Nexus [7] metacomputing infrastructures. We also detail NWS forecasts of resource performance using both the Legion and Globus/Nexus implementations. Our results show that simple forecasting techniques substantially outperform measurements of current conditions (commonly used to gauge resource availability and load) in terms of prediction accuracy. In addition, the techniques we have employed are almost as accurate as substantially more complex modeling methods. We compare our techniques to a sophisticated time-series analysis system in terms of forecasting accuracy and computational complexity.

Iterative methods for problems in computational fluid dynamics - Elman, Howard; Silvester, D. J; Wathen, A. J (Iterative Methods in Scientific Computing, 1997)

Local Parallel Computation of Stochastic Completion Fields - Williams,Lance R.; Jacobs, David W. (Neural Computation, 1997)
We describe a local parallel method for computing the stochastic completion field introduced in the previous article (Williams and Jacobs, 1997). The stochastic completion field represents the likelihood that a completion joining two contour fragments passes through any given position and orientation in the image plane. It is based on the assumption that the prior probability distribution of completion shape can be modeled as a random walk in a lattice of discrete positions and orientations. The local parallel method can be interpreted as a stable finite difference scheme for solving the underlying Fokker-Planck equation identified by Mumford (1994). The resulting algorithm is significantly faster than the previously employed method, which relied on convolution with large-kernel filters computed by Monte Carlo simulation. The complexity of the new method is O (n3m), while that of the previous algorithm was O(n4m2 (for an n × n image with m discrete orientations). Perhaps most significant, the use of a local method allows us to model the probability distribution of completion shape using stochastic processes that are neither homogeneous nor isotropic. For example, it is possible to modulate particle decay rate by a directional function of local image brightnesses (i.e., anisotropic decay). The effect is that illusory contours can be made to respect the local image brightness structure. Finally, we note that the new method is more plausible as a neural model since (1) unlike the previous method, it can be computed in a sparse, locally connected network, and (2) the network dynamics are consistent with psychophysical measurements of the time course of illusory contour formation.

A practical approximation algorithm for the LMS line estimator - Mount, Dave; Netanyahu,Nathan S.; Romanik,Kathleen; Silverman,Ruth; Wu,Angela Y. (Proceedings of the eighth annual ACM-SIAM symposium on Discrete algorithms, 1997)
Keywords: Approximation algorithms; least median-of-squares regression; line arrangements; line fitting; randomized algorithms; robust estimation

Stochastic completion fields: A neural model of illusory contour shape and salience - Williams,L. R; Jacobs, David W. (Neural Computation, 1997)
Describes an algorithm- and representation-level theory of illusory contour shape and salience. Unlike previous theories, the model is derived from a single assumption: that the prior probability distribution of boundary completion shape can be modeled by a random walk. The model does not use numerical relaxation or other explicit minimization, but instead relies on the fact that the probability that a particle following a random walk will pass through a given position, and orientation on a path joining 2 boundary fragments can be computed directly as the product of 2 vector-field convolutions. It is shown that for the random walk defined, the maximum likelihood paths are curves of least energy, that is, on average, random walks follow paths commonly assumed to model the shape of illusory contours. A computer model is demonstrated on numerous illusory contour stimuli from the literature. (PsycINFO Database Record (c) 2012 APA, all rights reserved)

The vegetation canopy lidar mission - Dubayah, R.; Blair,J. B.; Bufton,J. L.; Clark,D. B.; JaJa, Joseph F.; Knox,R.; Luthcke,S. B.; Prince,S.; Weishampel,J. (Proceedings of Land Satellite Information in the Next Decade, II: Sources and Applications. Bethesda (MD): American Society of Photogrammetry and Remote Sensing, 1997)
The Vegetation Canopy Lidar (VCL) is the first selected mission of NASA’s new EarthSystem Science Pathfinder program. The principal goal of VCL is the characterization of the three-dimensional structure of the earth; in particular, canopy vertical and horizontal structure and land surface topography. Its primary science objectives are: landcover characterization for terrestrial ecosystem modeling, monitoring and prediction; landcover characterization for climate modeling and prediction; and, production of a global reference data set of topographic spot heights and transects. VCL will provide unique data sets for understanding important environ- mental issues including climatic change and variability, biotic erosion and sustainable landuse, and will dramatically improve our estimation of global biomass and carbon stocks, fractional forest cover, forest extent and condition. It will also provide canopy data critical for biodiversity, natural hazard, and climate studies. Scheduled for launch in early 2000, VCL is an active lidar remote sensing system consisting of a five-beam instrument with 25 m contiguous along track resolution. The five beams are in a circular configuration 8 km across and each beam traces a separate ground track spaced 2 km apart, eventually producing 2 km coverage between 65° N and S. VCL’s core measurement objectives are: (1) canopy top heights; (2) vertical distribution of intercepted surfaces (e.g. leaves and branches); and, (3) ground surface topographic elevations. These measurements are used to derive a variety of science data products including canopy heights, canopy vertical distribution, and ground elevations gridded monthly at 1° resolution and every 6 months at 2 km resolution, as well as a 2 km fractional forest cover product.

Applying algebraic and differential invariants for logo recognition - David Doermann; Rivlin,E.; Weiss, I. (Machine Vision and Applications, 1996)
The problem of logo recognition is of great interest in the document domain, especially for document databases. By recognizing the logo we obtain semantic information about the document which may be useful in deciding whether or not to analyze the textual components. Given a logo block candidate from a document image and alogo database, we would like to determine whether the region corresponds to a logo in the database. Similarly, if we are given a logo block candidate and adocumentdatabase, we wish to determine whether there are any documents in the database of similar origin. Both problems require indexing into a possibly large model space.In this contribution, we present a novel application of algebraic and differential invariants to the problem of logo recognition. By using invariants we have shape descriptors for matching that are unique and independent of the point of view. The algebraic invariants handle cases in which the whole shape of the logo is given and it is easy to describe. The differential invariants cover complex arbitrary logo shape and handle situations in which only part of the logo is recovered. We outline a hierarchical approach to logo recognition and define methods for page segmentation, feature extraction, and indexing. We demonstrate our approach and present results on a database of approximately 100 logos.

A Block-GTH Algorithm for Finding the Stationary Vector of a Markov Chain - O'Leary, Dianne P.; Wu,Yuan-Jye Jason (SIAM Journal on Matrix Applications, 1996)

Controlled topology simplification - He,Taosong; Hong,Lichan; Varshney, Amitabh; Wang,S.W. (Visualization and Computer Graphics, IEEE Transactions on, 1996)
We present a simple, robust, and practical method for object simplification for applications where gradual elimination of high frequency details is desired. This is accomplished by converting an object into multi resolution volume rasters using a controlled filtering and sampling technique. A multiresolution triangle mesh hierarchy can then be generated by applying the Marching Cubes algorithm. We further propose an adaptive surface generation algorithm to reduce the number of triangles generated by the standard Marching Cubes. Our method simplifies the topology of objects in a controlled fashion. In addition, at each level of detail, multilayered meshes can be used for an efficient antialiased rendering
Keywords: (computer; algorithm; adaptive; algorithm; controlled; antialiased; Cubes; Cubes; antialiasing; computational; details; multi; filtering; controlled; Frequency; generation; geometry; rendering; graphics); topology; hierarchy; object; Marching; mesh; meshes; multiresolution; rasters; multilayered; rendering; high; resolution; simplification; efficient; simplification; sampling; surface; technique; standard; Topology; triangle; volume

Evaluating workflow and process automation in wide-area software development - Perry,D.; Porter, Adam; Votta,L.; Wade,M. (Software Process Technology, 1996)

Experimental models for software diagnosis - Zelkowitz, Marvin V; Wallace,D. (NIST IR, 1996)
Experimentation and data collection are becoming accepted practices within the software en-gineering community to determine the e ectiveness of various software development practices. However, there is wide disagreement as to exactly what the term \experimentation" means in this domain. It is important that we understand this concept and identify how we can best collect data needed to validate software methods that are e ective. This understanding will provide a basis for improved technical exchange of information between scientists and engineers within the software community.

Inferring phylogenies from DNA sequence data: The effects of sampling - Otto,S. P; Cummings, Michael P.; Wakeley,J. (New Uses for New PhylogeniesNew Uses for New Phylogenies, 1996)

Integrated network management of hybrid networks - Baras,John S; Ball,Mike; Karne,Ramesh K; Kelley,Steve; Jang,Kap D; Plaisant, Catherine; Roussopoulos, Nick; Stathatos,Kostas; Vakhutinsky,Andrew; Jaibharat,Valluri; Whitefield,David (AIP Conference Proceedings, 1996)
We describe our collaborative efforts towards the design and implementation of a next generation integrated network management system for hybrid networks (INMS/HN). We describe the overall software architecture of the system at its current stage of development. This network management system is specifically designed to address issues relevant for complex heterogeneous networks consisting of seamlessly interoperable terrestrial and satellite networks. Network management systems are a key element for interoperability in such networks. We describe the integration of configuration management and performance management. The next step in this integration is fault management. In particular we describe the object model, issues of the Graphical User Interface (GUI), browsing tools and performance data graphical widget displays, management information database (MIB) organization issues. Several components of the system are being commercialized by Hughes Network Systems. © 1996 American Institute of Physics.

LifeLines: visualizing personal histories - Plaisant, Catherine; Milash,Brett; Rose,Anne; Widoff,Seth; Shneiderman, Ben (Proceedings of the SIGCHI conference on Human factors in computing systems: common ground, 1996)
Keywords: History; justice; medical record; overview; personal record; screen design; screen management; timeline; Visualization

Modeling, Evaluation, and Testing of Paradyn Instrumentation System - Waheed, A.; Rover, D. T; Hollingsworth, Jeffrey K (Proceedings of the 1996 ACM/IEEE Conference on Supercomputing, 1996, 1996)
This paper presents a case study of modeling, evaluating, and testing the data collection services (called an instrumentation system) of the Paradyn parallel performance measurement tool using well-known performance evaluation and experiment design techniques. The overall objective of the study is to use modeling- and simulation-based evaluation to provide feedback to the tool developers to help them choose system configurations and task scheduling policies that can significantly reduce the data collection overheads. We develop and parameterize a resource occupancy model for the Paradyn instrumentation system (IS) for an IBM SP-2 platform. This model is parameterized with a measurement-based workload characterization and subsequently used to answer several "what if" questions regarding configuration options and two policies to schedule instrumentation system tasks: collect-and-forward (CF) and batch-and-forward (BF) policies. Simulation results indicate that the BF policy can significantly reduce the overheads. Based on this feedback, the BF policy was implemented in the Paradyn IS as an option to manage the data collection. Measurement-based testing results obtained from this enhanced version of the Paradyn IS are reported in this paper and indicate more than 60% reduction in the direct IS overheads when the BF policy is used.
Keywords: Distributed control; Feedback; High performance computing; Instruments; Monitoring; Real time systems; Software measurement; Software systems; Software testing; System testing

Simplification envelopes - Cohen,Jonathan; Varshney, Amitabh; Manocha,Dinesh; Turk,Greg; Weber,Hans; Agarwal,Pankaj; Brooks,Frederick; Wright,William (Proceedings of the 23rd annual conference on Computer graphics and interactive techniques, 1996)
Keywords: geometric modeling; hierarchical approximation; levels-of-detail generation; model simplification; offsets; shape approximation

Video representations - Bolle,Ruud; Aloimonos, J.; Fermüller, Cornelia (Recent Developments in Computer Vision, 1996)

Automatic generation of multiresolution for polygonal models - Varshney, Amitabh; Agarwal,P.; Brooks,F.; Wright,W.; Weber,H. (First Workshop on Simulation and Interaction in Virtual Environments, 1995)

Defining, Computing, and Visualizing Molecular Interfaces - Varshney, Amitabh; Brooks Jr,Frederick P.; Manocha,Dinesh; Wright,William V.; Richardson,David C. (Proceedings of the 6th conference on Visualization '95, 1995)
A parallel, analytic approach for defining and computing the inter- and intra-molecular interfaces in three dimensions is described. The "molecular interface surfaces" are derived from approximations to the power-diagrams over the participating molecular units. For a given molecular interface our approach can generate a family of interface surfaces parametrized by alpha and beta, where alpha is the radius of the solvent molecule (also known as the probe-radius) and beta is the interface radius that defines the size of the molecular interface. Molecular interface surfaces provide biochemists with a powerful tool to study surface complementarity and to efficiently characterize the interactions during a protein-substrate docking. The complexity of our algorithm for molecular environments is O(n k \log^2{k}), where n is the number of atoms in the participating molecular units and k is the average number of neighboring atoms -- a constant, given alpha and beta.
Keywords: Computational Biochemistry Algorithms Molecular Graphics; Connolly Surfaces; Molecular Interfaces; Molecular Surfaces; Protein-Protein Recognition

Evaluating Spatial and Textual Style of Displays - Shneiderman, Ben; Chimera,Richard; Jog,Ninog; Stimart,Ren; White,David (Institute for Systems Research Technical Reports, 1995)
The next generation of Graphic User Interfaces (GUIs) will offer rapid access to perceptually-rich, information abundant, and cognitively consistent interfaces. These new GUIs will be subjected to usability tests and expert reviews, plus new analysis methods and novel metrics to help guide designers. We have developed and tested first generation concordance tools to help developers to review terminology, capitalization, and abbreviation. We have also developed a dialog box summary table to help developers spot patterns and identify possible inconsistencies in layout, color fonts, font size, font style, and ordering of widgets. In this study we also explored the use of metrics such as widget counts, balance, alignment, density, and aspect ratios to provide further clues about where redesigns might be appropriate. Preliminary experience with several commercial projects is encouraging.
Keywords: human-computer interaction, Systems Integration Methodology

Generating levels of detail for large-scale polygonal models - Varshney, Amitabh; Agarwal,P. K; Brooks Jr,F. P; Wright,W. V; Weber,H. (Department of Computer Science, Duke University, North Carolina, 1995)
We present an e cient algorithm for generating various levels-of-detail approximations for agiven polygonal model. Our algorithm guarantees that all points of an approximation are within a user-speci able distance from the original model and all points of the original model are within a distance from the approximation. Each approximation attempts to minimize the total number of polygons required to satisfy the previous constraint. We show how the problem of generating levels- of-detail approximations reduces to the classic set partition problem. The various approximations are guaranteed to be topologically consistent with the input polygonal model. The approximations can be constrained by the user to preserve any desired edges of the input model. We also propose a method to compute an estimate of the quality of the approximation generated by our algorithm with respect to the optimal approximation satisfying the same constraints. We have implemented our algorithm and have obtained experimental results of multiresolution hierarchy generation on over a thousand polygonal objects from a CAD model of a notional submarine.

Going beyond integer programming with the Omega test to eliminate false data dependences - Pugh, William; Wonnacott,D. (IEEE Transactions on Parallel and Distributed Systems, 1995)
Array data dependence analysis methods currently in use generate false dependences that can prevent useful program transformations. These false dependences arise because the questions asked are conservative approximations to the questions we really should be asking. Unfortunately, the questions we really should be asking go beyond integer programming and require decision procedures for a subclass of Presburger formulas. In this paper, we describe how to extend the Omega test so that it can answer these queries and allow us to eliminate these false data dependences. We have implemented the techniques described here and believe they are suitable for use in production compilers
Keywords: Algorithm design and analysis; Arithmetic; Computer science; Data analysis; false data dependences; integer programming; Linear programming; Omega test; Privatization; Production; production compilers; program compilers; Program processors; program testing; program transformations; Testing

A miniaturized space-variant active vision system: Cortex-I - Bederson, Benjamin B.; Wallace,R.S.; Schwartz,E. (Machine Vision and applications, 1995)

Next generation network management technology - Baras,John S; Atallah,George C; Ball,Mike; Goli,Shravan; Karne,Ramesh K; Kelley,Steve; Kumar,Harsha; Plaisant, Catherine; Roussopoulos, Nick; Schneiderman,Ben; Srinivasarao,Mulugu; Stathatos,Kosta; et al. (AIP Conference Proceedings, 1995)
Today’s telecommunications networks are becoming increasingly large, complex, mission critical and heterogeneous in several dimensions. For example, the underlying physical transmission facilities of a given network may be ‘‘mixed media’’ (copper, fiber‐optic, radio, and satellite); the subnetworks may be acquired from different vendors due to economic, performance, or general availability reasons; the information being transmitted over the network may be ‘‘multimedia’’ (video, data, voice, and images) and, finally, varying performance criteria may be imposed e.g., data transfer may require high throughput while the others, whose concern is voice communications, may require low call blocking probability. For these reasons, future telecommunications networks are expected to be highly complex in their services and operations. Due to this growing complexity and the disparity among management systems for individual sub‐networks, efficient network management systems have become critical to the current and future success of telecommunications companies. This paper addresses a research and development effort which focuses on prototyping configuration management, since that is the central process of network management and all other network management functions must be built upon it. Our prototype incorporates ergonomically designed graphical user interfaces tailored to the network configuration management subsystem and to the proposed advanced object‐oriented database structure. The resulting design concept follows open standards such as Open Systems Interconnection (OSI) and incorporates object oriented programming methodology to associate data with functions, permit customization, and provide an open architecture environment. © 1995 American Institute of Physics

Sampling properties of DNA sequence data in phylogenetic analysis - Cummings, Michael P.; Otto,S. P; Wakeley,J. (Mol Biol Evol, 1995)
We inferred phylogenetic trees from individual genes and random samples of nucleotides from the mitochondrial genomes of 10 vertebrates and compared the results to those obtained by analyzing the whole genomes. Individual genes are poor samples in that they infrequently lead to the whole-genome tree. A large number of nucleotide sites is needed to exactly determine the whole-genome tree. A relatively small number of sites, however, often results in a tree close to the whole-genome tree. We found that blocks of contiguous sites were less likely to lead to the whole-genome tree than samples composed of sites drawn individually from throughout the genome. Samples of contiguous sites are not representative of the entire genome, a condition that violates a basic assumption of the bootstrap method as it is applied in phylogenetic studies.

SEL's software process improvement program - Basili, Victor R.; Zelkowitz, Marvin V; McGarry,F.; Page,J.; Waligora,S.; Pajerski,R. (Software, IEEE, 1995)
We select candidates for process change on the basis of quantified Software Engineering Laboratory (SEL) experiences and clearly defined goals for the software. After we select the changes, we provide training and formulate experiment plans. We then apply the new process to one or more production projects and take detailed measurements. We assess process success by comparing these measures with the continually evolving baseline. Based upon the results of the analysis, we adopt, discard, or revise the process
Keywords: baseline; detailed; engineering; engineering; evolving; improvement; Laboratory; continually; measurements; experiment; plans; production; process; program; software; projects; training; software; SEL; software

Stochastic completion fields: a neural model of illusory contour shape and salience - Williams,L. R; Jacobs, David W. (Computer Vision, 1995. Proceedings., Fifth International Conference on, 1995)
We describe an algorithm and representation level theory of illusory contour shape and salience. Unlike previous theories, our model is derived from a single assumption-namely, that the prior probability distribution of boundary completion shape can be modeled by a random walk in a lattice whose points are positions and orientations in the image plane (i.e. the space which one can reasonably assume is represented by neurons of the mammalian visual cortex). Our model does not employ numerical relaxation or other explicit minimization, but instead relies on the fact that the probability that a particle following a random walk will pass through a given position and orientation on a path joining two boundary fragments can be computed directly as the product of two vector-field convolutions. We show that for the random walk we define, the maximum likelihood paths are curves of least energy, that is, on average, random walks follow paths commonly assumed to model the shape of illusory contours. A computer model is demonstrated on numerous illusory contour stimuli from the literature
Keywords: boundary; completion; computational; Computer; contour; contours; convolutions; cortex; curves; detection; distribution; edge; energy; estimation; fields; fragments; geometry; illusory; image; lattice; least; likelihood; mammalian; maximum; model; nets; neural; of; paths; plane; probability; probability; random; recognition; shape; stimuli; Stochastic; vector-field; visual; walk

Voxel based object simplification - He,Taosong; Hong,Lichan; Kaufman,A.; Varshney, Amitabh; Wang,S. (Proceedings of the 6th conference on Visualization '95, 1995)
Presents a simple, robust and practical method for object simplification for applications where gradual elimination of high-frequency details is desired. This is accomplished by sampling and low-pass filtering the object into multi-resolution volume buffers and applying the marching cubes algorithm to generate a multi-resolution triangle-mesh hierarchy. Our method simplifies the genus of objects and can also help existing object simplification algorithms achieve better results. At each level of detail, a multi-layered mesh can be used for an optional and efficient antialiased rendering.
Keywords: antialiased rendering; antialiasing; buffer storage; data visualisation; high-frequency detail elimination; low-pass filtering; low-pass filters; marching cubes algorithm; mesh generation; multi-layered mesh; multi-resolution triangle-mesh hierarchy; multi-resolution volume buffers; object genus; Rendering (computer graphics); sampling; Smoothing methods; voxel based object simplification

AAAI 1994 Spring Symposium Series Reports - Woods,William; Uckun,Sendar; Kohane,Isaac; Bates,Joseph; Hulthage,Ingemar; Gasser,Les; Hanks,Steve; Gini,Maria; Ram,Ashwin; desJardins, Marie; Johnson,Peter; Etzioni,Oren; et al. (AI Magazine, 1994)

Adaptation of noncompetitive and competitive neural networks to focal lesions - Weinrich,M.; Sutton,G. G; Reggia, James A.; D'Autrechy,C. L (Journal of Artificial Neural Networks, 1994)

Beyond accuracy, reliability, and efficiency: criteria for a good computer system - Friedman,Batya; Levenson,Nancy; Shneiderman, Ben; Suchman,Lucy; Winograd,Terry (Conference companion on Human factors in computing systems, 1994)

Computing smooth molecular surfaces - Varshney, Amitabh; Brooks, F.P.,Jr.; Wright,W. V (Computer Graphics and Applications, IEEE, 1994)
We consider how we set out to formulate a parallel analytical molecular surface algorithm that has expected linear complexity with respect to the total number of atoms in a molecule. To achieve this goal, we avoided computing the complete 3D regular triangulation over the entire set of atoms, a process that takes time O(n log n), where n is the number of atoms in the molecule. We aim to compute and display these surfaces at interactive rates, by taking advantage of advances in computational geometry, making further algorithmic improvements and parallelizing the computations.<<ETX>>
Keywords: 3D; algorithm; smooth; algorithms; physics; analytical; atoms; three; complexity; computational; complexity; parallel; computing; computing; surface; dimensional; geometry; interactive; geometry; parallel; improvements; computation; molecular; rates; linear; regular; surface; time; computational; triangulation; algorithmic; triangulation; computational

Experiences with Constraint-based Array Dependence Analysis - Wonnacott,W. P.D (Principles and practice of constraint programming: second international workshop, PPCP'94, Rosario, Orcas Island, WA, USA, May 2-4, 1994: proceedings, 1994)

An extended cellular space method for simulating autocatalytic oligonucleotides - Chou,H. H.; Reggia, James A.; Navarro-Gonzalez,R.; Wu,J. (Computers & chemistry, 1994)

From syntactic encodings to thematic roles: Building lexical entries for interlingual MT - Dorr, Bonnie J; Garman,Joseph; Weinberg, Amy (Machine Translation, 1994)
Our goal is to construct large-scale lexicons for interlingual MT of English, Arabic, Korean, and Spanish. We describe techniques that predict salient linguistic features of a non-English word using the features of its English gloss (i.e., translation) in a bilingual dictionary. While not exact, owing to inexact glosses and language-to-language variations, these techniques can augment an existing dictionary with reasonable accuracy, thus saving significant time. We have conducted two experiments that demonstrate the value of these techniques. The first tested the feasibility of building a database of thematic grids for over 6500 Arabic verbs based on a mapping between English glosses and the syntactic codes in Longman's Dictionary of Contemporary English (LDOCE) (Procter, 1978). We show that it is more efficient and less error-prone to hand-verify the automatically constructed grids than it would be to build the thematic grids by hand from scratch. The second experiment tested the automatic classification of verbs into a richer semantic typology based on (Levin, 1993), from which we can derive a more refined set of thematic grids. In this second experiment, we show that a brute-force, non-robust technique provides 72% accuracy for semantic classification of LDOCE verbs; we then show that it is possible to approach this yield with a more robust technique based on fine-tuned statistical correlations. We further suggest the possibility of raising this yield by taking into account linguistic factors such as polysemy and positive and negative constraints on the syntax-semantics relation. We conclude that, while human intervention will always be necessary for the construction of a semantic classification from LDOCE, such intervention is significantly minimized as more knowledge about the syntax-semantics relation is introduced.
Keywords: humanities; Social Sciences and Law

Interactive visualization of weighted three-dimensional alpha hulls - Varshney, Amitabh; Brooks,Frederick P.; Wright,William V. (Proceedings of the tenth annual symposium on Computational geometry, 1994)
An interactive visualization of weighted three-dimensional &agr;-hulls is presented for static and dynamic spheres. The &agr;-hull is analytically computed and represented by a triangulated mesh. The entire surface is computed and displayed in real-time at interactive rates. The weighted three-dimensional &agr;-hulls are equivalent to smooth molecular surfaces of biochemistry. Biochemistry applications of interactive computation and display of &agr;-hulls or smooth molecular surfaces are outlined.

A miniature pan-tilt actuator: the spherical pointing motor - Bederson, Benjamin B.; Wallace,R.S.; Schwartz,E.L. (IEEE Transactions on Robotics and Automation, 1994)
A pan-tilt mechanism is a computer-controlled actuator designed to point an object such as a camera sensor. For applications in active vision, a pan-tilt mechanism should be accurate, fast, small, inexpensive and have low power requirements. The authors have designed and constructed a new type of actuator meeting these requirements, which incorporates both pan and tilt into a single, two-degree-of-freedom device. The spherical pointing motor (SPM) consists of three orthogonal motor windings in a permanent magnetic field, configured to move a small camera mounted on a gimbal. It is an absolute positioning device and is run open-loop. The SPM is capable of panning and tilting a load of 15 grams, for example a CCD image sensor, at rotational velocities of several hundred degrees per second with a repeatability of .15°. The authors have also built a miniature camera consisting of a single CCD sensor chip and miniature lens assembly that fits on the rotor of this motor. In this paper, the authors discuss the theory of the SPM, which includes its basic electromagnetic principles, and derive the relationship between applied currents and resultant motor position. The authors present an automatic calibration procedure and discuss open- and closed-loop control strategies. Finally, the authors present the physical characteristics and results of their prototype
Keywords: absolute positioning device; active vision; Actuators; Application software; Assembly; automatic calibration; camera sensor; CAMERAS; CCD image sensors; CCD sensor chip; Charge coupled devices; Charge-coupled image sensors; closed-loop control strategies; computerised control; Lenses; Magnetic fields; miniature lens assembly; miniature pan-tilt actuator; open-loop control strategies; orthogonal motor windings; pan-tilt mechanism; Permanent magnet motors; position control; Scanning probe microscopy; spherical pointing motor; two-degree-of-freedom device

A neural model of cortical map reorganization following a focal lesion - Armentrout,S. L; Reggia, James A.; Weinrich,M. (Artificial Intelligence in Medicine, 1994)

Next Generation Network Management Technology - Atallah,George C; Ball,Michael O; Baras,John S; Goli,Shravan K; Karne,Ramesh K; Kelley,Stephen; Kumar,Harsha P.; Plaisant, Catherine; Roussopoulos, Nick; Shneiderman, Ben; Srinivasarao,Mulugu; Stathatos,Kostas; et al. (Institute for Systems Research Technical Reports, 1994)
Today's telecommunications networks are becoming increasingly large, complex, mission critical and heterogeneous in several dimensions. For example, the underlying physical transmission facilities of a given network may be ﲭixed media (copper, fiber- optic, radio, and satellite); the sub networks may be acquired from different vendors due to economic, performance, or general availability reasons; the information being transmitted over the network may be ﲭultimedia (video, data, voice, and images) and, finally, varying performance criteria may be imposed e.g. data transfer may require high throughput while the others, whose concern is voice communications, may require low call blocking probability. For these reasons, future telecommunications networks are expected to be highly complex in their services and operations. Due to this growing complexity and the disparity among management systems for individual sub networks, efficient network management systems have become critical to the current and future success of telecommunications companies. This paper addresses a research and development effort which focuses on prototyping configuration management, since that is the central process of network management and all other network management functions must be built upon it. Our prototype incorporates ergonomically designed graphical user interfaces tailored to the network configuration management subsystem and to the proposed advanced object-oriented database structure. The resulting design concept follows open standards such as Open Systems Interconnection (OSI) and incorporates object oriented programming methodology to associate data with functions, permit customization, and provide an open architecture environment. A revised version of this technical report has been published in The 12th Symposium on Space Nuclear Power and Propulsion/Commercialization, pp. 75-82, Albuquerque, NM, January 8-12, 1995.
Keywords: Constraints for Network Management.; Network Configuration Management; network management; Object Oriented Data Base Model for Network Management; Rules; Systems Integration; Visual Information Management for Network Configuration Management

P element-mediated in vivo deletion analysis of white-apricot: deletions between direct repeats are strongly favored. - Kurkulos,M.; Weinberg,J. M.; Roy,D.; Mount, Stephen M. (GeneticsGenetics, 1994)
We have isolated and characterized deletions arising within a P transposon, P[hswa], in the presence of P transposase. P[hswa] carries white-apricot (wa) sequences, including a complete copia element, under the control of an hsp70 promoter, and resembles the original wa allele in eye color phenotype. In the presence of P transposase, P[hswa] shows a high overall rate (approximately 3%) of germline mutations that result in increased eye pigmentation. Of 234 derivatives of P[hswa] with greatly increased eye pigmentation, at least 205 carried deletions within copia. Of these, 201 were precise deletions between the directly repeated 276-nucleotide copia long terminal repeats (LTRs), and four were unique deletions. High rates of transposase-induced precise deletion were observed within another P transposon carrying unrelated 599 nucleotide repeats (yeast 2 mu FLP; recombinase target sites) separated by 5.7 kb. Our observation that P element-mediated deletion formation occurs preferentially between direct repeats suggests general methods for controlling deletion formation.

Software Process Improvement in the NASA Software Engineering Laboratory. - McGarry,Frank; Pajerski,Rose; Page,Gerald; Waligora,Sharon; Basili, Victor R. (CARNEGIE-MELLON UNIV PITTSBURGH PA SOFTWARE ENGINEERING INSTITUTE, 1994)
The Software Engineering Laboratory (SEL) was established in 1976 for the purpose of studying and measuring software processes with the intent of identifying improvements that could be applied to the production of ground support software within the Flight Dynamics Division (FDD) at the National Aeronautics and Space Administration (NASA)/Goddard Space Flight Center (GSFC). The SEL has three member organizations: NASA/GSFC, the University of Maryland, and Computer Sciences Corporation (CSC). The concept of process improvement within the SEL focuses on the continual understanding of both process and product as well as goal-driven experimentation and analysis of process change within a production environment.
Keywords: *AWARDS; *SOFTWARE ENGINEERING; *SYSTEMS ANALYSIS; *WORK MEASUREMENT; ADMINISTRATION AND MANAGEMENT; COMPUTER PROGRAMMING AND SOFTWARE; COMPUTER PROGRAMS; COMPUTERS; data acquisition; ENVIRONMENTS; EXPERIMENTAL DATA; GROUND SUPPORT.; measurement; Organizations; PE63756E; Production; SOFTWARE PROCESS IMPROVEMENT; SPI(SOFTWARE PROCESS IMPROVEMENT); SPN-19950120014

Space variant image processing - Wallace,R.S.; Ong,P.W.; Bederson, Benjamin B.; Schwartz,E.L. (International Journal of Computer Vision, 1994)

Special issue on data parallel algorithms and programming - JaJa, Joseph F.; Wang,Pearl Y. (Journal of Parallel and Distributed Computing, 1994)

Static analysis of upper and lower bounds on dependences and parallelism - Pugh, William; Wonnacott,David (ACM Transactions on Programming Languages and SystemsACM Trans. Program. Lang. Syst., 1994)

URV ESPRIT for tracking time-varying signals - Liu,K. J.R; O'Leary, Dianne P.; Stewart, G.W.; Wu,Y.-J.J. (Signal Processing, IEEE Transactions on, 1994)
ESPRIT is an algorithm for determining the fixed directions of arrival of a set of narrowband signals at an array of sensors. Unfortunately, its computational burden makes it unsuitable for real time processing of signals with time-varying directions of arrival. The authors develop a new implementation of ESPRIT that has potential for real time processing. It is based on a rank-revealing URV decomposition, rather than the eigendecomposition or singular value decomposition used in previous ESPRIT algorithms. The authors demonstrate its performance on simulated data representing both constant and time-varying signals. They find that the URV-based ESPRIT algorithm is effective for estimating time-varying directions-of-arrival at considerable computational savings over the SVD-based algorithm
Keywords: arrival; narrowband; decomposition; real; directions; ESPRIT; fixed; estimation; real-time; of; processing; time-varying; signals; performance; rank-revealing; signals; tracking; direction-of-arrival; systems; time-varying; systems; tracking; TIME; URV

An adaptive ESPRIT based on URV decomposition - Liu,K. J.R; O'Leary, Dianne P.; Stewart, G.W.; Wu,Y.-J.J. (Acoustics, Speech, and Signal Processing, 1993. ICASSP-93., 1993 IEEE International Conference on, 1993)
ESPRIT is an algorithm for determining the fixed directions of arrival of a set of narrowband signals at an array of sensors. Its computational burden makes it unsuitable for real-time processing of signals with time-varying directions of arrival. The authors develop a new implementation of ESPRIT that has potential for real-time processing. It is based on a rank-revealing URV decomposition, rather than the eigendecomposition or singular value decomposition (SVD) used in previous ESPRIT algorithms. Its performance is demonstrated on simulated data representing both constant and time-varying signals. It is shown that the URV-based ESPRIT algorithm is effective for estimating time-varying directions-of-arrival at considerable computational savings over the SVD-based algorithm.≪ETX≫
Keywords: algorithm; array; complexity; parameter; decomposition; real-time; ESPRIT; estimation; real-time; filters; array; of; processing; adaptive; processing; computational; savings; performance; rank-revealing; sensors; computational; signal; systems; systems; time-varying; URV; URV-based

On the area of overlap of translated polygons - Mount, Dave; Silverman,R.; Wu,A. (SPIE Vision Geometry II, 1993)
Given two simple polygons P and Q in the plane and a translation vector t 2R2, the area-of-overlap function of P and Q is the function Ar(t) = Area(P \(t + Q)), where t + Q denotes Q translated by t. This function has a number of applications in areas such as motion planning and object recognition. We present a number of mathematical results regarding this function. We also provide e cient algorithms for computing a representation of this function, and for tracing contour curves of constant area-of-overlap.

Bounding the number of neighbors in protein molecules - Varshney, Amitabh; Wright,W. V; Brooks Jr,F. P (Department of Computer Science, University of North Carolina at Chapel Hill, 1993)

Control and design of the spherical pointing motor - Bederson, Benjamin B.; Wallace,R.S.; Schwartz,E.L. (, 1993 IEEE International Conference on Robotics and Automation, 1993. Proceedings, 1993)
A miniature pan-tilt actuator, the spherical pointing motor (SPM) has been built. The SPM is an absolute positioning device, designed to orient a small camera sensor in two degrees-of-rotational-freedom. It is 4 cm×5 cm×6 cm and weighs 160 g. The operating principle of the SPM is to orient a permanent magnet to the magnetic field induced by three orthogonal coils by applying the appropriate ratio of currents to the coils. The open-loop control and design of the SPM are described. Physical characteristics and velocity measurements of the prototype are reported. The SPM is modeled with a simple second order system. Without control, it oscillates substantially when a single impulse is applied. By applying a second impulse without feedback, the oscillation can be reduced by as much as a factor of ten
Keywords: absolute positioning device; Actuators; camera sensor; CAMERAS; Coils; electric actuators; electric motors; Magnetic field measurement; Magnetic sensors; Open loop systems; open-loop control; orthogonal coils; pan-tilt actuator; permanent magnet; Permanent magnet motors; Permanent magnets; position control; Scanning probe microscopy; second order system; spherical pointing motor; velocity control; Velocity measurement; velocity measurements

Evaluating surface intersections in lower dimensions - Manocha,D.; Varshney, Amitabh; Weber,H. (Second International Conference on Curves and Surfaces, 1993)
We highlight a new algorithm for evaluating the sur-face intersection curve using a matrix formulation. The projection of the intersection curve is represented as the singular set of a bi- variate matrix polynomial. The resulting algorithm for evaluating the intersection curve is based on matrix computations like eigen- decomposition and singular value decomposition. Furthermore, at each stage of the algorithm we make use of inverse power iterations to march back to the curve. We also describe the performance of the resulting robust and accurate approach

A graphical query interface based on aggregation/generalization hierarchies - Weiland,William J; Shneiderman, Ben (Information Systems, 1993)
In order for automated information systems to be used effectively, they must be made easily accessible to a wide range of users and with short training periods. This work proposes a method of organizing documents based on the concepts of aggregation and generalization hierarchies. We propose a graphical user interface to provide a more intuitive form of Boolean query. This design is based on mapping the nodes of the aggregation hierarchy to Boolean intersection operations, mapping the nodes of the generalization hierarchy to Boolean union operations, and providing a concrete, graphical, manipulable representation of both of these node types. Finally, a working prototype interface was constructed and evaluated experimentally against a classical command-line Boolean query interface. In this formative evaluation with sixteen subjects, the graphical interface produced less than one-tenth the errors of the textual interface, on average. Significant differences in time spent specifying queries were not found. Observations and comments provide guidance for designers.
Keywords: aggregation/generalization hierarchies; empirical test; Graphical user interfaces; visual queries

Improving the accuracy of touchscreens: an experimental evaluation of three strategies - Potter,R.L.; Weldon,L.J.; Shneiderman, Ben (Sparks of innovation in human-computer interaction, 1993)

Logo Recognition - David Doermann; Rivlin,E.; Weiss, I. (University of Maryland, College Park, 1993)

Logo Recognition using Geomentric Invariants - David Doermann; Rivlin,E.; Weiss, I. (ICDAR, 1993)

SOCAP: lessons learned in automating military operations planning - Desimone,R.; Wilkins,D. E.; Bienkowski,M.; desJardins, Marie (Proceedings of the 6th international conference on Industrial and engineering applications of artificial intelligence and expert systems, 1993)

A competitive distribution theory of neocortical dynamics - Reggia, James A.; D'Autrechy,C. L; Sutton III,G. G.; Weinrich,M. (Neural Computation, 1992)

The Dynamic HomeFinder: Evaluating dynamic queries in a real-estate information exploration system - Williamson,C.; Shneiderman, Ben (Proceedings of the 15th annual international ACM SIGIR conference on Research and development in information retrieval, 1992)

Dynamic queries: database searching by direct manipulation - Shneiderman, Ben; Williamson,Christopher; Ahlberg,Christopher (Proceedings of the SIGCHI conference on Human factors in computing systems, 1992)

Dynamic queries for information exploration: an implementation and evaluation - Ahlberg,Christopher; Williamson,Christopher; Shneiderman, Ben (Proceedings of the SIGCHI conference on Human factors in computing systems, 1992)
We designed, implemented and evaluated a new concept for direct manipulation of databases, called dynamic queries, that allows users to formulate queries with graphical widgets, such as sliders. By providing a graphical visualization of the database and search results, users can find trends and exceptions easily. Eighteen undergraduate chemistry students performed statistically significantly faster using a dynamic queries interface compared to two interfaces both providing form fill-in as input method, one with graphical visualization output and one with all-textual output. The interfaces were used to explore the periodic table of elements and search on their properties.

Eliminating false data dependences using the Omega test - Pugh, William; Wonnacott,D. (Proceedings of the ACM SIGPLAN 1992 conference on Programming language design and implementation, 1992)

Lateral cortical inhibition without lateral inhibitory connections - Reggia, James A.; Sutton,G.; D'Autrechy,C. L; Weinrich,M. (Neural Networks, 1992. IJCNN., International Joint Conference on, 1992)
The authors consider how a set of neurons forming a cortical column, none of which individually can competitively distribute its activity, can function collectively to produce competitive distribution of activation. To address this issue, they describe a model cortical column composed of three populations of excitatory neurons that collectively distribute their activity competitively. The idea of competitive distribution and the neural circuitry that could bring it about are described. Computer simulation results, implications, and testable predictions of the theory are presented
Keywords: brain models; competitive distribution of activation; digital simulation; excitatory neurons; lateral cortical inhibition; neural circuitry; neurophysiology; physiological models

Six Generations of Building Walkthrough: Final Technical Report to the National Science Foundation - Brooks,Frederick P.; Airey,John; Alspaugh,John; Bell,Andrew; Brown,Randolph; Hill,Curtis; Nimscheck,Uwe; Rheingans,Penny; Rohlf,John; Smith,Dana; Turner,Douglass; Varshney, Amitabh; et al. (University of North Carolina at Chapel Hill, 1992)

Splicing signals in Drosophila: intron size, information content, and consensus sequences - Mount, Stephen M.; Burks,Christian; Herts,Gerald; Stormo,Gary D.; White,Owen; Fields,Chris (Nucleic Acids ResearchNucl. Acids Res., 1992)
A database of 209 Drosophila Introns was extracted from Genbank (release number 64.0) and examined by a number of methods in order to characterize features that might serve as signals for messenger RNA splicing. A tight distribution of sizes was observed: while the smallest introns in the database are 51 nucleotides, more than half are less than 80 nucleotides in length, and most of these have lengths in the range of 59 – 67 nucleotides. Drosophila splice sites found in large and small introns differ in only minor ways from each other and from those found in vertebrate Introns. However, larger introns have greater pyrimidlne-richness in the region between 11 and 21 nucleotides upstream of 3′ splice sites. The Drosophila branchpoint consensus matrix resembles C T A A T (in which branch formation occurs at the underlined A), and differs from the corresponding mammalian signal in the absence of G at the position immediately preceding the branchpoint. The distribution of occurrences of this sequence suggests a minimum distance between 5′ splice shies and branchpoints of about 38 nucleotides, and a minimum distance between 3′ splice sites and branchpoints of 15 nucleotides. The methods we have used detect no information in exon sequences other than in the few nucleotides immediately adjacent to the splice sites. However, Drosophila resembles many other species in that there is a discontinuity in A + T content between exons and introns, which are A + T rich.

Touchscreen toggle design - Plaisant, Catherine; Wallace,Daniel (Proceedings of the SIGCHI conference on Human factors in computing systems, 1992)

Two miniature pan-tilt devices - Bederson, Benjamin B.; Wallace,R.S.; Schwartz,E.L. (Robotics and Automation, 1992. Proceedings., 1992 IEEE International Conference on, 1992)

Voice-bandwidth visual communication through logmaps: the Telecortex - Wallace,R.S.; Bederson, Benjamin B.; Schwartz,E.L. (Applications of Computer Vision, Proceedings, 1992., IEEE Workshop on, 1992)

Optimal algorithms for adjacent side routing - Wu,S.A.; JaJa, Joseph F. (Algorithmica, 1991)
We consider the switchbox routing problem of two-terminal nets in the case when all thek nets lie on two adjacent sides of the rectangle. Our routing model is the standard two-layer model. We develop an optimal algorithm that routes all the nets whenever a routing exists. The routing obtained uses the fewest possible number of vias. A more general version of this problem (adjacent staircase) is also optimally solved.

Polyadenylylation in copia requires unusually distant upstream sequences - Kurkulos,M.; Weinberg,J. M.; Pepling,M. E.; Mount, Stephen M. (Proceedings of the National Academy of SciencesPNAS, 1991)
Retroviruses and related genetic elements generate terminally redundant RNA products by differential polyadenylylation within a long terminal repeat. Expression of the white-apricot (wa) allele of Drosophila melanogaster, which carries an insertion of the 5.1-kilobase retrovirus-like transposable element copia in a small intron, is influenced by signals within copia. By using this indicator, we have isolated a 518-base-pair deletion, 312 base pairs upstream of the copia polyadenylylation site, that is phenotypically like much larger deletions and eliminates RNA species polyadenylylated in copia. This requirement of distant upstream sequences for copia polyadenylylation has implications for the expression of many genetic elements bearing long terminal repeats.

Multiple underlying systems: Translating user requests into programs to produce answers - Bobrow,R.J.; Resnik, Philip; Weischedel,R.M. (Proceedings of the 28th annual meeting on Association for Computational Linguistics, 1990)

Parallel QR factorization by householder and modified Gram-Schmidt algorithms - O'Leary, Dianne P.; Whitman,Peter (Parallel Computing, 1990)
In this paper, the parallel implementation of two algorithms for forming a QR factorization of a matrix is studied. We propose parallel algorithms for the modified Gram-Schmidt and the Householder algorithms on message passing systems in which the matrix is distributed by blocks or rows. The models that predict performance of the algorithms are validated by experimental results on several parallel machines.
Keywords: Gram-Schmidt algorithm; Householder algorithm; Message passing systems; QR factorization

Two-directional record layout for multiple inheritance - Pugh, William; Weddell,G. (Proceedings of the ACM SIGPLAN 1990 conference on Programming language design and implementation, 1990)

A connectionist model for dynamic control - Whitfield,K. C; Goodall,S. M; Reggia, James A. (Telematics and Informatics, 1989)

Domino: A Transportable System for Parallel Processing - O'Leary, Dianne P.; Stewart, G.W.; Geijn,Robert van de (Parallel Processing and Medium-Scale Multiprocessors (Proceedings of a 1986 Conference)Parallel Processing and Medium-Scale Multiprocessors (Proceedings of a 1986 Conference), 1989)

Functional and psychosocial effects of multimodality limb-sparing therapy in patients with soft tissue sarcomas - Chang,A. E; Steinberg,S. M; Culnane,M.; Lampert,M. H; Reggia, James A.; Simpson,C. G; Hicks,J. E; White,D. E; Yang,J. J; Glatstein,E. (Journal of Clinical Oncology, 1989)

Generating plausible diagnostic hypotheses with self-processing causal networks - Wald,J.; Farach,M.; Tagamets,M.; Reggia, James A. (Journal of Experimental & Theoretical Artificial Intelligence, 1989)

Interactive graphics interfaces in hypertext systems - Weiland,W.; Shneiderman, Ben (Proc. 28th Annual ACM DC Technical Symposium, 1989)
One of the key design aspects of hypertext systems is the rapid selection of items displayed on the screen in a direct manipulation manner. The user can select next or back page turning icons or buttons, or select another item that might jump to a remote destination. Authors and browsers are confronted with the problem of recognizing and selecting these choices in textual and graphic databases. This paper discusses the problems and offers a variety of solutions.

A new approach to realizing partially symmetric functions - JaJa, Joseph F.; Wu,S.-M. (Computers, IEEE Transactions on, 1989)
Consideration is given to the class of partially symmetric functions and a method for realizing them is outlined. Each such function can be expressed as a sum of totally symmetric functions such that a circuit can be designed with its complexity dependent on the size of such symmetric cover. The authors compare the sizes of symmetric and sum-of-product covers and show that the symmetric cover will be substantially smaller for this class of functions
Keywords: class; complexity; logic; cover; symmetric; covers; switching; design; switching; functions; Boolean; functions; complexity; partially; functions; computational; functions; sum-of-product; of; symmetric; theory; theory; symmetric

On routing two-terminal nets in the presence of obstacles - JaJa, Joseph F.; Wu,S.A. (Computer-Aided Design of Integrated Circuits and Systems, IEEE Transactions on, 1989)
Consideration is given to the problem of routing <e1>k</e1> two-terminal nets in the presence of obstacles in two models: the standard two-layer model and the knock-knee model. Determining routability is known to be NP-complete for arbitrary <e1>k</e1>. The authors introduce a technique that reduces the general problem into finding edge-disjoint paths in a graph whose size depends only on the size of the obstacles. Two optimization criteria are considered: the total length of the wires and the number of vias used
Keywords: CAD; criteria; routability; routing; edge-disjoint; finding; Layout; length; model; number; model; total; nets; standard; of; paths; knock-knee; two-layer; two-terminal; vias; obstacles; optimization; wires; circuit

Active vision - Aloimonos, J.; Weiss, I.; Bandyopadhyay, A. (International Journal of Computer Vision, 1988)

The American Voice and Robotics" Guardian" System: A Case Study in User Interface Usability Evaluation - Wallace,D.F.; Norman,K. L; Plaisant, Catherine (University of Maryland, 1988)
American Voice and Robotics (AVR), in conjunction with the Maryland Industrial Partnerships(MIPS) program, contracted the Human-Computer Interaction Laboratory (HCIL) to evaluate the user interface of AVR's "Guardian"home automation system. Among their goals for the system were:Ease of use and learning of the system (intuitiveness), Aesthetic appeal, Unintimidating, Impressive, High Functionality, Fast and accurate input of useraction, Clear feedback, Forgiving to errors, and Fun to use. Researchers found that users were initially impressed with the system, but that they were not fully satisfied with it. Specific initial recommendations, theoretical and methodological concerns, procedures, results, and direction of future research will be discussed.

Analysis of competition-based spreading activation in connectionist models - Wang,P. Y; Seidman,S. B; Reggia, James A. (International journal of man-machine studies, 1988)

An empirical comparison of pie vs. linear menus - Callahan,J.; Hopkins,D.; Weiser,M.; Shneiderman, Ben (Proceedings of the SIGCHI conference on Human factors in computing systems, 1988)
Menus are largely formatted in a linear fashion listing items from the top to bottom of the screen or window. Pull down menus are a common example of this format. Bitmapped computer displays, however, allow greater freedom in the placement, font, and general presentation of menus. A pie menu is a format where the items are placed along the circumference of a circle at equal radial distances from the center. Pie menus gain over traditional linear menus by reducing target seek time, lowering error rates by fixing the distance factor and increasing the target size in Fitts's Law, minimizing the drift distance after target selection, and are, in general, subjectively equivalent to the linear style.

Locality principles in syntax and in parsing - Weinberg, Amy (Massachusetts Institute of Technology, Dept. of Linguistics and Philosophy, 1988)

The decomposition of a square into rectangles of minimal perimeter - Kong,T.Y; Mount, Dave; Werman,Michael (Discrete Applied Mathematics, 1987)
This paper solves the problem of subdividing a unit square into p rectangles of area 1/p in such a way that the maximal perimeter of a rectangle is as small as possible. The correctness of the solution is proved using the well-known theorems of Menger and Dilworth.

Time Stress Effects on Two Menu Selection Systems - Wallace,Daniel F; Anderson,Nancy S; Shneiderman, Ben (Proceedings of the Human Factors and Ergonomics Society Annual MeetingProceedings of the Human Factors and Ergonomics Society Annual Meeting, 1987)
The optimal number of menu items per display screen has been the topic of considerable debate and study. On the one hand, some designers have packed many items into each menu to conserve space and reduce the number of menus, whereas on the other hand there are designers who prefer a sparse display for menu structures and other videotex information. This study evaluated the effects of a broad/shallow menu compared to a narrow/deep menu structure under two conditions of time stress for inexperienced users. Results indicated that time stress both slowed performance, and increased errors. In addition, it was demonstrated that the broad/shallow menu was faster and resulted in fewer errors. Implications for menu design are discussed.

Cognitive layouts of windows and multiple screens for user interfaces - Norman,Kent L; Weldon,Linda J.; Shneiderman, Ben (International Journal of Man-Machine Studies, 1986)
In order to make computers easier to use and more versatile many system designers are exploring the use of multiple windows on a single screen and multiple coordinated screens in a single work station displaying linked or related information. The designers of such systems attempt to take into account the characteristics of the human user and the structure of the tasks to be performed. Central to this design issue is the way in which the user views and cognitively processes information presented in the windows or in multiple screens. This paper develops a theory of the “cognitive layout” of information presented in multiple windows or screens. It is assumed that users adopt a cognitive representation or layout of the type of information to be presented and the relationships among the windows or screens and the information they contain. A number of cognitive layouts are derived from theories in cognitive psychology and are discussed in terms of the intent of the software driving the system and congruence with the cognitive processing of the information. It is hypothesized that the particular layout adopted by a user will drastically affect the user's understanding and expectation of events at the human-computer interface and could either greatly facilitate or frustrate the interaction. Ways of ensuring the former and avoiding the latter are discussed in terms of implementations on existing multiple-window and multiple-screen systems.

Display Strategies for Program Browsing: Concepts and Experiment - Shneiderman, Ben; Shafer,P.; Simon,R.; Weldon,L. (IEEE Software, 1986)
The new, larger display screens can improve program comprehension—if the added space is used for mome effective presentation, not just more code or larger type.
Keywords: Computer errors; Content management; Fault detection; Information analysis; Large screen displays; Microscopy; Phase detection; Programming profession; User interfaces

Cognitive Representations of Windows and Multiple Screen Layouts of Computer Interfaces - Norman,K. L; Weldon,L.J.; Shneiderman, Ben (University of Maryland, 1985)

Deterministic parsing: A modern view - Berwick,R.; Weinberg, Amy (1985)

A formal model of abductive inference - Reggia, James A.; Nau, Dana S.; Wang,P.; Peng,Y. (Information Sciences, 1985)

A formal model of diagnostic inference, II. Algorithmic solution and application - Reggia, James A.; Nau, Dana S.; Wang,P. Y; Peng,Y. (Information Sciences, 1985)

Multi-splittings of Matrices and Parallel Solution of Linear Systems - O'Leary, Dianne P.; White,R. E. (SIAM Journal on Algebraic and Discrete Methods, 1985)

A New Approach for Compiling Boolean Functions - JaJa, Joseph F.; Wu,S. M. (Institute for Systems Research, University of Maryland, College Park, 1985)
We propose a new approach for laying out Boolean functions which is based on extracting the symmetries of a given set of functions and applying optimization procedures especially tailored to exploit these symmetries. This paper establishes a rigorous foundation for this approach and shows that it will outperform existing methods for many classes of the functions. The different components of a newly developed system, SYMBL, will be briefly described.
Keywords: Technical Report

The Structure of Information in Online and Paper Technical Manuals - Weldon,Linda J.; Koved,Larry; Shneiderman, Ben (Proceedings of the Human Factors and Ergonomics Society Annual MeetingProceedings of the Human Factors and Ergonomics Society Annual Meeting, 1985)
An experiment was conducted to compare online computer manuals to paper manuals. For each type of manual there were two different database structures – a linear (sequential) structure and a tree structure. The results showed that people using the paper manuals were faster at performing a switch setting task based on information in the manual than were people using the online manuals. No significant differences were found in speed of performance between the linear and tree structures. Nor were there any differences in the number of correct switch settings for the different types of manuals. The subjective evaluation data revealed that the online manuals were rated as better and judged to be more organized than the paper manuals.

SLIPS - Morris,M. S; Reggia, James A.; Ahuja,S. B; Hart,J.; Watson,V. (Journal of Medical Systems, 1984)

Diagnostic expert systems based on a set covering model - Reggia, James A.; Nau, Dana S.; Wang,P. Y (International Journal of Man-Machine Studies, 1983)

Dynamic parallel memories - Vishkin, Uzi; Wigderson,A. (Information and control, 1983)

A New Inference Method for Frame-based Expert System - Reggia, James A.; Nau, Dana S.; Wang,P. Y (Proceedings of the National Conference on Artificial Intelligence, 1983)

Parallel computation on 2-3-trees - Paul,W.; Vishkin, Uzi; Wagener,H. (RAIRO Informatique théorique, 1983)

Parallel dictionaries on 2–3 trees - Paul,W.; Vishkin, Uzi; Wagener,H. (Automata, Languages and Programming, 1983)

Pseudogenes for human small nuclear RNA U3 appear to arise by integration of self-primed reverse transcripts of the RNA into new chromosomal sites - Bernstein,L B; Mount, Stephen M.; Weiner,A M (CellCell, 1983)
We find that both human and rat U3 snRNA can function as self-priming templates for AMV reverse transcriptase in vitro. The 74 base cDNA is primed by the 3' end of intact U3 snRNA, and spans the characteristically truncated 69 or 70 base U3 sequence found in four different human U3 pseudogenes. The ability of human and rat U3 snRNA to self-prime is consistent with a U3 secondary structure model derived by a comparison between rat U3 snRNA and the homologous D2 snRNA from Dictyostelium discoideum. We propose that U3 pseudogenes are generated in vivo by integration of a self-primed cDNA copy of U3 snRNA at new chromosomal sites. We also consider the possibility that the same cDNA mediates gene conversion at the 5' end of bona fide U3 genes where, over the entire region spanned by the U3 cDNA, the two rat U3 sequence variants U3A and U3B are identical.
Keywords: Animals; Base Sequence; DNA; genes; HUMANS; Nucleic Acid Conformation; Rats; Recombination, Genetic; Repetitive Sequences, Nucleic Acid; RNA; RNA, Small Nuclear; RNA-Directed DNA Polymerase; Templates, Genetic; Transcription, Genetic

Small Ribonucleoproteins from Eukaryotes: Structures and Roles in RNA Biogenesis - Steitz,J. A.; Wolin,S. L.; Rinke,J.; Pettersson,I.; Mount, Stephen M.; Lerner,E. A.; Hinterberger,M.; Gottlieb,E. (Cold Spring Harbor Symposia on Quantitative BiologyCold Spring Harb Symp Quant Biol, 1983)
Detailed reviews describing work presented at the annual Cold Spring Harbor Symposia on Quantitative Biology

Syntactic constraints and efficient parsability - Berwick,Robert C.; Weinberg, Amy (Association for Computational Linguistics, 1983)
A central goal of linguistic theory is to explain why natural languages are the way they are. It has often been supposed that computational considerations ought to play a role in this characterization, but rigorous arguments along these lines have been difficult to come by. In this paper we show how a key "axiom" of certain theories of grammar, Subjacency, can be explained by appealing to general restrictions on on-line parsing plus natural constraints on the rule-writing vocabulary of grammars. The explanation avoids the problems with Marcus' [1980] attempt to account for the same constraint. The argument is robust with respect to machine implementation, and thus avoids the problems that often arise when making detailed claims about parsing efficiency. It has the added virtue of unifying in the functional domain of parsing certain grammatically disparate phenomena, as well as making a strong claim about the way in which the grammar is actually embedded into an on-line sentence processor.

Trade-offs between depth and width in parallel computation - Vishkin, Uzi; Wigderson,A. (Foundations of Computer Science, 1983., 24th Annual Symposium on, 1983)
A new technique for proving lower bounds for parallel computation is introduced. This technique enables us to obtain, for the first time. non-trivial tight lower bounds for shared-memory models of parallel computation that allow simultaneous read/write access to the same memory location. The size m of the common memory is called communication width or width in short. For a wide variety of problems (including parity and majority) we show that the time complexity T (depth) and the communication width m are related by the trade-off curve mT2 = #x03A9;(n) (where n is the size of the input). This bound is tight lot every m #x02264;n/log2n We extend our technique to prove mT3 = #x03A9;(n) trade-off for a class of "simpler" functions (includind Boolean Or) on a weaker model that forbids simultaneous write access. This result improves the lower bound of Cook and Dwork [CD-82] when communication is limited.

Algorithm 572: Solution of the Helmholtz Equation for the Dirichlet Problem on General Bounded Three-Dimensional Regions [D3] - O'Leary, Dianne P.; Widlund,Olof (ACM Transactions on Mathematical Software, 1981)

Are snRNPs involved in splicing? - Lerner,Michael R.; Boyle,John A.; Mount, Stephen M.; Wolin,Sandra L.; Steitz,Joan A. (Nature, 1980)
Discrete, stable small RNA molecules are found in the nuclei of cells from a wide variety of eukaryotic organisms. Many of these small nuclear RNA (snRNA) species, which range in size from about 90 to 220 nucleotides, have been well-characterised biochemically, and some sequenced. However, their function has remained obscure. The most abundant snRNA species exist as a closely related set of RNA–protein complexes called small nuclear ribonucleoproteins (snRNPs). snRNPs are the antigens recognised by antibodies from some patients with lupus erythematosus (LE), an autoimmune rheumatic disease. Anti-RNP antibodies from lupus sera selectively precipitate snRNP species containing Ula7 and Ulb9 RNAs from mouse Ehrlich ascites cell nuclei, whereas anti-Sm antibodies bind these snRNPs and four others containing U2, U4, US and U6 RNAs. Both antibody systems precipitate the same seven prominent nuclear proteins (molecular weight 12,000–32,000). All molecules of the snRNAs U1, U2, U4, U5 and U6 appear to exist in the form of antigenic snRNPs9. The particles sediment at about 10S and each probably contains a single snRNA molecule. Indirect immunofluorescence studies using anti-RNP and anti-Sm sera confirm the nuclear (but non-nucleolar) location of the antigenic snRNPs. Here we present several lines of evidence that suggest a direct involvement of snRNPs in the splicing of hnRNA. Most intriguing is the observation that the nucleotide sequence at the 5′ end of U1 RNA exhibits extensive complementarity to those across splice junctions in hnRNA molecules.

Human Factors of Software Design and Development - Weiser,M.; Shneiderman, Ben (Software Configuration Management, 1980)

Capacitance Matrix Methods for the Helmholtz Equation on General Three Dimensional Regions - O'Leary, Dianne P.; Widlund,Olof (Mathematics of Computation, 1979)

TORUS: A step towards bridging the gap between data bases and the casual user - Mylopoulos,J.; Borgida,A.; Cohen,P.; Roussopoulos, Nick; Tsotsos,J.; Wong,H. (Information Systems, 1976)
This paper describes TORUS, a natural language understanding system that serves as a front end to a data base management system in order to facilitate communication with casual users. The system employs a semantic network to store knowledge about a data base of student files. This knowledge is used to find the meaning of each input statement, to decide what action to take with respect to the data base, and to select information that must be output in response to the input statement. A prototype version of TORUS has been implemented.

TORUS-a natural language understanding system for data management - Mylopoulos,J.; Borgida,A.; Cohen,P.; Roussopoulos, Nick; Tsotsos,J.; Wong,H. (Proceedings of the Fourth International Conference on Artificial Intelligence, 1975)